Carbon and nutrient exchange of mangrove forests with the coastal ocean - Adame, María Fernanda; Lovelock, Catherine E. (Hydrobiologia, 2011)
Mangrove forests exchange materials with the coastal ocean through tidal inundation. In this study, we aim to provide an overview of the published data of carbon (C) and nutrient exchange of mangrove forests with the coastal ocean at different spatial scales to assess whether the exchange is correlated with environmental parameters. We collected data on C (dissolved and particulate organic C; DOC and POC) and nutrient exchange (dissolved and particulate nitrogen, N and phosphorus, P) and examined the role of latitude, temperature, precipitation, geomorphological setting, hydrology, dominant mangrove species and forest area in explaining the variability of the exchange. We identified that there are a range of methodologies used to determine material exchange of mangroves with the coastal zone, each methodology providing data on the exchange at different spatial scales. This variability of approaches has limited our understanding of the role of mangroves in the coastal zone. Regardless, we found that mangrove forests export C and nutrients to the coastal zone in the form of litter and POC. We found that precipitation is a major factor influencing the export of C in the form of litter; sites with low annual precipitation and high mean annual temperatures export more C as litter than sites with high precipitation and low temperature. Furthermore, export of POC is higher in zones with low mean annual minimum temperature. Identification of broad-scale trends in DOC and dissolved nutrients was more difficult, as the analysis was limited by scarcity of suitable studies and high variability in experimental approaches. However, tidal amplitude and the concentration of nutrients in the floodwater appears to be important in determining nutrient exchange. The strongest conclusion from our analysis is that mangrove forests are in general sources of C and nutrients in the form of litter and POC and that they are most likely to be exporting C subsidies in dry regions. © Springer Science+Business Media B.V. 2010.

Intense storms and the delivery of materials that relieve nutrient limitations in mangroves of an arid zone estuary - Lovelock, Catherine E.; Feller, Ilka C.; Adame, Maria Fernanda; Reef, Ruth; Penrose, Helen M.; Wei, Lili; Ball, Marilyn C. (Functional Plant Biology, 2011)
Tropical cyclones can be devastating to ecosystems, but they can also result in pulses of fresh water and sediments delivered in floodwaters to the coastal zone. In the arid zone the pulses provided by cyclones may be particularly important for the maintenance of productivity. We examined the impacts of Cyclone Pancho on growth and nutrient limitations to growth in mangroves on the arid coast of Western Australia. We found that growth of trees was enhanced after the cyclone, more than doubling their rates of stem extension. Fertilisation studies showed that before the cyclone tree growth was nutrient limited. After the cyclone fertilisation treatments had no significant effect on growth, indicating nutrients had been delivered during the storm. Additionally, before the cyclone the efficiency of resorption of phosphorus and nitrogen from senescent leaves was higher than after the cyclone, suggesting that nutrient availability was enhanced. Analysis of stable isotopes of leaf tissue indicated that the cyclone was associated with small changes in water use efficiency, consistent with decreased soil salinity associated with the cyclone. There was, however, significant reductions in δ15N indicating enhanced N supply potentially from a new source. We conclude that in the arid zone, floodwater associated with cyclones is important for the delivery of nutrient subsidies that stimulate mangrove growth and that predicted future reductions in the frequency of cyclones will have negative impacts on the productivity of these ecosystems. © CSIRO 2011.

Long-Term Effects of Adding Nutrients to an Oligotrophic Coastal Environment - Armitage, Anna R.; Frankovich, Thomas A.; Fourqurean, James W. (Ecosystems, 2011)
Management of ecological disturbances requires an understanding of the time scale and dynamics of community responses to disturbance events. To characterize long-term seagrass bed responses to nutrient enrichment, we established six study sites in Florida Bay, USA. In 24 plots (0.25 m2) at each site, we regularly added nitrogen (N) and phosphorus (P) in a factorial design for 7 years. Five of the six sites exhibited strong P limitation. Over the first 2 years, P enrichment increased Thalassia testudinum cover in the three most P-limited sites. After 3 years, Halodule wrightii began to colonize many of the P-addition plots, but the degree of colonization was variable among sites, possibly due to differences in the supply of viable propagules. Thalassia increased its allocation to aboveground tissue in response to P enrichment; Halodule increased in total biomass but did not appear to change its aboveground: belowground tissue allocation. Nutrient enrichment did not cause macroalgal or epiphytic overgrowth of the seagrass. Nitrogen retention in the study plots was variable but relatively low, whereas phosphorus retention was very high, often exceeding 100% of the P added as fertilizer over the course of our experiments. Phosphorus retentions exceeding 100% may have been facilitated by increases in Thalassia aboveground biomass, which promoted the settlement of suspended particulate matter containing phosphorus. Our study demonstrated that low-intensity press disturbance events such as phosphorus enrichment can initiate a slow, ramped successional process that may alter community structure over many years. © 2011 Springer Science+Business Media, LLC.

Managing for change: Wetland transitions under sea-level rise and outcomes for threatened species - Traill, Lochran W.; Perhans, Karin; Lovelock, Catherine E.; Prohaska, Ana; Mcfallan, Steve; Rhodes, Jonathan R.; Wilson, Kerrie A. (Diversity and Distributions, 2011)
Aim Global sea-level rise (SLR) could be as much as 1.8metres by 2100, which will impact coastal wetland communities and threatened species. We evaluated the likely outcomes of SLR for wetland communities using a process-based simulation model and coupled this with a metapopulation model for a threatened native rodent (Xeromys myoides). Furthermore, we tested the amplified impacts of SLR, urban growth and introduced predators on X. myoides persistence. Location South-east Queensland, Australia. Methods We adapted the Sea Level Affects Marshes Model to subtropical Australia. We used LiDAR elevation data, field data to parameterize surface accretion and shallow subsidence, and local knowledge to configure wetland transitions. SLR was simulated based on the IPCC B1 and A1FI scenarios, as well as the maximal limit of 1.8m by 2100. Further, we coupled our demographic model to projected shifts in wetland habitat, and estimates of future wetland loss to urban expansion and feral cat (Felis catus) predation. Results Our models project a general decline in wetland communities under SLR, with a noted exception of mangroves. Under the A1FI scenario, SLR allows mangroves to migrate inland, with urban development acting as an obstruction in some areas. Mangrove expansion provides an unexpected benefit for dependent X. myoides populations, although the inclusion of predation and habitat loss due to urban development still suggests extirpation in c. 50years. Main conclusions Through this case study, we illustrate the usefulness of process-based SLR models in understanding outcomes for wetland communities and dependent species. Our models will underscore decision-making in a dynamic system, with global applications for urban planning, conservation prioritization and wildlife management. © 2011 Blackwell Publishing Ltd.

Projected Reorganization of Florida Bay Seagrass Communities in Response to the Increased Freshwater Inflow of Everglades Restoration - Herbert, Darrell Anthony; Perry, William B.; Cosby, Bernard J.; Fourqurean, James W. (Estuaries and Coasts, 2011)
Historic changes in water-use management in the Florida Everglades have caused the quantity of freshwater inflow to Florida Bay to decline by approximately 60% while altering its timing and spatial distribution. Two consequences have been (1) increased salinity throughout the bay, including occurrences of hypersalinity, coupled with a decrease in salinity variability, and (2) change in benthic habitat structure. Restoration goals have been proposed to return the salinity climates (salinity and its variability) of Florida Bay to more estuarine conditions through changes in upstream water management, thereby returning seagrass species cover to a more historic state. To assess the potential for meeting those goals, we used two modeling approaches and long-term monitoring data. First, we applied the hydrological mass balance model FATHOM to predict salinity climate changes in sub-basins throughout the bay in response to a broad range of freshwater inflow from the Everglades. Second, because seagrass species exhibit different sensitivities to salinity climates, we used the FATHOM-modeled salinity climates as input to a statistical discriminant function model that associates eight seagrass community types with water quality variables including salinity, salinity variability, total organic carbon, total phosphorus, nitrate, and ammonium, as well as sediment depth and light reaching the benthos. Salinity climates in the western sub-basins bordering the Gulf of Mexico were insensitive to even the largest (5-fold) modeled increases in freshwater inflow. However, the north, northeastern, and eastern sub-basins were highly sensitive to freshwater inflow and responded to comparatively small increases with decreased salinity and increased salinity variability. The discriminant function model predicted increased occurrences of Halodule wrightii communities and decreased occurrences of Thalassia testudinum communities in response to the more estuarine salinity climates. The shift in community composition represents a return to the historically observed state and suggests that restoration goals for Florida Bay can be achieved through restoration of freshwater inflow from the Everglades. © 2011 Coastal and Estuarine Research Federation.

Remote Sensing of Mangrove Structure and Biomass - Fatoyinbo, Temilola; Simard, Marc (Workshop on Tropical Wetland Ecosystems on Indonesia: Science Needs to Address Climate Change Adaption and Mitigation. Sanur Beach Hotel, Bali 11‐14th April, 2011, 2011)
Introdution Mangrove and Wetland forests are one of the most important ecosystems from biodiversity, carbon sequestration and economical standpoints. By quantifying the amount of above and belowground biomass and consequently carbon stored in forest ecosystems, we are able to derive estimates of carbon sequestration, emission and storage. Quantifying mangrove extent, structure and biomass is also of great importance for addressing climate change adaptation and mitigation. Mangrove forests, in addition to providing habitat and nursery grounds for over 1300 animal species, are also an important sink of carbon. Although they only constitute about 3% of the total forested area globally, their carbon storage capacity-in forested biomass and soil carbon-is greater than that of tropical forests (Alongi, 2002; Lucas et al, 2007). In addition, the amount of mangrove carbon-in the form of litter and leaves-exported into offshore areas is immense, resulting in over 10% of the ocean's dissolved organic carbon originating from mangroves (Dittmar et al, 2006). Because of the difficult environmental conditions of constant or near constant inundation by water, the monitoring of these ecosystems from field data alone is very difficult. Remote Sensing has been extensively employed to measure wetland biomass. In this presentation, we review the most up-to-date methodologies for estimating mangrove structure (height and density) and biomass. Methods There are two distinct methodologies for estimating mangrove biomass from remote sensing data: 1) by using passive optical data and average biomass values and 2) through height or volume measurements from active LiDAR and radar instruments. We concentrate on measurements from active instruments from airborne and spaceborne platforms. In particular, we will concentrate on mangrove forest height and biomass measurements from: 1) Polarimetric SAR data from the Japanese ALOS/PALSAR and the NASA UAVSAR 2) Interferometric Synthetic Aperture Radar data (InSAR) from the Shuttle Radar Topography Mission (SRTM) 3) Lidar data from the GLAS instrument and airborne platforms Optical (or passive) remote sensing uses visible and near-infrared reflectance from the earth to form images. This type of remote sensing data forms the basis for much of current global scale vegetation mapping due to the large number of sensors such as Landsat, MODIS, ASTER, IKONOS, etc., the greater ease of image interpretation and

Response of the Sundarbans coastline to sea level rise and decreased sediment flow: A remote sensing assessment - Rahman, Abdullah F.; Dragoni, Danilo; El-Masri, Bassil (Remote Sensing of Environment, 2011)
The Sundarbans is the world's largest remaining single block of mangrove forest, covering approximately 1millionha (~10,000km2) of the Ganges-Brahmaputra delta along the coastal areas of India and Bangladesh. Sea level rise and alteration of water flows of the Himalayan headwaters are among the major disturbances threatening these coastal areas. But very few studies exist on the dynamics or current status of the Sundarbans coastline. We used Landsat images spanning from 1973 to 2010, and an algorithm that we developed, to consistently estimate the spatiotemporal dynamics of erosion and accretion for four different time intervals and the whole study period. Our results show that the direction and extent of erosion and accretion rates varied throughout the different periods. Erosion was the highest in the 1973-1979 interval, with 23.2km2year-1 of land loss. However, that rate substantially declined in the following periods, reaching a rate of 7-10km2year-1. Accretion showed a rate of 10km2year-1 between 1973 and 1989, but substantially declined to ~4km2year-1 between 1989 and 2010. Accretion rate has declined in the recent years but erosion rate has remained relatively high. As a result the delta front has undergone a net erosion of ~170km2 of coastal land in the 37years of our study period. These numbers are significantly higher than the previously reported rates and magnitudes of erosion in this area. The methods and maps developed in this study may be helpful in management planning of this vulnerable coastline. © 2011 Elsevier Inc.

Salinity influence on methane emissions from tidal marshes - Poffenbarger, Hanna J.; Needelman, Brian A.; Megonigal, J. Patrick (Wetlands, 2011)
The relationship between methane emissions and salinity is not well understood in tidal marshes, leading to uncertainty about the net effect of marsh conservation and restoration on greenhouse gas balance.We used published and unpublished field data to investigate the relationships between tidal marsh methane emissions, salinity, and porewater concentrations of methane and sulfate, then used these relationships to consider the balance between methane emissions and soil carbon sequestration. Polyhaline tidal marshes (salinity >18) had significantly lower methane emissions (mean ± sd=1±2 gm-2 yr-1) than other marshes, and can be expected to decrease radiative forcing when created or restored. There was no significant difference in methane emissions from fresh (salinity=0-0.5) and mesohaline (5-18) marshes (42±76 and 16±11 gm-2 yr-1, respectively), while oligohaline (0.5-5) marshes had the highest and most variable methane emissions (150±221 gm-2 yr-1). Annual methane emissions were modeled using a linear fit of salinity against log-transformed methane flux ( logCH4 = 0:056 salinity 1:38; r 2 = 0. 5 2 ; p < 0.0001). Managers interested in using marshes as greenhouse gas sinks can assume negligible methane emissions in polyhaline systems, but need to estimate or monitor methane emissions in lower-salinity marshes. © Society of Wetland Scientists 2011.

Spatial gradients in dissolved carbon due to tidal marsh outwelling into a Chesapeake Bay estuary - Tzortziou, Maria; Neale, Patrick J.; Megonigal, J. Patrick; Lee Pow, Crystal; Butterworth, Megan (Marine Ecology Progress Series, 2011)
Tidal marshes have been previously shown to affect fluxes of carbon and nutrients in adjacent estuaries by acting as sources, sinks or transformers of compounds transported in water exchanged between the marsh and estuary. Relative to information on the amount and direction of these exchanges, much less is known about the distribution and fate of the distinctive dissolved organic compounds derived from marshes, and the spatial extent to which this 'marsh signature' affects optical and biogeochemical variability in the estuary. In the present study we address the spatial distribution of both dissolved organic carbon (DOC) and dissolved inorganic carbon (DIC), as well as other biogeochemical components, in the Rhode River estuary-marsh complex of the Chesapeake Bay. High-spatial-resolution transects showed that the marshes are a major source of DOC, DIC and ρCO2 to the adjacent estuary and atmosphere, and that they seem to trap algae and other suspended particulate matter while releasing high-molecular-weight, aromatic-rich, highly colored dissolved organic matter (CDOM) into the estuary through tidal flushing. These processes result in strong variability in water characteristics considerably beyond the marsh-estuary interface. Non-conservative mixing in CDOM with salinity was probably due to both intense processing of the more labile marshexported components, as well as to mixing with other terrestrial and wetland inputs into the estuary. Despite the possible role of the adjacent subtidal mudflat as a sink for some of the material released from the marshes, the marsh signature was distinguishable from the regional estuarine background over a distance of more than 1 km into the river. © Inter-Research 2011.

The Role of Surface and Subsurface Processes in Keeping Pace with Sea Level Rise in Intertidal Wetlands of Moreton Bay, Queensland, Australia - Lovelock, Catherine E.; Bennion, Vicki; Grinham, Alistair; Cahoon, Donald R. (Ecosystems, 2011)
Increases in the elevation of the soil surfaces of mangroves and salt marshes are key to the maintenance of these habitats with accelerating sea level rise. Understanding the processes that give rise to increases in soil surface elevation provides science for management of landscapes for sustainable coastal wetlands. Here, we tested whether the soil surface elevation of mangroves and salt marshes in Moreton Bay is keeping up with local rates of sea level rise (2.358 mm y-1) and whether accretion on the soil surface was the most important process for keeping up with sea level rise. We found variability in surface elevation gains, with sandy areas in the eastern bay having the highest surface elevation gains in both mangrove and salt marsh (5.9 and 1.9 mm y-1) whereas in the muddier western bay rates of surface elevation gain were lower (1.4 and -0.3 mm y-1 in mangrove and salt marsh, respectively). Both sides of the bay had similar rates of surface accretion (~7-9 mm y-1 in the mangrove and 1-3 mm y-1 in the salt marsh), but mangrove soils in the western bay were subsiding at a rate of approximately 8 mm y-1, possibly due to compaction of organic sediments. Over the study surface elevation increments were sensitive to position in the intertidal zone (higher when lower in the intertidal) and also to variation in mean sea level (higher at high sea level). Although surface accretion was the most important process for keeping up with sea level rise in the eastern bay, subsidence largely negated gains made through surface accretion in the western bay indicating a high vulnerability to sea level rise in these forests. © 2011 Springer Science+Business Media, LLC.

Biogeosciences A cost-efficient method to assess carbon stocks in tropical peat soil - Warren, M W; Kauffman, J B; Murdiyarso, D; Anshari, G; Hergoualc, K; Kurnianto, S (2012)

Blue Carbon Policy Framework: Based on the discussion of the International blue Carbon Policy Working Group - Herr, Dorthee; Pidgeon, Emily; Laffoley, Dan (Iucn, 2012)
IUCN, International Union for Conservation of Nature, helps the world find pragmatic solutions to our most pressing environment and development challenges. IUCN’s work focuses on valuing and conserving nature, ensuring effective and equitable governance of its use, and deploying nature-based solutions to global challenges in climate, food and development. IUCN supports scientific research, manages field projects all over the world, and brings governments, NGOs, the UN and companies together to develop policy, laws and best practice. IUCN is the world’s oldest and largest global environmental organisation, with more than 1,200 government and NGO Members and almost 11,000 volunteer experts in some 160 countries. IUCN’s work is supported by over 1,000 staff in 45 offices and hundreds of partners in public, NGO and private sectors around the world

C 3 and C 4 Biomass Allocation Responses to Elevated CO 2 and Nitrogen: Contrasting Resource Capture Strategies - White, K. P.; Langley, J. A.; Cahoon, D. R.; Megonigal, J. P. (Estuaries and Coasts, 2012)
Plants alter biomass allocation to optimize resource capture. Plant strategy for resource capture may have important implications in intertidal marshes, where soil nitrogen (N) levels and atmospheric carbon dioxide (CO 2) are changing. We conducted a factorial manipulation of atmospheric CO 2 (ambient and ambient + 340 ppm) and soil N (ambient and ambient + 25 g m -2 year -1) in an intertidal marsh composed of common North Atlantic C 3 and C 4 species. Estimation of C 3 stem turnover was used to adjust aboveground C 3 productivity, and fine root productivity was partitioned into C 3-C 4 functional groups by isotopic analysis. The results suggest that the plants follow resource capture theory. The C 3 species increased aboveground productivity under the added N and elevated CO 2 treatment (P< 0. 0001), but did not under either added N or elevated CO 2 alone. C 3 fine root production decreased with added N (P< 0. 0001), but fine roots increased under elevated CO 2 (P = 0. 0481). The C 4 species increased growth under high N availability both above- and belowground, but that stimulation was diminished under elevated CO 2. The results suggest that the marsh vegetation allocates biomass according to resource capture at the individual plant level rather than for optimal ecosystem viability in regards to biomass influence over the processes that maintain soil surface elevation in equilibrium with sea level. © 2012 Coastal and Estuarine Research Federation.

Carbon, nitrogen and phosphorus storage in subtropical seagrass meadows: Examples from Florida Bay and Shark Bay - Fourqurean, James W.; Kendrick, Gary A.; Collins, Laurel S.; Chambers, Randolph M.; Vanderklift, Mathew A. (Marine and Freshwater Research, 2012)
Seagrass meadows in Florida Bay and Shark Bay contain substantial stores of both organic carbon and nutrients. Soils from both systems are predominantly calcium carbonate, with an average of 82.1% CaCO3 in Florida Bay compared with 71.3% in Shark Bay. Soils from Shark Bay had, on average, 21% higher organic carbon content and 35% higher phosphorus content than Florida Bay. Further, soils from Shark Bay had lower mean dry bulk density (0.780.01gmL-1) than those from Florida Bay (0.840.02mgmL-1). The most hypersaline regions of both bays had higher organic carbon content in surficial soils. Profiles of organic carbon and phosphorus from Florida Bay indicate that this system has experienced an increase in P delivery and primary productivity over the last century; in contrast, decreasing organic carbon and phosphorus with depth in the soil profiles in Shark Bay point to a decrease in phosphorus delivery and primary productivity over the last 1000 y. The total ecosystem stocks of stored organic C in Florida Bay averages 163.5 MgCorg ha-1, lower than the average of 243.0 MgCorg ha-1 for Shark Bay; but these values place Shark and Florida Bays among the global hotspots for organic C storage in coastal ecosystems. © 2012 CSIRO.

Characterising the sources and fate of dissolved organic matter in Shark Bay, Australia: A preliminary study using optical properties and stable carbon isotopes - Cawley, Kaelin M.; Ding, Yan; Fourqurean, James; Jaff́, Rudolf (Marine and Freshwater Research, 2012)
Low latitude, seagrass-dominated coastal bays, such as Shark Bay, Australia, are potential sources of chromophoric dissolved organic matter (CDOM) to coastal regions. Dissolved organic matter (DOM) is known to influence aquatic nutrient dynamics, microbial community structure, and depth of light penetration in estuarine systems. Shark Bay is a sub-tropical ecosystem with limited freshwater inputs and restricted tidal flushing. As such, much of the DOM is expected to be seagrass-derived. However, combining excitation/emission fluorescence spectroscopy and parallel factor analysis (EEM-PARFAC) with 13C stable isotope analysis of DOM, we found evidence for DOM inputs from terrestrial (riverine and possibly groundwater), autochthonous plankton, macroalgae, and seagrass sources. Isotopic analysis of 13C in DOM supports the idea that seagrass inputs contribute substantially to the DOM pool in Shark Bay, whereas, EEM-PARAFAC data suggests that much of this input is derived from decomposing seagrass detritus and to a lesser extent due to exudation during primary production. We also report increases in DOM concentrations and changes in DOM characteristics with increasing salinity in surface water samples, indicating that evaporation is an important control on DOM concentration and photo-degradation may play a critical role in transforming DOM within the system. © 2012 CSIRO.

Differential responses of the mangrove Avicennia marina to salinity and abscisic acid - Reef, Ruth; Schmitz, Nele; Rogers, Britt A.; Ball, Marilyn C.; Lovelock, Catherine E. (Functional Plant Biology, 2012)
Salinisation of the soil can cause plant water deficits, ion and nutrient imbalances and toxic reactions. The halophyte, Avicennia marina (Forssk.) Vierh., is a mangrove that tolerates a wide range of soil salinities. In order to understand how salinity affects plant growth and functioning and how salinity responses are influenced by the water deficit signalling hormone abscisic acid (ABA) we grew A. marina seedlings under two non-growth limiting salinities: 60% seawater and 90% seawater and with and without exogenously supplied ABA. We measured growth, photosynthesis, sap flow, aquaporin gene expression, hydraulic anatomy and nutrient status as well as sap ABA concentrations. ABA addition resulted in a drought phenotype (reduced sap flow, transpiration rates and photosynthesis and increased water use efficiency and aquaporin expression). In contrast, growth in high salinity did not lead to responses that are typical for water deficits, but rather, could be characterised as drought avoidance strategies (no reduction in sap flow, transpiration rates and photosynthesis and reduced aquaporin expression). Tissue nutrient concentrations were higher in seedlings grown at high salinities. We did not find evidence for a role for ABA in the mangrove salinity response, suggesting ABA is not produced directly in response to high concentrations of NaCl ions. © CSIRO 2012.

Effects of species richness, identity and environmental variables on growth in planted mangroves in Kenya - Kirui, Bernard Y.K.; Kairo, James G.; Skov, Martin W.; Mencuccini, Maurizio; Huxham, Mark (Marine Ecology Progress Series, 2012)
Anthropogenic impacts on biodiversity across a wide range of ecosystems are well documented; however the responses of ecosystems to reduced diversity are still poorly understood. We investigated the effects of species richness, species identity and environmental variables on aboveground biomass increment using replanted mangroves at Gazi Bay, Kenya. We planted 32 plots (36 m 2) with 8 treatments: all possible combinations of the trees Avicennia marina, Bruguiera gymnorrhiza, and Ceriops tagal and an unplanted control. Trees were planted in July and August 2004 and monitored annually until 2009. Growth was slow in the first 2 yr of the study, but by 2007 there was a significant treatment effect on aboveground biomass. A. marina showed strong competitive traits, with the best growth overall and enhanced growth of individual trees when planted in mixed species plots. The highest biomass was recorded in 3-species mixes; partitioning the net effects of species mixing showed a strong species selection effect, but there was also a complementarity effect in some of the three species plots. Biomass was positively correlated with presence of A. marina and negatively correlated with sediment salinity. We conclude that there is variation in the stages of plant development at which species richness effects manifest themselves; in addition the effects of environmental variables have a bearing on the nature and direction of the relationship between species richness and ecosystem function. © 2012 Inter-Research.

Field-based radiometry to estimate tidal marsh plant growth in response to elevated CO 2 and nitrogen addition - Langley, J. Adam; Megonigal, J. Patrick (Wetlands, 2012)
Plant growth is one of the most important variables to measure in long-term research plots, but the negative effects of labor-intensive and destructive sampling can restrict frequent assessment of plant biomass. Here, we used field-based, active radiometry to assess plant biomass in an ongoing, experimental manipulation of atmospheric CO 2 and soil nitrogen availability in a tidal wetland. We compared the ability of several radiometric vegetation indices (VIs) to predict total plant biomass and that of two plant functional groups, sedges and grasses. All VIs estimated total biomass better in July than in October, when senescence had begun. All VIs correlated strongly and positively to grass biomass (average r=0.83) and weakly or negatively to sedge biomass (r=-0.30). Modified soil-adjusted vegetation index (MSAVI2) performed well through space (average July total biomass r=0.83) and time (across four sampling times r=0.83) and predicted CO 2 and nitrogen treatment effect sizes. In conjunction with conventional biomass measurements field-based, active radiometry provides (1) a frequent estimate of biomass that can reveal plant responses to environmental stimuli that would otherwise escape detection, and (2) a viable alternative to frequent destructive sampling for assessing growth of fine-stemmed species such as Spartina patens and Distichlis spicata. © Society of Wetland Scientists 2012.

Integration, synthesis and climate change adaptation: A narrative based on coastal wetlands at the regional scale - Burley, Jennifer G.; McAllister, Ryan R.J.; Collins, Kerry A.; Lovelock, Catherine E. (Regional Environmental Change, 2012)
The idea that integration and synthesis are critical for designing climate change adaptation and mitigation is well entrenched conceptually. Here, we review the concepts of adaptation, synthesis and integration and apply them to the case study of coastal wetlands in South East Queensland, Australia. The distribution and condition of coastal wetlands will change as climate changes. This will create conservation challenges and economic costs, but these can be minimised by drawing from a broad sectoral perspective in undertaking adaptation planning and by ensuring integration into policy. Our review indicates that adaptations to sea level rise that are focussed on wetland and biodiversity conservation are likely to have impacts for urbanisation patterns. Planning regulations that provide spatial buffering around wetlands may give rise to more compact urban forms that may lead to reductions in the cost of defence against sea level rise, reduce energy usage per person and provide more green space. However, more compact urban forms could exacerbate heat island effects and place greater burden on the economically disadvantaged as, for example, single-family homes become more expensive. Planning for climate change needs to balance these equity and cross-sectoral issues in order to reduce the likelihood of unforeseen negative consequences. © 2011 Springer-Verlag.

Light-dependent maintenance of hydraulic function in mangrove branches: Do xylary chloroplasts play a role in embolism repair? - Schmitz, N.; Egerton, J. J.G.; Lovelock, C. E.; Ball, M. C. (New Phytologist, 2012)
To clarify the role of branch photosynthesis in tree functioning, the presence and function of chloroplasts in branch xylem tissue were studied in a diverse range of mangrove species growing in Australia. • The presence of xylary chloroplasts was observed via chlorophyll fluorescence of transverse sections. Paired, attached branches were selected to study the effects of covering branches with aluminium foil on the gas exchange characteristics of leaves and the hydraulic conductivity of branches. • Xylary chloroplasts occurred in all species, but were differently distributed among living cell types in the xylem. Covering stems altered the gas exchange characteristics of leaves, such that water-use efficiency was greater in exposed leaves of covered than of uncovered branches. • Leaf-specific hydraulic conductivity of stems was lower in covered than in uncovered branches, implicating stem photosynthesis in the maintenance of hydraulic function. Given their proximity to xylem vessels, we suggest that xylary chloroplasts may play a role in light-dependent repair of embolized xylem vessels. © 2012 The Authors. New Phytologist © 2012 New Phytologist Trust.

Local climate determines the NDVI-based primary productivity and flooding creates heterogeneity in semi-arid floodplain ecosystem - Wen, Li; Yang, Xihua; Saintilan, Neil (Ecological Modelling, 2012)
Water is clearly the key driver of ecosystem functioning in arid and semi-arid floodplain environment. Both local rainfall and overbank flow contribute to water accessible by a plant. Variability in rainfall and hydrological regimes at seasonal and longer time scales exerts strong influences shaping ecosystem structure and function in arid and semi-arid floodplains. Yet there are few studies exploring how the interplay of climatic and hydrologic factors affects the integrity of floodplain ecosystems, especially the intermittently flooded vegetated wetlands. In fact, the importance of hydrological regimes prevailingly dominates the literature on floodplain ecology. Consequently, re-establishing and maintaining hydrological regimes has become the cornerstone underpinning most large scale floodplain conservation and restoration programs. In this study, we quantified the relative contribution of climatic and hydrologic variables to ecosystem functioning in the generalized additive modelling (GAM) framework using indicators derived from time series of MODIS 250. m NDVI (Normalized Difference Vegetation Index). Results from the "best fitted" GAM models reveal that local rainfall has a closer and more important relationship with wetland mean NDVI (a surrogate of system primary productivity) although the co-variability between primary productivity and inflow is significantly positive. On the other hand, inflows play a dominant role in creating and maintaining the spatial heterogeneity represented by standard deviation of wetland NDVI while local rainfall has an opposite effect. Further, different vegetation community types exhibit distinct seasonality patterns in the NDVI-based primary productivity. These results illustrate the complexity of interactions between vegetation type, climate variations, and hydrology in floodplain wetlands. These results also demonstrate the sensitivity of floodplain wetlands to the perturbations in rainfall and temperature regimes, which would be more intense under the projected climate change. © 2012 Elsevier B.V.

Mandai mangrove, Singapore: Lessons for the conservation of Southeast Asia's mangroves - Friess, D. A.; Phelps, J.; Leong, R. C.; Lee, W. K.; Wee, A. K.S.; Sivasothi, N.; Oh, R. R.Y.; Webb, E. L. (Raffles Bulletin of Zoology, 2012)
Vital for their diverse ecosystem services, Southeast Asian mangroves are the most biodiverse in the world and are critically threatened, yet they remain woefully understudied. A notable exception is Mandai mangrove in Northwest Singapore, a hotspot of research for decades, with an intensive contemporary research agenda. It provides not only a baseline of mangrove research for the region, but exemplifies the threats facing mangroves across Southeast Asia: changing sediments and currents, insect pests, genetic disconnection from other mangrove patches, land reclamation, and future sea level rise. Many of these threats are unique to mangrove ecosystems, but associated data gaps prohibit informed mangrove conservation across the region. Mandai mangrove is one of Southeast Asia's few mangrove sites with the baseline and contemporary research capable of elucidating these broad threats to the region's mangrove systems. © National University of Singapore.

Mangrove adalah salah satu hutan terkaya karbon di kawasan tropis - Donato, Daniel C; Kauffman, J Boone; Murdiyarso, Daniel; Kurnianto, Sofyan; Stidham, Melanie; Kanninen, Markku (CIFOR Brief, 2012)
Hutan mangrove terdapat di sepanjang garis pantai di kawasan tropis, dan menjadi pendukung berbagai jasa ekosistem, termasuk produksi perikanan dan siklus unsur hara. Namun luas hutan mangrove telah mengalami penurunan sampai 30–50% dalam setengah abad terakhir ini karena pembangunan daerah pesisir, perluasan pembangunan tambak dan penebangan yang berlebihan.1-4 Besarnya emisi karbon akibat hilangnya mangrove masih belum diketahui dengan jelas, sebagian karena kurangnya data berskala besar tentang jumlah karbon yang tersimpan di dalam ekosistem ini, khususnya di bawah permukaan.5 Dalam penelitian ini kami mengkuantifikasikan simpanan karbon di dalam ekosistem mangrove secara keseluruhan dengan mengukur biomassa pohon dan kayu mati, kandungan karbon tanah dan kedalaman tanah di 25 hutan mangrove di sepanjang kawasan Indo-Pasifik, yang membentang selebar 30° garis lintang dan sepanjang 73° garis bujur, di mana mangrovenya sangat luas dan beragam.4,6 Data yang ada menunjukkan bahwa mangrove merupakan salah satu hutan terkaya karbon di kawasan tropis, yang mengandung sekitar 1023 Mg karbon per hektar. Tanah dengan kandungan organik tinggi memiliki kedalaman antara 0,5 m sampai dengan lebih dari 3 m dan merupakan 49–98% simpanan karbon dalam ekosistem ini. Dengan menggabungkan data kami dengan informasi lain yang telah dipublikasikan, kami memperkirakan bahwa deforestasi mangrove menyebabkan emisi sebesar 0,02- 0,12 Pg karbon per tahun, yang setara dengan sekitar 10% emisi dari deforestasi secara global, walaupun luasnya hanya 0,7% dari seluruh kawasan hutan tropis.

Mediterranean Seagrass Growth and Demography Responses to Experimental Warming - Olsen, Ylva S.; Sánchez-Camacho, María; Marbà, Núria; Duarte, Carlos M. (Estuaries and Coasts, 2012)
We experimentally examined the effects of increased temperature on growth and demography of two Mediterranean seagrasses Posidonia oceanica and Cymodocea nodosa. Shoots of C. nodosa and seedlings and shoots of P. oceanica were kept in mesocosms for 3 months and exposed to temperatures between 25 and 32 °C encompassing the range of maximum summer seawater temperatures projected for the Mediterranean Sea during the twenty-first century. The response of P. oceanica seedlings to warming was evident with reduced growth rates, leaf formation rates and leaf biomass per shoot. Younger life stages of P. oceanica may therefore be particularly vulnerable to climate change and warming. Leaf formation rates in the shoots of P. oceanica declined with increasing temperature and the lowest population growth (-0. 005 day -1) was found at 32 °C. Temperature effects on C. nodosa were variable. Rhizome growth increased with warming (0. 07-0. 09 cm day -1 °C of warming), whereas other indicators of plant performance (aboveground/belowground biomass, leaf biomass and population growth) appeared to be stimulated by increased temperature to a threshold temperature of around 29-30 °C beyond which they declined. P. oceanica and C. nodosa are likely to be negatively impacted by the effects of global warming over the next century and climate change poses a significant challenge to seagrasses and may stress these key habitat-forming species that are already suffering losses from anthropogenic impacts. © 2012 Coastal and Estuarine Research Federation.

Mediterranean seagrass vulnerable to regional climate warming - Jordà, Gabriel; Marbà, Núria; Duarte, Carlos M. (Nature Climate Change, 2012)
The Mediterranean Sea, one of the regions warming fastest under climate change, harbours lush seagrass (Posidonia oceanica) meadows that form the basis for a key ecosystem in the region. Recent field results have shown that increased maximum annual seawater temperature in the Mediterranean has already led to increased seagrass mortality. Here we project the trajectory of P. oceanica meadows under the warming expected in the western Mediterranean through the twenty-first century to conclude that warming will lead to the functional extinction of P. oceanica meadows by the middle of this century (year 2049±10) even under a relatively mild greenhouse-gas emissions scenario. Efforts to alleviate local stresses adding to the loss of P. oceanica meadows will have a limited effect in conserving the meadows under climate change. Efforts to mitigate climate change are urgently needed to preserve this key ecosystem. © 2012 Macmillan Publishers Limited. All rights reserved.

Negative relationships between the nutrient and carbohydrate content of the seagrass Thalassia testudinum - Campbell, Justin E.; Yarbro, Laura A.; Fourqurean, James W. (Aquatic Botany, 2012)
This study documents relationships between plant nutrient content and rhizome carbohydrate content of a widely distributed seagrass species, Thalassia testudinum, in Florida. Five distinct seagrass beds were sampled for leaf nitrogen, leaf phosphorus, and rhizome carbohydrate content from 1997 to 1999. All variables displayed marked intra- and inter- regional variation. Elemental ratios (meanN:P±S.E.) were lowest for Charlotte Harbor (9.9±0.2) and highest for Florida Bay (53.5±0.9), indicating regional shifts in the nutrient content of plant material. Rhizome carbohydrate content (mean±S.E.) was lowest for Anclote Keys (21.8±1.6mgg -1 FM), and highest for Homosassa Bay (40.7±1.7mgg -1 FM). Within each region, significant negative correlations between plant nutrient and rhizome carbohydrate content were detected; thus, nutrient-replete plants displayed low carbohydrate content, while nutrient-deplete plants displayed high carbohydrate content. Spearman's rank correlations between nutrient and carbohydrate content varied from a minimum in Tampa Bay (ρ=-0.2) to a maximum in Charlotte Harbor (ρ=-0.73). Linear regressions on log-transformed data revealed similar trends. This consistent trend across five distinct regions suggests that nutrient supply may play an important role in the regulation of carbon storage within seagrasses. Here we present a new hypothesis for studies which aim to explain the carbohydrate dynamics of benthic plants. © 2012 Elsevier B.V..

Nutrient exchange of extensive cyanobacterial mats in an arid subtropical wetland - Adame, Maria Fernanda; Reef, Ruth; Grinham, Alistair; Holmes, Glen; Lovelock, Catherine E. (Marine and Freshwater Research, 2012)
Cyanobacterial mats cover extensive areas of subtropical arid coastal wetlands and are sites of active nutrient exchange. To assess spatial (low v. high in the intertidal zone) and temporal (day v. night) variability in nitrogen (N) exchange in arid Exmouth Gulf, Western Australia, we measured nutrient exchange (NOx--N, NH4+ and soluble reactive phosphorus) during tidal inundation and N fixation of cyanobacterial mats before and during an unusual period of heavy rainfall. Additionally, we investigated the species composition within the cyanobacterial mat. We hypothesised that nutrients are released to the floodwater during tidal inundation, that N fixation is a significant path of N incorporation, that highest N fixation rates occur in the low intertidal zone at night, and that the cyanobacterial mat community composition varies across the intertidal zone. Our results showed that nutrients were removed from the floodwater during tidal inundation. N fixation accounted for 34% of N incorporation, with highest rates in the lower intertidal zone during the day. The cyanobacterial mat was dominated by Microcoleus chthonoplastes, but composition varied across the intertidal zone. The present study provided evidence of temporal and spatial variability in nutrient exchange and implied an important role of cyanobacterial mats in coastal production. © 2012 CSIRO.

Nutrient status of seagrasses cannot be inferred from system-scale distribution of phosphorus in Shark Bay, Western Australia - Fraser, Matthew W.; Kendrick, Gary A.; Grierson, Pauline F.; Fourqurean, James W.; Vanderklift, Mathew A.; Walker, Diana I. (Marine and Freshwater Research, 2012)
Differences in phosphorus (P) availability can influence the ecology and physiology of seagrass communities; and are usually inferred from changes in the relative P content in seagrass leaves. Shark Bay is a subtropical marine embayment, with decreasing P concentrations in the water column and sediments from north to south across the entire embayment. We examined the P and nitrogen (N) content of seagrass leaves and P content of sediments across the Faure Sill and Wooramel delta region of Shark Bay, to determine whether the leaf content of seagrasses in Shark Bay also decreased from north to south over smaller spatial scales. Nutrient content of Amphibolis antarctica and Halodule uninervis were highly variable and were not strongly correlated with sediment P concentrations. Mean N:P ratios of seagrasses (33.5) were not indicative of P limitation, as has been previously assumed for Shark Bay. We conclude that availability of P for uptake by seagrasses across Shark Bay may be highly localised and cannot be predicted from system-scale gradients (100km) of sedimentary P distributions. We suggest that P availability to seagrasses is more likely a complex function of differing nutrient inputs, rates of delivery to the plants and cycling rates. © 2012 CSIRO.

Seasonal sea ice cover as principal driver of spatial and temporal variation in depth extension and annual production of kelp in Greenland - Krause-Jensen, Dorte; Marbà, Núria; Olesen, Birgit; Sejr, Mikael K.; Christensen, Peter Bondo; Rodrigues, João; Renaud, Paul E.; Balsby, Thorsten J.S.; Rysgaard, Søren (Global Change Biology, 2012)
We studied the depth distribution and production of kelp along the Greenland coast spanning Arctic to sub-Arctic conditions from 78 oN to 64 oN. This covers a wide range of sea ice conditions and water temperatures, with those presently realized in the south likely to move northwards in a warmer future. Kelp forests occurred along the entire latitudinal range, and their depth extension and production increased southwards presumably in response to longer annual ice-free periods and higher water temperature. The depth limit of 10% kelp cover was 9-14 m at the northernmost sites (77-78 oN) with only 94-133 ice-free days per year, but extended to depths of 21-33 m further south (73 oN-64 oN) where >160 days per year were ice-free, and annual production of Saccharina longicruris and S. latissima, measured as the size of the annual blade, ranged up to sevenfold among sites. The duration of the open-water period, which integrates light and temperature conditions on an annual basis, was the best predictor (relative to summer water temperature) of kelp production along the latitude gradient, explaining up to 92% of the variation in depth extension and 80% of the variation in kelp production. In a decadal time series from a high Arctic site (74 oN), inter-annual variation in sea ice cover also explained a major part (up to 47%) of the variation in kelp production. Both spatial and temporal data sets thereby support the prediction that northern kelps will play a larger role in the coastal marine ecosystem in a warmer future as the length of the open-water period increases. As kelps increase carbon-flow and habitat diversity, an expansion of kelp forests may exert cascading effects on the coastal Arctic ecosystem. © 2012 Blackwell Publishing Ltd.

Sensitivity of dissolved organic carbon exchange and sediment bacteria to water quality in mangrove forests - Adame, María Fernanda; Reef, Ruth; Herrera-Silveira, Jorge A.; Lovelock, Catherine E. (Hydrobiologia, 2012)
Poor water quality affects the biogeochemistry functions and the biological community structure of coastal ecosystems. In this study we investigated the effect of water quality on: (a) The exchange of dissolved organic carbon (DOC) between floodwater and mangrove forests, (b) the abundance of sediment bacteria, (c) the microbial community composition, and (d) the microbial catabolic activity. We selected six mangrove forests that were flooded by creeks with differing water qualities to test for thresholds of nutrient concentrations associated with changes in DOC dynamics and the microbial community. Our results show that in sites flooded by water high in soluble reactive phosphorus (SRP) (>20 μg l -1) and NH 4+ (>30 μg l -1) the DOC concentrations in the floodwater were higher than in ebb water, suggesting DOC import by the mangroves. In contrast, in sites flooded by water low in SRP (<20 μg l -1) and NH 4+ (<30 μg l -1), DOC concentrations in the floodwater were lower than in the ebb water, suggesting DOC export by the mangroves. Bacterial abundance was higher in sediments with low bulk density, high organic carbon and when flooded by water with low N:P (1-2), but the microbial composition and total catabolic activity assessed using Biolog Ecoplates™ did not differ among sites. The relationship between water quality, microbial communities and DOC exchange suggests that, at least during some periods of the year, poor water quality increases bacterial abundance and modifies DOC exchange of mangrove forests with floodwater and thus, their role in supporting near-shore productivity. © 2012 Springer Science+Business Media B.V.

Stable isotope and fatty acid biomarkers of seagrass, epiphytic, and algal organic matter to consumers in a pristine seagrass ecosystem - Belicka, Laura L.; Burkholder, Derek; Fourqurean, James W.; Heithaus, Michael R.; MacKo, Stephen A.; Jaff́, Rudolf (Marine and Freshwater Research, 2012)
The relative importance of the identity and abundance of primary producers in structuring trophic ecology, particularly in seagrass-dominated ecosystems, remains unclear. We assessed the contributions of seagrass, epiphytes, macroalgae, and other primary producers to the diets of resident animals in the nearly pristine seagrass-dominated environment of Shark Bay, Australia, by combining fatty acid composition with carbon, nitrogen, and sulfur stable isotopes of primary producers and consumers. Overall, mixed inputs of these primary producers fuel secondary production, with tropical detrital seagrass inputs supporting most fish species, likely through benthic intermediates. Epiphytic organic matter inputs were most closely associated with snails, whereas seagrass detritus, macroalgae, gelatinous zooplankton, and/or phytoplankton may all contribute to higher trophic levels including sea turtles and sharks. The fatty acid and isotope data suggest that diets of large-bodied consumers were highly variable - future food web studies need to incorporate large sample sizes to account for this variability. © 2012 CSIRO.

Terrestrial-marine connectivity: Patterns of terrestrial soil carbon deposition in coastal sediments determined by analysis of Glomalin related soil protein - Adame, Maria Fernanda; Wright, Sara F.; Grinham, Alistair; Lobb, Kellie; Reymond, Claire E.; Lovelock, Catherine E. (Limnology and Oceanography, 2012)
Glomalin, an arbuscular mycorrhizal protein component of soil, can be used as an indicator of terrigenousderived carbon. We measured glomalin in sediments using the terrestrial end-member as a reference in four coastal settings: (1) intertidal seagrass meadows distributed over a rainfall gradient, (2) sediments inshore and offshore from the mouth of a river, (3) coastal coral reefs at various distances from the shore, and (4) intertidal wetlands with varying levels of groundwater influence. Across the rainfall gradient, glomalin in seagrass meadow sediments increased at sites with high mean annual rainfall during the wet season (r2 5 0.27; F1,29 5 5.75; p 5 0.029). Glomalin decreased in inshore river sediments (terrestrial) to offshore (marine) sediments (r2 5 0.81; F1,17 5 71.7; p ≤ 0.0001). Furthermore, glomalin in reef sediments decreased with distance from the shore. The high intertidal was rich in glomalin where groundwater flowed directly into the wetland compared with those with little groundwater influences. Our data indicate that rivers and groundwater transport terrestrial material, and that mangroves, salt marsh, seagrass meadows, and coral reefs accumulate it, but the connections vary among sites, within sites, and seasonally. Variations in glomalin concentrations are indicative of links between the terrestrial and marine environment that reflect proximity, filtration services, and the level of subsidies that marine ecosystems derive from terrestrial sources. Assessment of glomalin contributes to evaluating terrestrial-marine connectivity, and thus provides knowledge to improve catchment management for the protection of marine ecosystems.

The impact of a locust plague on mangroves of the arid Western Australia coast - Reef, Ruth; Ball, Marilyn C.; Lovelock, Catherine E. (Journal of Tropical Ecology, 2012)
Mangroves generally grow in nutrient-poor environments and maintain high levels of productivity through unique adaptations for nutrient conservation (Reef et al. 2010). One such adaptation in mangroves is highly efficient resorption of limiting nutrients from senescing leaves prior to abscission (Feller et al. 2003). Thus processes that lead to loss of foliage prior to senescence and nutrient resorption (e.g. storms and herbivory) can be detrimental to tree growth and productivity (Bryant et al. 1983, May & Killingbeck 1992). Furthermore, decomposition of fallen leaves by soil microbial communities (Alongi 1994, Holguin et al. 2001) and crabs (Nagelkerken et al. 2008) is another important process contributing to the recycling of nutrients that are in short supply. Therefore, processes that lead to a substantial reduction in litterfall can have a strong negative effect on nutrient cycling and forest productivity. Mangroves have long been recognized as an important source of organic carbon (both particulate and dissolved) for the surrounding tropical coastal ecosystems (Bouillon et al. 2008, Kristensen et al. 2008). Thus, processes affecting litterfall in mangroves can affect the surrounding marine food webs. © 2012 Cambridge University Press.

The use of representative species as surrogates for wetland inundation - Rogers, Kerrylee; Ralph, Timothy J.; Saintilan, Neil (Wetlands, 2012)
The complex task of determining the inundation requirements of large floodplain wetlands is often simplified through the use of representative, umbrella or flagship species. This subset of species is targeted based on the assumption that their collective inundation requirements serve as a surrogate for the broader suite of species found within the wetland. We tested the application of representative species commonly used in wetland and water management planning in the Murray-Darling Basin. In a review of the water requirements of 155 plants and animals, we collated information on preferred inundation timing, duration, depth, rate of rise and fall, and inter-flood period for 115 species. We then used cluster analysis to determine the extent to which ten commonly used representative species corresponded in inundation requirements to the broader suite of species. We found that the habitat surrogates of river red gum, black box, spike rush, coolibah, water couch, lignum and marsh clubrush represented only one third of species at a 60% level of similarity in inundation requirements, due mainly to the lower inundation return period and duration required by the habitat surrogates. The addition of faunal representative species facilitated the inclusion of a broader range of requirements, though primarily amongst related taxa. We recommend the inclusion of several additional indicator species to more adequately cover the inundation requirements of large wetland ecosystems. © Society of Wetland Scientists 2012.

Tropical wetlands for climate change adaptation and mitigation science and policy imperatives with special reference to Indonesia. - Murdiyarso, D.; Kauffman, J.B.; Warren, Matthew; Pramova, Emilia; Hergoualch, Kristell (Cifor, 2012)
The extent of tropical wetlands, the magnitude of loss, and the related socioeconomic ramifications of the destruction of Indonesian wetlands are of global significance. The carbon density and rates of land-cover change in these ecosystems are amongst the highest of any forest type on Earth. Therefore, addressing interrelated issues of climate change and land use could be valuable in generating new options on how mangroves and peatlands should be best managed. This paper is produced by bringing together Indonesian and international scientists from diverse backgrounds and with diverse experiences in both freshwater and coastal tropical wetlands. It describes the state of the science, significant research needs, and potential transdisciplinary approaches necessary to implement climate change adaptation and mitigation strategies.

Whole-island carbon stocks in the tropical Pacific: Implications for mangrove conservation and upland restoration - Donato, D. C.; Kauffman, J. B.; Mackenzie, R. A.; Ainsworth, A.; Pfleeger, A. Z. (Journal of Environmental Management, 2012)
Management of forest carbon (C) stocks is an increasingly prominent land-use issue. Knowledge of carbon storage in tropical forests is improving, but regional variations are still poorly understood, and this constrains forest management and conservation efforts associated with carbon valuation mechanisms (e.g., carbon markets). This deficiency is especially pronounced in tropical islands and low-lying coastal areas where climate change impacts are expected to be among the most severe. This study presents the first field estimate of island-wide carbon storage in ecosystems of Oceania, with special attention to the regional role of coastal mangroves, which occur on islands and coastal zones throughout the tropics. On two island groups of Micronesia (Yap and Palau), we sampled all above- and belowground C pools, including soil and vegetation, in 24 sites distributed evenly among the three major vegetation structural types: mangroves, upland forests, and open savannas (generally on degraded lands formerly forested). Total C stocks were estimated to be 3.9 and 15.2Tg C on Yap and Palau, respectively. Mangroves contained by far the largest per-hectare C pools (830-1218Mg Cha -1), with deep organic-rich soils alone storing more C (631-754Mg Cha -1) than all pools combined in upland systems. Despite coveringjust 12-13% of land area, mangroves accounted for 24-34% of total island C stocks. Savannas (156-203Mg Cha -1) contained significantly lower C stocks than upland forests (375-437Mg Cha -1), suggesting that reforesting savannas where appropriate has high potential for carbon-based funding to aid restoration objectives. For mangroves, these results demonstrate the key role of these systems within the broader context of C storage in island and coastal landscapes. Sustainable management of mangrove forests and their large C stocks is of high importance at the regional scale, and climate change mitigation programs such as REDD+ could play a large role in avoiding deforestation of mangroves where this is a management objective. © 2011 Elsevier Ltd.

Advanced land observing satellite phased array type L-Band SAR (ALOS PALSAR) to inform the conservation of mangroves: Sundarbans as a case study - Cornforth, William A.; Fatoyinbo, Temilola E.; Freemantle, Terri P.; Pettorelli, Nathalie (Remote Sensing, 2013)
Mangroves are an important bulkhead against climate change: they afford protection for coastal areas from tidal waves and cyclones, and are among the most carbon-rich forests in the tropics. As such, protection of mangroves is an urgent priority. This work provides some new information on patterns of degradation in the Sundarbans, the largest contiguous mangrove forest in the world, which are home to more than 35 reptile species, 120 commercial fish species, 300 bird species and 32 mammal species. Using radar imagery, we contrast and quantify the recent impacts of cyclone Sidr and anthropogenic degradation on this ecosystem. Our results, inferred from changes in radar backscatter, confirm already reported trends in coastline retreat for this region, with areas losing as much as 200 m of coast per year. They also suggest rapid changes in mangrove dynamics for Bangladesh and India, highlighting an overall decrease in mangrove health in the east side of the Sundarbans, and an overall increase in this parameter for the west side of the Sundarbans. As global environmental change takes its toll in this part of the world, more detailed, regular information on mangroves' distribution and health is required: our study illustrates how different threats experienced by mangroves can be detected and mapped using radar-based information, to guide management action. © 2013 by the authors.

Are mangroves in arid environments isolated systems? Life-history and evidence of dietary contribution from inwelling in a mangrove-resident shrimp species - Al-Maslamani, I.; Walton, M. E.M.; Kennedy, H. A.; Al-Mohannadi, M.; Le Vay, L. (Estuarine, Coastal and Shelf Science, 2013)
The Arabian Gulf represents one of the more northerly extremes of mangrove distribution in the Indo-Pacific, and is populated only by Avicennia marina, due to its tolerance of high salinity and wide temperature extremes. Recent studies suggest that in the arid coastal environment of the western Arabian Gulf, export of carbon and nitrogen from mangroves to adjacent habitats may be limited, though it is not clear if this is due to low productivity or physical factors such as the lack of freshwater flow and the tidal regime. Although seagrass and macroalgal habitats are relatively much more dominant by area, with only small pockets of mangrove around the edges of embayments, it is not evident if inwelling from these habitats support mangrove fauna. Year-round sampling in mangroves at Al-Khor, Qatar, indicates that Palaemon khori, an endemic shrimp species, is strongly associated with mangroves throughout its post-settlement life cycle, from recruitment as small 9-10mm juveniles through to mating and egg production. Rapid post-recruitment growth (k=1.8, L∞=42mm for females, k=1.5, L∞=35mm for male) means that most individuals reached adult size in the first few months after settlement, with reproduction occurring in the following spring. As might be expected from year-round residence in the mangrove, dual 13C and 15N isotope analysis indicated a strong contribution of mangroves to shrimp tissue growth (Mean and 95% confidence range, 37% and 27-48%), but with a weaker significant contribution from particulate organic matter (20% and 1-37%), mangrove epiphytes (16% and 2-33%) and seagrasses (9% and 0.2-18%). Other primary producers contribute the remaining 18% to shrimp nutrition but the 95% confidence ranges include zero, suggesting possibly non-significant roles in supporting the shrimp population. This dietary information supports the view that fauna resident within arid mangrove systems are mainly dependent on localised retention and cycling of nutrients with a smaller contribution from inwelling. © 2013 Elsevier Ltd.

Assessing stream restoration works in the southern Macquarie Marshes using hydrodynamic modeling - Wen, L.; Ralph, T.; Hosking, T.; Barma, D.; Saintilan, N. (Proceedings - 20th International Congress on Modelling and Simulation, MODSIM 2013, 2013)
The Macquarie Marshes are an extensive wetland system located in central New South Wales within the lower Macquarie Catchment, representing one of the largest semi-permanent wetlands in southeastern Australia. The Marshes are one of most biologically diverse wetland systems in the Murray Darling Basin, and support some of the largest waterbird breeding events in Australia. A number of studies have demonstrated the critical role of inundation in maintaining the ecological values of the Marshes. The inundation extent, duration and depth of the core wetlands in the Marshes are variable over long and short time-scales, related to geomorphology and flow variability in the Macquarie River. Processes of sedimentation and erosion underlie channel changes in the Marshes and have created a range of landforms with distinct characteristics and spatial distribution. As channels change and move on the floodplain, flooding and sedimentation patterns change and the wetlands respond by relocating, expanding and contracting. The streams and wetlands of the southern part of the Macquarie Marshes have been associated with notable hydrological and geomorphic changes over recent history including channel erosion, changing flow paths and reductions in wetland inundation. Some wetlands have been partly or wholly abandoned by the modern streams (e.g. Macquarie Terminus Marsh and Willie Marsh), while ecologically important wetlands have also developed and changed over time (e.g. Willancorah Swamp). In addition to natural fluvial landforms, there are many anthropogenic features (e.g. roads, levee banks, regulators and channels) that modify the natural landscape and influence flow in the system. While channel change over time is a significant factor for wetland conservation, the impacts of channel change and potential intervention scenarios have never been assessed at the wetland system or sub-system scale in the South Marshes. In this study, we built a 1D/2D coupled hydrodynamic model (MIKE FLOOD) at fine spatial resolution (30 m) for the South Marshes. The MIKE FLOOD gives us the ability to evaluate the impacts of channel change on flow distribution both within channels and on the floodplain. We constructed and simulated three scenarios representing the baseline (i.e. no change to the current channel depth as in 2008), worsening (i.e. erosion keeps on going resulting deepened and built-up channels), and improved (through channel stabilizing etc.). The flow distribution and inundation extent under the three scenarios were compared for low, medium and high flows. The results showed that there were substantial differences in flooding patterns in terms of river flow distribution, flow breaking (into floodplain) locations, and inundation extents even for low flow conditions. However, the biggest changes were for medium flow. The study demonstrated that hydrodynamic models could be a useful tool in floodplain restoration through comparing the outcomes of alternative remediating works and predicting the outcomes of proposed works on wetland system hydrology and inundation patterns.

Assessing the capacity of seagrass meadows for carbon burial: Current limitations and future strategies - Duarte, Carlos M.; Kennedy, Hilary; Marbà, Núria; Hendriks, Iris (Ocean and Coastal Management, 2013)
Seagrass meadows support high primary production rates and their canopies are efficient at filtering particles out of their water column as well as in preventing resuspension of the sediments. In addition, decomposition rates in seagrass sediments are slow, because of low nutrient concentration in seagrass detritus and low oxygen concentration in seagrass sediments. These characteristics result in high carbon burial rates in seagrass meadows, which have the capacity to accumulate large stores of carbon in their sediments, raising the seafloor. Carbon fingerprinting techniques allow to calculate both the age of these deposits and, therefore, the rate of carbon burial and identify the contribution of carbon produced by the seagrass. Yet, data on the regional cover and carbon stocks in seagrass meadows is sparse for some regions, particularly the Indo-Pacific, Africa and South America. In addition, our understanding of the factors regulating the variability in carbon sink capacity among seagrass meadows is limited. These gaps limit the capacity to formulate strategies to mitigate climate change based on the carbon sink capacity of seagrass meadows. A research strategy needs be formulated to address these gaps and provide the necessary protocols to ensure the accountability of mitigation actions involving the conservation and restoration of seagrass meadows. © 2011 Elsevier Ltd.

Assessing the CO2 capture potential of seagrass restoration projects - Duarte, Carlos M.; Sintes, Tomás; Marbà, Núria (Journal of Applied Ecology, 2013)
Summary: Seagrass meadows are important carbon sinks, and they are experiencing a global decline. Restoration of seagrass meadows provides a strategy to mitigate climate change while conserving these important ecosystems. We examined the long-term carbon sequestration expected for seagrass restoration programmes by developing a model that combined models of patch growth, patch survival in seagrass planting projects and estimates of seagrass CO2 sequestration per unit area for the five seagrass species commonly used in restoration programmes. The model results indicated that the cumulative C sequestered increased rapidly over time and with planting density to reach an asymptote at a planting density of 100 units ha-1 (or 6 m spacing between units). At this planting density, the modelled cumulative C sequestered ranges from 177 to over 1337 tons CO2 ha-1 after 50 years. The value corresponding to this carbon sequestration suggests that the costs of seagrass restoration programmes may be fully recovered by the total CO2 captured in societies with a carbon tax in place, providing additional ecosystem services derived from the role of seagrasses in providing ecosystem services, such as enhanced biodiversity. Synthesis and applications. Seagrass restoration programmes are economically viable strategies to mitigate climate change through carbon sequestration, particularly in subtropical and tropical island states where land-based options have a limited scope. Seagrass restoration programmes are economically viable strategies to mitigate climate change through carbon sequestration, particularly in subtropical and tropical island states where land-based options have a limited scope. © 2013 British Ecological Society.

Climate change mitigation strategies should include tropical wetlands Climate change mitigation strategies should include tropical wetlands - Taylor, Publisher; Murdiyarso, Daniel; Kauffman, J Boone; Verchot, Louis V (Carbon Management, 2013)

Climate warming and Mediterranean seagrass - Jordà, Gabriel; Marbà, Núria; Duarte, Carlos M. (Nature Climate Change, 2013)

CO2 Efflux from Shrimp Ponds in Indonesia - Sidik, Frida; Lovelock, Catherine E. (PLoS ONE, 2013)
The conversion of mangrove forest to aquaculture ponds has been increasing in recent decades. One of major concerns of this habitat loss is the release of stored 'blue' carbon from mangrove soils to the atmosphere. In this study, we assessed carbon dioxide (CO2) efflux from soil in intensive shrimp ponds in Bali, Indonesia. We measured CO2 efflux from the floors and walls of shrimp ponds. Rates of CO2 efflux within shrimp ponds were 4.37 kg CO2 m-2 y-1 from the walls and 1.60 kg CO2 m-2 y-1 from the floors. Combining our findings with published data of aquaculture land use in Indonesia, we estimated that shrimp ponds in this region result in CO2 emissions to the atmosphere between 5.76 and 13.95 Tg y-1. The results indicate that conversion of mangrove forests to aquaculture ponds contributes to greenhouse gas emissions that are comparable to peat forest conversion to other land uses in Indonesia. Higher magnitudes of CO2 emission may be released to atmosphere where ponds are constructed in newly cleared mangrove forests. This study indicates the need for incentives that can meet the target of aquaculture industry without expanding the converted mangrove areas, which will lead to increased CO2 released to atmosphere. © 2013 Sidik and Lovelock.

Current status and conservation of mangroves in Africa: An overview. - Ajonina, G; Diamé, A; Kairo, J (Journal of Chemical Information and Modeling, 2013)
Predicting the binding mode of flexible polypeptides to proteins is an important task that falls outside the domain of applicability of most small molecule and protein−protein docking tools. Here, we test the small molecule flexible ligand docking program Glide on a set of 19 non-α-helical peptides and systematically improve pose prediction accuracy by enhancing Glide sampling for flexible polypeptides. In addition, scoring of the poses was improved by post-processing with physics-based implicit solvent MM- GBSA calculations. Using the best RMSD among the top 10 scoring poses as a metric, the success rate (RMSD ≤ 2.0 Å for the interface backbone atoms) increased from 21% with default Glide SP settings to 58% with the enhanced peptide sampling and scoring protocol in the case of redocking to the native protein structure. This approaches the accuracy of the recently developed Rosetta FlexPepDock method (63% success for these 19 peptides) while being over 100 times faster. Cross-docking was performed for a subset of cases where an unbound receptor structure was available, and in that case, 40% of peptides were docked successfully. We analyze the results and find that the optimized polypeptide protocol is most accurate for extended peptides of limited size and number of formal charges, defining a domain of applicability for this approach.

Detecting large scale conversion of mangroves to aquaculture with change point and mixed-pixel analyses of high-fidelity MODIS data - Rahman, Abdullah F.; Dragoni, Danilo; Didan, Kamel; Barreto-Munoz, Armando; Hutabarat, Joseph A. (Remote Sensing of Environment, 2013)
Mangrove forests of the tropical and subtropical regions provide critical ecosystem services, fulfill important socio-economic and environmental functions, and support coastal livelihoods. These forests are also among the most vulnerable ecosystems, both to anthropogenic disturbance and climate change. Yet, no map or published study exists showing detailed spatiotemporal trends of mangrove deforestation at local to regional scales. This study uses change point and mixed-pixel analyses with a time series (2000-2010) of high-fidelity imagery from NASA's Moderate Resolution Imaging Spectroradiometer (MODIS) for tracking deforestation of mangroves in the Mahakam Delta of Indonesia at 250. m spatial scale and a 3-monthly temporal interval. The results show that a total of 21,000 ± 152. ha of mangrove land in the Mahakam Delta were deforested and converted to shrimp ponds in 11. years. In 2000, the deforested lands covered 47% of the entire delta, while in 2010 it increased to 75%. Deforestation rates varied in each year, but peaked in 2002 and declined since then. The combination of high-fidelity time series data and a robust method of change detection resulted in a virtual reconstruction of 11. years of drastic land change history of the delta's mangrove areas at a consistent spatiotemporal scale. We anticipate that the methodology developed in this study will be useful to reconstruct deforestation histories of other places as well. Also, our findings can potentially be used to further explore the socioeconomic drivers of mangrove deforestation so that reliable, appropriate and sustainable methods of local and regional scale adaptation/mitigation strategies can be developed. © 2012 Elsevier Inc.

Diversity of European seagrass indicators: Patterns within and across regions - Marbà, Núria; Krause-Jensen, Dorte; Alcoverro, Teresa; Birk, Sebastian; Pedersen, Are; Neto, Joao M.; Orfanidis, Sotiris; Garmendia, Joxe M.; Muxika, Iñigo; Borja, Angel; Dencheva, Kristina; Duarte, Carlos M. (Hydrobiologia, 2013)
Seagrasses are key components of coastal marine ecosystems and many monitoring programmes worldwide assess seagrass health and apply seagrasses as indicators of environmental status. This study aims at identifying the diversity and characteristics of seagrass indicators in use within and across European ecoregions in order to provide an overview of seagrass monitoring effort in Europe. We identified 49 seagrass indicators used in 42 monitoring programmes and including a total of 51 metrics. The seagrass metrics represented 6 broad categories covering different seagrass organizational levels and spatial scales. The large diversity is particularly striking considering that the pan-European Water Framework Directive sets common demands for the presence and abundance of seagrasses and related disturbance-sensitive species. The diversity of indicators reduces the possibility to provide pan-European overviews of the status of seagrass ecosystems. The diversity can be partially justified by differences in species, differences in habitat conditions and associated communities but also seems to be determined by tradition. Within each European region, we strongly encourage the evaluation of seagrass indicator-pressure responses and quantification of the uncertainty of classification associated to the indicator in order to identify the most effective seagrass indicators for assessing ecological quality of coastal and transitional water bodies. © 2012 Springer Science+Business Media Dordrecht.

Ecosystem functioning: The basis for sustainable management of Terminos Lagoon, Campeche Mexico - Yáñez-Arancibia, Alejandro; Day, John W.; Lara-Domínguez, Ana L.; Sánchez-Gil, Patricia; Villalobos, Guillermo J.; Herrera-Silveira, Jorge A. (Gulf of Mexico Origin, Waters, and Biota: Volume 4, Ecosystem-Based Management, 2013)

Effects of in situ CO2 enrichment on the structural and chemical characteristics of the seagrass Thalassia testudinum - Campbell, Justin E.; Fourqurean, James W. (Marine Biology, 2013)
Seagrasses commonly display carbon-limited photosynthetic rates. Thus, increases in atmospheric pCO2, and consequentially oceanic CO2(aq) concentrations, may prove beneficial. While addressed in mesocosms, these hypotheses have not been tested in the field with manipulative experimentation. This study examines the effects of in situ CO2(aq) enrichment on the structural and chemical characteristics of the tropical seagrass, Thalassia testudinum. CO2(aq) availability was manipulated for 6 months in clear, open-top chambers within a shallow seagrass meadow in the Florida Keys (USA), reproducing forecasts for the year 2100. Structural characteristics (leaf area, leaf growth, shoot mass, and shoot density) were unresponsive to CO2(aq) enrichment. However, leaf nitrogen and phosphorus content declined on average by 11 and 21 %, respectively. Belowground, non-structural carbohydrates increased by 29 %. These results indicate that increased CO2(aq) availability may primarily alter the chemical composition of seagrasses, influencing both the nutrient status and resilience of these systems. © 2013 Springer-Verlag Berlin Heidelberg.

Global warming enhances sulphide stress in a key seagrass species (NW Mediterranean) - García, Rosa; Holmer, Marianne; Duarte, Carlos M.; Marbà, Núria (Global Change Biology, 2013)
The build-up of sulphide concentrations in sediments, resulting from high inputs of organic matter and the mineralization through sulphate reduction, can be lethal to the benthos. Sulphate reduction is temperature dependent, thus global warming may contribute to even higher sulphide concentrations and benthos mortality. The seagrass Posidonia oceanica is very sensitive to sulphide stress. Hence, if concentrations build up with global warming, this key Mediterranean species could be seriously endangered. An 8-year monitoring of daily seawater temperature, the sulphur isotopic signatures of water (δ34Swater), sediment (δ34SCRS) and P. oceanica leaf tissue (δ34Sleaves), along with total sulphur in leaves (TSleaves) and annual net population growth along the coast of the Balearic archipelago (Western Mediterranean) allowed us to determine if warming triggers P. oceanica sulphide stress and constrains seagrass survival. From the isotopic S signatures, we estimated sulphide intrusion into the leaves (Fsulphide) and sulphur incorporation into the leaves from sedimentary sulphides (SSleaves). We observed lower δ34Sleaves, higher Fsulphide and SSleaves coinciding with a 6-year period when two heat waves were recorded. Warming triggered sulphide stress as evidenced by the negative temperature dependence of δ34Sleaves and the positive one of Fsulphide, TSleaves and SSleaves. Lower P. oceanica net population growth rates were directly related to higher contents of TSleaves. At equivalent annual maximum sea surface water temperature (SSTmax), deep meadows were less affected by sulphide intrusion than shallow ones. Thus, water depth acts as a protecting mechanism against sulphide intrusion. However, water depth would be insufficient to buffer seagrass sulphide stress triggered by Mediterranean seawater summer temperatures projected for the end of the 21st century even under scenarios of moderate greenhouse gas emissions, A1B. Mediterranean warming, therefore, is expected to enhance P. oceanica sulphide stress, and thus compromise the survival of this key habitat along its entire depth distribution range. © 2013 John Wiley & Sons Ltd.

Height and biomass of mangroves in Africa from ICESat/GLAS and SRTM - Fatoyinbo, Temilola E.; Simard, Marc (International Journal of Remote Sensing, 2013)
The accurate quantification of the three-dimensional (3-D) structure of mangrove forests is of great importance, particularly in Africa where deforestation rates are high and the lack of background data is a major problem. The objectives of this study are to estimate (1) the total area, (2) canopy height distributions, and (3) above-ground biomass (AGB) of mangrove forests in Africa. To derive the 3-D structure and biomass maps of mangroves, we used a combination of mangrove maps derived from Landsat Enhanced Thematic Mapper Plus (ETM+), lidar canopy height estimates from ICESat/GLAS (Ice, Cloud, and land Elevation Satellite/Geoscience Laser Altimeter System), and elevation data from SRTM (Shuttle Radar Topography Mission) for the African continent. The lidar measurements from the large footprint GLAS sensor were used to derive local estimates of canopy height and calibrate the interferometric synthetic aperture radar (InSAR) data from SRTM. We then applied allometric equations relating canopy height to biomass in order to estimate AGB from the canopy height product. The total mangrove area of Africa was estimated to be 25,960 km2 with 83% accuracy. The largest mangrove areas and the greatest total biomass were found in Nigeria covering 8573 km2 with 132 × 106 Mg AGB. Canopy height across Africa was estimated with an overall root mean square error of 3.55 m. This error includes the impact of using sensors with different resolutions and geolocation error. This study provides the first systematic estimates of mangrove area, height, and biomass in Africa. © 2013 Taylor and Francis.

Insuring mangrove forests for their role in mitigating coastal erosion and storm-surge: An australian case study - Bell, Justine; Lovelock, Catherine E. (Wetlands, 2013)
Mangrove forests provide important ecosystem services, including protecting coastlines from the impacts of extreme weather events, such as storm surge and erosion. Unfortunately, these same extreme weather events also degrade mangrove forests. Currently, there are no comprehensive financial mechanisms in place to ensure that mangroves are rehabilitated following storm damage. This article explores whether there is a legal basis for applying insurance to mangrove forests, to ensure that mangroves are rehabilitated to retain their protective functions. This article uses Australian insurance law as a case study, and first analyses whether the legal principles underpinning insurance can be extended to mangrove forests, and then addresses the practical difficulties involved in developing an insurance product of this type. This article concludes that mangrove insurance is technically feasible, and provides a series of recommendations for policy-makers and the insurance industry. © US Government 2013.

Integrated carbon budget models for the everglades terrestrial-coastal-oceanic gradient: Current status and needs for inter-site comparisons - Troxler, Tiffany G.; Gaiser, Evelyn; Barr, Jordan; Fuentes, Jose D.; Jaffé, Rudolf; Childers, Daniel L.; Colado-Vides, Ligia; Rivera-Monroy, Victor H.; Castañeda-Moya, Edward; Anderson, William; Chambers, Randy; Chen, Meilian; et al. (Oceanography, 2013)
Recent studies suggest that coastal ecosystems can bury significantly more C than tropical forests, indicating that continued coastal development and exposure to sea level rise and storms will have global biogeochemical consequences. The Florida Coastal Everglades Long Term Ecological Research (FCE LTER) site provides an excellent subtropical system for examining carbon (C) balance because of its exposure to historical changes in freshwater distribution and sea level rise and its history of significant long-term carbon-cycling studies. FCE LTER scientists used net ecosystem C balance and net ecosystem exchange data to estimate C budgets for riverine mangrove, freshwater marsh, and seagrass meadows, providing insights into the magnitude of C accumulation and lateral aquatic C transport. Rates of net C production in the riverine mangrove forest exceeded those reported for many tropical systems, including terrestrial forests, but there are considerable uncertainties around those estimates due to the high potential for gain and loss of C through aquatic fluxes. C production was approximately balanced between gain and loss in Everglades marshes; however, the contribution of periphyton increases uncertainty in these estimates. Moreover, while the approaches used for these initial estimates were informative, a resolved approach for addressing areas of uncertainty is critically needed for coastal wetland ecosystems. Once resolved, these C balance estimates, in conjunction with an understanding of drivers and key ecosystem feedbacks, can inform cross-system studies of ecosystem response to long-term changes in climate, hydrologic management, and other land use along coastlines. © 2013 by The Oceanography Society. All rights reserved.

Latitudinal Patterns of Herbivory in Mangrove Forests: Consequences of Nutrient Over-Enrichment - Feller, Ilka C.; Chamberlain, Anne H.; Piou, Cyril; Chapman, Samantha; Lovelock, Catherine E. (Ecosystems, 2013)
Ecosystems in the tropics are predicted to have stronger responses to nutrient enrichment, greater diversity, and more intense biotic interactions than in temperate areas. Mangrove forests, which occur across a broad biogeographic range from warm temperate to tropical, provide a unique opportunity to test these hypotheses by investigating the responses of herbivores to nutrient enrichment in temperate versus tropical latitudes. Mangroves are complex intertidal ecosystems with spatial differences in structure and diversity along tidal gradients and are threatened globally by human activities including nutrient over-enrichment. In this study, we used long-term fertilization experiments at the Indian River Lagoon, FL; Twin Cays, Belize; and Bocas del Toro, Panamá to determine how increased nutrients impact herbivore abundance and herbivory of Rhizophora mangle at the tree, forest, and regional scales. At these locations, which span approximately 2185 km and 18.4o of latitude, we fertilized individual trees with one of three treatments (Control, +N, +P) in two zones (fringe, scrub) along transects perpendicular to the shoreline and measured their responses for 4 years. Herbivory was measured as folivory, loss of yield, and tissue mining. Although nutrient enrichment altered plant growth, leaf traits, and nutrient dynamics, these variables had little effect on folivory at any location. Our results did not support the prediction that herbivory and per capita consumption are greatest at the most tropical location. Instead, folivory was highest at the most temperate location and lowest at the intermediate location. Folivory was generally higher in the fringe than in the scrub zone, but the pattern varied by location, herbivore, and nutrient treatment. Folivory by a dominant herbivore, Aratus pisonii, decreased from the highest to the lowest latitude. Our data suggest that factors controlling population dynamics of A. pisonii cascade to the mangrove canopy, linking herbivory to crab densities. © 2013 Springer Science+Business Media New York.

Mangrove biomass estimation in Southwest Thailand using machine learning - Jachowski, Nicholas R.A.; Quak, Michelle S.Y.; Friess, Daniel A.; Duangnamon, Decha; Webb, Edward L.; Ziegler, Alan D. (Applied Geography, 2013)
Mangroves play a disproportionately large role in carbon sequestration relative to other tropical forest ecosystems. Accurate assessments of mangrove biomass at the site-scale are lacking, especially in mainland Southeast Asia. This study assessed tree biomass and species diversity within a 151ha mangrove ecosystem on the Andaman Coast of Thailand. High-resolution GeoEye-1 satellite imagery, medium resolution ASTER satellite elevation data, field-based tree measurements, published allometric biomass equations, and a suite of machine learning techniques were used to develop spatial models of mangrove biomass. Field measurements derived a whole-site tree density of 1313treesha-1, with Rhizophora spp. comprising 77.7% of the trees across forty-five 400m2 sample plots. A support vector machine regression model was found to be most accurate by cross-validation for predicting biomass at the site level. Model-estimated above-ground biomass was 250Mgha-1; below-ground root biomass was 95Mgha-1. Combined above-ground and below-ground biomass for the entire 151-ha stand was 345 (±72.5)Mgha-1, equivalent to 155 (±32.6)MgCha-1. Model evaluation shows the model had greatest prediction error at high biomass values, indicating a need for allometric equations determined over a larger range of tree sizes. © 2013 Elsevier Ltd.

Mapping of mangrove forest land cover change along the Kenya coastline using Landsat imagery - Kirui, K. B.; Kairo, J. G.; Bosire, J.; Viergever, K. M.; Rudra, S.; Huxham, M.; Briers, R. A. (Ocean and Coastal Management, 2013)
Mangroves in Kenya provide a wide range of valuable services to coastal communities despite their relatively small total area. Studies at single sites show reductions in extent and quality caused by extraction for fuel wood and timber and clearance for alternative land use including saltpans, aquaculture, and tourism. Such studies suggest that Kenyan mangroves are likely to conform to the general global trend of declining area but there are no reliable recent estimates of either total mangrove extent or trends in coverage for the country. The total extent of Kenyan mangroves was estimated at four points in time (1985, 1992, 2000 and 2010) using Landsat satellite imagery. Due to its medium resolution, Landsat may underestimate mangrove areas in Kenya where relatively small, linear, coastal features occur. There is also a high frequency of clouds in the coastal areas which can cause data gaps during analysis. However comparison with aerial photographs taken in 1992 showed satisfactory levels of accuracy (87.5%) and Cohen's Kappa (0.54) validating its use in this context. These 1992 data provided an independently validated baseline from which to detect changes (fore- and hind-casted) in other periods after removing cloud coverage. We estimated total mangrove coverage in 2010 at 45,590ha representing a loss of 18% (0.7%yr-1) in the 25 years between 1985 and 2010. Rates of mangrove loss for Kenya varied both spatially and temporally with variations possibly due to legislative inadequacies and differences in habitat alteration patterns. Hence freely available Landsat images proved adequate to detect changes in mangroves and revealed that Kenya shows rates of decline similar to (although slower than) global estimates. © 2011 Elsevier Ltd.

Mechanisms of bicarbonate use influence the photosynthetic carbon dioxide sensitivity of tropical seagrasses - Campbell, Justin E.; Fourqurean, James W. (Limnology and Oceanography, 2013)
The photosynthetic bicarbonate (HCO3-) use properties of three widely distributed tropical seagrasses were compared using a series of laboratory experiments. Photosynthetic rates of Thalassia testudinum, Halodule wrightii, and Syringodium filiforme were monitored in an enclosed chamber while being subjected to shifts in pH and dissolved inorganic carbon. Specific mechanisms of seagrass HCO3- use were compared by examining the photosynthetic effects of the carbonic anhydrase inhibitor acetazolamide (AZ). All seagrasses increased photosynthetic rates with reduced pH, suggesting a large effect of dissolved aqueous carbon dioxide (CO2(aq)). However, there was considerable interspecific variation in pH response. T. testudinum was highly sensitive, increasing photosynthetic rates by 100% as the pH was reduced from 8.2 to 7.4, whereas rates in H. wrightii and S. filiforme increased by only 20% over a similar range, and displayed prominent photosynthetic plateaus, indicating an increased capacity for HCO3- use. Additional incubations that manipulated [HCO3-] under constant [CO2(aq)] support these findings, as only H. wrightii and S. filiforme increased photosynthetic rates with increasing [HCO3-]. T. testudinum responded to AZ addition, indicating that carbonic anhydrase enzymes facilitate limited HCO3- use. H. wrightii and S. filiforme showed no response to AZ, suggesting alternate, more efficient mechanisms of HCO3- use. Estimated kinetic parameters, Ks(CO2) and Vmax, revealed interspecific variation and further support these conclusions. Variation in photosynthetic pH responses and AZ sensitivity indicate distinctions in the carbon use properties of seagrasses exposed to similar environmental conditions. These results suggest that not all seagrasses will similarly respond to future increases in CO2(aq) availability. Attention towards potential shifts in competitive interactions within multispecific seagrass beds is warranted. © 2013, by the Association for the Sciences of Limnology and Oceanography, Inc.

Nutrient Availability and Soil Organic Matter Decomposition Response to Prescribed Burns in Mid-Atlantic Brackish Tidal Marshes - Geatz, George W.; Needelman, Brian A.; Weil, Raymond R.; Megonigal, J. Patrick (Soil Science Society of America Journal, 2013)
Prescribed fire in tidal marshes has been shown to generate short-term increases in plant-available nutrients, but the long-term implications of fire on nutrient availability and organic matter decomposition have not been well established. Two manipulative experiments were conducted over 1 yr within long-term annual burn and no-burn blocks at the Blackwater National Wildlife Refuge in Cambridge, MD to study the effects of canopy removal and ash deposition on nutrient availability and organic matter decomposition rates following burning. Ash deposition had no significant effects on study variables. At no-burn sites, porewater NH4+ and PO43+ were significantly lower in July in sites with canopy removal (0.15 mg NH4+ L-1 and 0.04 mg PO 43+ L-1) compared to sites with a canopy (0.73 mg NH4+ L-1 and 0.08 mg PO43+ L-1). Similar results were found through a canopy replacement treatment at annual burn sites. Decreased porewater NH 4+ and PO43+ corresponded to increased total biomass nutrient content. No-burn sites with canopy removal treatments showed significantly lower organic matter decomposition rates than did treatments with a canopy in July (66.5 vs. 74.1 % cotton tensile strength loss), corresponding to decreases in porewater NH4+ and PO43+. Plant ash provided a fertilizer pulse of 0.22 g N m-2 and 0.16 g P m-2, which were amounts of N and P likely too small to increase plant productivity when deposited during late winter/early spring. Prescribed fire appears to affect nutrient availability and organic matter decomposition in these marsh soils primarily through the mechanism of increased biomass production due to canopy removal. © Soil Science Society of America, All rights reserved.

Propagating uncertainty to estimates of above-ground biomass for Kenyan mangroves: A scaling procedure from tree to landscape level - Cohen, R.; Kaino, J.; Okello, J. A.; Bosire, J. O.; Kairo, J. G.; Huxham, M.; Mencuccini, M. (Forest Ecology and Management, 2013)
Mangroves are globally important carbon stores and as such have potential for inclusion in future forest-based climate change mitigation strategies such as Reduced Emissions from Deforestation and Degradation (REDD+). Participation in REDD+will require developing countries to produce robust estimates of forest above-ground biomass (AGB) accompanied by an appropriate measure of uncertainty. Final estimates of AGB should account for known sources of uncertainty (measurement and predictive) particularly when estimating AGB at large spatial scales. In this study, mixed-effects models were used to account for variability in the allometric relationship of Kenyan mangroves due to species and site effects. A generic biomass equation for Kenyan mangroves was produced in addition to a set of species-site specific equations. The generic equation has potential for broad application as it can be used to predict the AGB of new trees where there is no pre-existing knowledge of the specific species-site allometric relationship: the most commonly encountered scenario in practical biomass studies. Predictions of AGB using the mixed-effects model showed good correspondence with the original observed values of AGB although displayed a poorer fit at higher AGB values, suggesting caution in extrapolation. A strong relationship was found between the observed and predicted values of AGB using an independent validation dataset from the Zambezi Delta, Mozambique (R2=0.96, p= <0.001). The simulation based approach to uncertainty propagation employed in the current study produced estimates of AGB at different spatial scales (tree - landscape level) accompanied by a realistic measure of the total uncertainty. Estimates of mangrove AGB in Kenya are presented at the plot, regional and landscape level accompanied by 95% prediction intervals. The 95% prediction intervals for landscape level estimates of total AGB stocks suggest that between 5.4 and 7.2 megatonnes of AGB is currently held in Kenyan mangrove forests. © 2013 The Authors.

Radiocarbon dating and wood density chronologies of mangrove trees in arid Western Australia - Santini, Nadia S.; Hua, Quan; Schmitz, Nele; Lovelock, Catherine E. (PLoS ONE, 2013)
Mangrove trees tend to be larger and mangrove communities more diverse in tropical latitudes, particularly where there is high rainfall. Variation in the structure, growth and productivity of mangrove forests over climatic gradients suggests they are sensitive to variations in climate, but evidence of changes in the structure and growth of mangrove trees in response to climatic variation is scarce. Bomb-pulse radiocarbon dating provides accurate dates of recent wood formation and tree age of tropical and subtropical tree species. Here, we used radiocarbon techniques combined with X-ray densitometry to develop a wood density chronology for the mangrove Avicennia marina in the Exmouth Gulf, Western Australia (WA). We tested whether wood density chronologies of A. marina were sensitive to variation in the Pacific Decadal Oscillation Index, which reflects temperature fluctuations in the Pacific Ocean and is linked to the instrumental rainfall record in north WA. We also determined growth rates in mangrove trees from the Exmouth Gulf, WA. We found that seaward fringing A. marina trees (∼10 cm diameter) were 48±1 to 89±23 years old (mean ± 1σ) and that their growth rates ranged from 4.08±2.36 to 5.30±3.33 mm/yr (mean±1σ). The wood density of our studied mangrove trees decreased with increases in the Pacific Decadal Oscillation Index. Future predicted drying of the region will likely lead to further reductions in wood density and their associated growth rates in mangrove forests in the region. © 2013 Santini et al.

Regeneration of a mangrove forest in a nature reserve and participatory management context (Mida Creek, Kenya) - Céline, F; Kairo, J; Mohamed, MOS (Vliz.Be, 2013)
Mida Creek mangrove forest is part of what was the first marine protected area in Kenya, established in 1968 and amongst the first in Africa. This establishment followed a growing pressure of human activity on the forest, mainly linked with the high wood requirements of the growing tourism sector. Ten years later, the mangrove was also included in the Arabuko-Sokoke Nature Reserve, which is today the largest protected fragment of a forest mosaic that once stretched from southern Somalia to northern Mozambique. In addition to this national protection, Mida Creek also benefits from the international status of 'Man and Biosphere Reserve' from UNESCO and the 'Important Bird Area' by BirdLife International in 2001. Those multiple protection statuses represent valuable legal tools in helping restoration of this human-impacted forest but in practice it also lead to conflicts of interest between stakeholders who share management and resources. After being excluded of the mangrove management for many years, the local population which depends to a large degree on the mangrove resources, is finally officially recognized as one of the stakeholders of the forests, through a governmental act signed in 2005 (Forest Act 2005, revised in 2012). However, the implementation of that act is slow and issues of trust and corruption are still an important obstacle to the efforts given to conservation and restoration. Our study aims at evaluating changes occurring in terms of management and forest regeneration, by the use of socio-ecological indicators. The first indicator concerns the new management approach implementation and the level of community involvement into restoration and conservation projects. The second indicator is an assessment of mangrove regeneration patterns and artificial restoration (i.e. plantations) success. The tools used to measure those indicators were: interviews with key-informants and population, policy analysis, satellite images and botanical surveys in plantations. Our first results show that involvement of local population is perceived as low and partial. 32% of the respondents cited the community as one of the forest's managers, while state organizations were cited in 91% of the cases. Only 20% of people interviewed were currently involved in a mangrove conservation-related project, while dependence on the mangrove and its resources is still high amongst the population. Alternative activities such as bee-keeping or Casuarina equistifolia planting exist and are spreading but still often considered as marginal. Concerning the mangrove forest, an increase in tree coverage from 2000 to 2013 with older and bigger trees was observed from the maps. However, low success and poor management of the plantations hamper the idea that they could be used in the future by the community. brought to you by CORE View metadata, citation and similar papers at core.ac.uk provided by Open Marine Archive

Sedimentation, elevation and marsh evolution in a southeastern Australian estuary during changing climatic conditions - Rogers, Kerrylee; Saintilan, Neil; Howe, Alice J.; Rodríguez, José F. (Estuarine, Coastal and Shelf Science, 2013)
Mangrove and salt marsh vertical accretion and surface elevation change was measured at Kooragang Island within the Ramsar-listed Lower Hunter estuarine wetlands in New South Wales, Australia, using surface elevation tables and marker horizons over a ten-year period. We surveyed mangrove, salt marsh and a zone of mangrove encroachment into salt marsh. The period of analysis was dominated by El Niño (drought) climatic conditions, though included a series of east coast low pressure systems and associated storms over the central coast of NSW in June 2007. The storms may have initially caused scouring of sediments in the mangrove zone, followed by significant accretion within both the mangrove and salt marsh during the six months following the storms, with most of this accretion corresponding to spring tides several months after the storms. These accretion events were not accompanied by an equivalent elevation change, and robust elevation trends over the study period in mangrove and salt marsh indicate that the storms may have had little impact on the longer-term elevation dynamics within both the mangrove and salt marsh at Kooragang Island. Elevation dynamics in these zones appear to be regulated by vertical accretion over longer time periods and modulated by hydrology at shorter temporal scales. Elevation declined in the mangrove encroachment zone despite continued vertical accretion and we propose that this discrepancy may be associated with expansion of tidal creeks near the zone of mangrove encroachment or loss of salt marsh vegetation. This pattern of encroachment is consistent with observations from sites throughout the region and may be related to climatic perturbations (El Niño Southern Oscillation) rather than directly attributed to the storms. © 2013 Elsevier Ltd.

Spatial pattern in seagrass stoichiometry indicates both N-limited and P-limited regions of an iconic P-limited subtropical bay - Burkholder, Derek A.; Fourqurean, James W.; Heithaus, Michael R. (Marine Ecology Progress Series, 2013)
We investigated seagrass species distribution and nutrient content in the iconic phosphorus- limited Shark Bay, Western Australia. We found the slower-growing, temperate species Amphibolis antarctica and Posidonia spp. had lower N and P content compared to the fastergrowing tropical species Halodule uninervis, Syringodium isoetifolium, Cymodocea angustata, Halophila ovalis and Halophila spinulosa. Further, by comparing elemental content of different seagrass species at sites where species co-occurred, we were able to standardize seagrass elemental content across sites with different species composition. This standardization allowed us to make ecosystem-scale inferences about resource availability despite taxon-specific distributions and elemental content. We found a marked spatial pattern in N:P of seagrasses across the system, indicating that P limitation occurred, despite calcium carbonate sediments, only in the most isolated portions of the bay. Large areas closer to the mouth of the bay were either N limited or were not limited by N or P availability. Our results suggest that large-scale nutrient budgets may oversimplify our understanding of limiting factors in a system, resulting in management decisions that may have unforeseen effects on different areas within the same ecosystem. © Inter-Research 2013.

Species mixing boosts root yield in mangrove trees - Lang'at, Joseph K.Sigi; Kirui, Bernard K.Y.; Skov, Martin W.; Kairo, James G.; Mencuccini, Maurizio; Huxham, Mark (Oecologia, 2013)
Enhanced species richness can stimulate the productivity of plant communities; however, its effect on the belowground production of forests has scarcely been tested, despite the role of tree roots in carbon storage and ecosystem processes. Therefore, we tested for the effects of tree species richness on mangrove root biomass: thirty-two 6 m by 6 m plots were planted with zero (control), one, two or three species treatments of six-month-old Avicennia marina (A), Bruguiera gymnorrhiza (B) and Ceriops tagal (C). A monoculture of each species and the four possible combinations of the three species were used, with four replicate plots per treatment. Above- and belowground biomass was measured after three and four years' growth. In both years, the all-species mix (ABC) had significant overyielding of roots, suggesting complementarity mediated by differences in rhizosphere use amongst species. In year four, there was higher belowground than aboveground biomass in all but one treatment. Belowground biomass was strongly influenced by the presence of the most vigorously growing species, A. marina. These results demonstrate the potential for complementarity between fast- and slow-growing species to enhance belowground growth in mangrove forests, with implications for forest productivity and the potential for belowground carbon sequestration. © 2012 Springer-Verlag Berlin Heidelberg.

The anatomical basis of the link between density and mechanical strength in mangrove branches - Santini, Nadia S.; Schmitz, Nele; Bennion, Vicki; Lovelock, Catherine E. (Functional Plant Biology, 2013)
Tree branches are important as they support the canopy, which controls photosynthetic carbon gain and determines ecological interactions such as competition with neighbours. Mangrove trees are subject to high wind speeds, strong tidal flows and waves that can damage their branches. The survival and establishment of mangroves partly depend on the structural and mechanical characteristics of their branches. In addition, mangroves are exposed to soils that vary in salinity. Highly saline conditions can increase the tension in the water column, imposing mechanical stresses on the xylem vessels. Here, we investigated how mechanical strength, assessed as the modulus of elasticity (MOE) and the modulus of rupture (MOR), and density relate to the anatomical characteristics of intact mangrove branches from southeast Queensland and whether the mechanical strength of branches varies among mangrove species. Mechanical strength was positively correlated with density of mangrove intact branches. Mechanical strength (MOE) varied among species, with Avicennia marina (Forssk.) Vierh. branches having the highest mechanical strength (2079±176MPa), and Rhizophora stylosa Griff. and Bruguiera gymnorrhiza (L.) Savigny ex Lam. and Poiret having the lowest mechanical strength (536.8±39.2MPa in R. stylosa and 554±58.2MPa in B. gymnorrhiza). High levels of mechanical strength were associated with reductions in xylem vessel lumen area, pith content and bark content, and positively associated with increases in fibre wall thickness. The associations between mechanical strength and anatomical characteristics in mangrove branches suggest trade-offs between mechanical strength and water supply, which are linked to tree growth and survival. © 2013 CSIRO.

The impact of sea-level rise on organic matter decay rates in Chesapeake Bay brackish tidal marshes - Kirwan, M. L.; Langley, J. A.; Guntenspergen, G. R.; Megonigal, J. P. (Biogeosciences, 2013)
The balance between organic matter production and decay determines how fast coastal wetlands accumulate soil organic matter. Despite the importance of soil organic matter accumulation rates in influencing marsh elevation and resistance to sea-level rise, relatively little is known about how decomposition rates will respond to sea-level rise. Here, we estimate the sensitivity of decomposition to flooding by measuring rates of decay in 87 bags filled with milled sedge peat, including soil organic matter, roots and rhizomes. Experiments were located in field-based mesocosms along 3 mesohaline tributaries of the Chesapeake Bay. Mesocosm elevations were manipulated to influence the duration of tidal inundation. Although we found no significant influence of inundation on decay rate when bags from all study sites were analyzed together, decay rates at two of the sites increased with greater flooding. These findings suggest that flooding may enhance organic matter decay rates even in water-logged soils, but that the overall influence of flooding is minor. Our experiments suggest that sea-level rise will not accelerate rates of peat accumulation by slowing the rate of soil organic matter decay. Consequently, marshes will require enhanced organic matter productivity or mineral sediment deposition to survive accelerating sea-level rise. © 2013 Author(s).

Tidal marsh plant responses to elevated CO2, nitrogen fertilization, and sea level rise - Adam Langley, J.; Mozdzer, Thomas J.; Shepard, Katherine A.; Hagerty, Shannon B.; Patrick Megonigal, J. (Global Change Biology, 2013)
Elevated CO2 and nitrogen (N) addition directly affect plant productivity and the mechanisms that allow tidal marshes to maintain a constant elevation relative to sea level, but it remains unknown how these global change drivers modify marsh plant response to sea level rise. Here we manipulated factorial combinations of CO2 concentration (two levels), N availability (two levels) and relative sea level (six levels) using in situ mesocosms containing a tidal marsh community composed of a sedge, Schoenoplectus americanus, and a grass, Spartina patens. Our objective is to determine, if elevated CO2 and N alter the growth and persistence of these plants in coastal ecosystems facing rising sea levels. After two growing seasons, we found that N addition enhanced plant growth particularly at sea levels where plants were most stressed by flooding (114% stimulation in the + 10 cm treatment), and N effects were generally larger in combination with elevated CO2 (288% stimulation). N fertilization shifted the optimal productivity of S. patens to a higher sea level, but did not confer S. patens an enhanced ability to tolerate sea level rise. S. americanus responded strongly to N only in the higher sea level treatments that excluded S. patens. Interestingly, addition of N, which has been suggested to accelerate marsh loss, may afford some marsh plants, such as the widespread sedge, S. americanus, the enhanced ability to tolerate inundation. However, if chronic N pollution reduces the availability of propagules of S. americanus or other flood-tolerant species on the landscape scale, this shift in species dominance could render tidal marshes more susceptible to marsh collapse. © 2013 Blackwell Publishing Ltd.

Tropical species at the northern limit of their range: Composition and distribution in Bermuda's benthic habitats in relation to depth and light availability - Manuel, Sarah A.; Coates, Kathryn A.; Kenworthy, W. Judson; Fourqurean, James W. (Marine Environmental Research, 2013)
Surveys were undertaken on the shallow Bermuda marine platform between 2006 and 2008 to provide a baseline of the distribution, condition and environmental characteristics of benthic communities. Bermuda is located in temperate latitudes but coral reefs, tropical seagrasses and calcareous green algae are common in the shallow waters of the platform. The dominant organisms of these communities are all living at or near their northern latitudinal range limits in the Atlantic Ocean. Among the major benthic autotrophs surveyed, seagrasses were most restricted by light availability. We found that the relatively slow-growing and long-lived seagrass Thalassia testudinum is restricted to habitats with much higher light availability than in the tropical locations where this species is commonly found. In contrast, the faster growing tropical seagrasses in Bermuda, Syringodium filiforme, Halodule sp. and Halophila decipiens, had similar ecological compensation depths (ECD) as in tropical locations. Increasing sea surface temperatures, concomitant with global climate change, may either drive or allow the poleward extensions of the ranges of such tropical species. However, due to latitudinal light limitations at least one abundant and common tropical autotroph, T.testudinum, is able to occupy only shallower depths at the more temperate latitudes of Bermuda. We hypothesize that the poleward shift of seagrass species ranges would be accompanied by restrictions to even shallower depths of T.testudinum and by very different seagrass community structures than in tropical locations. © 2013 Elsevier Ltd.

Variability in herbivory in subtropical seagrass ecosystems and implications for seagrass transplanting - Bourque, Amanda S.; Fourqurean, James W. (Journal of Experimental Marine Biology and Ecology, 2013)
Herbivory structures ecosystems in multiple and complex ways and is capable of affecting the success of ecological restoration projects that involve reestablishing plant communities. Direct herbivory on experimental planting units assembled from leaves of the seagrasses Thalassia testudinum, Syringodium filiforme, and Halodule wrightii was assayed in 2009-2010 in south Florida, USA. Seagrass biomass loss to herbivory was compared with elemental composition of donor and ambient seagrass leaves as well as with fish communities at the assay sites. Seagrass herbivores were capable of removing substantial biomass from our experimental planting units, and this varied across seagrass species, location, and time. Seagrass biomass loss to herbivory ranged from 0% to 82%. More biomass was lost during the spring assays than in fall and winter assays. Biomass loss was greatest in S. filiforme and H. wrightii, and negligent in T. testudinum. The assay site closest to tidal cuts leading to the coral reef tract experienced the highest average levels of herbivory. C:N ratios and salinity were predictors of seagrass biomass loss, but not C:P ratios, temperature, or herbivorous fish abundance. Leaf loss to seagrass herbivores appears to be a spatially variable but critically important determinant of seagrass transplanting success. We recommend that local knowledge of herbivory pressure be considered during restoration planning. In our system, a conservative approach to seagrass transplanting, limiting projects to winter months, and refraining from seagrass transplanting all together in areas proximal to coral reefs, are likely to maximize the potential for success. © 2013.

Vegetation and soil characteristics as indicators of restoration trajectories in restored mangroves - Salmo, Severino G.; Lovelock, Catherine; Duke, Norman C. (Hydrobiologia, 2013)
We investigated the restoration trajectories in vegetation and soil parameters of monospecific Rhizophora mucronata stands planted 6, 8, 10, 11, 12, 17, 18, and 50 years ago (restored system). We tested the hypothesis that the changes in vegetation characteristics, with progressing mangrove age, are related to the changes in soil characteristics. The vegetation and soil parameters were compared across this restoration sequence using a reference system comprising mature, natural mangrove stands of unknown age. Rapid increases in leaf area index and aboveground biomass, and declines in tree density and size (in terms of tree diameter and height) occurred with increasing stand age. Soil organic matter, total nitrogen, and soil redox potential increased, and soil temperature decreased as stands aged. These patterns tended to stabilize at approximately the 11th year, indicating the probable age that restoration plots tend toward forest maturity. The time for the restored systems to reach forest maturity, attaining characteristics similar to the reference system, is estimated at 25 years, which is relatively slow compared to forest regeneration trajectories estimated for natural mangroves. Our study describes the trajectory patterns for planted mangroves, which are important for the assessment of both the progress and success of mangrove rehabilitation programs. © 2013 Springer Science+Business Media Dordrecht.

Vegetative and reproductive phenological traits of Rhizophora mucronata Lamk. and Sonneratia alba Sm. - Wang'ondu, Virginia W.; Kairo, James G.; Kinyamario, Jenesio I.; Mwaura, Francis B.; Bosire, Jared O.; Dahdouh-Guebas, Farid; Koedam, Nico (Flora: Morphology, Distribution, Functional Ecology of Plants, 2013)
Mangrove phenology is important in understanding the past, present and future response of mangrove species to impacts of climate change. Our study is the first long term direct observation of the phenology of Rhizophora mucronata and Sonneratia alba in Kenya. Objective of the study was to determine, interpret and document the timing of the various phenoevents and phenophases, and to establish relationships between phenology and the climatic variables. Phenological traits were investigated in six monospecific mangrove stands in Gazi Bay, south of Mombasa, for 2 years. Leaf emergence, leaf fall, flower bud, flower and fruit initiation data were recorded every fortnight in 54 shoots of 9 trees at each site. Continuous leaf emergence and loss characterized by multimodal peaks was observed for the two species. Leaf emergence and leaf fall peaked in the wet months and was reduced in the dry months. There was a relationship between the leaf emergence and drop with the reproductive phenology in the two species. Mean leaf longevity for R. mucronata and S. alba was 12.8. ±. 1.2 and 4.9. ±. 0.5 months respectively. The reproductive cycle took approximately 16-20 months in R. mucronata and 4-5 months in S. alba. Bud initiation in R. mucronata was seasonal and occurred in October and September. Buds were observed for 8-11 months developing slowly on the shoots. Shifts were observed in the timing of flower initiation, and the flowering period lasted in total for 4-5 months. The time period from flower appearance to the developmental start of immature propagules lasted about 1 month at reforested sites and up to 5 months in stands of natural vegetation. In R. mucronata initiation of immature propagules was not seasonal and varied among the sites. Fruiting in S. alba was short and seasonal without overlap, and shifts were observed in the timing of flowering, flowering and fruiting peaks. Abscission of reproductive parts started in July and in June, respectively, in the years 2005 and 2006. Fruiting was observed starting in August in both years, and fruiting peak was reached in October in 2005 and one month earlier in 2006. In R. mucronata vegetative and reproductive phenophases significantly correlated with climatic variables, whereas in S. alba only leaf emergence and leaf fall correlated with temperature. The flowering plasticity in the reproductive phenology of the two species indicates possible sensitivity to certain climatic and environmental triggers. Our results also indicate that R. mucronata trees have a distinctly higher investment in the reproductive cycle than S. alba. © 2013 Elsevier GmbH.

Water use patterns of estuarine vegetation in a tidal creek system - Wei, Lili; Lockington, David A.; Poh, Seng Chee; Gasparon, Massimo; Lovelock, Catherine E. (Oecologia, 2013)
Water availability is a key determinant of the zonation patterns in estuarine vegetation, but water availability and the use of different water sources over space and time are not well understood. We have determined the seasonal water use patterns of riparian vegetation over an estuarine ecotone. Our aim was to investigate how the water use patterns of estuarine vegetation respond to variations in the availability of tidal creek water and rain-derived freshwater. The levels of natural stable isotopes of oxygen and hydrogen were assessed in the stem of the mangrove Avicennia marina (tall and scrub growth forms), Casuarina glauca and Melaleuca quinquenervia that were distributed along transects from river/creek-front towards inland habitats. The isotopic composition of plant tissues and the potential water sources were assessed in both the wet season, when freshwater from rainfall is present, and the dry season, when mangrove trees are expected to be more dependent on tidal water, and when Casuarina and Melaleuca are expected to be dependent on groundwater. Our results indicate that rainwater during the wet season contributes significantly to estuarine vegetation, even to creek-side mangroves which are inundated by tidal creek water daily, and that estuarine vegetation depends primarily on freshwater throughout the year. In contrast, high intertidal scrub mangroves were found to use the greatest proportion of tidal creek water, supplemented by groundwater in the dry season. Contrary to prediction, inland trees C. glauca and M. quinquenervia were found also to rely predominantly on rainwater-even in the dry season. The results of this study reveal a high level of complexity in vegetation water use in estuarine settings. © 2012 Springer-Verlag Berlin Heidelberg.

2013 Supplement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories: Wetlands. Chapter 4: Coastal Wetlands. - Kennedy, Hilary; Alongi, Daniel M; Karim, Ansarul (Comprehensive OrganicSynthesis, 2014)
Methodological Guidance on Lands with Wet and Drained Soils, and Constructed Wetlands for Wastewater Treatment - The 2013 Supplement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories: Wetlands (Wetlands Supplement) provides methods for estimating anthropogenic emissions and removals of greenhouse gases from wetlands and drained soils. The scope of the Wetlands Supplement is broader than the coverage of Wetlands in the 2006 IPCC Guidelines for National Greenhouse Gas Inventories2 (2006 IPCC Guidelines), where managed wetlands are defined as lands where the water table is artificially changed (e.g. drained or raised) or those created through human activity (e.g. damming a river) and that do not fall into Forest Land, Cropland, or Grassland categories. The emissions and removals from wetlands and drained soils addressed in the Wetlands Supplement can occur under any land-use category or other relevant category of the 2006 IPCC Guidelines. The guidance in the Wetlands Supplement is not intended to change the allocation of wetlands for reporting purposes. The guidance provided is supplementary to that contained in the 2006 IPCC Guidelines, which provide methodologies for estimating national anthropogenic emissions by sources and removals by sinks of greenhouse gases not controlled by the Montreal Protocol3. The content of the 2006 IPCC Guidelines on wetlands is restricted to peatlands drained and managed for peat extraction, conversion to flooded lands, and some guidance for drained organic soils. It is therefore incomplete; it does not cover all wetland types and does not characterize all of the significant activities occurring on wetlands that are covered (e.g., rewetting of peatlands is not included). This Wetlands Supplement supplements the 2006 IPCC Guidelines by filling in gaps in the coverage and providing updated information reflecting scientific advances. This includes updating of emission factors. It covers inland organic soils and wetlands on mineral soils, coastal wetlands including mangrove forests, tidal marshes and seagrass meadows, and constructed wetlands for wastewater treatment. For the reasons described subsequently, the Wetlands Supplement does not provide guidance on permanently flooded lands such as reservoirs.

Assessment of Mangrove Carbon Stocks in Cameroon, Gabon, the Republic of Congo (RoC) and the Democratic Republic of Congo (DRC) Including their Potential for Reducing Emissions from Deforestation and Forest Degradation (REDD+) - Ajonina, Gordon N.; Kairo, James; Grimsditch, Gabriel; Sembres, Thomas; Chuyong, George; Diyouke, Eugene (2014)
We present results of the field assessment using a total of fifteen 0.1 ha mangrove permanent sample plots (PSPs) in four selected countries in Central Africa, including: Cameroon, Gabon, Republic of Congo and Democratic of Republic, which together account for 90 % of mangroves in Central Africa. Above- and belowground carbon stocks were computed using data from the PSPs in all four countries. Long-term monitoring data in Cameroon were used to estimate carbon sequestration rates. Four major carbon pools were considered: aboveground carbon, belowground root carbon, deadwood and the soil organic carbon. All the eight mangrove species described in Central Africa were encountered in the study. The dominant species in Central Africa is Rhizophora racemosa, and it occupies more than 70 % of the forest formation. The average stand density ranged from a low of 450 tree/ha in degraded forest of RoC to a high of 3,256 tree/ha in undisturbed stands of Cameroon. Standing volume ranged from a low of 213 m3/ha in RoC to a high of 428 m3/ha in Cameroon; corresponding to aboveground biomass values of 251 and 505 Mg/ha, respectively. Together with the deadwoods, the total vegetation biomass in the study area ranged from a low of 394 Mg/ha in RoC to a high of 825 Mg/ha in Cameroon. Mean diameter increment for primary and secondary stems was 0.15 cm/year. This translates to above- and belowground annual biomass increments of 12.7 and 3.1 Mg/ha/year, respectively. Total ecosystem carbon in undisturbed system was estimated at 1520 ± 164 Mg/ha with 982 Mg/ha (or 65 %) in belowground component (soils and roots) and 538 Mg/ha (35 %) in the aboveground components. Carbon density differed significantly (p < 0.05) with forest conditions. The least total ecosystem carbon of 808 ± 236 Mg/ha was recorded in heavily exploited forests, translating to CO2 equivalent of 2,962 Mg/ha. Undisturbed mangrove forests sequester annually 16.5 MgC/ha against 6.9 MgC/ha for degraded systems. Certain recommendations are made to improve and consolidate these estimates especially through validation of cover change, continuous monitoring PSP as well the development of site specific allometric equations for mangroves in Central Africa.

Assessment of vegetation and soil conditions in restored mangroves interrupted by severe tropical typhoon 'Chan-hom' in the Philippines - Salmo, Severino G.; Lovelock, Catherine E.; Duke, Norman C. (Hydrobiologia, 2014)
Using a space-for-time substitution approach, we investigated the effects of a typhoon on the vegetation and soil development trajectories of monospecific stands of Rhizophora mucronata mangroves of different ages (6-, 8- 10-, 11-, 12-, 17-, 18- and 50-year stands). The vegetation and soil parameters were compared to a reference system comprised of mature, natural mangrove stands. Pre-typhoon measures of vegetation and soil parameters were compared with 1-mo, 7-mo and 9-mo post-typhoon. Prior to the occurrence of the typhoon, there were clear patterns of vegetation and soil development with age of the stands. The development trajectory was however interrupted by the occurrence of the typhoon. Severe damage was more apparent in older mangrove stands (11- and 18- year stands) with very low to no damage in the younger stands. The typhoon-impacted sites experienced a number of changes, including: complete defoliation; reduced living tree densities of 61-69 %; decreased above-ground biomass of 70-79 %; increased soil nutrient levels of 40-60 %; more waterlogged soils by at least 113 % and increased soil temperature of 8-10 °C. Cumulative tree mortality, compounded by the lack of seedling recruits and unfavourable soil conditions may limit long-term recovery of the typhoon-impacted stands. © 2013 Springer Science+Business Media Dordrecht.

Coastal Blue Carbon: Methods for Assessing Carbon Stocks and Emissions Factors in Mangroves, Tidal Salt Marshes, and Seagrass Meadows - Howard, J.; Hoyt, S.; Isensee, K.; Pidgeon, E.; Telszewski, M. (Conservation International, Intergovernmental Oceanographic Commission of UNESCO, International Union for Conservation of Nature. Arlington, Virginia, USA., 2014)
Mangroves, tidal salt marshes, and seagrasses sequester and store significant amounts of coastal blue carbon from the atmosphere and ocean and are now recognized for their role in mitigating climate change. Conservation and restoration of these coastal ecosystems has been increasingly addressed in international and national climate change mitigation policy and finance mechanisms. However, to date, countries have not incorporated coastal blue carbon into their portfolio of climate change mitigation or coastal management policies and actions, largely because the mechanisms for assessing blue carbon were not well defined or standardized. To address this concern, of the International Blue Carbon Initiative’s team of 34 experts in the fields of coastal carbon measurement, remote sensing, and climate policy produced this manual with the goal standardizing protocols for sampling methods, laboratory measurements, and analysis of blue carbon stocks and fluxes. The manual will provide scientists and coastal managers with a practical tool to produce robust blue carbon data.

Conceptualizing the Project and Developing a Field Measurement Plan - Fourqurean, James; Johnson, Beverly; Kauffman, J. Boone; Kennedy, Hilary; Emmer, Igino; Howard, Jennifer; Pidgeon, Emily; Serrano, Oscar (Coastal Blue Carbon: Methods for Assessing Carbon Stocks and Emissions Factors in Mangroves, Tidal Salt Marshes, and Seagrass Meadows, 2014)
… of total carbon stock or carbon stock change must be adjusted to reflect the change in area. … For example, seagrass beds will often have a few mangrove propagules and leaves, and …

Contemporary rates of carbon sequestration through vertical accretion of sediments in mangrove forests and saltmarshes of South East Queensland, Australia - Lovelock, Catherine E.; Adame, Maria Fernanda; Bennion, Vicki; Hayes, Matthew; O’Mara, Julian; Reef, Ruth; Santini, Nadia S. (Estuaries and Coasts, 2014)
Mangrove forests and saltmarshes are important habitats for carbon (C) sequestration in the coastal zone but variation in rates of C sequestration and the factors controlling sequestration are poorly understood.We assessed C sequestration in Moreton Bay, South East Queensland in mangrove forests and tidal marshes that span a range of environmental settings and plant communities, including mangrove forests and tidal marshes on the oligotrophic sand islands of the eastern side of Moreton Bay and on the nutrient enriched, western side of the bay adjacent to the city of Brisbane. We found that rates of C sequestration in sediments were similar amongmangrove forests over the bay, despite large differences in the C density of sediments, because of different rates of vertical accretion of sediments. The C sequestration on the oligotrophic sand island tidal marshes, dominated by Juncus kraussii , had the highest rate of C sequestration in the bay while the western saltmarshes, which were dominated by Sarcocornia quinqueflora, had the lowest rate of C sequestration. Our data indicate C sequestration varies among different tidal wetland plant community types, due to variation in sediment characteristics and rates of sediment accretion over time.

Contribution of L-band SAR to systematic global mangrove monitoring - Lucas, Richard; Rebelo, Lisa Maria; Fatoyinbo, Lola; Rosenqvist, Ake; Itoh, Takuya; Shimada, Masanobu; Simard, Marc; Souza-Filho, Pedro Walfir; Thomas, Nathan; Trettin, Carl; Accad, Arnon; Carreiras, Joao; et al. (Marine and Freshwater Research, 2014)
Information on the status of and changes in mangroves is required for national and international policy development, implementation and evaluation. To support these requirements, a component of the Japan Aerospace Exploration Agency's (JAXA) Kyoto and Carbon (K&C) initiative has been to design and develop capability for a Global Mangrove Watch (GMW) that routinely monitors and reports on local to global changes in the extent of mangroves, primarily on the basis of observations by Japanese L-band synthetic aperture radar (SAR). The GMW aims are as follows: (1) to map progression of change within or from existing (e.g. Landsat-derived) global baselines of the extent of mangroves by comparing advanced land-observing satellite 2 (ALOS-2) phased array L-band SAR 2 (PALSAR-2) data from 2014 with that acquired by the Japanese earth resources satellite (JERS-1) SAR (1992-1998) and ALOS PALSAR (2006-2011); (2) to quantify changes in the structure and associated losses and gains of carbon on the basis of canopy height and above-ground biomass (AGB) estimated from the shuttle radar topographic mission (SRTM; acquired 2000), the ice, cloud and land-elevation satellite (ICESAT) geoscience laser altimeter system (GLAS; 2003-2010) and L-band backscatter data; (3) to determine likely losses and gains of tree species diversity through reference to International Union for the Conservation of Nature (IUCN) global thematic layers on the distribution of mangrove species; and (4) to validate maps of changes in the extent of mangroves, primarily through comparison with dense time-series of Landsat sensor data and to use these same data to describe the causes and consequences of change. The paper outlines and justifies the techniques being implemented and the role that the GMW might play in supporting national and international policies that relate specifically to the long-term conservation of mangrove ecosystems and the services they provide to society. © CSIRO 2014.

Deforestation in the Ayeyarwady Delta and the conservation implications of an internationally-engaged Myanmar - Webb, Edward L.; Jachowski, Nicholas R.A.; Phelps, Jacob; Friess, Daniel A.; Than, Maung Maung; Ziegler, Alan D. (Global Environmental Change, 2014)
Myanmar is a country of huge biodiversity importance that is undergoing major political change, bringing with it new international engagement. This includes access to international markets, which will likely spur investment in export-oriented agriculture, leading to increased pressures on already threatened ecosystems. This scenario is illustrated in the Ayeyarwady Delta, the country's agricultural heartland sustaining high deforestation rates. Using the Delta as a model system, we use an integrated approach to inquire about whether and how imminent agricultural reforms associated with an internationally-engaged Myanmar could introduce new actors and incentives to invest in agricultural expansion that could affect deforestation rates. We use a novel remote sensing analysis to quantify deforestation rates for the Delta from 1978 to 2011, develop business-as-usual deforestation scenarios, and contextualize those results with an analysis of contemporary policy changes within Myanmar that are expected to alter the principal drivers of land-cover change. We show that mangrove systems of Myanmar are under greater threat than previously recognized, and that agriculture has been the principle driver of deforestation on the Delta. The centrality of agriculture to the Myanmar economy indicates that emerging policies are likely to tip the scales towards agricultural expansion, agro-industrial investment and potentially greater rates of deforestation due to the introduction of well-funded investors, insufficient land tenure agreements, and low governance effectiveness. The broad national challenge is to initiate environmental governance reforms (including safeguards) in the face of significant pressures for land grabbing and opportunistic resource extraction. © 2013 Elsevier Ltd.

Effects of common seagrass restoration methods on ecosystem structure in subtropical seagrass meadows - Bourque, Amanda S.; Fourqurean, James W. (Marine Environmental Research, 2014)
Seagrass meadows near population centers are subject to frequent disturbance from vessel groundings. Common seagrass restoration methods include filling excavations and applying fertilizer to encourage seagrass recruitment. We sampled macrophytes, soil structure, and macroinvertebrate infauna at unrestored and recently restored vessel grounding disturbances to evaluate the effects of these restoration methods on seagrass ecosystem structure. After a year of observations comparing filled sites to both undisturbed reference and unrestored disturbed sites, filled sites had low organic matter content, nutrient pools, and primary producer abundance. Adding a nutrient source increased porewater nutrient pools at disturbed sites and in undisturbed meadows, but not at filled sites. Environmental predictors of infaunal community structure across treatments included soil texture and nutrient pools. At the one year time scale, the restoration methods studied did not result in convergence between restored and unrestored sites. Particularly in filled sites, soil conditions may combine to constrain rapid development of the seagrass community and associated infauna. Our study is important for understanding early recovery trajectories following restoration using these methods. © 2014.

Effects of experimental sedimentation on the phenological dynamics and leaf traits of replanted mangroves at Gazi bay, Kenya - Okello, Judith A.; Robert, Elisabeth M.R.; Beeckman, Hans; Kairo, James G.; Dahdouh-Guebas, Farid; Koedam, Nico (Ecology and Evolution, 2014)
Sedimentation results in the creation of new mudflats for mangroves to colonize among other benefits. However, large sediment input in mangrove areas may be detrimental to these forests. The dynamics of phenological events of three mangrove tree species (Avicennia marina, Ceriops tagal, and Rhizophora mucronata) were evaluated under experimental sediment burial simulating sedimentation levels of 15, 30, and 45 cm. While there was generally no shift in timing of phenological events with sedimentation, the three mangrove tree species each responded differently to the treatments. Partially buried A. marina trees produced more leaves than the controls during the wet season and less during the dry season. Ceriops tagal on the other hand had higher leaf loss and low replacement rates in the partially buried trees during the first 6 months of the experiment but adapted with time, resulting in either equal or higher leaf emergence rates than the controls. Rhizophora mucronata maintained leaf emergence and loss patterns as the unaffected controls but had a higher fecundity and productivity in the 15-cm sedimentation level. The results suggest that under incidences of large sedimentation events (which could be witnessed as a result of climate change impacts coupled with anthropogenic disturbances), mangrove trees may capitalize on "advantages" associated with terrestrial sediment brought into the biotope, thus maintaining the pattern of phenological events. © 2014 The Authors.

Expansion of vegetated coastal ecosystems in the future Arctic - Krause-Jensen, Dorte; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
Warming occurs particularly fast in the Arctic and exerts profound effects on arctic ecosystems. Sea ice-associated ecosystems are projected to decline but reduced arctic sea ice cover also increases the solar radiation reaching the coastal seafloors with the potential for expansion of vegetated habitats, i.e., kelp forests and seagrass meadows. These habitats support key ecosystem functions, some of which may mitigate effects of climate change. Therefore, the likely expansion of vegetated coastal habitats in the Arctic will generate new productive ecosystems, offer habitat for a number of invertebrate and vertebrate species, including provision of refugia for calcifiers from possible threats from ocean acidification, contribute to enhance CO2 sequestration and protect the shoreline from erosion. The development of models allowing quantitative forecasts of the future of vegetated arctic ecosystems requires that key hypotheses underlying such forecasts be tested. Here we propose a set of three key testable hypotheses along with a research agenda for testing them using a broad diversity of approaches, including analyses of paleo-records, space-for-time substitutions and experimental studies. The research agenda proposed would provide a solid underpinning to guide forecasts on the spread of marine macrophytes onto the Arctic with climate change and contribute to balance our understanding of climate change impacts on the arctic ecosystem through a focus on the role of engineering species. Anticipating these changes in ecosystem structure and function is key to develop managerial strategies to maximize these ecosystem services in a future warmer Arctic.

Global unbalance in seaweed production, research effort and biotechnology markets - Mazarrasa, Inés; Olsen, Ylva S.; Mayol, Eva; Marbà, Núria; Duarte, Carlos M. (Biotechnology Advances, 2014)
Exploitation of the world's oceans is rapidly growing as evidenced by a booming patent market of marine products including seaweed, a resource that is easily accessible without sophisticated bioprospecting technology and that has a high level of domestication globally. The investment in research effort on seaweed aquaculture has recently been identified to be the main force for the development of a biotechnology market of seaweed-derived products and is a more important driver than the capacity of seaweed production. Here, we examined seaweed patent registrations between 1980 and 2009 to assess the growth rate of seaweed biotechnology, its geographic distribution and the types of applications patented. We compare this growth with scientific investment in seaweed aquaculture and with the market of seaweed production. We found that both the seaweed patenting market and the rate of scientific publications are rapidly growing (11% and 16.8% per year respectively) since 1990. The patent market is highly geographically skewed (95% of all registrations belonging to ten countries and the top two holding 65% of the total) compared to the distribution of scientific output among countries (60% of all scientific publications belonging to ten countries and the top two countries holding a 21%), but more homogeneously distributed than the production market (with a 99.8% belonging to the top ten countries, and a 71% to the top two). Food industry was the dominant application for both the patent registrations (37.7%) and the scientific publications (21%) followed in both cases by agriculture and aquaculture applications. This result is consistent with the seaweed taxa most represented. Kelp, which was the target taxa for 47% of the patent registrations, is a traditional ingredient in Asian food and Gracilaria and Ulva, which were the focus of 15% and 13% of the scientific publications respectively, that are also used in more sophisticated applications such as cosmetics, chemical industry or bioremediation. Our analyses indicate a recent interest of non-seaweed producing countries to play a part in the seaweed patenting market focusing on more sophisticated products, while developing countries still have a limited share in this booming market. We suggest that this trend could be reverted by promoting partnerships for R and D to connect on-going efforts in aquaculture production with the emerging opportunities for new biotech applications of seaweed products. © 2014 Elsevier Inc.

Historical analysis of mangrove leaf traits throughout the 19th and 20th centuries reveals differential responses to increases in atmospheric CO2 - Reef, Ruth; Lovelock, Catherine E. (Global Ecology and Biogeography, 2014)
Aim: To reconstruct the historic response of two dominant mangrove species to increases in atmospheric CO2 over the past two centuries. Location: Indo-Pacific. Methods: We use a novel approach to assess plant responses to rising atmospheric CO2 concentrations by measuring leaf traits of herbarium specimens of two dominant and widespread mangrove species. Results: Leaf traits were correlated with atmospheric CO2 concentration and latitude, but not with rainfall or the multidecadal multivariate El Niño-Southern Oscillation index. Rhizophora stylosa and Avicennia marina exhibited significant differences in their response to elevated CO2. Increases in atmospheric CO2 concentrations over the past 165 years have led to a corresponding rise in photosynthetic carbon gain by the widespread mangrove A.marina, but not by R.stylosa. Main conclusions: CO2 fixation is at the heart of plant energy acquisition, global primary productivity and CO2 sequestration. Given that atmospheric CO2 concentrations have been rapidly rising for the past two centuries, surprisingly few datasets have examined the long-term response of trees to rising CO2. Our results suggest changes to interspecific interactions, nutrient cycling and carbon sequestration in these globally significant forests are expected as CO2 concentrations continue to increase.

Interdependency of tropical marine ecosystems in response to climate change - Saunders, Megan I.; Leon, Javier X.; Callaghan, David P.; Roelfsema, Chris M.; Hamylton, Sarah; Brown, Christopher J.; Baldock, Tom; Golshani, Aliasghar; Phinn, Stuart R.; Lovelock, Catherine E.; Hoegh-Guldberg, Ove; Woodroffe, Colin D.; et al. (Nature Climate Change, 2014)
Ecosystems are linked within landscapes by the physical and biological processes they mediate. In such connected landscapes, the response of one ecosystem to climate change could have profound consequences for neighbouring systems. Here, we report the first quantitative predictions of interdependencies between ecosystems in response to climate change. In shallow tropical marine ecosystems, coral reefs shelter lagoons from incoming waves, allowing seagrass meadows to thrive. Deepening water over coral reefs from sea-level rise results in larger, more energetic waves traversing the reef into the lagoon, potentially generating hostile conditions for seagrass. However, growth of coral reef such that the relative water depth is maintained could mitigate negative effects of sea-level rise on seagrass. Parameterizing physical and biological models for Lizard Island, Great Barrier Reef, Australia, we find negative effects of sea-level rise on seagrass before the middle of this century given reasonable rates of reef growth. Rates of vertical carbonate accretion typical of modern reef flats (up to 3 mm yr ̂'1) will probably be insufficient to maintain suitable conditions for reef lagoon seagrass under moderate to high greenhouse gas emissions scenarios by 2100. Accounting for interdependencies in ecosystem responses to climate change is challenging, but failure to do so results in inaccurate predictions of habitat extent in the future. © 2014 Macmillan Publishers Limited. All rights reserved.

Legal frameworks for unique ecosystems - How can the EPBC Act offsets policy address the impact of development on seagrass? - Bell, Justine; Saunders, Megan I.; Lovelock, Catherine E.; Possingham, Hugh P. (Environmental and Planning Law Journal, 2014)
Environmental or biodiversity offset policies allow for impacts occurring at one site to be offset through activities at another site. The federal government has recently released a policy for offsetting the impacts of activities approved under the Environment Protection and Biodiversity Conservation Act 1999 (Cth) (EPBC Act). The EPBC Act policy can be used to offset impacts on terrestrial and marine ecosystems, and one of the first applications of the policy has been to offset impacts on seagrass meadows at risk due to the Abbot Point coal terminal expansion.The significant ecological differences between terrestrial and marine ecosystems, such as seagrass meadows, require different management approaches to ensure that impacts are offset. This article analyses the EPBC Act policy to determine whether it adequately caters for offsetting impacts on marine ecosystems, with seagrass used as an example. It concludes with recommendations for policy change directed at ensuring that the unique characteristics of seagrass ecosystems are considered in offset policies.

Litter Fall Dynamics of Restored Mangroves (Rhizophora mucronata Lamk. and Sonneratia alba Sm.) in Kenya - Wang'ondu, Virginia W.; Bosire, Jared O.; Kairo, James G.; Kinyamario, Jenesio I.; Mwaura, Francis B.; Dahdouh-Guebas, Farid; Koedam, Nico (Restoration Ecology, 2014)
Mangrove forests are active carbon sinks and important for nutrient cycling in coastal ecosystems. Restoration of degraded mangrove habitats enhances return of ecosystem goods and services, including carbon sequestration. Our objective was to assess the restoration of primary productivity of reforested mangrove stands in comparison with natural reference stands in Gazi Bay, Kenya. Litter fall data were collected in nine Rhizophora mucronata and Sonneratia alba monospecific stands by use of litter traps over 2 years. Litter was emptied monthly, dried, sorted, and weighed. The reforested and natural stands showed seasonality patterns only in the production of reproductive material. Leaves constituted the highest percentage to total litter fall. Litter productivity rates for the R. mucronata stands were not significantly different and ranged from 6.61-10.15 to 8.36-11.02 t ha-1 yr-1 for the restored and natural stands, respectively. The productivity of 5 years R. mucronata stands reached 5.22 t ha-1 yr-1 and was significantly different from other stands. Litter productivity rates for S. alba stands was 7.77-7.85 for the restored stands and 10.15 t ha-1 yr-1 for the natural stand but differences were not significant. Our results indicate that plantations of at least 11 years have attained litter productivity rates comparable to the natural forests. This suggests that productivity of replanted mangroves is likely to reach complete recovery by this age under the prevailing environmental conditions.

Long term state of coastal lagoons in Veracruz, Mexico: Effects of land use changes in watersheds on seagrasses habitats - Rivera-Guzmán, Nadia E.; Moreno-Casasola, Patricia; Ibarra-Obando, Silvia E.; Sosa, Vinicio J.; Herrera-Silveira, Jorge (Ocean and Coastal Management, 2014)
An increase in population over the last 50 years along the central coast of Veracruz on the Gulf of Mexico has led to a corresponding intensification of agriculture, urbanization, and other economic activities. Most significantly, this has resulted in rapid changes of land use and an increase in the area dedicated to agriculture and livestock. Native coastal wetland vegetation has declined significantly, and coastal lagoons systems are altered as they receive excess nutrients and sediments from agricultural and economic activities. The aim of this study was to evaluate the influence of productive activities on four coastal lagoons and one estuary at the watershed level and to establish reference points or ecological indicators upon which future changes in coastal wetlands may be measured. For this purpose we analyzed the physico-chemical characteristics of the water column, assessed the abundance and biomass of seagrasses, and determined the historical and current trophic status of these coastal water bodies. Our results indicate that over time the lagoons have remained in a eutrophic state, and only one has become mesotrophic. The biomass of the seagrass Halodule wrightii decreased by 28% from 1991 to 2001 in La Mancha Lagoon. Our results provide a baseline to assess future changes in the water quality of the selected study sites and the seagrasses populations they contain. © 2013 Elsevier Ltd.

Long-term versus daily stem diameter variation in co-occurring mangrove species: Environmental versus ecophysiological drivers - Vandegehuchte, Maurits W.; Guyot, Adrien; Hubau, Michiel; De Groote, Stefanie R.E.; De Baerdemaeker, Niels J.F.; Hayes, Matthew; Welti, Nina; Lovelock, Catherine E.; Lockington, David A.; Steppe, Kathy (Agricultural and Forest Meteorology, 2014)
High temporal resolution stem diameter variation (SDV) patterns have been widely recognized as a tool to study fundamental plant physiological mechanisms underlying whole-plant functioning and growth. As an integrative response to hydraulic and carbon related processes, SDV research has greatly improved insights in plant functioning of several herbaceous and woody species. Nevertheless, to date little detailed information on SDV and related physiological processes is available for mangrove species. By measuring continuous tree physiological variables such as stem diameter variations, sap flow and stem water potential in relation to the microclimatic conditions, the water use strategies of two co-occurring mangrove species, Avicennia marina (Forssk.) Vierh. and Rhizophora stylosa Griff. were investigated. Even though both species showed a similar long-term growth trend, closely linked to the environmental conditions, their daily SDV pattern was markedly different. While for Avicennia marina the SDV showed the standard daily pattern of morning decline and evening rise, the opposite daily SDV pattern was observed for Rhizophora stylosa. The contrasting patterns of SDV in both species thriving in the same environment indicates the importance and complexity of physiological endogenous mechanisms in addition to environmental conditions in controlling SDV and radial stem growth. © 2014 Elsevier B.V.

Macquarie river floodplain flow modeling: Implications for ecogeomorphology - Rojas, S. G.Sandi; Rodríguez, J. F.; Saco, P.; Riccardi, G.; Wen, L.; Saintilan, N.; Stenta, H.; Trivisonno, F.; Basile, P. A. (Proceedings of the International Conference on Fluvial Hydraulics, RIVER FLOW 2014, 2014)
This work presents preliminary results of implementing a quasi-2D hydrodynamic module (VMMHH 1.0) to simulate flows and flooding patterns throughout the Macquarie Marshes, south east Australia, in order to assess habitat requirements. The model uses an interconnected cell scheme that solves mass conservation and uses simplified versions of the momentum equations to represent flow between cells. This model has been used before to assess geomorphological changes in large river flood-plains and vegetation evolution in estuarine wetlands, showing results consistent with cases of gradual floodplain inundation following overbank flow. The simplified characteristics of the quasi-2D model allow for an adequate representation of hydrodynamic processes with similar performance of other higher dimensional models. Model results and computational times are compared with outputs from a conventional 1D/2D model (MIKE FLOOD) applied to the same domain showing that the VMMHH 1.0 is adequate for representation of floods in the Macquarie Marshes. © 2014 Taylor & Francis Group, London.

Mammalian herbivores in Australia transport nutrients from terrestrial to marine ecosystems via mangroves - Reef, Ruth; Feller, Ilka C.; Lovelock, Catherine E. (Journal of Tropical Ecology, 2014)
Nutrient subsidies from one ecosystem to another serve a critical link among ecosystems. The transfer of materials across the terrestrial-to-marine boundary is considered to be driven by hydrological connectivity, but animal movement can provide another pathway for nutrient transfers. In two separate studies we assessed the role mammals (bats and kangaroos) play in alleviating nutrient limitation in mangrove forests in Australia. At Lizard Island, we measured tree growth and foliar elemental and isotopic composition of trees growing within and outside a large flying fox roost. In Western Australia, we measured foliar elemental and isotopic composition of trees within two forests frequented by kangaroos that feed in spinifex grasslands and shelter in the shade of the mangroves. We compared those with mangroves from adjacent forests that are not frequented by kangaroos. We show that at both locations, the mangrove forest receives terrestrial nutrient subsidies through animal movement. At Lizard Island dominant mangrove species were significantly enriched in nitrogen within the bat roost, as evidenced by higher foliar N concentrations (by up to 150%), N:P and N:C ratios in trees within the roost compared with trees outside the roost. The isotopic signature of foliar N was significantly enriched in 15N by 1-3‰ within the roost, further suggesting that the source of the N enrichment was the bat roost. Growth rates of mangroves within the roost were nearly six times higher than trees outside the roost. In the arid coast of Western Australia, we show elevated foliar 15N abundance of up to 3‰ in mangroves where kangaroos shelter relative to trees where they do not. Thus, this study presents two examples for mammalian herbivore mediated localized transport of nutrients from terrestrial to marine ecosystems, consequently affecting mangrove tree growth, productivity and forest structure. © 2014 Cambridge University Press.

Mangroves facing climate change: Landward migration potential in response to projected scenarios of sea level rise - Di Nitto, D.; Neukermans, G.; Koedam, N.; Defever, H.; Pattyn, F.; Kairo, J. G.; Dahdouh-Guebas, F. (Biogeosciences, 2014)
Mangrove forests prominently occupy an intertidal boundary position where the effects of sea level rise will be fast and well visible. This study in East Africa (Gazi Bay, Kenya) addresses the question of whether mangroves can be resilient to a rise in sea level by focusing on their potential to migrate towards landward areas. The combinatory analysis between remote sensing, DGPS-based ground truth and digital terrain models (DTM) unveils how real vegetation assemblages can shift under different projected (minimum (+9 cm), relative (+20 cm), average (+48 cm) and maximum (+88 cm)) scenarios of sea level rise (SLR). Under SLR scenarios up to 48 cm by the year 2100, the landward extension remarkably implies an area increase for each of the dominant mangrove assemblages except for Avicennia marina/and Ceriops tagal/, both on the landward side. On the one hand, the increase in most species in the first three scenarios, including the socio-economically most important species in this area, Rhizophora mucronata/and C. tagal/on the seaward side, strongly depends on the colonisation rate of these species. On the other hand, a SLR scenario of +88 cm by the year 2100 indicates that the area flooded only by equinoctial tides strongly decreases due to the topographical settings at the edge of the inhabited area. Consequently, the landward Avicennia/-dominated assemblages will further decrease as a formation if they fail to adapt to a more frequent inundation. The topography is site-specific; however non-invadable areas can be typical for many mangrove settings. © 2014 Author(s).

Mangroves in peril: Unprecedented degradation rates of peri-urban mangroves in Kenya - Bosire, J. O.; Kaino, J. J.; Olagoke, A. O.; Mwihaki, L. M.; Ogendi, G. M.; Kairo, J. G.; Berger, U.; Macharia, D. (Biogeosciences, 2014)
Marine ecosystems are experiencing unprecedented degradation rates higher than any other ecosystem on the planet, which in some instances are up to 4 times those of rainforests. Mangrove ecosystems have especially been impacted by compounded anthropogenic pressures leading to significant cover reductions of between 35 and 50% (equivalent to 1-2% loss pa) for the last half century. The main objective of this study was to test the hypothesis that peri-urban mangroves suffering from compounded and intense pressures may be experiencing higher degradation rates than the global mean (and/or national mean for Kenya) using Mombasa mangroves (comprising Tudor and Mwache creeks) as a case study. Stratified sampling was used to sample along 22 and 10 belt transects in Mwache and Tudor respectively, set to capture stand heterogeneity in terms of species composition and structure in addition to perceived human pressure gradients using proximity to human habitations as a proxy. We acquired SPOT (HRV/HRVIR/HRS) images of April 1994, May 2000 and January 2009 and a vector mangrove map of 1992 at a scale of 1:50 000 for cover change and species composition analysis. Results from image classification of the 2009 image had 80.23% overall accuracy and Cohen's kappa of 0.77, thus proving satisfactory for use in this context. Structural data indicate that complexity index (CI) which captures stand structural development was higher in Mwache at 1.80 compared to Tudor at 1.71. From cover change data, Tudor lost 86.9% of the forest between 1992 and 2009, compared to Mwache at 45.4%, representing very high hitherto undocumented degradation rates of 5.1 and 2.7% pa, respectively. These unprecedentedly high degradation rates, which far exceed not only the national mean (for Kenya of 0.7% pa) but the global mean as well, strongly suggest that these mangroves are highly threatened due to compounded pressures. Strengthening of governance regimes through enforcement and compliance to halt illegal wood extraction, improvement of land-use practices upstream to reduce soil erosion, restoration in areas where natural regeneration has been impaired, provision of alternative energy sources/building materials and a complete moratorium on wood extraction especially in Tudor Creek to allow recovery are some of the suggested management interventions. copyright © Author(s) 2014.

Mediterranean seagrass (Posidonia oceanica) loss between 1842 and 2009 - Marbà, Núria; Díaz-Almela, Elena; Duarte, Carlos M. (Biological Conservation, 2014)
We compiled published data in peer-review articles and grey literature reports, which we appended with our own data, to assess the changes in areal extent, cover and shoot density that P. oceanica meadows have experienced between years 1842 and 2009 in the Mediterranean basin. Our results demonstrate an overall tendency towards decline of the areal extent, cover and shoot density of P. oceanica meadows during the last 50. years, the period with the largest availability of records. Available estimates indicated that between 13% and 50% of seagrass areal extent of P. oceanica in the Mediterranean basin appear to be lost, and that the remaining meadows of the Mediterranean may have thinned shoot density by 50% for the last 20. years and have became more fragmented. Considering the changes quantified in P. oceanica areal extent, cover and density, about 6.9% of the potential P. oceanica vegetation would have been lost annually over the last 50. years. The loss of P. oceanica meadows in the Mediterranean may have lead to a substantial (between 11% and 52%) reduction of the capacity of this key coastal ecosystem to sequester carbon in the last 50. years, hence reducing the carbon sink capacity of the entire Mediterranean Sea. The major causes of P. oceanica loss were widespread local disturbances, but recently, global disturbances, such as climate change and the spread of invasive exotic species, were also seriously threatening Posidonia meadows in the Mediterranean. These findings urgently call for implementation of management measures aiming at mitigating coastal deterioration by combining local and global actions. © 2014 Elsevier Ltd.

Ocean acidification outweighs nutrient effects in structuring seagrass epiphyte communities - Campbell, Justin E.; Fourqurean, James W. (Journal of Ecology, 2014)
Developing a framework for assessing interactions between multiple anthropogenic stressors remains an important goal in environmental research. In coastal ecosystems, the relative effects of aspects of global climate change (e.g. CO2 concentrations) and localized stressors (e.g. eutrophication), in combination, have received limited attention. Using a long-term (11 month) field experiment, we examine how epiphyte assemblages in a tropical seagrass meadow respond to factorial manipulations of dissolved carbon dioxide (CO2(aq)) and nutrient enrichment. In situ CO2(aq) manipulations were conducted using clear, open-top chambers, which replicated carbonate parameter forecasts for the year 2100. Nutrient enrichment consisted of monthly additions of slow-release fertilizer, nitrogen (N) and phosphorus (P), to the sediments at rates equivalent to theoretical maximum rates of anthropogenic loading within the region (1.54 g N m-2 d-1 and 0.24 g P m-2 d-1). Epiphyte community structure was assessed on a seasonal basis and revealed declines in the abundance of coralline algae, along with increases in filamentous algae under elevated CO2(aq). Surprisingly, nutrient enrichment had no effect on epiphyte community structure or overall epiphyte loading. Interactions between CO2(aq) and nutrient enrichment were not detected. Furthermore, CO2(aq)-mediated responses in the epiphyte community displayed strong seasonality, suggesting that climate change studies in variable environments should be conducted over extended time-scales. Synthesis. The observed responses indicate that for certain locations, global stressors such as ocean acidification may take precedence over local eutrophication in altering the community structure of seagrass epiphyte assemblages. Given that nutrient-driven algal overgrowth is commonly cited as a widespread cause of seagrass decline, our findings highlight that alternate climate change forces may exert proximate control over epiphyte community structure. Developing a framework for assessing interactions between multiple anthropogenic stressors remains an important goal in environmental research. In coastal ecosystems, the relative effects of global climate change (e.g. CO2 concentrations) and localized stressors (e.g. eutrophication), in combination, have received limited attention. Our in situ experiment reveals that global stressors such as ocean acidification (OA) may take precedence over local eutrophication in altering the community structure of seagrass epiphytes. Given that nutrient-driven algal overgrowth is commonly cited as a widespread cause of seagrass decline, our findings highlight that alternate climate change forces, such as OA, may exert proximate control over epiphyte community structure. © 2014 British Ecological Society.

Outwelling from arid mangrove systems is sustained by inwelling of seagrass productivity - Walton, M. E.M.; Al-Maslamani, I.; Skov, M. W.; Al-Shaikh, I.; Al-Ansari, I. S.; Kennedy, H. A.; Le Vay, L. (Marine Ecology Progress Series, 2014)
Mangrove forest productivity is normally sustained by nutrients from terrestrial runoff, with freshwater inputs driving the resulting outwelling of production, but arid mangroves lack this input. The movement of material between seagrass beds and mangroves was examined using the stable C and N isotopic composition of organisms, sediments and suspended matter in 3 seagrass-mangrove transects in the Arabian Gulf. The isotopic signal of suspended particulate material indicated a mixed origin that did not differ over a spring tide. Filter feeders showed significant 13C enrichment along transects from mangrove forests into seagrass beds, indicating that location within a habitat had a significant effect on isotopic composition. Similarly, δ13C of both sediments and grazers increased sharply outside the mangrove forest, suggesting retention of mangrove carbon, although some outwelling was detected, the strength of which was site specific. The lack of freshwater-mediated nutrient inputs suggests any outwelling of mangrove ecosystem productivity must be balanced by inwelling, and isotopic signatures of both sediment grazers and filter feeders found within the mangrove forest confirmed the inwelling of seagrass production. Significant mangrove isotope signals in the tissue of juveniles of fishes commercially harvested offshore indicate ontogenetic movement of carbon. Additional biological movement of mangrove carbon through ontogenetic migration and 'trophic relay' is evidenced by the isotopic signature of juvenile and mature fish captured in waters exiting the mangrove forest, which indicated they fed on mangrove-sustained food webs. This study demonstrates tight coupling between arid mangroves and subtidal seagrass areas and implies that arid mangroves cannot be managed or replanted without consideration of connectivity to downstream systems such as seagrasses. © Inter-Research 2014.

Respuestas morfológicas y fisiológicas de los pastos marinos (Alismatales) a los herbívoros (Testudines: Cheloniidae) y el papel de estas respuestas como señales de abandono de parches de pastoreo - Lacey, Elizabeth A.; Collado-Vides, Ligia; Fourqurean, James W. (Revista de Biologia Tropical, 2014)
Green sea turtles, Chelonia mydas, are grazers influencing the distribution of seagrass within shallow coastal ecosystems, yet the drivers behind C. mydas patch use within seagrass beds are largely unknown. Current theories center on food quality (nutrient content) as the plant responds to grazing disturbances; however, no study has monitored these parameters in a natural setting without grazer manipulation. To determine the morphological and physiological responses potentially influencing seagrass recovery from grazing disturbances, seagrasses were monitored for one year under three different grazing scenarios (turtle grazed, fish grazed and ungrazed) in a tropical ecosystem in Akumal Bay, Quintana Roo, Mexico. Significantly less soluble carbohydrates and increased nitrogen and phosphorus content in Thalassia testudinum were indicative of the stresses placed on seagrasses during herbivory. To determine if these physiological responses were the drivers of the heterogeneous grazing behavior by C. mydas recorded in Akumal Bay, patches were mapped and monitored over a six-month interval. The abandoned patches had the lowest standing crop rather than leaf nutrient or rhizome soluble carbohydrate content. This suggests a modified Giving Up Density (GUD) behavior: the critical threshold where cost of continued grazing does not provide minimum nutrients, therefore, new patches must be utilized, explains resource abandonment and mechanism behind C. mydas grazing. This study is the first to apply GUD theory, often applied in terrestrial literature, to explain marine herbivore grazing behavior.

Root biomass and production of mangroves surrounding a karstic oligotrophic coastal lagoon - Adame, Maria Fernanda; Teutli, Claudia; Santini, Nadia S.; Caamal, Juan P.; Zaldívar-Jiménez, Arturo; Herńndez, Raquel; Herrera-Silveira, Jorge A. (Wetlands, 2014)
Root production influences a range of belowground processes, such as soil accretion, carbon sequestration and nutrient acquisition. Here, we measured biomass and root production of mangroves surrounding a karstic oligotrophic lagoon that spans a nutrient and salinity gradient. We also measured forest structure and soil physicochemical conditions (salinity, bulk density, carbon, nitrogen (N) and phosphorus (P)) in order to determine factors associated with root production. We tested the following hypotheses: 1) root biomass and production increase at low soil P and N in order to maximize resource utilization, and 2) root biomass and production increase with high interstitial salinity. Root biomass (947- 3,040 g m-2) and production (0.46-1.85 g m-2 day-1) increased where soil P and interstitial salinity were relatively high. Thus, we rejected the first hypothesis and confirmed the second. The larger root fraction (5-20 mm) was the major contributor to root biomass and production. Our findings suggest that root production and thus capacity for belowground carbon storage in karstic regions, where P is often limiting, is greater where interstitial salinity and P are higher. This contrasts with past assessments indicating that Pdeficiency stimulates root growth, suggesting wide variation in belowground responses in mangroves. © Society of Wetland Scientists 2014.

Special Focus: Coastal Blue Carbon - Emmett-Mattox, Steve; Crooks, Steve (Coastal Blue Carbon, 2014)
The promise of " coastal blue carbon " is that the climate mitigation benefits of salt marsh, mangrove, sea grass, and other tidal wetland habitats will stimulate new investment in and prioritization of wetland management, including restoration and conservation. Six leaders in this field discuss lessons learned and recommendations for a way forward. To our readers, As we bid farewell to Leah Stetson, I am delighted to take over the role of editing the Newsletter with the help of the Environmental Law Institute's (ELI's) publication team. This issue focuses on coastal blue carbon, and I could not think of a more apropos topic for my inaugu-ral Newsletter. At ELI, I work primarily with our Ocean Program on marine policy and management topics, so coastal issues are of great personal and professional inter-est to me. Moreover, I recently relocated from Washing-ton, D.C., to New Orleans, Louisiana; living in a state suffering from such unprecedented coastal wetlands loss has placed wetlands issues at the front of my mind. The relationship between coastal wetlands and climate change is a particularly important one in Louisiana. But the promise of coastal blue carbon takes this link-age a step further by providing an opportunity to di-rectly mitigate climate change. Louisiana's plight figures prominently in this series—both Jerome Zeringue and coauthors and Sarah Mack focus primarily on Louisiana wetlands—but coastal blue carbon is an opportunity that can be realized around the country, as our other authors show. Steve Emmett-Mattox and Steve Crooks provide an introduction to the topic, Sara Ward and Scott Settelmyer discuss the carbon sequestration ben-efits of peatland restoration, Igino Emmer and Moritz von Unger present recommendations for project devel-opers, and Ariana Sutton-Grier and coauthors discuss opportunities to incorporate ecosystem carbon into fed-eral policies.

Turning the Tide: How Blue Carbon and Payments for Ecosystem Services (PES) Might Help Save Mangrove Forests - Locatelli, Tommaso; Binet, Thomas; Kairo, James Gitundu; King, Lesley; Madden, Sarah; Patenaude, Genevieve; Upton, Caroline; Huxham, Mark (Ambio, 2014)
In this review paper, we aim to describe the potential for, and the key challenges to, applying PES projects to mangroves. By adopting a “carbocentric approach,” we show that mangrove forests are strong candidates for PES projects. They are particularly well suited to the generation of carbon credits because of their unrivaled potential as carbon sinks, their resistance and resilience to natural hazards, and their extensive provision of Ecosystem Services other than carbon sequestration, primarily nursery areas for fish, water purification and coastal protection, to the benefit of local communities as well as to the global population. The voluntary carbon market provides opportunities for the development of appropriate protocols and good practice case studies for mangroves at a small scale, and these may influence larger compliance schemes in the future. Mangrove habitats are mostly located in developing countries on communally or state-owned land. This means that issues of national and local governance, land ownership and management, and environmental justice are the main challenges that require careful planning at the early stages of mangrove PES projects to ensure successful outcomes and equitable benefit sharing within local communities.

Variable effects of nutrient enrichment on soil respiration in mangrove forests - Lovelock, Catherine E.; Feller, Ilka C.; Reef, Ruth; Ruess, Roger W. (Plant and Soil, 2014)
Background and Aims: Mangrove forests are globally important sites of carbon burial that are increasingly exposed to nutrient pollution. Here we assessed the response of soil respiration, an important component of forest carbon budgets, to nutrient enrichment over a wide range of mangrove forests. Methods: We assessed the response of soil respiration to nutrient enrichment using fertilization experiments within 22 mangrove forests over ten sites. We used boosted regression tree (BRT) models to determine the importance of environmental and plant factors for soil respiration and its responsiveness to fertilizer treatments. Results: Leaf area index explained the largest proportion of variation in soil respiration rates (LAI, 45.9 %) followed by those of site, which had a relative influence of 39.9 % in the BRT model. Nutrient enrichment enhanced soil respiration only in nine out of 22 forests. Soil respiration in scrub forests showed a positive response to nutrient addition more frequently than taller fringing forests. The response of soil respiration to nutrient enrichment varied with changes in specific leaf area (SLA) and stem extension, with relative influences of 14.4 %, 13.6 % in the BRT model respectively. Conclusions: Soil respiration in mangroves varied with LAI, but other site specific factors also influenced soil respiration and its response to nutrient enrichment. Strong enhancements in aboveground growth but moderate increases in soil respiration with nutrient enrichment indicated that nutrient enrichment of mangrove forests has likely increased net ecosystem production. © 2014 Springer International Publishing Switzerland.

Watershed scale analyses of land cover change in the contributing upland area of mangrove ecosystems - Corcoran, Jennifer; Simard, Marc; Fatoyinbo, Lola; Rosenberg, Melanie (International Geoscience and Remote Sensing Symposium (IGARSS), 2014)
Mangrove Ecosystems thrive in the tropical transition zones between the land and the sea. These marine ecosystems contribute to the biodiversity of land and ocean habitats at various scales, acting as direct link to biogeochemical cycles of both upland and coastal regions. All of the positive and negative drivers of change of both natural and anthropogenic, within watershed and political boundaries play a role in the health and function of mangroves. As a result, they are among the most rapidly changing landscapes in the Americas; yet, the landscape scale dynamics are not well understood, difficult to measure in cloudy regions, and not operationally monitored at the global scale. This research presents a watershed scale monitoring approach of mangrove ecosystems using datasets that are freely available and techniques that are robust for application at the global scale.

An approach to monitoring mangrove extents through time-series comparison of JERS-1 SAR and ALOS PALSAR data - Thomas, Nathan; Lucas, Richard; Itoh, Takuya; Simard, Marc; Fatoyinbo, Lola; Bunting, Peter; Rosenqvist, Ake (Wetlands Ecology and Management, 2015)
Between 2007 and 2010, Japan’s Advanced Land Observing Satellite (ALOS) Phased Arrayed L-band Synthetic Aperture Radar (PALSAR) captured dual polarization HH and HV data across the tropics and sub-tropics. A pan tropical dataset of Japanese Earth Resources Satellite (JERS-1) SAR (HH) data was also acquired between 1995 and 1998. The provision of these comparable cloud-free datasets provided an opportunity for observing changes in the extent of coastal mangroves over more than a decade. Focusing on nine sites distributed through the tropics, this paper demonstrates how these data can be used to backdate and update existing baseline maps of mangrove extent. The benefits of integrating dense time-series of Landsat sensor data for both validating assessments of change and determining the causes of change are outlined. The approach is evaluated for wider application across the geographical range of mangroves in order to advance the development of JAXA’s Global Mangrove Watch (GMW) program.

An individual-based model of long-term forest growth and carbon sequestration in planted mangroves under salinity and inundation stresses - Salmo, Severino; Juanico, Dranreb Earl (International Journal of Philippine Science and Technology, 2015)
We developed a spatially explicit individual-based model of forest development trajectories of monospecific Rhizophora mucronata plantations. The model incorporates stochastic initial seedling spacing, propagule dispersal, recruitment, and mortality. We simulated and compared the growth, development and accumulation of carbon stocks of restored mangroves between optimal and sub-optimal settings. Salinity is considered as a stressor, while flooding effects are described as an inundation stress factor. In the optimal setting, the simulated mangrove population accumulated large aboveground carbon stocks (of around 140 T/ ha) after 100 years. Under sub-optimal conditions, we observed delayed maturity by at least 10 years near the salinity threshold and the carbon stock decreased through time towards much lower values (25 T/ha). More importantly, the continuous presence of stressors may lead to forest population collapse (at 50 yrs post-planting) probably as a result of the accumulated effects of physiological stresses. Thus, restored mangrove populations that are located in highly saline and frequently inundated sites, may eventually collapse even though they may appear to be healthy in the early stages of forest development. Our results imply that current and future restoration practices should carefully consider site selection in order to ensure viable long-term forest development and to have an optimum contribution to carbon sequestration.

Applying Climate Compatible Development and economic valuation to coastal management: A case study of Kenya's mangrove forests - Huxham, Mark; Emerton, Lucy; Kairo, James; Munyi, Fridah; Abdirizak, Hassan; Muriuki, Tabitha; Nunan, Fiona; Briers, Robert A. (Journal of Environmental Management, 2015)
Mangrove forests are under global pressure. Habitat destruction and degradation persist despite longstanding recognition of the important ecological functions of mangroves. Hence new approaches are needed to help stakeholders and policy-makers achieve sound management that is informed by the best science. Here we explore how the new policy concept of Climate Compatible Development (CCD) can be applied to achieve better outcomes. We use economic valuation approaches to combine socio-economic data, projections of forest cover based on quantitative risk mapping and storyline scenario building exercises to articulate the economic consequences of plausible alternative future scenarios for the mangrove forests of the South Kenya coast, as a case study of relevance to many other areas. Using data from 645 household surveys, 10 focus groups and 74 interviews conducted across four mangrove sites, and combining these with information on fish catches taken at three landing sites, a mangrove carbon trading project and published data allowed us to make a thorough (although still partial) economic valuation of the forests. This gave a current value of the South Coast mangroves of USD 6.5 million, or USD 1166ha-1, with 59% of this value on average derived from regulating services. Quantitative risk mapping, projecting recent trends over the next twenty years, suggests a 43% loss of forest cover over that time with 100% loss at the most vulnerable sites. Much of the forest lost between 1992 and 2012 has not been replaced by high value alternative land uses hence restoration of these areas is feasible and may not involve large opportunity costs. We invited thirty eight stakeholders to develop plausible storyline scenarios reflecting Business as Usual (BAU) and CCD - which emphasises sustainable forest conservation and management - in twenty years time, drawing on local and regional expert knowledge of relevant policy, social trends and cultures. Combining these scenarios with the quantitative projections and economic baseline allowed the modelling of likely value added and costs avoided under the CCD scenario. This suggests a net present value of more than US$20 million of adoption of CCD rather than BAU. This work adds to the economic evidence for mangrove conservation and helps to underline the importance of new real and emerging markets, such as for REDD+ projects, in making this case for carbon-rich coastal habitats. It demonstrates a policy tool - CCD - that can be used to engage stakeholders and help to co-ordinate policy across different sectors towards mangrove conservation.

Comparing the performance of multispectral vegetation indices and machine-learning algorithms for remote estimation of chlorophyll content: a case study in the Sundarbans mangrove forest - Gholizadeh, Hamed; Robeson, Scott M.; Rahman, Abdullah F. (International Journal of Remote Sensing, 2015)
Optical vegetation indices (VIs) have been used to retrieve and assess biophysical variables from satellite reflectance data. These indices, however, also are sensitive to a number of confounding factors, such as canopy geometry, soil optical properties, and solar position. This suggests that VIs should be used cautiously for biophysical parameter estimation. Among biophysical variables, chlorophyll content is of particular importance as an indicator of photosynthetic activity. The goal of this study is to investigate the performance of multispectral optical VIs for chlorophyll content estimation in the world’s largest mangrove forest, the Sundarbans, and to compare these with machine-learning algorithms (MLAs). To this end, we have investigated the performance of 15 multispectral VIs and six state-of-the-art MLAs that are widely used for adaptive data fitting. The MLAs are Artificial Neural Networks (ANNs), Genetic Algorithm (GA), Gaussian Processes for Machine Learning (GPML), Kernel Ridge Regression (KRR), Locally Weighted Polynomials (LWP), and Multivariate Adaptive Regression Splines (MARS). We use an in situ data set of reflectance and chlorophyll measurements to develop and validate our models. Each MLA was evaluated 500 times with random partitions of training and validation data. Results showed that the weight optimization and term selection used within GA produce the most reliable chlorophyll content estimation. However, green normalized difference VI (GNDVI) is a simple and computationally efficient VI that produces results that are nearly as accurate as GA in terms of model fit and performance. Results also show that all methods except ANNs and MARS produce a quasi-linear relationship between spectral reflectance and chlorophyll content. Statistical transformations of GNDVI and chlorophyll content have the capability of further reducing model error.

Development of a vegetation dynamics model for freshwater wetland assessment in the Macquarie Marshes - Sandi, Steven; Rodriguez, Jose; Saco, Patricia; Saintilan, Neil; Wen, Li; Kuczera, George (The Art and Science of Water - 36th Hydrology and Water Resources Symposium, HWRS 2015, 2015)
The configuration of the Macquarie Marshes is a mosaic-like collection of swamps, marshes and lagoons. The Macquarie Marshes is also one of the most ecologically important wetland systems in Australia. It contains unique plant communities that serve as a sanctuary for many species of waterbirds and other fauna such as frogs and mammals. A significant deterioration of the ecological features of the Macquarie Marshes has been recorded in the past decades. This fact is mostly attributed to reductions of the input discharges to the marshes due to water allocations for industrial, agricultural and domestic usage. Reduction of water supply translates into changes of the hydraulic regime which has a direct impact on the flood dependent vegetation species of the marshes. The complexity of the system and its ecological significance requires the use of an adequate computational tool that would allow for a realistic assessment of the site. In this paper we present initial work regarding the development of a vegetation dynamics model that can integrate vegetation establishment with time aggregated characteristics of the flow. We simulate floods on a fictional wetland by implementing a quasi-2D hydrodynamic model (VHHMM 1.0) over a rectangular cell grid. This same grid constitutes the basis for a cellular vegetation model that can calculate changes in the vegetation for each element inside the domain. The work presented here for a fictional site was developed in order to test the capability of our model to recreate consistent vegetation gradients by using deterministic transitional rules. These rules relate time aggregated characteristics of the flow such as flood period and depth of water to water requirements of different vegetation communities. We found that a well calibrated set of deterministic transitional rules based on water preferences can recreate consistent vegetation distributions; however, succession and critical conditions for succession rules will have to be defined for a specific site application. Further development of this model will result in a strategic tool for managing environmental water allocations and water sharing plans in the Macquarie Marshes.

Eelgrass Zostera marina in subarctic Greenland: Dense meadows with slow biomass turnover in cold waters - Olesen, Birgit; Krause-Jensen, Dorte; Marbà, Núria; Christensen, Peter Bondo (Marine Ecology Progress Series, 2015)
Eelgrass Zostera marina L. is the most dominant seagrass species throughout the temperate northern hemisphere, and knowledge on its distribution and production in relation to climatic conditions is relevant for predicting the future of the meadows. We synthesized past and present information on eelgrass near the northern distribution limit in Greenland, and quantified the biomass, production and reproductive potential of eelgrass populations in 4 widely separated locations of Godtha˚bsfjorden at 64° N. Eelgrass observations in Greenland date back to 1813; most of the meadows recorded in the past still exist, and new ones were identified. The meadows are relatively small and geographically isolated, typically occurring in inner branches of the fjord system where summer water temperatures are higher (13 to 15°C) than in the outer part (<10°C). The shoot density (871 to 2045 shoots m-2), aboveground biomass (90 to 327 g dry wt [DW] m-2) and rhizome extension rates (8 to 29 cm yr-1) match levels further south. By contrast, the annual production of 7 to 13 leaves shoot-1 is considerably lower and leads to slow leaf biomass turnover (1.6 to 2.6 yr-1) in these northern populations. Even though flowering was common, mature seeds were found only once, after a warm summer, and no seedlings were observed. An analysis of published data on eelgrass leaf biomass and production across the entire species distribution range revealed that leaf biomass is not affected by either latitude or air temperature, whereas annual leaf formation rates are significantly lower in cold areas at high latitude compared to warm areas at low latitude. The results suggest that distribution and production in Greenland are currently limited by low temperature and likely to increase in a warmer future.

Extreme temperatures, foundation species, and abrupt ecosystem change: an example from an iconic seagrass ecosystem - Thomson, Jordan A.; Burkholder, Derek A.; Heithaus, Michael R.; Fourqurean, James W.; Fraser, Matthew W.; Statton, John; Kendrick, Gary A. (Global Change Biology, 2015)
Extreme climatic events can trigger abrupt and often lasting change in ecosystems via the reduction or elimination of foundation (i.e., habitat-forming) species. However, while the frequency/intensity of extreme events is predicted to increase under climate change, the impact of these events on many foundation species and the ecosystems they support remains poorly understood. Here, we use the iconic seagrass meadows of Shark Bay, Western Australia - a relatively pristine subtropical embayment whose dominant, canopy-forming seagrass, Amphibolis antarctica, is a temperate species growing near its low-latitude range limit - as a model system to investigate the impacts of extreme temperatures on ecosystems supported by thermally sensitive foundation species in a changing climate. Following an unprecedented marine heat wave in late summer 2010/11, A. antarctica experienced catastrophic (>90%) dieback in several regions of Shark Bay. Animal-borne video footage taken from the perspective of resident, seagrass-associated megafauna (sea turtles) revealed severe habitat degradation after the event compared with a decade earlier. This reduction in habitat quality corresponded with a decline in the health status of largely herbivorous green turtles (Chelonia mydas) in the 2 years following the heat wave, providing evidence of long-term, community-level impacts of the event. Based on these findings, and similar examples from diverse ecosystems, we argue that a generalized framework for assessing the vulnerability of ecosystems to abrupt change associated with the loss of foundation species is needed to accurately predict ecosystem trajectories in a changing climate. This includes seagrass meadows, which have received relatively little attention in this context. Novel research and monitoring methods, such as the analysis of habitat and environmental data from animal-borne video and data-logging systems, can make an important contribution to this framework.

Global change accelerates carbon assimilation by a wetland ecosystem engineer - Caplan, Joshua S.; Hager, Rachel N.; Megonigal, J. Patrick; Mozdzer, Thomas J. (Environmental Research Letters, 2015)
The primary productivity of coastal wetlands is changing dramatically in response to rising atmospheric carbon dioxide (CO2) concentrations, nitrogen (N) enrichment, and invasions by novel species, potentially altering their ecosystem services and resilience to sea level rise. In order to determine how these interacting global change factors will affect coastal wetland productivity, we quantified growing-season carbon assimilation (≈gross primary productivity, or GPP) and carbon retained in living plant biomass (≈net primary productivity, or NPP) of North American mid-Atlantic saltmarshes invaded by Phragmites australis (common reed) under four treatment conditions: two levels of CO2 (ambient and +300 ppm) crossed with two levels of N (0 and 25 g N added m-2 yr-1). For GPP, we combined descriptions of canopy structure and leaf-level photosynthesis in a simulation model, using empirical data from an open-top chamber field study. Under ambient CO2 and low N loading (i.e., the Control), we determined GPP to be 1.66 ± 0.05 kg C m-2 yr-1 at a typical Phragmites stand density. Individually, elevated CO2 and N enrichment increased GPP by 44 and 60%, respectively. Changes under N enrichment came largely from stimulation to carbon assimilation early and late in the growing season, while changes from CO2 came from stimulation during the early and mid-growing season. In combination, elevated CO2 and N enrichment increased GPP by 95% over the Control, yielding 3.24 ± 0.08 kg C m-2 yr-1. We used biomass data to calculate NPP, and determined that it represented 44%-60% of GPP, with global change conditions decreasing carbon retention compared to the Control. Our results indicate that Phragmites invasions in eutrophied saltmarshes are driven, in part, by extended phenology yielding 3.1× greater NPP than native marsh. Further, we can expect elevated CO2 to amplify Phragmites productivity throughout the growing season, with potential implications including accelerated spread and greater carbon storage belowground.

Glomalin accumulated in seagrass sediments reveals past alterations in soil quality due to land-use change - López-Merino, Lourdes; Serrano, Oscar; Adame, María Fernanda; Mateo, Miguel Ángel; Martínez Cortizas, Antonio (Global and Planetary Change, 2015)
Arbuscular mycorrhizal fungi (AMF), symbionts with most terrestrial plants, produce glomalin-related soil protein (GRSP), which plays a major role in soil structure and quality. Both fungi hyphae and protein production in soils are affected by perturbations related to land-use changes, implying that GRSP is a sensitive indicator of soil quality. Unfortunately, GRSP degrades within years to decades in oxic environments, preventing its use as palaeoecological proxy. However, GRSP is transported to marine, near-shore anoxic sediments, where it accumulates and remains non-degraded, enabling the assessment of its potential as a palaeoecological proxy for soil ecosystem's health. Exploiting this fact, we have obtained for the first time a long-term record (c. 1250. years) of GRSP content using a Posidonia oceanica seagrass mat sediment core from the Western Mediterranean (Portlligat Bay, Spain). The trends in GRSP content matched well with land-use changes related to agrarian activities reconstructed by pollen analysis. In periods of cultivation, GRSP accumulation in the mat decreased. Given the role played by GRSP, the results suggest that agrarian intensification may have resulted in perturbations to soil quality. Thus, GRSP in seagrass mat sediments can be used to assess long-term trends in continental soil quality induced by human activities. These findings open new possibilities in long-term ecology research, as other anoxic environments could be potentially valid too. Testing them would open the possibility to identify long-term patterns in soil quality and other environmental stressors that could also affect AMF and GRSP production in soils.

Harnessing the climate mitigation, conservation and poverty alleviation potential of seagrasses: Prospects for developing blue carbon initiatives and payment for ecosystem service programmes - Hejnowicz, Adam P.; Kennedy, Hilary; Rudd, Murray A.; Huxham, Mark R. (Frontiers in Marine Science, 2015)
Seagrass ecosystems provide numerous ecosystem services that support coastal communities around the world. They sustain abundant marine life as well as commercial and artisanal fisheries, and help protect shorelines from coastal erosion. Additionally, seagrass meadows are a globally significant sink for carbon and represent a key ecosystem for combating climate change. However, seagrass habitats are suffering rapid global decline. Despite recognition of the importance of "Blue Carbon," no functioning seagrass restoration or conservation projects supported by carbon finance currently operate, and the policies and frameworks to achieve this have not been developed. Yet, seagrass ecosystems could play a central role in addressing important international research questions regarding the natural mechanisms through which the ocean and the seabed can mitigate climate change, and how ecosystem structure links to service provision. The relative inattention that seagrass ecosystems have received represents both a serious oversight and a major missed opportunity. In this paper we review the prospects of further inclusion of seagrass ecosystems in climate policy frameworks, with a particular focus on carbon storage and sequestration, as well as the potential for developing payment for ecosystem service (PES) schemes that are complementary to carbon management. Prospects for the inclusion of seagrass Blue Carbon in regulatory compliance markets are currently limited; yet despite the risks the voluntary carbon sector offers the most immediately attractive avenue for the development of carbon credits. Given the array of ecosystem services seagrass ecosystems provide the most viable route to combat climate change, ensure seagrass conservation and improve livelihoods may be to complement any carbon payments with seagrass PES schemes based on the provision of additional ecosystem services.

High-resolution forest canopy height estimation in an African blue carbon ecosystem - Lagomasino, David; Fatoyinbo, Temilola; Lee, Seung Kuk; Simard, Marc (Remote Sensing in Ecology and Conservation, 2015)
Mangrove forests are one of the most productive and carbon dense ecosystems that are only found at tidally inundated coastal areas. Forest canopy height is an important measure for modeling carbon and biomass dynamics, as well as land cover change. By taking advantage of the flat terrain and dense canopy cover, the present study derived digital surface models (DSMs) using stereo-photogrammetric techniques on high-resolution spaceborne imagery (HRSI) for southern Mozambique. A mean-weighted ground surface elevation factor was subtracted from the HRSI DSM to accurately estimate the canopy height in mangrove forests in southern Mozambique. The mean and H100 tree height measured in both the field and with the digital canopy model provided the most accurate results with a vertical error of 1.18–1.84 m, respectively. Distinct patterns were identified in the HRSI canopy height map that could not be discerned from coarse shuttle radar topography mission canopy maps even though the mode and distribution of canopy heights were similar over the same area. Through further investigation, HRSI DSMs have the potential of providing a new type of three-dimensional dataset that could serve as calibration/validation data for other DSMs generated from spaceborne datasets with much larger global coverage. HSRI DSMs could be used in lieu of Lidar acquisitions for canopy height and forest biomass estimation, and be combined with passive optical data to improve land cover classifications.

Impact of seagrass loss and subsequent revegetation on carbon sequestration and stocks - Marbà, Núria; Arias-Ortiz, Ariane; Masqué, Pere; Kendrick, Gary A.; Mazarrasa, Inés; Bastyan, Geoff R.; Garcia-Orellana, Jordi; Duarte, Carlos M. (Journal of Ecology, 2015)
Seagrass meadows are sites of high rates of carbon sequestration and they potentially support 'blue carbon' strategies to mitigate anthropogenic CO2 emissions. Current uncertainties on the fate of carbon stocks following the loss or revegetation of seagrass meadows prevent the deployment of 'blue carbon' strategies. Here, we reconstruct the trajectories of carbon stocks associated with one of the longest monitored seagrass restoration projects globally. We demonstrate that sediment carbon stocks erode following seagrass loss and that revegetation projects effectively restore seagrass carbon sequestration capacity. We combine carbon chronosequences with 210Pb dating of seagrass sediments in a meadow that experienced losses until the end of 1980s and subsequent serial revegetation efforts. Inventories of excess 210Pb in seagrass sediments revealed that its accumulation, and thus sediments, coincided with the presence of seagrass vegetation. They also showed that the upper sediments eroded in areas that remained devoid of vegetation after seagrass loss. Seagrass revegetation enhanced autochthonous and allochthonous carbon deposition and burial. Carbon burial rates increased with the age of the restored sites, and 18 years after planting, they were similar to that in continuously vegetated meadows (26.4 ± 0.8 gCorg m-2 year-1). Synthesis. The results presented here demonstrate that loss of seagrass triggers the erosion of historic carbon deposits and that revegetation effectively restores seagrass carbon sequestration capacity. Thus, conservation and restoration of seagrass meadows are effective strategies for climate change mitigation.

Impacts of physical disturbance on ecosystem structure in subtropical seagrass meadows - Bourque, Amanda S.; Kenworthy, W. Judson; Fourqurean, James W. (Marine Ecology Progress Series, 2015)
Soil disturbance, a key contributor to physical degradation in seagrass ecosystems, can lead to long-term changes in ecosystem function. We used a chronosequence of vessel grounding disturbances of different ages (0 yr, 1 yr, 3 yr, 4 yr, 5+ yr) as a model for soil disturbance to test hypotheses that disturbance alters primary producer communities, soil properties, biogeochemical processes, and infauna communities in seagrass ecosystems and that altered structure and processes will change following disturbance through seagrass bed development and ecosystem recovery. Disturbance involving excavated surface soils resulted in long-term loss of seagrass and macroalgae and stored organic carbon, nitrogen, and phosphorus. Disturbed sites were characterized by reductions in variables related to organic matter and inorganic nutrient content. Disturbance altered habitat quality for some taxa including amphipods, as evident from differences in invertebrate community structure. These impacts persisted in study sites for 5+ yr after the disturbance, likely because of physical and chemical soil modification accompanied by slow development of the seagrass community. We estimate that disturbance from 0.4 m deep excavations led to losses of 6.0 kg m-2 organic C (Corg), 0.4 kg m-2 N, and 0.03 kg m-2 P from the disturbed areas. First-order conservative estimates of scarring excavation rate in Miami-Dade County, Florida, USA, suggest potential annual fluxes of 1.1 × 106 kg Corg, 74 000 kg N, and 5500 kg P from seagrass soils in the region. Our findings suggest that vessel grounding disturbances create complex and long-term resource losses that are undervalued by resource trustees.

Influence of temporospatial variation in sap flux density on estimates of whole-tree water use in Avicennia marina - Van de Wal, Bart A.E.; Guyot, Adrien; Lovelock, Catherine E.; Lockington, David A.; Steppe, Kathy (Trees - Structure and Function, 2015)
Key message: Our study shows that sap flow inAvicennia marinavaries significantly throughout the sapwood and that spatial patterns in sap flux density are dependent on meteorological conditions. Abstract: Sap flux density measurements are used worldwide as a relatively inexpensive means to provide estimates of whole-tree and whole-stand water use in forest ecosystems. However, erroneous upscaling from point measurements to the entire sapwood area remains an issue, since sap flow is hardly ever constant throughout the tree. In this study, two widely used sap flow methodologies (the Heat Ratio or HR method and the Heat Field Deformation or HFD method) are used to assess radial and azimuthal variations in sap flux density in three mature trees of the mangrove species Avicennia marina in Brisbane, Australia. The genus Avicennia is characterised by secondary growth via successive cambia, resulting in an atypical sapwood pattern of xylem patches braided with phloem strings. Water use estimates were calculated in different ways. At first, spatial variation was ignored when upscaling from point measurements. Then, radial and azimuthal variations were incorporated subsequently by measuring at different depths and aspects around the tree. Ignoring azimuthal variation led to over- or underestimations of up to 102 %, while radial variation accounted for discrepancies of up to 25 %. Furthermore, the influence of changing meteorological conditions was assessed, which showed that radial profiles changed in shape during rain events, such that maximum sap flow rates occurred at different depths compared to dry periods. Our study thus indicates that spatial variation in sap flux density is highly unpredictable in A. marina due to its hydraulic architecture, and that changing meteorological conditions alter the pattern of this variation. These two factors should be accounted for when assessing whole-tree water use.

Limits to seaward expansion of mangroves: Translating physical disturbance mechanisms into seedling survival gradients - Balke, Thorsten; Swales, Andrew; Lovelock, Catherine E.; Herman, Peter M.J.; Bouma, Tjeerd J. (Journal of Experimental Marine Biology and Ecology, 2015)
Mangroves are valuable coastal habitats that are globally under pressure due to climate change and coastal development. Small-scale physical disturbance by tidal inundation and wave-induced sediment dynamics has been described as the main bottlenecks to mangrove seedling establishment on exposed tidal flats. However, such biophysical bottlenecks remain poorly studied.Mangrove progradation at our study site at the Firth of Thames (New Zealand) has been described as rapid but disturbance limited. For this site, we apply a mechanistic model according to the 'Window of Opportunity' (WoO) concept, which analyses real time series of external forcing for disturbance free periods. The model was parameterized with manipulative experiments on seedling stability and monitoring data. The modelled inundation free periods for initial anchoring were validated by a caging experiment with loose and tethered propagules.Although the time series of external forcing derived from monitoring data are simplified, our model confirms the absence of mangrove progradation due to failed recruitment events on the tidal flat since 1997. The model also shows, that a temporary reduction in external forcing would lead to a sudden progradation of the mangrove forest.WoO dynamics, where vegetation establishment requires temporarily benign conditions, may be of general importance to other ecosystems with stochastic external forcing. Understanding the biophysical interactions between vegetation and geomorphic processes is key to better manage and protect disturbance-driven ecosystems in times of changing wind pattern and accelerated sea-level rise.

Macroalgae contribute to nested mosaics of pH variability in a sub-Arctic fjord - Krause-Jensen, D.; Duarte, C. M.; Hendriks, I. E.; Meire, L.; Blicher, M. E.; Marbà, N.; Sejr, M. K. (Biogeosciences Discussions, 2015)
The Arctic Ocean is considered the most vulnerable ecosystem to ocean acidification (OA) and large-scale assessments of pH and the saturation state for aragonite (Ωarag) indicate that it is already close to corrosive states (Ωarag < 1). In high-latitude coastal waters the regulation of pH and Ωarag is far more complex than offshore because increased biological activity and input of glacial meltwater affect pH. As most calcifiers occupy coastal habitats, the assessment of risks from OA to these vulnerable organisms cannot be derived from extrapolation of current and forecasted offshore conditions, but requires an understanding of the regimes of pH and Ωarag in their coastal habitats. To increase knowledge of the natural variability of pH in the Arctic coastal zone and specifically to test the influence of benthic vegetated habitats, we quantified pH-variability in a Greenland fjord in a nested scale approach. A sensor array logging pH, O2, PAR, temperature and salinity was applied on spatial scales ranging from km-scale across the horizontal extension of the fjord, over 100 m scale vertically in the fjord, 10-100 m scale between subtidal habitats with and without kelp forests and between vegetated tidal pools and adjacent vegetated shores, to cm-m scale within kelp forests and mm-scale across boundary layers of macrophyte tissue. In addition, we assessed the temporal variability in pH on diurnal and seasonal scales. Based on pH-measurements combined with relationships between salinity, total alkalinity and dissolved inorganic carbon we also estimated variability of Ωarag. Results show variability in pH and Ωarag of up to 0.2-0.3 units at several scales, i.e. along the horizontal and vertical extension of the fjord, between seasons and on a diel basis in benthic habitats and within 1 m3 of kelp forest. Vegetated intertidal pools exhibited extreme diel pH variability of > 1.5 units and macrophyte boundary layers a pH-range of up to 0.8 units. Overall, Ωarag was favorable to calcification, and pelagic and benthic metabolism was an important driver of pH and Ωarag producing mosaics of variability from low levels in the dark to peak levels at high irradiance. We suggest that productive coastal environments may form niches of high pH in a future acidified Arctic Ocean.

Mangrove Shorelines - Woodrofe, Colin D.; Lovelock, Catherine E.; Rogers, Kerylee (Coastal Environments and Global Change, 2015)
Mangrove forests are highly productive ecosystems that support both terrestrial and marine biodiversity. They are important habitats for fish and crustaceans on which humans are dependent. Mangrove tree communities are relatively species-poor along Atlantic and East Pacific shorelines, however they also comprise more diverse forests associated with complex habitats around the margin of the Indian Ocean and throughout the west Pacific, and reach their greatest floristic and geomorphological diversity in Southeast Asia and northern Australia. It is often possible to recognize a zonation of species; whether this indicates successional change depends on the environmental setting. Ecogeomorphic models have been developed that recognize various geomorphological settings within which there are ecologically distinct mangrove forests. Mangrove shorelines have adapted to past patterns of climate and sea-level change, some of which have occurred more rapidly than at rates occurring at present, or anticipated in the immediate future.

Mangrove-forest evolution in a sediment-rich estuarine system: Opportunists or agents of geomorphic change? - Swales, Andrew; Bentley, Samuel J.; Lovelock, Catherine E. (Earth Surface Processes and Landforms, 2015)
The majority of the world's mangrove forests occur on mostly mineral sediments of fluvial origin. Two perspectives exist on the biogeomorphic development of these forests, i.e. that mangroves are opportunistic, with forest development primarily driven by physical processes, or alternatively that biophysical feedbacks strongly influence sedimentation and resulting geomorphology. On the Firth of Thames coast, New Zealand, we evaluate these two possible scenarios for sediment accumulation and forest development using high-resolution sedimentary records and a detailed chronology of mangrove-forest (Avicennia marina) development since the 1950s. Cores were collected along a shore-normal transect of known elevation relative to mean sea level (MSL). Activities for lead-210 (210Pb), caesium-137 (137Cs) and beryllium-7 (7Be), and sediment properties were analysed, with 210Pb sediment accumulation rates (SARs), compensated for deep subsidence (~8mmyr-1) used as a proxy for elevation gain. At least four phases of forest development since the 1950s are recognized. An old-growth forest developed by the late-1970s with more recent seaward forest expansion thereafter. Excess 210Pb profiles from the old-growth forest exhibit relatively low SARs near the top (7-12mmyr-1) and bottom (10-22mmyr-1) of cores, separated by an interval of higher SARs (33-100mmyr-1). A general trend of increasing SAR over time characterizes the recent forest. Biogeomorphic evolution of the system is more complex than simple mudflat accretion/progradation and mangrove-forest expansion. Surface-elevation gain in the old-growth forest displays an asymptotic trajectory, with a secondary depocentre developing on the seaward mudflat from the mid-1970s. Two- to ten-fold increases in 210Pb SARs are unambiguously large and occurred years to decades before seedling recruitment, demonstrating that mangroves do not measurably enhance sedimentation over annual to decadal timescales. This suggests that mangrove-forest development is largely dependent on physical processes, with forests occupying mudflats once they reach a suitable elevation in the intertidal.

Microbial community structure and dynamics in restored subtropical seagrass sediments - Bourque, Amanda S.; Vega-Thurber, Rebecca; Fourqurean, James W. (Aquatic Microbial Ecology, 2015)
Microorganisms in seagrass sediments facilitate many key ecosystem processes, yet current knowledge of microbial facilitation of seagrass community recovery following disturbance or restoration is limited. We studied microbial community responses to restoration of a subtropical seagrass meadow disturbed by vessel groundings in south Florida, USA, and relationships between microbial communities and sediment properties at the study sites using terminal restriction fragment length polymorphism. Two restoration methods were evaluated: the installation of bird roosting stakes as a means to provide a nutrient source, and placement of sand fill into excavations to prevent erosion. Both disturbed and restoration sites had less complex microbial community structure than undisturbed reference seagrass sediments. Microbial community structure varied little between disturbed and fertilized sites, but was distinct in filled sites. Sediment bulk density, sediment organic matter and total phosphorus content, porewater ammonium, soluble reactive phosphorus, and dissolved sulfide concentrations were important environmental predictors of microbial community structure across the restoration treatments. We show that community structure and diversity varied with sediment depth, among restoration treatments, and through time. Our results indicate that microbial communities in seagrass meadows are changed by physical disturbance of the rhizosphere, and that common restoration techniques lead to the formation of distinct microbial communities during the first year of recovery.

Nitrogen sharing and water source partitioning co-occur in estuarine wetlands - Wei, Lili; Lockington, David A.; Yu, Shen; Lovelock, Catherine E. (Functional Plant Biology, 2015)
Plant-plant interactions are particularly complex in multi-resource limited environments. The aim of this study was to assess species interactions in estuarine wetlands where both N and fresh water are limited. We combined stable isotope methods and dissimilarity analyses to compare interspecific interactions in N source use and water source use. Both Melaleuca quinquenervia (Cav.) S. T Blake and Avicennia marina (Forssk.) Vierh. had a lower leaf δ15N when they were growing together with the N-fixer Casuarina glauca Sieb. ex Spreng. compared with those trees growing in monospecific stands, but their water isotopes, δ18O and δD, were different from C. glauca. Our results indicate that the N-fixer C. glauca shared their N with co-existing neighbours, either indirectly or directly, but that water sources were partitioned among them. Further analyses showed that M. quinquenervia and C. glauca had lower dissimilarity in N source use but higher dissimilarity in water source use than the C. glauca-A. marina pair, implying that the co-existence between M. quinquenervia and C. glauca is relatively stable. Our results suggest that facilitative interaction and resource partitioning can co-occur in estuarine wetlands, and which could be important in maintaining diversity across resource gradients.

Nutrient enrichment intensifies hurricane impact in scrub mangrove ecosystems in the Indian River Lagoon, Florida, USA - Feller, Ilka C.; Dangremond, Emily M.; Devlin, Donna J.; Lovelock, Catherine E.; Proffitt, C. Edward; Rodriguez, Wilfrid (Ecology, 2015)
Mangroves are an ecological assemblage of trees and shrubs adapted to grow in intertidal environments along tropical, subtropical, and warm temperate coasts. Despite repeated demonstrations of their ecologic and economic value, multiple stressors including nutrient over-enrichment threaten these and other coastal wetlands globally. These ecosystems will be further stressed if tropical storm intensity and frequency increase in response to global climate changes. These stressors will likely interact, but the outcome of that interaction is uncertain. Here, we examined potential interaction between nutrient over-enrichment and the September 2004 hurricanes. Hurricanes Frances and Jeanne made landfall along Florida's Indian River Lagoon and caused extensive damage to a long-term fertilization experiment in a mangrove forest, which previously revealed that productivity was nitrogen (N) limited across the forest and, in particular, that N enrichment dramatically increased growth rates and aboveground biomass of stunted Avicennia germinans trees in the interior scrub zone. During the hurricanes, these trees experienced significant defoliation with three to four times greater reduction in leaf area index (LAI) than control trees. Over the long term, the +N scrub trees took four years to recover compared to two years for controls. In the adjacent fringe and transition zones, LAI was reduced by >70%, but with no differences based on zone or fertilization treatment. Despite continued delayed mortality for at least five years after the storms, LAI in the fringe and transition returned to pre-hurricane conditions in two years. Thus, nutrient over-enrichment of the coastal zone will increase the productivity of scrub mangroves, which dominate much of the mangrove landscape in Florida and the Caribbean; however, that benefit is offset by a decrease in their resistance and resilience to hurricane damage that has the potential to destabilize the system.

Nutrient subsidies delivered by seabirds to mangrove islands - Adame, M. F.; Fry, B.; Gamboa, J. N.; Herrera-Silveira, J. A. (Marine Ecology Progress Series, 2015)
In nutrient-poor landscapes, external nutrient subsidies are important for sustaining local production. Seabirds can transport marine nutrients in the form of guano to terrestrial and coastal ecosystems where they can relieve nutrient limitation. We assessed whether seabirds provide nutrient subsidies to mangrove islands that are strongly limited by phosphorus (P) in the Yucatan Peninsula. Our hypotheses were: (1) seabirds transport nutrients to mangrove islands, (2) mangroves use marine-derived nutrients and (3) nutrient inputs are higher during the nesting season. We chose 6 mangrove islands within a coastal lagoon: 2 with no birds, 2 with temporary birds and 2 with permanent bird colonies. On each, we measured forest structure and soil characteristics (P, pH, salinity and organic matter) for 3 seasons (dry, wet and trade wind season). We collected leaves (green and senescent) to determine P content and resorption efficiency as a measurement of nutrient limitation. Green leaves were also sampled for δ13C and δ15N to determine nutrient origin. Results show that islands with permanent bird colonies have the highest soil nutrients, which are used by the mangrove trees and relieve some of their nutrient limitation. Nutrient inputs were homogenously distributed through the sediment column, although a decrease in P and an increase in the N:P ratio in the first 20 cm suggests bacterial consumption. Bird nutrient inputs are seasonal, with highest inputs during the nesting season. This study shows an example in which marine-derived nutrients could be important for production of coastal mangrove islands.

Ratios for Higher Plantsl Two Categories of L3C /' 2C - Ferren Jr, Wayne R; Hubbard, David M; Wiseman, Sheila; Parikh, Anuja K; Gale, Nathan; Kneitel, Jamie M.; Kohn, Matthew J; Kraft, Nathan J. B.; Crutsinger, Gregory M.; Forrestel, Elisabeth J.; Emery, Nancy C.; Marton, J. M.; et al. (Oikos, 2015)
Vernal pools in the Santa Barbara area of southern California are restricted to narrow coastal terraces that occur south of the More Ranch Fault. To compensate partially for the historic loss of 90% of the vernal pools in this area, we implemented in 1986, in conjunction with the Isla Vista Recreation and Park District, an enhancement project at Del Sol Open Space and Vernal Pool Reserve in three phases involving 16 pools to: (1) enhance or restore existing degraded vernal pools; (2) re-create vernal pools where they occurred historically; and (3) create vernal pools from upland habitat. Manipulated sites were treated variously with or without vernal pool inoculum. Post-construction monitoring of 16 pools for plants, aquatic invertebrate fauna and amphibians, and/or avifauna occurred at different intervals; however, taken together the intervals reflect three post-construction monitoring phases including an early (year 1-3), mid (year 5-6), and late (year 10) phase. We hypothesized from the start of the manipulative projects that enhanced, restored, and created pools of the Santa Barbara area would eventually resemble natural vernal pools visually, possess an array of their known ecosystem functions, and be self-sustaining, as determined through comparative biological monitoring of natural reference pools. Six years after the manipulation of sites, vegetation and avifauna showed trends toward replication of natural pool characteristics. For aquatic invertebrates, however, we found distinct differences in the species diversity, taxonomic composition, and abundance among pool types. In 1996, we found that vegetation zonation, cover, and floristic composition and invertebrate faunas and tadpoles in the various pool treatments approached those of natural pools of the region, except for uninoculated created pools that continued to be different from natural pools and other manipulated pools.

Regulation of water balance in Mangroves - Reef, Ruth; Lovelock, Catherine E. (Annals of Botany, 2015)
Background: Mangroves are a group of highly salt-tolerant woody plants. The high water use efficiency of mangroves under saline conditions suggests that regulation of water transport is a crucial component of their salinity tolerance. Scope: This reviewfocuses on the processes that contribute to the ability of mangroves to maintainwater uptake and limit water loss to the soil and the atmosphere under saline conditions, from micro to macro scales. These processes include: (1) efficient filtering of the incoming water to exclude salt; (2) maintenance of internal osmotic potentials lower than that of the rhizosphere; (3) water-saving properties; and (4) efficient exploitation of less-saline water sources when these become available. Conclusions: Mangroves are inherently plastic and can change their structure at the root, leaf and stand levels in response to salinity in order to exclude salt from the xylem stream, maintain leaf hydraulic conductance, avoid cavitation and regulatewater loss (e.g. suberization of roots and alterations of leaf size, succulence and angle, hydraulic anatomy and biomass partitioning). However, much is still unknown about the regulation of water uptake in mangroves, such as how they sense and respond to heterogeneity in root zone salinity, the extent to which they utilize non-stomatally derived CO2 as a water-saving measure and whether they can exploit atmospheric water sources.

Sea level and turbidity controls on mangrove soil surface elevation change - Lovelock, Catherine E.; Adame, Maria Fernanda; Bennion, Vicki; Hayes, Matthew; Reef, Ruth; Santini, Nadia; Cahoon, Donald R. (Estuarine, Coastal and Shelf Science, 2015)
Increases in sea level are a threat to seaward fringing mangrove forests if levels of inundation exceed the physiological tolerance of the trees; however, tidal wetlands can keep pace with sea level rise if soil surface elevations can increase at the same pace as sea level rise. Sediment accretion on the soil surface and belowground production of roots are proposed to increase with increasing sea level, enabling intertidal habitats to maintain their position relative to mean sea level, but there are few tests of these predictions in mangrove forests. Here we used variation in sea level and the availability of sediments caused by seasonal and inter-annual variation in the intensity of La Nina-El Nino to assess the effects of increasing sea level on surface elevation gains and contributing processes (accretion on the surface, subsidence and root growth) in mangrove forests. We found that soil surface elevation increased with mean sea level (which varied over 250mm during the study) and with turbidity at sites where fine sediment in the water column is abundant. In contrast, where sediments were sandy, rates of surface elevation gain were high, but not significantly related to variation in turbidity, and were likely to be influenced by other factors that deliver sand to the mangrove forest. Root growth was not linked to soil surface elevation gains, although it was associated with reduced shallow subsidence, and therefore may contribute to the capacity of mangroves to keep pace with sea level rise. Our results indicate both surface (sedimentation) and subsurface (root growth) processes can influence mangrove capacity to keep pace with sea level rise within the same geographic location, and that current models of tidal marsh responses to sea level rise capture the major feature of the response of mangroves where fine, but not coarse, sediments are abundant.

Spatial and Temporal Hydrological Variations in the Inner Estuaries of a Large Coastal Lagoon of the Southern Gulf of Mexico - Medina-Gómez, Israel; Villalobos-Zapata, Guillermo J.; Herrera-Silveira, Jorge A. (Journal of Coastal Research, 2015)
Medina-Gómez, I.; Villalobos-Zapata, G.J., and Herrera-Silveira, J.A., 2015. Spatial and temporal hydrological variations in the inner estuaries of a large coastal lagoon of the southern Gulf of Mexico. Coastal lagoons receive significant inputs from river basins, leading to inner estuaries or fluvial lagoon subsystems subject to the bidirectional flow of energy, organic matter, nutrients, and sometimes toxic materials between river mouths and lagoons. Such exchanges are highly dynamic and enhance lagoon productivity. Terminos Lagoon (TL) is a large coastal lagoon in the southern Gulf of Mexico that has two deep permanent inlets connecting the lagoon to the Gulf and strong riverine input. We evaluated the influence of river discharge on seasonal and spatial patterns of water quality in six fluvial lagoon subsystems in TL. Six bimonthly samplings were carried out from February to December 2001. Temperature, salinity, dissolved oxygen, dissolved inorganic nutrients (nitrate, nitrite, ammonium, soluble reactive phosphorus, and soluble reactive silica), and chlorophyll a were measured. There were large differences between the western and eastern river mouths due to differences in river discharge and the nature of their watersheds (e.g., land use, size). Furthermore, the influence that the dominant depositional environment and local habitats (i.e. submerged aquatic vegetation) developing adjacent to these estuarine lagoon subsystems may exert over the nutrient concentrations of the water column is discussed. These differences were more evident during the rainy season when river discharge was highest. It is suggested that the input of N rather than P could have the greatest impact on TL in the future.

The cost and feasibility of marine coastal restoration - Bayraktarov, Elisa; Saunders, Megan Irene; Abdullah, Sabah; Mills, Morena; Beher, Jutta; Possingham, Hugh P.; Mumby, Peter J.; Lovelock, Catherine E. (Ecological Applications, 2015)
Land-use change in the coastal zone has led to worldwide degradation of marine coastal ecosystems and a loss of the goods and services they provide. Restoration is the process of assisting the recovery of an ecosystem that has been degraded, damaged, or destroyed and is critical for habitats where natural recovery is hindered. Uncertainties about restoration cost and feasibility can impede decisions on whether, what, how, where, and how much to restore. Here, we perform a synthesis of 235 studies with 954 observations from restoration or rehabilitation projects of coral reefs, seagrass, mangroves, saltmarshes and oyster reefs worldwide, and evaluate cost, survival of restored organisms, project duration, area, and techniques applied. Findings showed that while the median and average reported costs for restoration of one hectare of marine coastal habitat were around 80,000 US$ (2010) and 1,600,000 US$ (2010) respectively, the real total costs (median) are likely to be 2-4 times higher. Coral reefs and seag...
Keywords: cost; feasibility; marine coastal ecosystems; rehabilitation; restoration; success and failure

The effect of atmospheric carbon dioxide concentrations on the performance of the mangrove Avicennia germinans over a range of salinities - Reef, Ruth; Winter, Klaus; Morales, Jorge; Adame, Maria Fernanda; Reef, Dana L.; Lovelock, Catherine E. (Physiologia Plantarum, 2015)
By increasing water use efficiency and carbon assimilation, increasing atmospheric CO2 concentrations could potentially improve plant productivity and growth at high salinities. To assess the effect of elevated CO2 on the salinity response of a woody halophyte, we grew seedlings of the mangrove Avicennia germinans under a combination of five salinity treatments [from 5 to 65 parts per thousand (ppt)] and three CO2 concentrations (280, 400 and 800ppm). We measured survivorship, growth rate, photosynthetic gas exchange, root architecture and foliar nutrient and ion concentrations. The salinity optima for growth shifted higher with increasing concentrations of CO2, from 0ppt at 280ppm to 35ppt at 800ppm. At optimal salinity conditions, carbon assimilation rates were significantly higher under elevated CO2 concentrations. However, at salinities above the salinity optima, salinity had an expected negative effect on mangrove growth and carbon assimilation, which was not alleviated by elevated CO2, despite a significant improvement in photosynthetic water use efficiency. This is likely due to non-stomatal limitations to growth at high salinities, as indicated by our measurements of foliar ion concentrations that show a displacement of K+ by Na+ at elevated salinities that is not affected by CO2. The observed shift in the optimal salinity for growth with increasing CO2 concentrations changes the fundamental niche of this species and could have significant effects on future mangrove distribution patterns and interspecific interactions.

The puzzling existence of arid mangroves - what sustains Qatar mangroves? - Skov, Martin; Al-Maslamani, Ibrahim; Walton, Mark EM; Al-Ansari, Ebrahim; Kennedy, Hilary; Robbins, Peter; le Vay, Lewis (2015)
Ecological dogma holds that mangroves are predominantly exporting and are sources for production of offshore systems including fisheries (the ‘outwelling hypothesis’). Yet, the amount of export, and thereby the economic benefits to fisheries, varies greatly between locations. Mangrove functional research has focused on tropical and subtropical areas, where rainfall-driven transport of terrestrial nutrients into mangroves makes forests productive and runoff flow makes export likely. It remains unclear to what degree the outwelling hypothesis applies to arid mangroves; and, at a more basic level, in the absence of rainfall-driven runoff, what are the sources of nutrients that sustain arid mangrove production? This presentation will address these fundamental questions and review the sources for contextual variation in mangrove outwelling; it will detail the findings of several recent multi-disciplinary ecological and oceanographic research projects on Qatar mangroves. Our research explored the notion that the extent of outwelling globally depends on interactions of coastal geomorphology, tidal regime and mangrove production. Findings show that outwelling is less prevalent than previously thought, particularly in areas where in-house herbivory is intense. In mangroves with low freshwater through-flow the net balance between import and export might well be lead to net inwelling: a net import of organic material from subtidal habitats. Thus, seagrass beds are source of inwelling at Al-Khor mangrove in Qatar. At Al-Khor, limited export of mangrove-derived carbon to adjacent food webs has been attributed to the arid environment where the lack of rainfall eliminates a significant flushing mechanism, reducing the opportunity for outwelling of particulate organic material. This presentation concludes that mangroves in the western Arabian Gulf are nutrient limited and dependent on localized retention and cycling of nutrients and inwelling of nutrients from adjacent habitats, partially driven by tidal asymmetry. We suggest that inwelling of particulate material from down-stream habitats, such as seagrass beds, makes a significant contribution in supporting mangrove resident fauna and sustains mangroves in arid countries.

The response of the mangrove Avicennia marina to heterogeneous salinity measured using a split-root approach - Reef, Ruth; Markham, Hannah L.; Santini, Nadia S.; Lovelock, Catherine E. (Plant and Soil, 2015)
Aims: To investigate the physiological processes underlying freshwater utilisation in halophytes under non-uniform salinity conditions in order to determine whether preferential uptake of freshwater occurs and whether transient freshwater availability improves plant water relations and photosynthesis Methods: In a split-root experiment, we grew Avicennia marina (Forssk.) Vierh. at uniform salinity conditions (35:35 ppt) and then lowered (35:5 ppt) or increased (35:65 ppt) salinity to one compartment. Using δ18O-labelled water we calculated the extent of preferential water uptake of either source. Results: When given a 35:5 treatment, A. marina took-up three times more water from the fresher compartment than predicted by a root-weighted-no-salinity-preference model. No difference between compartments was observed in the 35:65 treatment, suggesting that avoidance of the more saline water did not occur. In the 35:5 treatment, stomatal conductance increased within 1.5 h, but photosynthetic rates were not enhanced over the 48-h period of the experiment and rapidly decreased in the 35:65 treatment. Conclusions: Avicennia marina responds to transient freshwater patches by increasing water uptake from areas of the root zone where the salinity is better for growth. However, photosynthetic rates respond to the highest salinity in the root zone; thus, reductions in salinity in part of the root zone may enhance water storage in stem tissues but positive effects on photosynthesis may require longer periods.

The use of fresh and saline water sources by the mangrove Avicennia marina - Santini, Nadia S.; Reef, Ruth; Lockington, David A.; Lovelock, Catherine E. (Hydrobiologia, 2015)
Mangroves are distributed along tropical and subtropical riverine and coastal shores. Although mangroves are highly adapted to saline environments, maintaining water uptake under saline conditions is energetically expensive. Therefore, salinity is a limiting factor for mangrove growth and productivity, and access to fresh water sources, such as rainwater and groundwater, which reduce water salinity, increase mangrove ecosystem productivity. Here, we investigated the extent of fresh water utilization by mangroves to better predict current and future mangrove productivity. We used the abundance of 18O isotope in stem water to assess: (1) the extent of fresh water utilization by Avicennia marina (Forssk.) Vierh across hydrological settings; and (2) whether growth, measured as increments in stem circumference, is sensitive to variation in rainfall availability. The δ18O isotopic composition of stem water indicated mangroves use both fresh and saline water sources for metabolic processes. However, our results suggest that the proportion of fresh water used by mangroves increases with the availability of fresh water. Growth of the main stems of trees was correlated with rainfall (r2 = 0.34 and r2 = 0.37, P = 0.001). Our results indicate that access to fresh water is important for mangrove productivity because it enhances their growth rates.

Variable nutrient stoichiometry (carbon:nitrogen:phosphorus) across trophic levels determines community and ecosystem properties in an oligotrophic mangrove system - Scharler, U. M.; Ulanowicz, R. E.; Fogel, M. L.; Wooller, M. J.; Jacobson-Meyers, M. E.; Lovelock, C. E.; Feller, I. C.; Frischer, M.; Lee, R.; McKee, K.; Romero, I. C.; Schmit, J. P.; et al. (Oecologia, 2015)
Our study investigated the carbon:nitrogen:phosphorus (C:N:P) stoichiometry of mangrove island of the Mesoamerican Barrier Reef (Twin Cays, Belize). The C:N:P of abiotic and biotic components of this oligotrophic ecosystem was measured and served to build networks of nutrient flows for three distinct mangrove forest zones (tall seaward fringing forest, inland dwarf forests and a transitional zone). Between forest zones, the stoichiometry of primary producers, heterotrophs and abiotic components did not change significantly, but there was a significant difference in C:N:P, and C, N, and P biomass, between the functional groups mangrove trees, other primary producers, heterotrophs, and abiotic components. C:N:P decreased with increasing trophic level. Nutrient recycling in the food webs was highest for P, and high transfer efficiencies between trophic levels of P and N also indicated an overall shortage of these nutrients when compared to C. Heterotrophs were sometimes, but not always, limited by the same nutrient as the primary producers. Mangrove trees and the primary tree consumers were P limited, whereas the invertebrates consuming leaf litter and detritus were N limited. Most compartments were limited by P or N (not by C), and the relative depletion rate of food sources was fastest for P. P transfers thus constituted a bottleneck of nutrient transfer on Twin Cays. This is the first comprehensive ecosystem study of nutrient transfers in a mangrove ecosystem, illustrating some mechanisms (e.g. recycling rates, transfer efficiencies) which oligotrophic systems use in order to build up biomass and food webs spanning various trophic levels.

Vegetation persistence and carbon storage: Implications for environmental water management for Phragmites australis - Whitaker, Kai; Rogers, Kerrylee; Saintilan, Neil; Mazumder, Debashish; Wen, Li; Morrison, R. J. (Water Resources Research, 2015)
Environmental water allocations are used to improve the ecological health of wetlands. There is now increasing demand for allocations to improve ecosystem productivity and respiration, and enhance carbon sequestration. Despite global recognition of wetlands as carbon sinks, information regarding carbon dynamics is lacking. This is the first study estimating carbon sequestration for semiarid Phragmites australis reedbeds. The study combined aboveground biomass assessments with stable isotope analyses of soils and modeling of biomass using Normalized Digital Vegetation Index (NDVI) to investigate the capacity of environmental water allocations to improve carbon storage. The study considered relationships between soil organic carbon (SOC), carbon sources, and reedbed persistence in the Macquarie Marshes, a regulated semiarid floodplain of the Murray-Darling Basin, Australia. SOC storage levels to 1 m soil depth were higher in persistent reedbeds (167 Mg ha-1) than ephemeral reedbeds (116-138 Mg ha-1). In situ P. australis was the predominant source of surface SOC at persistent reedbeds; mixed sources of surface SOC were proposed for ephemeral reedbeds. 13C enrichment with increasing soil depth occurred in persistent and ephemeral reedbeds and may not relate to flow characteristics. Despite high SOC at persistent reedbeds, differences in the rate of accretion contributed to significantly higher rates of carbon sequestration at ephemeral reedbeds (approximately 554 and 465 g m-2 yr-1) compared to persistent reedbeds (5.17 g m-2 yr-1). However, under current water regimes, rapid accretion at ephemeral reedbeds cannot be maintained. Effective management of persistent P. australis reedbeds may enhance carbon sequestration in the Macquarie Marshes and floodplain wetlands more generally.

Viviparous mangrove propagules of Ceriops tagal and Rhizophora mucronata, where both Rhizophoraceae show different dispersal and establishment strategies - Robert, Elisabeth M.R.; Oste, Jorien; Van der Stocken, Tom; De Ryck, Dennis J.R.; Quisthoudt, Katrien; Kairo, James G.; Dahdouh-Guebas, Farid; Koedam, Nico; Schmitz, Nele (Journal of Experimental Marine Biology and Ecology, 2015)
For plants to reproduce successfully, it is crucial that their seeds be adapted to survive the environmental conditions in which they disperse and establish. The buoyant dispersal units (propagules) of viviparous mangrove species seem perfect adaptations for dispersal and establishment within the mangrove environment. However, much remains unknown about the structural changes mangrove propagules undergo between abscission from the parent tree and establishment. Mature propagules of two viviparous mangrove species (. Rhizophora mucronata and Ceriops tagal) were submitted to experimental conditions in order to test: (i) how substrate influences propagule mass and volume during dispersal; (ii) if stranding of propagules on solid soil triggers root development and thus establishment. Our results showed that dehydration stimulates root formation and propagule establishment and that the establishment phase is faster at lower rather than higher salinity. Furthermore, it was found that the larger propagules of R. mucronata were less vulnerable to dehydration than those of C. tagal, that their root growth started later and that, once initiated, their roots grew faster. This indicated that Rhizophora propagules are better suited for long distance dispersal than those of Ceriops and that Rhizophora has an advantage for establishment in the lower part of the intertidal zone, where inundation is more frequent and propagules need to anchor more rapidly. This study therefore points out that two co-living species of the same family have different dispersal and establishment strategies, thereby contributing to the understanding of their local and global distribution and of the species-specific dynamics within mangrove forests

Water quality, isoscapes and stoichioscapes of seagrasses indicate general P limitation and unique N cycling in shallow water benthos of Bermuda - Fourqurean, J. W.; Manuel, S. A.; Coates, K. A.; Kenworthy, W. J.; Boyer, J. N. (Biogeosciences, 2015)
Striking spatial patterns in stable isotope ratios (isoscapes) and elemental ratios (stoichioscapes) of seagrass leaves and the water column nutrients indicate general P-limitation of both water column and benthic primary productivity on the Bermuda Platform, and they highlight the role of the Bermuda Islands as a source of N and P. We found consistent differences among the four seagrass species (Syringodium filiforme, Thalassia testudinum, Halodule sp. and Halophila decipiens) in the N, P, δ13C and δ15N of leaf tissues. The δ15N of seagrass leaves was especially variable, with values from -10.1 to 8.8 %, greatly expanding the reported range of values for all seagrass species globally. Spatial patterns from both the water column and the seagrass leaves indicated that P availability was higher near shore, and δ15N values suggest this was likely a result of human waste disposal. Spatially contiguous areas of extremely depleted seagrass 15N suggest unique N sources and cycling compared to other seagrass-dominated environments. Seagrass N : P values were not as far from the stoichiometric balance between N and P availability as in the water column, and there were no strong relationships between the water column N : P and the seagrass N : P. Such isoscapes and stoichioscapes provide valuable ecogeochemical tools to infer ecosystem processes as well as provide information that can inform food web and animal movement studies.

Where We Stand: A Synthesis of Status Reports of Mangroves in Northwestern Luzon - Salmo III, Dr Severino G.; Favis, Abigail Marie T.; Ting, Marie Nathalie S. (State of the Mangrove Summit: Northwestern Luzon Proceedings, 2015)
CITATIONS 0 READS 248 3 authors, including: Some of the authors of this publication are also working on these related projects: Mangrove Modelling View project IFS Mangrove Restoration View project Sev Salmo Ateneo de Manila University 50 PUBLICATIONS 697 CITATIONS SEE PROFILE All content following this page was uploaded by Sev Salmo on 16 August 2015. The user has requested enhancement of the downloaded file.

A comparison of mangrove Canopy height using multiple independent measurements from land, air, and space - Lagomasino, David; Fatoyinbo, Temilola; Lee, Seung Kuk; Feliciano, Emanuelle; Trettin, Carl; Simard, Marc (Remote Sensing, 2016)
Canopy height is one of the strongest predictors of biomass and carbon in forested ecosystems. Additionally, mangrove ecosystems represent one of the most concentrated carbon reservoirs that are rapidly degrading as a result of deforestation, development, and hydrologic manipulation. Therefore, the accuracy of Canopy Height Models (CHM) over mangrove forest can provide crucial information for monitoring and verification protocols. We compared four CHMs derived from independent remotely sensed imagery and identified potential errors and bias between measurement types. CHMs were derived from three spaceborne datasets; Very-High Resolution (VHR) stereophotogrammetry, TerraSAR-X add-on for Digital Elevation Measurement, and Shuttle Radar Topography Mission (TanDEM-X), and lidar data which was acquired from an airborne platform. Each dataset exhibited different error characteristics that were related to spatial resolution, sensitivities of the sensors, and reference frames. Canopies over 10 m were accurately predicted by all CHMs while the distributions of canopy height were best predicted by the VHR CHM. Depending on the guidelines and strategies needed for monitoring and verification activities, coarse resolution CHMs could be used to track canopy height at regional and global scales with finer resolution imagery used to validate and monitor critical areas undergoing rapid changes.

A review of seagrass economic valuations: Gaps and progress in valuation approaches - Dewsbury, Bryan M.; Bhat, Mahadev; Fourqurean, James W. (Ecosystem Services, 2016)
Multiple studies have documented the ecologically important role that seagrasses play in estuarine and marine ecosystems. Unfortunately, economic valuations of these systems have not been as widespread. To date, most techniques rely on mechanisms that do not incorporate the actual ecological drivers behind the economic service, but rather rely on proxy measures to derive value. In this manuscript we review the many values that seagrasses have that result in economic services, and the valuation techniques used to estimate their monetary value. We present a conceptual framework linking seagrass ecosystems to the economic services they provide, showing the areas where novel valuation approaches are most lacking. We conclude that indirect methods used to valuate seagrass ecosystems underestimate the economic value of their services, and that more derivative-based models linking ecological structure and function to all associated economic services are essential for accurate estimations of their dollar value.

Allometry data and equations for coastal marsh plants - Lu, Meng; Caplan, Joshua S.; Bakker, Jonathan D.; Langley, J. Adam; Mozdzer, Thomas J.; Drake, Bert G.; Megonigal, J. Patrick (Ecology, 2016)
Coastal marshes are highly valued for ecosystem services such as protecting inland habitats from storms, sequestering carbon, removing nutrients and other pollutants from surface water, and providing habitat for fish, shellfish, and birds. Because plants largely determine the structure and function of coastal marshes, quantifying plant biomass is essential for evaluating these ecosystem services, understanding the biogeochemical processes that regu-late ecosystem function, and forecasting tidal wetland responses to accelerated sea level rise. Allometry is a convenient and efficient technique for nondestructive estimation of plant bio-mass, and it is commonly used in studies of carbon and nitrogen cycles, energy flows, and marsh surface elevation change. We present plant allometry data and models developed for three long-term experiments at the Smithsonian Global Change Research Wetland, a brackish marsh in the Rhode River subestuary of the Chesapeake Bay. The dataset contains 9,771 measurements of stem height, dry mass, and (in 9638 cases) stem width across 11 plant species. The vast majority of observations are for Schoenoplectus americanus (8430) and Phragmites austra-lis (311), with fewer observations for other common species: Amaranthus cannabinus, Atriplex patula, Iva frutescens, Kosteletzkya virginica, Polygonum hydropiper, Solidago sempervirens, Spartina alterniflora, Spartina cynosuroides, and Typha angustifolia. Allometric relationships take the form of linear regressions of biomass (transformed using the Box-Cox procedure) on either stem height and width, or on stem height alone. Allometric relationships for Schoenoplectus americanus were not meaningfully altered by elevated CO2, N enrichment, the community context, interannual variation in climate, or year, showing that a single equation can be used across a broad range of conditions for this species. Archived files include: (1) raw data used to derive allometric equations for each species, (2) reports and evaluations of the allometric equations we derived from the data, and (3) R code with which our derivations can be replicated. Methodological details of our experiments, data collection efforts, and statistical modeling are described in the metadata. The allometric equations can be used for biomass estimation in empirical and modeling studies of North American coastal wetlands, and the data can be used in ecological studies of terrestrial plant allometry.

Are Peri-Urban Mangroves Vulnerable? An Assessment Through Litter Fall Studies - Mohamed, Mohamed Omar Said; Mangion, Perrine; Mwangi, Steve; Kairo, James Gitundu; Dahdouh-Guebas, Farid; Koedam, Nico (2016)
It is in estuaries and deltas where the richness of the land meets the abundance of the sea, creating an environment of high diversity, dynamism and productivity. Nevertheless, the important contributions estuaries make to local livelihoods and national economies, as well as to their complex role in the functioning of the land-ocean interface, are often overlooked. The Western Indian Ocean is dotted with important estuaries and deltas, including the Tana and Sabaki in Kenya, Pangani, Rufiji and Ruvuma in Tanzania, Zambezi, Incomati, Maputo, Pungwe and Limpopo in Mozambique, Thukela in South Africa and Betsiboka in Madagascar. With numerous plans and investments in place for a massive acceleration in infrastructure development and energy and food production, human activities will increasingly impact these important estuarine and coastal ecosystems and the life-supporting services they provide. In this regard, the unique, diverse and productive estuaries and deltas of the Western Indian Ocean stand at a crucial crossroad. The Western Indian Ocean is internationally recognized as a hot spot of biodiversity, hosting one-third of the 38 globally, recognized marine and coastal habitats, an abundance of fish species and marine mammals, all five marine turtle species, over 40 species of seabirds and the longest fringing reef in the world. The region is also home to the charismatic coelacanth, nicknamed the living fossil, and the critically, endangered sawfish and seahorse. Furthermore, the region’ s coastal and marine waters are important fishing grounds, supporting the livelihoods of the local population. Its marine parks and other protected areas are also the basis for an active tourism industry. The unfortunate reality, however, is that human activities in these river catchments are having increasingly serious impacts on these sensitive downstream estuarine and coastal ecosystems. The damming of rivers over the past 50 years, combined with reduced rainfall, expansion of irrigated agriculture and other increasing water abstraction and land uses within various catchments, are among the underlying causes of those changes. Furthermore, pollution from municipal and industrial effluents is exacerbating the serious degradation of waters and sediment quality that is being observed in these rivers, estuaries and coastal waters, resulting in a loss of biodiversity, increasing eutrophication and reduced fish catches in many locations in the Western Indian Ocean. To set the stage for addressing the continuing degradation of these important land-sea interfacing water systems, this publication was made possible due to the leadership of four scientists: Prof. Salif Diop from the University of Dakar; Dr. Peter Scheren from WWF; Prof. John Machiwa from the University of Dar es Salaam and Prof. Jean-Paul Ducrotoy from the Institute of Estuarine and Coastal Studies, The University of Hull, UK. The focus of this book is on estuaries, but its scope and implications extend well beyond this particular coastal feature. Indeed, estuaries can only be considered as part of the life cycle of the entire river basins draining into them and the downstream marine areas that receive these riverine inputs. These interlinked systems and the life-supporting ecosystem services they provide are particularly sensitive to human and natural pressures; hence the title of this book“Estuaries: a Lifeline of Ecosystem Services in the Western Indian Ocean”

Biomass and productivity of seagrasses in Africa - Githaiga, Michael N.; Gilpin, Linda; Kairo, James G.; Huxham, Mark (Botanica Marina, 2016)
There is growing interest in carbon stocks and flows in seagrass ecosystems, but recent global reviews suggest a paucity of studies from Africa. This paper reviews work on seagrass productivity, biomass and sediment carbon in Africa. Most work was conducted in East Africa with a major geographical gap in West Africa. The mean above-ground, below-ground and total biomasses from all studies were 174.4, 474.6 and 514 g DW m-2, respectively with a global range of 461-738 g DW m-2. Mean annual production rate was 913 g DW m-2 year-1 (global range 816-1012 g DW m-2 year-1). No studies were found giving sediment organic carbon, demonstrating a major gap in seagrass blue carbon work. Given the small numbers of relevant papers and the large geographical areas left undescribed in Africa, any conclusions remain tentative and much remains to be done on seagrass studies in Africa.

CARBON STOCKS AND EMISSIONS FROM DEGRADATION AND CONVERSION OF TROPICAL PEAT SWAMP FORESTS IN WEST KALIMANTAN , INDONESIA Abstract No : A-053 CARBON STOCKS AND EMISSIONS FROM DEGRADATION AND CONVERSION - International, Winrock; Kauffman, John Boone; Murdiyarso, Daniel; Anshari, Gusti Z (2016)

Coastal "blue" carbon: A revised guide to supporting coastal wetland programs and projects using climate finance and other financial mechanisms - Herr, D.; Agardy, T.; Benzaken, D.; Hicks, F.; Howard, J.; Landis, E.; Soles, A.; Vegh, T. (Coastal "blue" carbon: A revised guide to supporting coastal wetland programs and projects using climate finance and other financial mechanisms, 2016)
A revised guide to supporting coastal wetland programs and projects using climate finance and other financial mechanisms

Complex invader-ecosystem interactions and seasonality mediate the impact of non-native Phragmites on CH4 emissions - Mueller, Peter; Hager, Rachel N.; Meschter, Justin E.; Mozdzer, Thomas J.; Langley, J. Adam; Jensen, Kai; Megonigal, J. Patrick (Biological Invasions, 2016)
Invasive plants can influence ecosystem processes such as greenhouse gas (GHG) emissions from wetland systems directly through plant-mediated transfer of GHGs to the atmosphere or through indirect modification of the environment. However, patterns of plant invasion often co-vary with other environmental gradients, so attributing ecosystem effects to invasion can be difficult in observational studies. Here, we assessed the impact of Phragmites australis invasion into native shortgrass communities on methane (CH4) emissions by conducting field measurements of CH4 emissions along transects of invasion by Phragmites in two neighboring brackish marsh sites and compared these findings to those from a field-based mesocosm experiment. We found remarkable differences in CH4 emissions and the influence of Phragmites on CH4 emissions between the two neighboring marsh sites. While Phragmites consistently increased CH4 emissions dramatically by 10.4 ± 3.7 µmol m−2 min−1 (mean ± SE) in our high-porewater CH4 site, increases in CH4 emissions were much smaller (1.4 ± 0.5 µmol m−2 min−1) and rarely significant in our low-porewater CH4 site. While CH4 emissions in Phragmites-invaded zones of both marsh sites increased significantly, the presence of Phragmites did not alter emissions in a complementary mesocosm experiment. Seasonality and changes in temperature and light availability caused contrasting responses of CH4 emissions from Phragmites- versus native zones. Our data suggest that Phragmites-mediated CH4 emissions are particularly profound in soils with innately high rates of CH4 production. We demonstrate that the effects of invasive species on ecosystem processes such as GHG emissions may be predictable qualitatively but highly variable quantitatively. Therefore, generalizations cannot be made with respect to invader-ecosystem processes, as interactions between the invader and local abiotic conditions that vary both spatially and temporally on the order of meters and hours, respectively, can have a stronger impact on GHG emissions than the invader itself.

Deep rooting and global change facilitate spread of invasive grass - Mozdzer, Thomas J.; Langley, J. Adam; Mueller, Peter; Megonigal, J. Patrick (Biological Invasions, 2016)
Abiotic global change factors, such as rising atmospheric CO2, and biotic factors, such as exotic plant invasion, interact to alter the function of terrestrial ecosystems. An invasive lineage of the common reed, Phragmites australis, was introduced to North America over a century ago, but the belowground mechanisms underlying Phragmites invasion and persistence in natural systems remain poorly studied. For instance, Phragmites has a nitrogen (N) demand higher than native plant communities in many of the ecosystems it invades, but the source of the additional N is not clear. We exposed introduced Phragmites and native plant assemblages, containing Spartina patens and Schoenoplectus americanus, to factorial treatments of CO2 (ambient or +300 ppm), N (0 or 25 g m−2 year−1), and hydroperiod (4 levels), and focused our analysis on changes in root productivity as a function of depth and evaluated the effects of introduced Phragmites on soil organic matter mineralization. We report that non-native invasive Phragmites exhibited a deeper rooting profile than native marsh species under all experimental treatments, and also enhanced soil organic matter decomposition. Moreover, exposure to elevated atmospheric CO2 induced a sharp increase in deep root production in the invasive plant. We propose that niche separation accomplished through deeper rooting profiles circumvents nutrient competition where native species have relatively shallow root depth distributions; deep roots provide access to nutrient-rich porewater; and deep roots further increase nutrient availability by enhancing soil organic matter decomposition. We expect that rising CO2 will magnify these effects in deep-rooting invasive plants that compete using a tree-like strategy against native herbaceous plants, promoting establishment and invasion through niche separation.

Effect of high sedimentation rates on surface sediment dynamics and mangrove growth in the Porong River, Indonesia - Sidik, Frida; Neil, David; Lovelock, Catherine E. (Marine Pollution Bulletin, 2016)
Large quantities of mud from the LUSI (Lumpur Sidoarjo) volcano in northeastern Java have been channeled to the sea causing high rates of sediment delivery to the mouth of the Porong River, which has a cover of natural and planted mangroves. This study investigated how the high rates of sediment delivery affected vertical accretion, surface elevation change and the growth of Avicennia sp., the dominant mangrove species in the region. During our observations in 2010-2011 (4-5 years after the initial volcanic eruption), very high rates of sedimentation in the forests at the mouth of the river gave rise to high vertical accretion of over 10 cm y-1. The high sedimentation rates not only resulted in reduced growth of Avicennia sp. mangrove trees at the two study sites at the Porong River mouth, but also gave rise to high soil surface elevation gains.

Effects of nesting waterbirds on nutrient levels in mangroves, Gulf of Fonseca, Honduras - McFadden, Tyler Neal; Kauffman, J. Boone; Bhomia, Rupesh K. (Wetlands Ecology and Management, 2016)
Mangroves provide numerous ecosystem services, including biodiversity values such as nesting sites for piscivorous waterbirds. High concentrations of waterbirds at nest sites are hypothesized to affect ecosystem dynamics, yet few studies have examined their effects as a nutrient source in mangroves. We examined the effects of nutrient enrichment by colonial waterbirds at a mangrove rookery in the Gulf of Fonseca, Honduras. We compared nutrient inputs via bird guano deposition and macronutrient levels in the vegetation and soils between a small island that hosted large numbers of roosting waterbirds and an adjacent island with little evidence of waterbird activity. Nest density at the rookery was 1721 ± 469 nests ha−1. Rookery birds deposited 7.2 ± 3.4 g m−2 day−1 guano dry weight, delivering an estimated 1.12 Mg ha−1 nitrogen and 0.16 Mg ha−1 phosphorus to the island over a 120 day breeding season. This large nutrient influx contributed to substantially higher concentrations of biologically important nutrients in the rookery soils (seven times more plant available phosphorus, eight times more nitrate, and two times more ammonium). Rookery mangrove leaves contained significantly higher concentrations of nitrogen and phosphorus compared to the control site. These results suggest that colonial waterbirds significantly influence nutrient dynamics of mangroves at local scales. Further research is needed to understand the effects of avian derived nutrients on mangrove growth rates, nutrient export to adjacent waters, invertebrate communities, and mangrove associated fisheries.
Keywords: Guano; Macronutrient cycling; Mangroves; Nutrient enrichment; Waterbirds

Elevated CO2 promotes long-term nitrogen accumulation only in combination with nitrogen addition - Pastore, Melissa A.; Megonigal, J. Patrick; Langley, J. Adam (Global Change Biology, 2016)
Biogeochemical models that incorporate nitrogen (N) limitation indicate that N availability will control the magnitude of ecosystem carbon uptake in response to rising CO2. Some models, however, suggest that elevated CO2 may promote ecosystem N accumulation, a feedback that in the long term could circumvent N limitation of the CO2 response while mitigating N pollution. We tested this prediction using a nine-year CO2xN experiment in a tidal marsh. Although the effects of CO2 are similar between uplands and wetlands in many respects, this experiment offers a greater likelihood of detecting CO2 effects on N retention on a decadal timescale because tidal marshes have a relatively open N cycle and can accrue soil organic matter rapidly. To determine how elevated CO2 affects N dynamics, we assessed the three primary fates of N in a tidal marsh: (1) retention in plants and soil, (2) denitrification to the atmosphere, and (3) tidal export. We assessed changes in N pools and tracked the fate of a 15N tracer added to each plot in 2006 to quantify the fraction of added N retained in vegetation and soil, and to estimate lateral N movement. Elevated CO2 alone did not increase plant N mass, soil N mass, or 15N label retention. Unexpectedly, CO2 and N interacted such that the combined N+CO2 treatment increased ecosystem N accumulation despite the stimulation in N losses indicated by reduced 15N label retention. These findings suggest that in N-limited ecosystems, elevated CO2 is unlikely to increase long-term N accumulation and circumvent progressive N limitation without additional N inputs, which may relieve plant-microbe competition and allow for increased plant N uptake.

Evaluating deep subsidence in a rapidly-accreting mangrove forest using GPS monitoring of surface-elevation benchmarks and sedimentary records - Swales, Andrew; Denys, Paul; Pickett, Vernon I.; Lovelock, Catherine E. (Marine Geology, 2016)
Ultimately, the fate of mangrove forests depends on substrate-elevation gains keeping pace with relative sea-level rise (RSLR). Some of the world's largest mangrove forests occur on tectonically active margins, river deltas and sedimentary basins where sea-level trends are largely controlled by vertical land motion (i.e., subsidence), so that RSLR can be markedly higher than sea-level rise induced by climate warming. The Rod Surface Elevation Table — Marker Horizon (RSET-MH) method has been applied globally to evaluate coastal-wetland resilience to SLR by quantifying net rates of elevation change relative to a benchmark. A limitation of the RSET method is that the stability of the benchmark (i.e., vertical trend) is unknown and RSLR in wetlands is typically inferred from regional tide-gauge records. In the present study, we evaluate RSLR in a rapidly-subsiding Avicenna marina mangrove forest with a large terrigenous sediment supply (Firth of Thames, New Zealand) using independent and complimentary methods: (1) campaign-GPS surveys of the stability of three RSET benchmarks driven 18 m into unconsolidated sediment, a tide gauge some 10 km distant and a reference station located on basement rock (2007–2016) that are tied to a network of satellite-based geodetic sites; and (2) 137Cs-validated 210Pb sediment accumulation rates (SAR) measured in cores as a proxy for RSLR. The similarity of deep-subsidence rates at the RSET benchmarks located several-hundred metres apart (7.7 ± 0.5 to 9.4 ± 0.5 mm yr− 1) provides confidence in these results. These subsidence rates are two- to five-fold higher than recorded at the nearby tide gauge (3.6 ± 0.7 mm yr− 1) and reference station (1.6 ± 0.5 mm yr− 1). Weighted-average 210Pb SAR of 9.9 mm and 9.3 mm yr− 1 yield similar estimates of deep subsidence (i.e., 8.4 and 6.9 mm yr− 1 + SLR adjusted for vertical land motion), indicating that this geological process is the major driver of the long-term sea-level trend in the mangrove forest. Our findings suggest that regional tide gauge records may not provide reliable estimates of RSLR for all coastal wetlands due to local subsidence associated with natural processes and human activities. Subsidence rates and RSLR within coastal wetlands can be evaluated using campaign-GPS surveys of RSET benchmarks and independently from longer-term sedimentary records. Finally, evaluations of the resilience of coastal wetlands to rising sea levels over the coming decades must be based on measurements of RSLR from these systems themselves.

Extreme 15N Depletion in Seagrasses - Walton, M. E.M.; Al-Maslamani, I.; Haddaway, N.; Kennedy, H.; Castillo, A.; Al-Ansari, E. S.; Al-Shaikh, I.; Abdel-Moati, M.; Al-Yafei, M. A.A.; Le Vay, L. (Estuaries and Coasts, 2016)
Seagrass beds form an important part of the coastal ecosystem in many parts of the world but are very sensitive to anthropogenic nutrient increases. In the last decades, stable isotopes have been used as tracers of anthropogenic nutrient sources and to distinguish these impacts from natural environmental change, as well as in the identification of food sources in isotopic food web reconstruction. Thus, it is important to establish the extent of natural variations on the stable isotope composition of seagrass, validating their ability to act as both tracers of nutrients and food sources. Around the world, depending on the seagrass species and ecosystem, values of seagrass N normally vary from 0 to 8 ‰ δ15N. In this study, highly unusual seagrass N isotope values were observed on the east coast of Qatar, with significant spatial variation over a scale of a few metres, and with δ15N values ranging from +2.95 to −12.39 ‰ within a single bay during March 2012. This pattern of variation was consistent over a period of a year although there was a seasonal effect on the seagrass δ15N values. Seagrass, water column and sediment nutrient profiles were not correlated with seagrass δ15N values and neither were longer-term indicators of nutrient limitation such as seagrass biomass and height. Sediment δ15N values were correlated with Halodule uninervis δ15N values and this, together with the small spatial scale of variation, suggest that localised sediment processes may be responsible for the extreme isotopic values. Consistent differences in sediment to plant 15N discrimination between seagrass species also suggest that species-specific nutrient uptake mechanisms contribute to the observed δ15N values. This study reports some of the most extreme, negative δ15N values ever noted for seagrass (as low as −12.4 ‰) and some of the most highly spatially variable (values varied over 15.4 ‰ in a relatively small area of only 655 ha). These results are widely relevant, as they demonstrate the need for adequate spatial and temporal sampling when working with N stable isotopes to identify food sources in food web studies or as tracers of anthropogenic nutrients.

Global analysis of seagrass restoration: The importance of large-scale planting - van Katwijk, Marieke M.; Thorhaug, Anitra; Marbà, Núria; Orth, Robert J.; Duarte, Carlos M.; Kendrick, Gary A.; Althuizen, Inge H.J.; Balestri, Elena; Bernard, Guillaume; Cambridge, Marion L.; Cunha, Alexandra; Durance, Cynthia; et al. (Journal of Applied Ecology, 2016)
In coastal and estuarine systems, foundation species like seagrasses, mangroves, saltmarshes or corals provide important ecosystem services. Seagrasses are globally declining and their reintroduction has been shown to restore ecosystem functions. However, seagrass restoration is often challenging, given the dynamic and stressful environment that seagrasses often grow in. From our world-wide meta-analysis of seagrass restoration trials (1786 trials), we describe general features and best practice for seagrass restoration. We confirm that removal of threats is important prior to replanting. Reduced water quality (mainly eutrophication), and construction activities led to poorer restoration success than, for instance, dredging, local direct impact and natural causes. Proximity to and recovery of donor beds were positively correlated with trial performance. Planting techniques can influence restoration success. The meta-analysis shows that both trial survival and seagrass population growth rate in trials that survived are positively affected by the number of plants or seeds initially transplanted. This relationship between restoration scale and restoration success was not related to trial characteristics of the initial restoration. The majority of the seagrass restoration trials have been very small, which may explain the low overall trial survival rate (i.e. estimated 37%). Successful regrowth of the foundation seagrass species appears to require crossing a minimum threshold of reintroduced individuals. Our study provides the first global field evidence for the requirement of a critical mass for recovery, which may also hold for other foundation species showing strong positive feedback to a dynamic environment. Synthesis and applications. For effective restoration of seagrass foundation species in its typically dynamic, stressful environment, introduction of large numbers is seen to be beneficial and probably serves two purposes. First, a large-scale planting increases trial survival - large numbers ensure the spread of risks, which is needed to overcome high natural variability. Secondly, a large-scale trial increases population growth rate by enhancing self-sustaining feedback, which is generally found in foundation species in stressful environments such as seagrass beds. Thus, by careful site selection and applying appropriate techniques, spreading of risks and enhancing self-sustaining feedback in concert increase success of seagrass restoration. For effective restoration of seagrass foundation species in its typically dynamic, stressful environment, introduction of large numbers is seen to be beneficial and probably serves two purposes. First, a large-scale planting increases trial survival - large numbers ensure the spread of risks, which is needed to overcome high natural variability. Secondly, a large-scale trial increases population growth rate by enhancing self-sustaining feedback, which is generally found in foundation species in stressful environments such as seagrass beds. Thus, by careful site selection and applying appropriate techniques, spreading of risks and enhancing self-sustaining feedback in concert increase success of seagrass restoration. Journal of Applied Ecology

Impacts and effects of ocean warming on tidal marsh and tidal freshwater forest ecosystems - Megonigal, J. P.; Chapman, S.; Crooks, S.; Dijkstra, P.; Kirwan, M.; Langley, A (IUCN GLOBAL MARINE AND POLAR PROGRAMME Explaining Ocean Warming: Causes, scale, effects and consequences, 2016)
The Antarctic marine ecosystem is strongly dependent on the regional circulation and climate of the ocean, and is important because of its role in the global carbon cycle, fisheries, and for the conservation of many of the globe’s iconic marine mammals, penguins and flying seabirds. • The oceans around Antarctica are changing rapidly, with average rates of warming and freshening that greatly exceed the global mean, but with complex regional structure to the changes. • The prognosis for the region is difficult to assess because the coupled climate models of the sort used by the IPCC perform poorly at simulating the Southern Ocean, including the sea ice environment. Nevertheless, the coupled climate models consistently predict a warming of the Southern Ocean in coming decades, along with a freshening of upper-layer water masses, and a shallowing of the surface mixed layers. • The knowledge that is available points to a changing system that will have consequences for species and the ecosystems as a whole, largely resulting in a contraction of this ecosystem to higher latitudes. • Management bodies in the region will need to adapt management practices to a changing future. A critical gap in capability is sustained circumpolar observations needed to assess current and future ecosystem states.

Indonesia’s blue carbon: a globally significant and vulnerable sink for seagrass and mangrove carbon - Alongi, D. M.; Murdiyarso, D.; Fourqurean, J. W.; Kauffman, J. B.; Hutahaean, A.; Crooks, S.; Lovelock, C. E.; Howard, J.; Herr, D.; Fortes, M.; Pidgeon, E.; Wagey, T. (Wetlands Ecology and Management, 2016)
The global significance of carbon storage in Indonesia’s coastal wetlands was assessed based on published and unpublished measurements of the organic carbon content of living seagrass and mangrove biomass and soil pools. For seagrasses, median above- and below-ground biomass was 0.29 and 1.13 Mg C ha−1 respectively; the median soil pool was 118.1 Mg C ha−1. Combining plant biomass and soil, median carbon storage in an Indonesian seagrass meadow is 119.5 Mg C ha−1. Extrapolated to the estimated total seagrass area of 30,000 km2, the national storage value is 368.5 Tg C. For mangroves, median above- and below-ground biomass was 159.1 and 16.7 Mg C ha−1, respectively; the median soil pool was 774.7 Mg C ha−1. The median carbon storage in an Indonesian mangrove forest is 950.5 Mg C ha−1. Extrapolated to the total estimated mangrove area of 31,894 km2, the national storage value is 3.0 Pg C, a likely underestimate if these habitats sequester carbon at soil depths >1 m and/or sequester inorganic carbon. Together, Indonesia’s seagrasses and mangroves conservatively account for 3.4 Pg C, roughly 17 % of the world’s blue carbon reservoir. Continued degradation and destruction of these wetlands has important consequences for CO2 emissions and dissolved carbon exchange with adjacent coastal waters. We estimate that roughly 29,040 Gg CO2 (eq.) is returned annually to the atmosphere–ocean pool. This amount is equivalent to about 3.2 % of Indonesia’s annual emissions associated with forest and peat land conversion. These results highlight the urgent need for blue carbon and REDD+ projects as a means to stem the decline in wetland area and to mitigate the release of a significant fraction of the world’s coastal carbon stores.

Long photoperiods sustain high pH in arctic kelp forests - Krause-Jensen, Dorte; Marbà, Núria; Sanz-Martin, Marina; Hendriks, Iris E.; Thyrring, Jakob; Carstensen, Jacob; Sejr, Mikael Kristian; Duarte, Carlos M. (Science Advances, 2016)
Concern on the impacts of ocean acidification on calcifiers, such as bivalves, sea urchins, and foraminifers, has led to efforts to understand the controls on pH in their habitats, which include kelp forests and seagrass meadows. The metabolism of these habitats can lead to diel fluctuation in pH with increases during the day and declines at night, suggesting no net effect on pH at time scales longer than daily. We examined the capacity of subarctic and Arctic kelps to up-regulate pH in situ and experimentally tested the role of photoperiod in determining the capacity of Arctic macrophytes to up-regulate pH. Field observations at photoperiods of 15 and 24 hours in Greenland combined with experimental manipulations of photoperiod show that photoperiods longer than 21 hours, characteristic of Arctic summers, are conducive to sustained up-regulation of pH by kelp photosynthesis. We report a gradual increase in pH of 0.15 units and a parallel decline in pCO2 of 100 parts per million over a 10-day period in an Arctic kelp forest over midsummer, with ample scope for continued pH increase during the months of continuous daylight. Experimental increase in CO2 concentration further stimulated the capacity of macrophytes to deplete CO2 and increase pH. We conclude that long photoperiods in Arctic summers support sustained up-regulation of pH in kelp forests, with potential benefits for calcifiers, and propose that this mechanism May increase with the projected expansion of Arctic vegetation in response to warming and loss of sea ice.

Mangrove Sedimentation and Response to Relative Sea-Level Rise - Woodroffe, C. D.; Rogers, K.; McKee, K. L.; Lovelock, C. E.; Mendelssohn, I. A.; Saintilan, N. (Annual Review of Marine Science, 2016)
Mangroves occur on upper intertidal shorelines in the tropics and subtropics. Complex hydrodynamic and salinity conditions, related primarily to elevation and hydroperiod, influence mangrove distributions; this review considers how these distributions change over time. Accumulation rates of allochthonous and autochthonous sediment, both inorganic and organic, vary between and within different settings. Abundant terrigenous sediment can form dynamic mudbanks, and tides redistribute sediment, contrasting with mangrove peat in sediment-starved carbonate settings. Sediments underlying mangroves sequester carbon but also contain paleoenvironmental records of adjustments to past sea-level changes. Radiometric dating indicates long-term sedimentation, whereas measurements made using surface elevation tables and marker horizons provide shorter perspectives, indicating shallow subsurface processes of root growth and substrate autocompaction. Many tropical deltas also experience deep subsidence, which augments relative sea-level rise. The persistence of mangroves implies an ability to cope with moderately high rates of relative sea-level rise. However, many human pressures threaten mangroves, resulting in a continuing decline in their extent throughout the tropics.∗

Mapping spatial distribution and biomass of coastal wetland vegetation in Indonesian Papua by combining active and passive remotely sensed data - Aslan, Aslan; Rahman, Abdullah F.; Warren, Matthew W.; Robeson, Scott M. (Remote Sensing of Environment, 2016)
There is ongoing interest to develop remote sensing methods for mapping and monitoring the spatial distribution and biomass of mangroves. In this study, we develop a suite of methods to evaluate the combination of Landsat-8, ALOS PALSAR, and SRTM data for mapping spatial distribution of mangrove composition, canopy height, and aboveground biomass in the wide intertidal zones and coastal plains of Mimika district, Papua, Indonesia. Image segmentation followed by visual interpretation of composite PALSAR images was used to delineate mangrove areas, whereas a flexible statistical rule based classification of spectral signatures from Landsat-8 images was used to classify mangrove associations. The overall accuracy of land cover classification was 94.38% with a kappa coefficient of 0.94 when validated with field inventory data and Google Earth images. Mangrove height and aboveground biomass were mapped using the SRTM DEM, which were calibrated with field-measured data via quantile regression models. There was a strong correlation between the SRTM DEM and the 0.98 quantile of field canopy heights (H.98), which was used to represent the tallest trees in each of 196 10 m radius subplots (r = 0.84 and R2 = 0.804). Model performance was evaluated through 10,000 bootstrapped simulations, producing a mean absolute error (MAE) of 3.0 m for canopy height estimation over 30 m pixels of SRTM data. Quantile regression revealed a relatively strong non-linear relationship between the SRTM derived canopy height model and aboveground biomass measured in 0.5 ha mangrove inventory plots (n = 33, R2 = 0.46). The model results produced estimates of mean standing biomass of 237.52 ± 98.2 Mg/ha in short canopy (Avicennia/Sonneratia) stands to 353.52 ± 98.43 Mg/ha in mature tall canopy (Rhizophora) dominated forest. The model estimates of mangrove biomass were within 90% confidence intervals of area-weighted biomass derived from field measurements. When validated at the landscape scale, the difference between modeled and measured aboveground mangrove biomass was 3.48% with MAE of 105.75 Mg/ha. These results indicate that the approaches developed here are reliable for mapping and monitoring mangrove composition, height, and biomass over large areas of Indonesia.

Policy challenges and approaches for the conservation of mangrove forests in Southeast Asia - Friess, Daniel A.; Thompson, Benjamin S.; Brown, Ben; Amir, A. Aldrie; Cameron, Clint; Koldewey, Heather J.; Sasmito, Sigit D.; Sidik, Frida (Conservation biology : the journal of the Society for Conservation Biology, 2016)
Many drivers of mangrove forest loss operate over large scales and are most effectively addressed by policy interventions. However, conflicting or unclear policy objectives exist at multiple tiers of government, resulting in contradictory management decisions. To address this, we considered four approaches that are being used increasingly or could be deployed in Southeast Asia to ensure sustainable livelihoods and biodiversity conservation. First, a stronger incorporation of mangroves into marine protected areas (that currently focus largely on reefs and fisheries) could resolve some policy conflicts and ensure that mangroves do not fall through a policy gap. Second, examples of community and government comanagement exist, but achieving comanagement at scale will be important in reconciling stakeholders and addressing conflicting policy objectives. Third, private-sector initiatives could protect mangroves through existing and novel mechanisms in degraded areas and areas under future threat. Finally, payments for ecosystem services (PES) hold great promise for mangrove conservation, with carbon PES schemes (known as blue carbon) attracting attention. Although barriers remain to the implementation of PES, the potential to implement them at multiple scales exists. Closing the gap between mangrove conservation policies and action is crucial to the improved protection and management of this imperiled coastal ecosystem and to the livelihoods that depend on them.

Rates and drivers of mangrove deforestation in Southeast Asia, 2000-2012 - Richards, Daniel R.; Friess, Daniel A. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The mangrove forests of Southeast Asia are highly biodiverse and provide multiple ecosystem services upon which millions of people depend. Mangroves enhance fisheries and coastal protection, and store among the highest densities of carbon of any ecosystem globally. Mangrove forests have experienced extensive deforestation owing to global demand for commodities, and previous studies have identified the expansion of aquaculture as largely responsible. The proportional conversion of mangroves to different land use types has not been systematically quantified across Southeast Asia, however, particularly in recent years. In this study we apply a combined geographic information system and remote sensing method to quantify the key proximate drivers (i.e., replacement land uses) of mangrove deforestation in Southeast Asia between 2000 and 2012. Mangrove forests were lost at an average rate of 0.18% per year, which is lower than previously published estimates. In total, more than 100,000 ha of mangroves were removed during the study period, with aquaculture accounting for 30% of this total forest change. The rapid expansion of rice agriculture in Myanmar, and the sustained conversion of mangroves to oil palm plantations in Malaysia and Indonesia, are identified as additional increasing and under-recognized threats to mangrove ecosystems. Our study highlights frontiers of mangrove deforestation in the border states of Myanmar, on Borneo, and in Indonesian Papua. To implement policies that conserve mangrove forests across Southeast Asia, it is essential to consider the national and subnational variation in the land uses that follow deforestation.
Keywords: Aquaculture; Forest loss; Indonesia; Myanmar; Oil palm

Response of seagrass indicators to shifts in environmental stressors: A global review and management synthesis - Roca, G.; Alcoverro, T.; Krause-Jensen, D.; Balsby, T. J.S.; Van Katwijk, M. M.; Marbà, N.; Santos, R.; Arthur, R.; Mascaró, O.; Fernández-Torquemada, Y.; Pérez, M.; Duarte, C. M.; et al. (Ecological Indicators, 2016)
Although seagrass-based indicators are widely used to assess coastal ecosystem status, there is little universality in their application. Matching the plethora of available indicators to specific management objectives requires a detailed knowledge of their species-specific sensitivities and their response time to environmental stressors. We conducted an extensive survey of experimental studies to determine the sensitivity and response time of seagrass indicators to ecosystem degradation and recovery. We identified seagrass size and indicator type (i.e. level of biological organization of the measure) as the main factors affecting indicator sensitivity and response time to degradation and recovery. While structural and demographic parameters (e.g. shoot density, biomass) show a high and unspecific sensitivity, biochemical/physiological indicators present more stressor-specific responses and are the most sensitive detecting early phases of environmental improvement. Based on these results we present a simple decision tree to assist ecosystem managers to match adequate and reliable indicators to specific management goals.

Response of Thalassia Testudinum morphometry and distribution to environmental drivers in a pristine tropical lagoon - Medina-Gómez, Israel; Madden, Christopher J.; Herrera-Silveira, Jorge; Kjerfve, Björn (PLoS ONE, 2016)
This study was undertaken to determine the relationships between the biomass, morphometry, and density of short shoots (SS) of the tropical seagrass Thalassia testudinum and the physical-environmental forcing in the region. Seasonal sampling surveys were undertaken four times in Bahia de la Ascension, a shallow estuary in the western Mexican Caribbean, to measure plant morphology and environmental variables. The estuary has a fresh water-influenced inner bay, a large central basin and a marine zone featuring a barrier reef at the seaward margin. Leaf size was positively correlated with increasing salinity, but total biomass was not, being similar across most of the sites. Aboveground biomass exhibited seasonal differences in dry and rainy seasons along the bay, most markedly in the brackish inner bay where an abrupt decline in biomass coincided with the rainy season. The relationship between nutrients and biomass indicates that the aboveground/belowground biomass ratio increases as nutrient availability increases. Areal cover was inversely correlated with SS density during both dry and rainy seasons. Maximum SS recruitment coincided with the rainy season. Peaks in SS density were recorded in the freshwater-influenced inner bay during an ENSO cold phase in 2007 ("La Niña") which is associated with a wetter dry season and following a strong storm (Hurricane Dean). The onset of the rainy season influences both shoot density and T. testudinum biomass by controlling the freshwater input to the bay and thus, the system's salinity gradient and external nutrients supply from the coastal wetland.

Scaling mangrove aboveground biomass from site-level to continental-scale - Rovai, A.S.; Riul, P.; Twilley, R.R.; Castañeda-Moya, E.; Rivera-Monroy, V.H.; Williams, A.A.; Simard, M.; Cifuentes-Jara, M.; Lewis, R.R.; Crooks, S.; Horta, P.A.; Schaeffer-Novelli, Y.; et al. (Global Ecology and Biogeography, 2016)
Aim: We developed a set of statistical models to improve spatial estimates of mangrove aboveground biomass (AGB) based on the environmental signature hypothesis (ESH). We hypothesized that higher tidal amplitudes, river discharge, temperature, direct rainfall and decreased potential evapotranspiration explain observed high mangrove AGB. Location: Neotropics and a small portion of the Nearctic region. Methods: A universal forest model based on site-level forest structure statistics was validated to spatially interpolate estimates of mangrove biomass at different locations. Linear models were then used to predict mangrove AGB across the Neotropics. Results: The universal forest site-level model was effective in estimating mangrove AGB using pre-existing mangrove forest structure inventories to validate the model. We confirmed our hypothesis that at continental scales higher tidal amplitudes contributed to high forest biomass associated with high temperature and rainfall, and low potential evapotranspiration. Our model explained 20% of the spatial variability in mangrove AGB, with values ranging from 16.6 to 627.0t ha-1 (mean, 88.7t ha-1). Our findings show that mangrove AGB has been overestimated by 25-50% in the Neotropics, underscoring a commensurate bias in current published global estimates using site-level information. Main conclusions: Our analysis show how the ESH significantly explains spatial variability in mangrove AGB at hemispheric scales. This finding is critical to improve and explain site-level estimates of mangrove AGB that are currently used to determine the relative contribution of mangrove wetlands to global carbon budgets. Due to the lack of a conceptual framework explicitly linking environmental drivers and mangrove AGB values during model validation, previous works have significantly overestimated mangrove AGB; our novel approach improved these assessments. In addition, our framework can potentially be applied to other forest-dominated ecosystems by allowing the retrieval of extensive databases at local levels to generate more robust statistical predictive models to estimate continental-scale biomass values.
Keywords: Allometric models; Carbon stock; Climate change; Coastal management policies; Macroecology; Mangrove forest structure; Neotropics

Seagrass growth, reproductive, and morphological plasticity across environmental gradients over a large spatial scale - McDonald, Ashley M.; Prado, Patricia; Heck, Kenneth L.; Fourqurean, James W.; Frankovich, Thomas A.; Dunton, Kenneth H.; Cebrian, Just (Aquatic Botany, 2016)
Phenotypic variability is a valuable adaptive mechanism for seagrass species that exist in a dynamic environment and can lead to significant intraspecific regional distinctions in life history. Research is lacking in studies examining the significance of within-species phenotypic variation in relation to gradients in environmental condition at a large spatial scale. These studies are essential to better understanding the potential for acclimatization and tolerance capabilities of seagrasses in declining coastal environments. Thalassia testudinum (turtlegrass) is a ubiquitous keystone seagrass species across the Caribbean and Gulf of Mexico (GoM) that populates both environmentally dynamic estuaries and stable coastal environments. In order to elucidate environmentally driven distinctions in spatially separated populations, we examined characteristics of shoots exposed to widely separated distinct coastal environments with varying degrees of environmental stability and suitability. In our comparison, three sampling locations vary considerably in ambient water temperature, salinity, and water column clarity along a gradient from oscillating, higher stress conditions to stable, more favorable conditions. Shoots tended to have larger leaves with more biomass in the stable environment and also exhibited an older shoot age structure and higher horizontal expansion rate. However, shoots in the more variable, higher stress environment exhibited greater evidence of flowering and first flowered at an earlier age. The results elucidate large spatially distinct and environmentally relevant differences in morphology, growth, and life history highlighting the need for more studies regarding phenotypic variability of seagrass populations across environmental gradients.

Sedimentary Factors are Key Predictors of Carbon Storage in SE Australian Saltmarshes - Kelleway, Jeffrey J.; Saintilan, Neil; Macreadie, Peter I.; Ralph, Peter J. (Ecosystems, 2016)
Although coastal vegetated ecosystems are widely recognised as important sites of long-term carbon (C) storage, substantial spatial variability exists in quantifications of these ‘blue C’ stocks. To better understand the factors behind this variability we investigate the relative importance of geomorphic and vegetation attributes to variability in the belowground C stocks of saltmarshes in New South Wales (NSW), southeast Australia. Based on the analysis of over 140 sediment cores, we report mean C stocks in the surface metre of sediments (mean ± SE = 164.45 ± 8.74 Mg C ha−1) comparable to global datasets. Depth-integrated stocks (0–100 cm) were more than two times higher in fluvial (226.09 ± 12.37 Mg C ha−1) relative to marine (104.54 ± 7.11) geomorphic sites, but did not vary overall between rush and non-rush vegetation structures. More specifically, sediment grain size was a key predictor of C density, which we attribute to the enhanced C preservation capacity of fine sediments and/or the input of stable allochthonous C to predominantly fine-grained, fluvial sites. Although C density decreased significantly with sediment depth in both geomorphic settings, the importance of deep C varied substantially between study sites. Despite modest spatial coverage, NSW saltmarshes currently hold approximately 1.2 million tonnes of C in the surface metre of sediment, although more C may have been returned to the atmosphere through habitat loss over the past approximately 200 years. Our findings highlight the suitability of using sedimentary classification to predict blue C hotspots for targeted conservation and management activities to reverse this trend.

Sensitivity of the sediment trapping capacity of an estuarine mangrove forest - Willemsen, P. W.J.M.; Horstman, E. M.; Borsje, B. W.; Friess, D. A.; Dohmen-Janssen, C. M. (Geomorphology, 2016)
Intertidal mangrove forests exist in a dynamic coastal environment that is increasingly impacted by human interference, leading to habitat fragmentation, reduced habitat quality and changing hydrodynamic and geomorphological conditions. Biophysical feedback mechanisms are essential to maintain mangrove ecosystems under such changing conditions, for example by facilitating sediment deposition during periods of tidal flooding to allow for long-term coastal accretion. However, human interferences affect these biophysical interactions. This study investigated the consequences of two widespread anthropogenic intervention scenarios on biophysical interactions in mangroves: sediment starvation (reduced sediment supply) and coastal squeeze (limited landward accommodation space). Field observations of hydrodynamics and sediment dynamics were conducted in Mandai mangrove fringing the sheltered northern shore of Singapore. A process-based numerical model (Delft3D) of this field site was set-up, providing accurate approximations of the observed flow velocities and deposition rates. This model was used for a scenario analysis of the initial response of the sediment trapping capacity in the mangrove system to instantaneous changes related to anthropogenic interventions. This analysis showed increased deposition rates in major parts of the mangrove when sediment supplies increased (up to three times more deposition after 1 tide) or when the landward accommodation space of the mangrove was extended (+ 17% deposition). A comparison of the outcomes of these scenarios with the current state of the mangrove underlined a lack of short-term sediment trapping capacity, affecting the (longer-term) adaptive capacity of the system. Thus, at present Mandai mangrove is potentially affected by reduced sediment supply and limited landward accommodation space. Importantly, actions to reduce this anthropogenic influence could enhance mangroves’ sediment trapping capacity, facilitating increased resilience to future projected changes such as sea-level rise. Understanding this influence of anthropogenic interventions on mangrove resilience is essential if we are aiming to maintain coastal ecosystem stability, especially along rapidly changing and urbanizing tropical shorelines.

Simulation of the vegetation state and flow regime interaction in the Macquarie Marshes - Sandi, S. G.; Rodriguez, J. F.; Saco, P. M.; Wen, L.; Saintilan, N. (River Flow - Proceedings of the International Conference on Fluvial Hydraulics, RIVER FLOW 2016, 2016)
The Macquarie Marshes is a complex wetland system located in the lower floodplain of the Macquarie River in semiarid Australia. This paper is focused on the northern end of the Macquarie Marshes, where some areas have undergone a complete succession from permanent and semi-permanent wetland to terrestrial species and dryland. This is mainly due to high regulation of input discharges that have modified the hydraulic regime. Estimating discharges that can guarantee preservation and maintenance of the ecological features of the Macquarie Marshes requires the implementation of models that can predict the state of the vegetation and its response to watering conditions. In this publication we use results from a quasi-2D hydrodynamic model (VMMHH 1.0) in order to assess the implementation of simple deterministic transitional rules for analyzing the interaction between the flow regime and the vegetation over an extended discharge series.

The effects of CO2 and nutrient fertilisation on the growth and temperature response of the mangrove Avicennia germinans - Reef, Ruth; Slot, Martijn; Motro, Uzi; Motro, Michal; Motro, Yoav; Adame, Maria F.; Garcia, Milton; Aranda, Jorge; Lovelock, Catherine E.; Winter, Klaus (Photosynthesis Research, 2016)
In order to understand plant responses to both the widespread phenomenon of increased nutrient inputs to coastal zones and the concurrent rise in atmospheric CO2 concentrations, CO2–nutrient interactions need to be considered. In addition to its potential stimulating effect on photosynthesis and growth, elevated CO2 affects the temperature response of photosynthesis. The scarcity of experiments testing how elevated CO2 affects the temperature response of tropical trees hinders our ability to model future primary productivity. In a glasshouse study, we examined the effects of elevated CO2 (800 ppm) and nutrient availability on seedlings of the widespread mangrove Avicennia germinans. We assessed photosynthetic performance, the temperature response of photosynthesis, seedling growth and biomass allocation. We found large synergistic gains in both growth (42 %) and photosynthesis (115 %) when seedlings grown under elevated CO2 were supplied with elevated nutrient concentrations relative to their ambient growing conditions. Growth was significantly enhanced under elevated CO2 only under high-nutrient conditions, mainly in above-ground tissues. Under low-nutrient conditions and elevated CO2, root volume was more than double that of seedlings grown under ambient CO2 levels. Elevated CO2 significantly increased the temperature optimum for photosynthesis by ca. 4 °C. Rising CO2 concentrations are likely to have a significant positive effect on the growth rate of A. germinans over the next century, especially in areas where nutrient availability is high.

The Mangroves of Ambanja and Ambaro Bays, Northwest Madagascar: Historical Dynamics, Current Status and Deforestation Mitigation Strategy - Jones, Trevor Gareth; Ratsimba, Harifidy Rakoto; Carro, Aude; Ravaoarinorotsihoarana, Lalao; Glass, Leah; Teoh, Marianne; Benson, Lisa; Cripps, Garth; Giri, Chandra; Zafindrasilivonona, Bienvenue; Raherindray, Raymond; Andriamahenina, Zo; et al. (2016)
Madagascar contains Africa’s fourth largest extent of mangroves, representing approxi- mately 2% of the global distribution. Since 1990, more than 20% of Madagascar’s mangrove ecosystems have been heavily degraded or deforested due primarily to increased harvest for charcoal and timber and the expansion of agriculture and aquaculture. Anthropogenic-driven loss is particularly prominent in the north-western Ambanja and Ambaro Bays (AAB). At over 24,000 ha, AAB is one of Madagascar’s largest mangrove ecosystems, including prominent estuaries fed by rivers and streams originating in the country’s highest mountain range. Similar to the national rate, AAB has experienced approximately 20% loss since 1990, driven primarily by over-harvesting for charcoal and timber. Continued loss threatens the livelihoods and wellbeing of thousands of residents who rely on the many goods and services provided by a healthy, relatively intact mangrove ecosystem. To combat this loss, Blue Ventures (BV), in partnership with local communities and the University of Antananarivo, is working to protect, restore and encourage the sustainable use of mangroves. BVs’ Blue Forests project aims to help maintain and diversify local livelihoods and to sustainably manage mangroves and their associated biodiversity in AAB, as well as throughout western Madagascar. This chapter provides an overview of the biophysical characteristics, historic dynamics and current status of the AAB mangrove ecosystem, and mitigation strategies being implemented through BVs’ Blue Forests project.

The Physiology of Mangrove Trees with Changing Climate - Lovelock, Catherine E.; Krauss, Ken W.; Osland, Michael J.; Reef, Ruth; Ball, Marilyn C. (2016)
Mangrove forests grow on saline, permanently or periodically flooded soils of the tropical and subtropical coasts. The tree species that compose the mangrove are halophytes that have suites of traits that confer differing levels of tolerance of salinity, aridity,...

The role of economic, policy, and ecological factors in estimating the value of carbon stocks in Everglades mangrove forests, South Florida, USA - Jerath, Meenakshi; Bhat, Mahadev; Rivera-Monroy, Victor H.; Castañeda-Moya, Edward; Simard, Marc; Twilley, Robert R. (Environmental Science and Policy, 2016)
Old growth mangroves in existing protected areas store more carbon than restored forests or plantations. Carbon storage in such forests has economic value independent of additionality, offering opportunities for policy makers to ensure their maintenance, and inclusion in climate change mitigation strategies. Mangrove forests of the Everglades National Park (ENP), South Florida, though protected, face external stressors such as hydrological alterations because of flooding control structures and agriculture impacts and saltwater intrusion as a result of increasing sea level rise. Moreover, decreased funding of Everglades’ restoration activities following the recent economic crisis (beginning 2008) threatens the restoration of the Greater Everglades including mangrove dominated coastal regions. We evaluate several economic and ecological challenges confronting the economic valuation of total (vegetation plus soil) organic carbon (TOC) storage in the ENP mangroves. Estimated TOC storage for this forested wetland ranges from 70 to 537 Mg C/ha and is higher than values reported for tropical, boreal, and temperate forests. We calculate the average abatement cost of C specific for ENP mangroves to value the TOC from $2–$3.4 billion; estimated unit area values are $13,859/ha–$23,728/ha. The valuation of the stored/legacy carbon is based on the: 1) ecogeomorphic attributes, 2) regional socio-economic milieu, and 3) status of the ENP mangroves as a protected area. The assessment of C storage estimates and its economic value can change public perception about how this regulating ecosystem service of ENP mangrove wetlands (144,447 ha) supports human well-being and numerous economic activities. This perception, in turn, can contribute to future policy changes such that the ENP mangroves, the largest mangrove area in the continental USA, can be included as a potential alternative in climate change mitigation strategies.

The state of legislation and policy protecting Australia's mangrove and salt marsh and their ecosystem services - Rogers, Kerrylee; Boon, Paul I.; Branigan, Simon; Duke, Norman C.; Field, Colin D.; Fitzsimons, James A.; Kirkman, Hugh; Mackenzie, Jock R.; Saintilan, Neil (Marine Policy, 2016)
Saline coastal wetlands, such as mangrove and coastal salt marsh, provide many ecosystem services. In Australia, large areas have been lost since European colonization, particularly as a result of drainage, infilling and flood-mitigation works, often starting in the mid-19th century and aimed primarily towards converting land to agricultural, urban or industrial uses. These threats remain ongoing, and will be exacerbated by rapid population growth and climate change in the 21st century. Establishing the effect of wetland loss on the delivery of ecosystem services is confounded by the absence of a nationally consistent approach to mapping wetlands and defining the boundaries of different types of coastal wetland. In addition, climate change and its projected effect on mangrove and salt marsh distribution and ecosystem services is poorly, if at all, acknowledged in existing legislation and policy. Intensifying climate change means that there is little time to be complacent; indeed, there is an urgent need for proper valuation of ecosystem services and explicit recognition of ecosystem services within policy and legislation. Seven actions are identified that could improve protection of coastal wetlands and the ecosystem services they provide, including benchmarking and improving coastal wetland extent and health, reducing complexity and inconsistency in governance arrangements, and facilitating wetland adaptation and ecosystem service delivery using a range of relevant mechanisms. Actions that build upon the momentum to mitigate climate change by sequestering carbon – ‘blue carbon’ – could achieve multiple desirable objectives, including climate-change mitigation and adaptation, floodplain rehabilitation and habitat protection.

Turning the tide on mangrove loss - Friess, D. A.; Lee, S. Y.; Primavera, J. H. (Marine Pollution Bulletin, 2016)

Vulnerability analysis of mangroves in the west coast of Baja California Sur, México: An Approach to Identify Local Adaptation Measures - Bautista-González, KA.; Cifuentes-Jara, M.; Castillo-López, A. (The arid mangrove forest from Baja California Peninsula volume 2, 2016)
This chapter looks into the vulnerability of mangrove forests and the livelihood analysis conducted in six coastal communities of Baja California Sur (BCS), Mexico. Variables that could affect the distribution and health of mangroves, such as an increase of the sea level or an increase in air or sea surface temperature, are expected under different projections of future climate. People already perceive changes in water and air temperature and the El Niño (ENSO) effect, as well as changes in waves and tides patterns, which coincides with the results of Baja California Sur action plan for climate change (PEACC-BCS 2012). Expected changes in climate would considerably affect the main economic activities in this region such as fishing, aquaculture and tourism, negatively impacting the development of coastal communities. The type and magnitude of the impact will depend on the environmental, social and economic characteristics of each community or region and will influence the degree of disruption to mangrove forests and communities. There are different ways to evaluate vulnerability, based on the biophysical perspective and on the social perspective. This study was made from the social perspective, taking into account the vision of the stakeholders. It is them who make decisions that could help to decrease their vulnerability and strengthen their adaptation capacities. Likewise, we analyzed the adaptive capacity that these communities have and how they are facing these changes. We found that the adaptive capacity of the different communities varied due to the actions they are taking, their level of organization and the diversity of livelihoods. Finally, actions for local adaptation were identified in a participative manner to reduce the vulnerability of mangrove forests and associated livelihoods.

Wetlands exchange — Lessons Learned - Lovelock, Catherine; Sinclair, Zoe; Shribman, Zoë (Commonwealth of Australia, 2016)

An appraisal of Indonesia ’ s immense peat carbon stock using national peatland maps : uncertainties and potential losses from conversion - Warren, Matthew; Hergoualc, Kristell; Kauffman, J Boone; Murdiyarso, Daniel; Kolka, Randall (Carbon Balance and Management, 2017)
Keywords: Tropical peatlands,Wetlands,Climate change mitigat; carbon emissions; carbon pools; climate change mitigation; tropical peatlands; wetlands

Case Study : Coastal blue carbon in climate change mitigation - Wylie, Lindsay; Sutton-Grier, Ariana E.; Moore, Amber; Cai, Wei-Jun; McLeod, Elizabeth; Chmura, Gail L.; Bouillon, Steven; Salm, Rodney; Björk, Mats; Duarte, Carlos M.; Lovelock, Catherine E.; Schlesinger, William H.; et al. (Marine Policy, 2017)
Vegetated coastal habitats, including seagrass and macroalgal beds, mangrove forests and salt-marshes, form highly productive ecosystems, but their contribution to the global carbon budget remains overlooked and these forests remain “hidden” in representations of the global carbon budget. Despite being confined to a narrow belt around the shoreline of the world’s oceans, where they cover less than 7 million km2, vegetated coastal habitats support about 10 % of the global marine net primary production, and generate a large organic carbon surplus, of about 40 % of their NPP, which is either buried in sediments within these habitats or exported away. Large, 10-fold uncertainties in the area covered by vegetated coastal habitats, along with variability about carbon flux estimates, result in a 10-fold bracket around the estimates of their contribution to organic carbon sequestration in sediments and the deep sea from 73 Tg C year−1 to 866 Tg C year−1 , representing up to 1/3 of the biological CO2 removal by marine biota. Up to 1/2 of this carbon sequestration occurs in sink reservoirs (sediments or the deep sea) beyond these habitats. The organic carbon exported that does not reach depositional sites subsidizes the metabolism of heterotrophic organisms. In addition to their significant contribution to organic carbon production and sequestration, vegetated coastal habitats contribute as much to carbonate accumulation as coral reefs do. Whereas globally-relevant, the magnitude of global carbon fluxes supported by salt-marsh, mangrove, seagrass and macroalgal habitats is declining due to rapid habitat loss, contributing to loss of CO2 sequestration, storage capacity and carbon subsidies. Incorporating the carbon fluxes vegetated coastal habitats support into depictions of the carbon budget of the global ocean and its perturbations will improve current representations of the carbon budget of the global ocean.

Coastal Halophytic Vegetation - Keith, D A; Rogers, K; Boon, P; Lovelock, C; Saintilan, N (AUSTRALIAN VEGETATION, 3RD EDITION, 2017)
Coastal halophytes are plants of the coastal zone that are capable of growing and reproducing under saline conditions. Mostly they occur in areas subject to tidal inundation, though may also occur on headlands where salt spray elevates soil salinity. Mangrove and saltmarsh are the primary plant communities occupying the saline intertidal zone of Australia. Mangrove diversity is greatest in the tropics and saltmarsh diversity greatest in temperate zones. Coastal halophytes are most extensive where tidal conditions facilitate the development of a sedimentary substrate for plant establishment and growth. Over time, strong zonation can develop within the tidal frame. Where mangrove and saltmarsh co-occur saltmarsh is typically positioned higher in the tidal frame and thus is subject to less frequent inundation. Seagrass beds often adjoin mangrove in the lower intertidal and sub-tidal zones where environmental conditions are suitable. Mangrove and saltmarsh plants exhibit unique adaptations that enable them to establish and grow within the harsh conditions created by tidal inundation, conditions typified by recurrent waterlogging, elevated salinity and anaerobic substrate. Common adaptations include mechanisms to exclude, extrude or store salt ions, and unique root morphologies that improve stability and create aerated rhizospheres around the roots. Coastal halophyte communities have responded over geological timescales to fluctuating sea levels by shifting their distribution and by accumulating sediments. More recently, coastal halophytes have increasingly succumbed to habitat change and exploitation, both globally and in Australia, with large areas of former mangrove or saltmarsh lost to development. A shift to ecosystem-based management and policy aims to protect increasingly valued ecosystem services provided by coastal halophytes by reversing their loss and degradation. However, losses of coastal halophyte communities are likely to continue in the 21st century due to the effect of climate change on sea-levels, higher air and sea temperatures, and a suite of related impacts on primary productivity. Adaptation to climate change should aim to limit further losses of coastal halophyte vegetation, and urgently improve or restore ecosystem services provided by these highly valuable coastal plant communities.

Colonization and shift of mollusc assemblages as a restoration indicator in planted mangroves in the Philippines - Salmo, Severino G.; Tibbetts, Ian; Duke, Norman C. (Biodiversity and Conservation, 2017)
We compared the mollusc assemblages of planted mono-specific Rhizophora mangroves of known different ages. As forest age increased, there was a shift in species composition, abundance and biomass of mollusc assemblages for all faunal types (infauna, epifauna and arboreal fauna). This shift was correlated with the changes in vegetation (increasing forest cover and above-ground biomass) and sediment characteristics (increasing organic matter and decreasing sand content). Some species dominate in young plantations (<10 years old; Pirenella cingulata) and in intermediate plantations (10–15 years old; Nerita polita), while other species only occur in mature plantations and natural mangrove stands (>15 years; Terebralia sulcata, Nerita planospira). The two former groups of species are mostly species of infaunal and epifaunal habitats, while the latter group is mainly composed of arboreal species. The shift in mollusc species composition and dominance may serve as a useful indicator of restoration patterns in planted mangroves.

Current state of seagrass ecosystem services: Research and policy integration - Ruiz-Frau, A.; Gelcich, S.; Hendriks, I. E.; Duarte, C. M.; Marbà, N. (Ocean and Coastal Management, 2017)
Seagrasses contribute to the maintenance of human wellbeing. However certain aspects of their role as ecosystem service (ES) providers remain understudied. Here, we synthesise the state of seagrass ES (SGES) research and policy implications. Additionally, we recommend ways in which SGES research can be integrated in to policy design, by drawing lessons from the case of Blue Carbon (BC). SGES research suffers from three main biases: a geographical bias, SGES has been restricted to chartered seagrass areas; a type of service research bias, provisioning and regulating services have received extensive attention while cultural services remain understudied; a type of discipline bias, the ecological aspects of SGES have been well documented while economic and social aspects remain in comparison understudied. These are particularly important, as an understanding of the social and economic considerations of the provision of ES is fundamental to facilitate its integration into policy frameworks. Lessons drawn from the operationalization process of BC show the reoccurrence of certain aspects that have enabled the integration of BC into policy. These aspects are grouped under 4 different categories. From the analysis of these elements we draw lessons that could facilitate the operationalization of other ecosystem services and their incorporation into management policy frameworks.

Depth-Related Changes in Reproductive Strategy of a Cold-Temperate Zostera marina Meadow - Olesen, Birgit; Krause-Jensen, Dorte; Christensen, Peter Bondo (Estuaries and Coasts, 2017)
Biomass allocation and demographic characteristics of a Danish Zostera marina population were determined along a depth gradient of light and exposure to evaluate the reproductive strategy for meadow maintenance and recovery. From May to September, biomass, shoot growth and reproductive allocation were measured monthly at three depths (1.8, 4 and 6 m). Also, seedling survival along the deep edge (6.2 m) of the studied meadow was followed over a 12-month period. Shoot density and biomass showed pronounced differences among depths with up to 12-fold lower shoot density and 6-fold lower biomass at deep compared to shallow sites. Comparatively, little variation was found in leaf formation rates and rhizome elongation rates among depths. However, new shoots formed through vegetative reproduction and surviving until September constituted a significantly higher fraction of total shoot density in shallow water (45.7 %) than in deep water (17.3–21.1 %). Conversely, allocation to sexual reproduction was highest at intermediate and high water depths where the proportion of reproductive shoots to total shoot density at time of maximum density was 21.1 and 10.6 %, respectively, and only 3.9 % at the shallow depth. Seed production was also higher at intermediate depth (1970 seeds m−2) than at the upper (1230 seeds m−2) and lower (760 seeds m−2) distribution limit. Seedling recruitment within the meadow took place at all sampling depths but no seedlings persisted throughout the summer period, whereas 8 % of the seedlings established in bare areas along the deep meadow edge (0.43 seedlings m−2) survived their first year. Overall, the results suggest that the shallow edge of the meadow is primarily maintained by vegetative recruitment whereas the deep edge to larger extent relies on sexual recruitment. The intermediate depth zone may act as a buffer zone supporting the maintenance of shallower and deeper eelgrass through seed supply and vegetative expansion, thereby stabilizing the meadow by increasing its resilience towards disturbances and its recovery potential upon disturbances.

Dynamics of carbon sources supporting burial in seagrass sediments under increasing anthropogenic pressure - Mazarrasa, Inés; Marbà, Núria; Garcia-Orellana, Jordi; Masqué, Pere; Arias-Ortiz, Ariane; Duarte, Carlos M. (Limnology and Oceanography, 2017)
Seagrass meadows are strong coastal carbon sinks of autochthonous and allochthonous carbon. The aim of this study was to assess the effect of coastal anthropogenic pressure on the variability of carbon sources in seagrass carbon sinks during the last 150 yr. We did so by examining the composition of the sediment organic carbon (Corg) stocks by measuring the δ13Corg signature and C : N ratio in 210Pb dated sediments of 11 Posidonia oceanica seagrass meadows around the Balearic Islands (Spain, Western Mediterranean) under different levels of human pressure. On average, the top meter sediment carbon deposits were mainly (59% ± 12%) composed by P. oceanica derived carbon whereas seston contribution was generally lower (41% ± 8%). The contribution of P. oceanica to the total sediment carbon stock was the highest (∼ 80%) in the most pristine sites whereas the sestonic contribution was the highest (∼ 40–80%) in the meadows located in areas under moderate to very high human pressure. Furthermore, an increase in the contribution of sestonic carbon and a decrease in that of seagrass derived carbon toward present was observed in most of the meadows examined, coincident with the onset of the tourism industry development and coastal urbanization in the region. Our results demonstrate a general increase of total carbon accumulation rate in P. oceanica sediments during the last century, mainly driven by the increase in sestonic Corg carbon burial, which may have important implications in the long-term carbon sink capacity of the seagrass meadows in the region examined.

Dynamics of sediment carbon stocks across intertidal wetland habitats of Moreton Bay, Australia - Hayes, Matthew A.; Jesse, Amber; Hawke, Bruce; Baldock, Jeff; Tabet, Basam; Lockington, David; Lovelock, Catherine E. (Global Change Biology, 2017)
Coastal wetlands are known for high carbon storage within their sediments, but our understanding of the variation in carbon storage among intertidal habitats, particularly over geomorphological settings and along elevation gradients, is limited. Here, we collected 352 cores from 18 sites across Moreton Bay, Australia. We assessed variation in sediment organic carbon (OC) stocks among different geomorphological settings (wetlands within riverine settings along with those with reduced riverine influence located on tide-dominated sand islands), across elevation gradients, with distance from shore and among habitat and vegetation types. We used mid-infrared (MIR) spectroscopy combined with analytical data and partial least squares regression to quantify the carbon content of ~2500 sediment samples and provide fine-scale spatial coverage of sediment OC stocks to 150 cm depth. We found sites in river deltas had larger OC stocks (175–504 Mg/ha) than those in nonriverine settings (44–271 Mg/ha). Variation in OC stocks among nonriverine sites was high in comparison with riverine and mixed geomorphic settings, with sites closer to riverine outflow from the east and south of Moreton Bay having higher stocks than those located on the sand islands in the northwest of the bay. Sediment OC stocks increased with elevation within nonriverine settings, but not in riverine geomorphic settings. Sediment OC stocks did not differ between mangrove and saltmarsh habitats. OC stocks did, however, differ between dominant species across the research area and within geomorphic settings. At the landscape scale, the coastal wetlands of the South East Queensland catchments (17,792 ha) are comprised of approximately 4,100,000–5,200,000 Mg of sediment OC. Comparatively high variation in OC storage between riverine and nonriverine geomorphic settings indicates that the availability of mineral sediments and terrestrial derived OC may exert a strong influence over OC storage potential across intertidal wetland systems.

Effect of environmental factors (wave exposure and depth) and anthropogenic pressure in the C sink capacity of Posidonia oceanica meadows - Mazarrasa, Inés; Marbà, Núria; Garcia-Orellana, Jordi; Masqué, Pere; Arias-Ortiz, Ariane; Duarte, Carlos M. (Limnology and Oceanography, 2017)
Seagrass are among the most important natural carbon sinks on Earth with Posidonia oceanica (Mediterranean Sea) considered as the most relevant species. Yet, the number of direct measurements of organic carbon burial rates in P. oceanica is still scarce and the effect of local environmental factors remains largely unexplored. In addition, P. oceanica meadows are declining due to the increase in anthropogenic pressure in coastal areas during the last century. The aim of this study is to assess the recent carbon sink capacity of P. oceanica and particularly the effect of human pressure and two environmental factors, water depth and exposure to wave energy (based on a fetch index), on the carbon burial rate since 1900. We conducted an extensive survey of sediment cores in meadows distributed across a gradient of depth, fetch, and human pressure around The Balearic Islands. Sediment and carbon accumulation rates were obtained from 210Pb concentrations profiles. Top-30 centimeters carbon stocks (6.1 ± 1.4 kg C m−2) and burial rates (26 ± 6 g C m−2 yr1) varied up to fivefold across meadows. No significant effect of water depth in carbon burial rates was observed. Although fetch was significantly correlated with sediment mean grain size, confirming the effect of wave exposure in the patterns of sedimentation, fetch alone could not explain the differences in carbon burial rates among the meadows examined. Human pressure affected carbon burial rates, leading to increased rates since the onset of the rise in anthropogenic pressure, particularly so in sheltered meadows supporting high human pressure.

Elevated CO2 and nitrogen addition accelerate net carbon gain in a brackish marsh - Pastore, Melissa A.; Megonigal, J. Patrick; Langley, J. Adam (Biogeochemistry, 2017)
Wetlands have an inordinate influence on the global greenhouse gas budget, but how global changes may alter wetland contribution to future greenhouse gas fluxes is poorly understood. We determined the greenhouse gas balance of a tidal marsh exposed to nine years of experimental carbon dioxide (CO2) and nitrogen (N) manipulation. We estimated net carbon (C) gain rates by measuring changes in plant and soil C pools over nine years. In wetland soils that accrete primarily through organic matter inputs, long-term measurements of soil elevation, along with soil C density, provide a robust estimate of net soil C gain. We used net soil C gain along with methane and nitrous oxide fluxes to determine the radiative forcing of the marsh under elevated CO2 and N addition. Nearly all plots exhibited a net gain of C over the study period (up to 203 g C m−2 year−1), and C gain rates were greater with N and CO2 addition. Treatment effects on C gain and methane emissions dominated trends in radiative forcing while nitrous oxide fluxes in all treatments were negligible. Though these soils experience salinities that typically suppress methane emissions, our results suggest that elevated CO2 can stimulate methane emissions, overcoming positive effects of elevated CO2 on C gain, converting brackish marshes that are typically net greenhouse gas sinks into sources. Adding resources, either CO2 or N, will likely increase “blue carbon” accumulation rates in tidal marshes, but importantly, each resource can have distinct influences on the direction of total greenhouse forcing.

Elevated CO2 and nitrogen addition affect the microbial abundance but not the community structure in salt marsh ecosystem - Lee, Seung Hoon; Megonigal, Patrick J.; Langley, Adam J.; Kang, Hojeong (Applied Soil Ecology, 2017)
With unique and important characteristics, salt marsh ecosystems are expected to be affected by elevated CO2 and N enrichment. Although various studies have assessed the effects of those changes on the vegetation of salt marshes, little information is available about their impact on microbes. In this study, we comprehensively analyzed the microbial community structure of soils responding to elevated CO2 (eCO2) and N addition (N) over 3 years in salt marsh ecosystem. We employed pyrosequencing, T-RFLP analysis, and quantitative PCR to study the bacterial, archaeal, and fungal communities. The overall results indicated that 1) eCO2 and N affected the microbial abundance but not community structure significantly in salt marsh system, 2) due to their different ecophysiology, the responses of the three different microbial communities to eCO2 and/or N addition varied with each group, 3) the composition (C3/C4 or diversity) of the plant community was important in structuring the microbial community of salt marsh ecosystems, which generally have low plant diversity, 4) the archaeal and fungal communities responded more strongly to eCO2 and/or N addition than the bacterial community. This study represents the first comprehensive report of the effects of eCO2 and/or N addition on the diverse microbial community structures of tidal marsh systems. It suggests that single or combined effect of eCO2 and N on microbial abundance in salt marsh was obvious, and that the key groups playing an important role in the biogeochemical process can be shifted.

Estimation and mapping of above-ground biomass of mangrove forests and their replacement land uses in the Philippines using Sentinel imagery - Castillo, Jose Alan A.; Apan, Armando A.; Maraseni, Tek N.; Salmo, Severino G. (ISPRS Journal of Photogrammetry and Remote Sensing, 2017)
The recent launch of the Sentinel-1 (SAR) and Sentinel-2 (multispectral) missions offers a new opportunity for land-based biomass mapping and monitoring especially in the tropics where deforestation is highest. Yet, unlike in agriculture and inland land uses, the use of Sentinel imagery has not been evaluated for biomass retrieval in mangrove forest and the non-forest land uses that replaced mangroves. In this study, we evaluated the ability of Sentinel imagery for the retrieval and predictive mapping of above-ground biomass of mangroves and their replacement land uses. We used Sentinel SAR and multispectral imagery to develop biomass prediction models through the conventional linear regression and novel Machine Learning algorithms. We developed models each from SAR raw polarisation backscatter data, multispectral bands, vegetation indices, and canopy biophysical variables. The results show that the model based on biophysical variable Leaf Area Index (LAI) derived from Sentinel-2 was more accurate in predicting the overall above-ground biomass. In contrast, the model which utilised optical bands had the lowest accuracy. However, the SAR-based model was more accurate in predicting the biomass in the usually deficient to low vegetation cover non-forest replacement land uses such as abandoned aquaculture pond, cleared mangrove and abandoned salt pond. These models had 0.82–0.83 correlation/agreement of observed and predicted value, and root mean square error of 27.8–28.5 Mg ha−1. Among the Sentinel-2 multispectral bands, the red and red edge bands (bands 4, 5 and 7), combined with elevation data, were the best variable set combination for biomass prediction. The red edge-based Inverted Red-Edge Chlorophyll Index had the highest prediction accuracy among the vegetation indices. Overall, Sentinel-1 SAR and Sentinel-2 multispectral imagery can provide satisfactory results in the retrieval and predictive mapping of the above-ground biomass of mangroves and the replacement non-forest land uses, especially with the inclusion of elevation data. The study demonstrates encouraging results in biomass mapping of mangroves and other coastal land uses in the tropics using the freely accessible and relatively high-resolution Sentinel imagery.

Export from seagrass meadows contributes to marine carbon sequestration - Duarte, Carlos M.; Krause-Jensen, Dorte (Frontiers in Marine Science, 2017)
Seagrasses export a substantial portion of their primary production, both in particulate and dissolved organic form, but the fate of this export production remains unaccounted for in terms of seagrass carbon sequestration. Here we review available evidence on the fate of seagrass carbon export to conclude that this represents a significant contribution to carbon sequestration, both in sediments outside seagrass meadows and in the deep sea. The evidence presented implies that the contribution of seagrass meadows to carbon sequestration has been underestimated by only including carbon burial within seagrass sediments.

Growth performance and structure of a mangrove afforestation project on a former seagrass bed, Mindanao Island, Philippines - Sharma, Sahadev; Nadaoka, Kazuo; Nakaoka, Masahiro; Uy, Wilfredo H.; MacKenzie, Richard A.; Friess, Daniel A.; Fortes, Miguel D. (Hydrobiologia, 2017)
The Philippines has lost nearly 70% of its natural mangrove cover since the early 1900s. As a result, large investments have been made to restore mangrove forests and the many ecosystem services that they provide. Most of these restoration efforts have been through outplanting of Rhizophora sp. seedlings, many of which have failed because the proper hydrological and ecological conditions were not properly assessed. Other afforestation projects involved planting seedlings in inappropriate places (e.g., seagrass beds, mudflats) that resulted in replacing one valuable ecosystem with another. The aim of this research was to investigate the growth of 3-, 9-, and 21-year-old afforested stands of Rhizophora spp. mangrove forest. We also investigated the impact of these plantations on local seagrass beds. The total aboveground biomass was 42.6, 74.4, and 111.7 Mg ha−1 for the 3-, 9-, and 21-year-old mangrove stands, respectively. Seagrass bed cover decreased under the closed canopy of the mangrove due to reduced photosynthetically active radiation and competition for growing space. This study shows that mangroves can grow to some extent on seagrass beds, though mangrove planting in these areas could eventually lead to seagrass loss. Thus, mangroves should not be planted in areas that are naturally occupied by other ecologically important ecosystems. The purpose of mangrove restoration should be clear and efforts should be focused on formerly deforested or degraded areas. Additional studies are needed from different locations to understand how mangrove planting in seagrass beds impacts growth performance and ecological functions of the latter ecosystem.

Habitat fragmentation has some impacts on aspects of ecosystem functioning in a sub-tropical seagrass bed - Sweatman, Jennifer L.; Layman, Craig A.; Fourqurean, James W. (Marine Environmental Research, 2017)
Habitat fragmentation impacts ecosystem functioning in many ways, including reducing the availability of suitable habitat for animals and altering resource dynamics. Fragmentation in seagrass ecosystems caused by propeller scarring is a major source of habitat loss, but little is known about how scars impact ecosystem functioning. Propeller scars were simulated in seagrass beds of Abaco, Bahamas, to explore potential impacts. To determine if plant-herbivore interactions were altered by fragmentation, amphipod grazers were excluded from half the experimental plots, and epiphyte biomass and community composition were compared between grazer control and exclusion plots. We found a shift from light limitation to phosphorus limitation at seagrass patch edges. Fragmentation did not impact top-down control on epiphyte biomass or community composition, despite reduced amphipod density in fragmented habitats. Seagrass and amphipod responses to propeller scarring suggest that severely scarred seagrass beds could be subject to changes in internal nutrient stores and amphipod distribution.

Hydraulic conductivity and xylem structure of partially buried mangrove tree species - Okello, Judith Auma; Schmitz, Nele; Beeckman, Hans; Dahdouh-Guebas, Farid; Kairo, James G.; Koedam, Nico; Robert, Elisabeth M.R. (Plant and Soil, 2017)
Aims: Natural sedimentation rates may not affect mangrove trees adversely, but large and sometimes episodic delivery of sediment may result in decreased growth, dieback or mortality. In this study, we aim to assess the effects of different levels of partial sediment burial on mangrove tree structure and function. Methods: Trees of Avicennia marina, Ceriops tagal and Rhizophora mucronata were experimentally buried with terrestrial sediment to simulate different sedimentation levels (15, 30 and 45 cm). After 14 months, branch hydraulic conductivity, xylem structure and stomatal properties were assessed. Results: Sedimentation resulted in general increase in hydraulic conductivity following intermediate levels of burial. The process is also associated with varied anatomical modification in vessel grouping, vessel lumen size and potential conductive area in the three investigated mangrove tree species. Additionally, stomatal adjustment was observed in C. tagal with up to 37% reduction of total stomata area in leaves of buried trees. Conclusions: Although sedimentation may stimulate modification in vessel and stomatal properties of buried mangrove trees after a relatively short period of exposure, these traits may not necessarily be important in ensuring hydraulic conductivity which either increases or remains the same as in control following burial.

Impact of pollution on the feeding, bioturbation and biomass of Uca annulipes in Gazi and Mikindani mangroves, Kenya - Owuor, Margaret Awuor; Aloo-Obudho, Peninna; Cannicci, Stefano; Gitundu, James Kairo (Ocean Life, 2017)
Owuor MA, Aloo-Obudho P, Cannicci S, Gitundu JK. 2017. Impact of pollution on the feeding, bioturbation and biomass of Uca annulipes in Gazi and Mikindani mangroves, Kenya. Ocean Life 1: 61-68. Marine pollution is one of the main anthropogenic factors globally recognized that affect the estuarine and coastal ecosystems. Mangroves received the pollutant since they are intercepting between land and ocean. Despite the utilization of natural mangrove as pollution buffers, how these pollutants might impact the biodiversity of the ecosystems remains a great question. Here, we aimed at determining the impact of pollution on the feeding, bioturbation, and biomass of the fiddler crab Uca annulipes in two regions, Gazi and Mikindani, all along the Kenya Coast. The mangroves in Mikindani on Tudor creek represented peri-urban mangroves that are heavily impacted by municipal wastewater. Meanwhile, the mangroves in Gazi Bay in the South Coast of Kenya served mangroves not affected by direct sewage input. Furthermore, Crabs U. annulipes are one of the most important groups of mangrove epifauna. We adopted a stratified nested design to investigate the impacts of pollution on the feeding, bioturbation, and biomass of U. annulipes. We applied a layered random sampling approach at each site that spanned in 2 × 2 m 2 quadrats in desert and Avicennia zones during July, August and October 2005. The data collection depended on each full moon springs and new moon springs. Different parameters were measured, chlorophyll a (Chl a) concentrations in the feeding pellets and unprocessed soils, amount of bioturbated clays (expressed as dry weight of excavated material and feeding pellets), and biomass (dry weight) of U. annulipes. Four-factor Analysis of Variance (ANOVA) tests were applied to determine whether there was a significant difference in feeding, bioturbation, and biomass of U. annulipes within the two sites. Our findings show substantial differences in chlorophyll a concentration in the feeding pellets in the Avicennia zone of the peri-urban mangroves. Moreover chlorophyll a level did not vary between the processed and unprocessed soils in the Avicennia zone. In Gazi, a significant difference in the bioturbated material was recorded compared to Mikindani. The results demonstrate a consistent increase in crab biomass at the peri-urban site, then the non-urban mangroves. The Avicennia zone of the suburban location had a higher U. annulipes biomass compared to the non-urban Gazi. There was no association between the mass of bioturbated material and Uca biomass. The results also show that the amount of excavated material did not relate to the Uca biomass.

Interactive effects of climate and nutrient enrichment on patterns of herbivory by different feeding guilds in mangrove forests - Feller, Ilka C.; Ball, Marilyn C.; Ellis, Joanne I.; Lovelock, Catherine E.; Reef, Ruth (Global Ecology and Biogeography, 2017)
Aim: Global warming and eutrophication are major threats to coastal environments worldwide. As a result of differences between temperate and tropical ecosystems in nutrient availability, nitrogen (N):phosphorus (P) coupling and carbon retention, primary productivity and biotic interactions in the tropics are predicted to have stronger responses to increased nutrients than in temperate ecosystems. Habitats that occur across broad climatic ranges, such as mangrove forests, provide an opportunity to test this hypothesis by investigating the responses of herbivores to nutrient enrichment in temperate versus tropical latitudes on the same species. Location: Australia and New Zealand. Time period: Fertilization experiments were established at Port Douglas and Cape Cleveland in October 2000; Batemans Bay and Waikopua in August 2001; Whangapoua in January 2003; Tinchi Tamba in September 2005; and Garalia in October 2007. Herbivory was measured in 2009. Major taxa studied: Insect leaf miners; insect and fungal leaf gallers. Methods: We used seven fertilization experiments in Australia and New Zealand across 20° of latitude to determine how increased nutrients affected herbivory and diversity of leaf miners and gallers of the mangrove Avicennia marina. Individual trees were fertilized annually with one of three treatments (Control, +N, +P); herbivory was measured in 2009. Results: Fertilization did not significantly affect herbivory or herbivore diversity. Leaf N:P, latitude and rainfall contributed significantly to herbivory, accounting for > 56% of the variation. Latitude, temperature, %P and salinity differentiated herbivory by feeding guild in the tropical versus subtropical and temperate latitudes. The effect of N fertilization on folivory differed across climatic regions; relative to Control trees, N-fertilized trees in temperate areas had greater folivory than in tropical and subtropical latitudes. Species richness for leaf miners and gallers was correlated with latitude, with more species in subtropical and tropical latitudes than in temperate latitudes. The abundance of galls and mines differed by location, but differences were not correlated with latitude. Main conclusions: Results indicate that latitude and nutrients may have had an interactive effect on herbivory and herbivore diversity of A. marina. However, the strength of the interactions varied by climatic region and was not the same for all groups of herbivores.

Involvement, knowledge and perception in a natural reserve under participatory management: Mida Creek, Kenya - Frank, Céline; Kairo, James G.; Bosire, Jared O.; Mohamed, Mohamed O.S.; Dahdouh-Guebas, Farid; Koedam, Nico (Ocean and Coastal Management, 2017)
Participatory forest management (PFM), as opposed to top down state management, is part of the decentralization process that has occurred in Africa over the past few decades. In Kenya, the process is still at its dawn with enforcing laws dating from 2005 and many pilot projects now in course. Little feedback has been given so far. This case study evaluates, for the first time, participatory management of a Kenyan protected mangrove forest. PFM, coupled with a status of protection, is believed to be an efficient way to preserve the threatened mangrove forests. Semi-structured interviews with local community members (people living within or next to the forest) and key-informants (people working in the forest management) were performed in order to measure three major components of participatory management: Knowledge, involvement, and perception of local communities. Those interviews revealed a partial and overall low involvement of local communities in the formal participatory management structure. Knowledge of the policy concerning mangrove forest management was higher for the people having a job related to natural resources from the forest (e.g. fishing or tour guiding) and for people holding at least a primary level education. The former group was also more involved in the management process. Villagers who were better informed about PFM approaches were also generally more involved in the management. Perceptions of PFM were contrasted and many criticisms were revealed at this early stage of implementation. These results are believed to evolve positively as the government regains trust among local communities who are given more power and wardenship on the forest.

J.G. Watson, Inundation Classes, and their Influence on Paradigms in Mangrove Forest Ecology - Friess, D. A. (Wetlands, 2017)
The influence of tidal inundation on mangrove vegetation species distribution is a key concept in mangrove ecology, and is especially important when considering the vulnerability of mangroves to predicted future sea level rise. While the tidal inundation-vegetation relationship defines a huge number of studies in mangrove science, it is not a new concept, but was mapped in the 1920s by scientists such as James Gilbert Watson, a forester with the colonial Forestry Department in Malaysia. Watson is particularly famous for his description of “Inundation Classes”, which described the flooding frequency at which different mangrove vegetation species could be found. It is interesting to consider how current paradigms and management practices (e.g. mangrove restoration) are shaped by the historical research that contributed to them. This article introduces JG Watson as a key figure in mangrove ecology, describes his seminal work on mangrove species distribution in peninsular Malaysia, and charts his legacy and contribution to current scientific debates surrounding physical controls on mangrove ecology. Importantly, research on tidal inundation and species distribution by Watson and others must be used correctly, including an acknowledgement that vegetation-inundation linkages are not universally applicable, and that species distribution is multi-factorial, and not dependent on inundation alone.

Limits on carbon sequestration in arid blue carbon ecosystems - Schile, Lisa M.; Kauffman, J. Boone; Crooks, Stephen; Fourqurean, James W.; Glavan, Jane; Megonigal, J. Patrick (Ecological Applications, 2017)
Coastal ecosystems produce and sequester significant amounts of carbon ("blue carbon"), which has been well documented in humid and semi-humid regions of temperate and tropical climates but less so in arid regions where mangroves, marshes, and seagrasses exist near the limit of their tolerance for extreme temperature and salinity. To better understand these unique systems, we measured whole-ecosystem carbon stocks in 58 sites across the United Arab Emirates (UAE) in natural and planted mangroves, salt marshes, seagrass beds, microbial mats, and coastal sabkha (inter- and supratidal unvegetated salt flats). Natural mangroves held significantly more carbon in above- and belowground biomass than other vegetated ecosystems. Planted mangrove carbon stocks increased with age, but there were large differences for sites of similar age. Soil carbon varied widely across sites (2-367 Mg C/ha), with ecosystem averages that ranged from 49 to 156 Mg C/ha. For the first time, microbial mats were documented to contain soil carbon pools comparable to vascular plant-dominated ecosystems, and could arguably be recognized as a unique blue carbon ecosystem. Total ecosystem carbon stocks ranged widely from 2 to 515 Mg C/ha (seagrass bed and mangrove, respectively). Seagrass beds had the lowest carbon stock per unit area, but the largest stock per total area due to their large spatial coverage. Compared to similar ecosystems globally, mangroves and marshes in the UAE have lower plant and soil carbon stocks; however, the difference in soil stocks is far larger than with plant stocks. This incongruent difference between stocks is likely due to poor carbon preservation under conditions of weakly reduced soils (200-350 mV), coarse-grained sediments, and active shoreline migration. This work represents the first attempt to produce a country-wide coastal ecosystem carbon accounting using a uniform sampling protocol, and was motivated by specific policy goals identified by the Abu Dhabi Global Environmental Data Initiative. These carbon stock data supported two objectives: to quantify carbon stocks and infer sequestration capacity in arid blue carbon ecosystems, and to explore the potential to incorporate blue carbon science into national reporting and planning documents.

Long-term patterns of eelgrass (Zostera marina) occurrence and associated herbivorous waterbirds in a danish coastal inlet - Balsby, Thorsten J.S.; Clausen, Preben; Krause-Jensen, Dorte; Carstensen, Jacob; Madsen, Jesper (Frontiers in Marine Science, 2017)
Seagrasses in coastal areas have substantial importance for the marine environment and also serve as food for herbivorous waterbirds. We investigated potential relationships between the autumn population of herbivorous waterbirds and eelgrass (Zostera marina) abundance in the EU protected area, Nibe-Gjøl Bredning, a broad of the Limfjorden estuarine complex in Denmark. This is an important site for migratory herbivorous waterbirds such as mute swan (Cygnus olor), coot (Fulica atra), brent goose (Branta bernicla), and wigeon (Anas penelope). We explored long-term (27 years) changes in eelgrass and bird-populations and relationships between eelgrass- and bird abundance. We applied trend- and correlative analyses of yearly monitoring data on eelgrass and waterbirds between 1989 and 2015 coupled with estimates of the potential grazing pressure exerted by the birds. Around 1990 eelgrass was abundant in this area covering more than 40 km2, but eelgrass coverage and biomass declined drastically around 1995 and remained low until 2011 when natural recolonization accelerated and by 2015 had restored the lost meadows. The number of herbivorous waterbirds also fluctuated substantially during the monitoring period with large abundance until the mid-end 1990s followed by reduced abundance in the 2000s and recovery after 2010. The number of bird-days showed a positive relationship with the same year's eelgrass abundance in the 1-2 m depth stratum. For the 0-1 m depth stratum, where the eelgrass meadows are most exposed to bird grazing but also to physical control from e.g., wind and ice, only a particularly detailed eelgrass data set available for a subset of the study period, showed a significant relationship with bird grazing. The potential waterbird consumption of eelgrass, estimated by multiplying average intake rate and number of bird-days for each species, ranged from less than 16% of the eelgrass biomass in most years to more than 40% of the eelgrass biomass in years with extremely sparse eelgrass populations. Hence, the study suggests that dense eelgrass populations stimulate herbivorous waterbirds whereas top-down control is only likely when abundant bird populations graze on sparse eelgrass populations.

Mangrove carbon stocks and ecosystem cover dynamics in southwest Madagascar and the implications for local management - Benson, Lisa; Glass, Leah; Jones, Trevor Gareth; Ravaoarinorotsihoarana, Lalao; Rakotomahazo, Cicelin (Forests, 2017)
Of the numerous ecosystem services mangroves provide, carbon storage is gaining particular attention for its potential role in climate change mitigation strategies. Madagascar contains 2% of the world's mangroves, over 20% of which is estimated to have been deforested through charcoal production, timber extraction and agricultural development. This study presents a carbon stock assessment of the mangroves in Helodrano Fagnemotse in southwest Madagascar alongside an analysis of mangrove land-cover change from 2002 to 2014. Similar to other mangrove ecosystems in East Africa, higher stature, closed-canopy mangroves in southwest Madagascar were estimated to contain 454.92 (±26.58) Mg·C·ha-1. Although the mangrove extent in this area is relatively small (1500 ha), these mangroves are of critical importance to local communities and anthropogenic pressures on coastal resources in the area are increasing. This was evident in both field observations and remote sensing analysis, which indicated an overall net loss of 3.18% between 2002 and 2014. Further dynamics analysis highlighted widespread transitions of dense, higher stature mangroves to more sparse mangrove areas indicating extensive degradation. Harnessing the value that the carbon stored within these mangroves holds on the voluntary carbon market could generate revenue to support and incentivise locally-led sustainable mangrove management, improve livelihoods and alleviate anthropogenic pressures.

Mangrove root biomass and the uncertainty of belowground carbon estimations - Adame, M. Fernanda; Cherian, Sam; Reef, Ruth; Stewart-Koster, Ben (Forest Ecology and Management, 2017)
Mangroves sequester large amounts of carbon (C) and they are increasingly recognized for their potential role in climate change mitigation programs. However, there is uncertainty in the C content of many mangrove forests because the amount of C stored in the roots is usually estimated from allometric equations and not from direct field measurements. There are only a handful of allometric equations in mangroves that are used worldwide to estimate root biomass, however, root biomass can vary from the allometric relationship if the environmental conditions are different from those where the equation was developed. In this study, we compiled recent information on how mangrove roots are affected by environmental conditions. Then, we explored the effect of sampling methodology on root biomass estimations. Finally, we compared published values of root biomass from field measurements against our estimations from allometric equations. The goal was to calculate the uncertainty associated with the estimation of root biomass and thus, the belowground C content of mangroves. The results showed that sampling methodology has a significant effect on root biomass estimations. The highest biomass estimations are reported where both live and dead roots are measured and when the roots are sampled by digging trenches. When comparing measured values against estimations from allometric equations, on average the general allometric equation provided root biomass values that were 40 ± 12% larger than those obtained from field measurements with cores. The result suggests that either: (a) sampling with cores largely underestimates root biomass, or (b) allometric equations overestimate root biomass when used outside the region where they were developed. The uncertainty in root biomass estimates from allometric equations corresponds to 4–15% of the ecosystem C stock (trees + soil), with higher uncertainties in forests with low tree density and low interstitial salinity. We provide a statistical model that includes salinity, forest density and root biomass to correct for this systematic bias. The estimated uncertainty is important to consider when quantifying C budgets at large spatial scales and to validate methodological approaches to C stock estimations.

Measuring the role of seagrasses in regulating sediment surface elevation - Potouroglou, Maria; Bull, James C.; Krauss, Ken W.; Kennedy, Hilary A.; Fusi, Marco; Daffonchio, Daniele; Mangora, Mwita M.; Githaiga, Michael N.; Diele, Karen; Huxham, Mark (Scientific Reports, 2017)
Seagrass meadows provide numerous ecosystem services and their rapid global loss may reduce human welfare as well as ecological integrity. In common with the other 'blue carbon' habitats (mangroves and tidal marshes) seagrasses are thought to provide coastal defence and encourage sediment stabilisation and surface elevation. A sophisticated understanding of sediment elevation dynamics in mangroves and tidal marshes has been gained by monitoring a wide range of different sites, located in varying hydrogeomorphological conditions over long periods. In contrast, similar evidence for seagrasses is sparse; the present study is a contribution towards filling this gap. Surface elevation change pins were deployed in four locations, Scotland, Kenya, Tanzania and Saudi Arabia, in both seagrass and unvegetated control plots in the low intertidal and shallow subtidal zone. The presence of seagrass had a highly significant, positive impact on surface elevation at all sites. Combined data from the current work and the literature show an average difference of 31 mm per year in elevation rates between vegetated and unvegetated areas, which emphasizes the important contribution of seagrass in facilitating sediment surface elevation and reducing erosion. This paper presents the first multi-site study for sediment surface elevation in seagrasses in different settings and species.

Methane fluxes from tropical coastal lagoons surrounded by mangroves, Yucatán, Mexico - Chuang, P. C.; Young, M. B.; Dale, A. W.; Miller, L. G.; Herrera-Silveira, J. A.; Paytan, A. (Journal of Geophysical Research: Biogeosciences, 2017)
Methane concentrations in the water column and emissions to the atmosphere were determined for three tropical coastal lagoons surrounded by mangrove forests on the Yucatán Peninsula, Mexico. Surface water dissolved methane was sampled at different seasons over a period of 2 years in areas representing a wide range of salinities and anthropogenic impacts. The highest surface water methane concentrations (up to 8378 nM) were measured in a polluted canal associated with Terminos Lagoon. In Chelem Lagoon, methane concentrations were typically lower, except in the polluted harbor area (1796 nM). In the relatively pristine Celestún Lagoon, surface water methane concentrations ranged from 41 to 2551 nM. Methane concentrations were negatively correlated with salinity in Celestún, while in Chelem and Terminos high methane concentrations were associated with areas of known pollution inputs, irrespective of salinity. The diffusive methane flux from surface lagoon water to the atmosphere ranged from 0.0023 to 15 mmol CH4 m−2 d−1. Flux chamber measurements revealed that direct methane release as ebullition was up to 3 orders of magnitude greater than measured diffusive flux. Coastal mangrove lagoons may therefore be an important natural source of methane to the atmosphere despite their relatively high salinity. Pollution inputs are likely to substantially enhance this flux. Additional statistically rigorous data collected globally are needed to better consider methane fluxes from mangrove-surrounded coastal areas in response to sea level changes and anthropogenic pollution in order to refine projections of future atmospheric methane budgets.

Modeled CO2 emissions from coastal wetland transitions to other land uses: Tidal marshes, mangrove forests, and seagrass beds - Lovelock, Catherine E.; Fourqurean, James W.; Morris, James T. (Frontiers in Marine Science, 2017)
The sediments of coastal wetlands contain large stores of carbon which are vulnerable to oxidation once disturbed, resulting in high levels of CO2 emissions that may be avoided if coastal ecosystems are conserved or restored. We used a simple model to estimate CO2 emissions from mangrove forests, seagrass beds, and tidal marshes based on known decomposition rates for organic matter in these ecosystems under either oxic or anoxic conditions combined with assumptions of the proportion of sediment carbon being deposited in either oxic or anoxic environments following a disturbance of the habitat. Our model found that over 40 years after disturbance the cumulative CO2 emitted from tidal marshes, mangrove forests, and seagrass beds were ~70-80% of the initial carbon stocks in the top meter of the sediment. Comparison of our estimates of CO2 emissions with empirical studies suggests that (1) assuming 50% of organic material moves to an oxic environment after disturbance gives rise to estimates that are similar to CO2 emissions reported for tidal marshes; (2) field measurements of CO2 emissions in disturbed mangrove forests were generally higher than our modeled emissions that assumed 50% of organic matter was deposited in oxic conditions, suggesting higher proportions of organic matter may be exposed to oxic conditions after disturbance in mangrove ecosystems; and (3) the generally low observed rates of CO2 emissions from disturbed seagrasses compared to our estimates, assuming removal of 50% of the organic matter to oxic environments, suggests that lower proportions may be exposed to oxic conditions in seagrass ecosystems. There are significant gaps in our knowledge of the fate of wetland sediment carbon in the marine environment after disturbance. Greater knowledge of the distribution, form, decomposition, and emission rates of wetland sediment carbon after disturbance would help to improve models.

Partitioning the relative contributions of organic matter and mineral sediment to accretion rates in carbonate platform mangrove soils - Breithaupt, Joshua L.; Smoak, Joseph M.; Rivera-Monroy, Victor H.; Castañeda-Moya, Edward; Moyer, Ryan P.; Simard, Marc; Sanders, Christian J. (Marine Geology, 2017)
In coming decades, the global rate of sea-level rise (SLR) is projected to accelerate beyond rates observed over the past several millennia when mangrove wetlands have expanded in tropical, sub-tropical and temperate regions. There is substantial uncertainty about how distinct mangrove ecotypes inhabiting a wide range of geomorphic settings will respond to SLR acceleration, including the thresholds at which they will submerge permanently. In this study, the relative contributions of soil organic and inorganic matter (SOM and SIM) to 210Pb-derived accretion rates were examined at 23 mangrove sites in southwest Florida, USA and the Yucatan Peninsula in Mexico. These sites are situated atop carbonate platforms where there is wide variation in the availability of SIM (generally marine marl). To account for this variability, research sites were classified by SIM presence based on the SOM content (%) estimated using loss-on-ignition: organic sites (SOM > 70%), intermediate sites (SOM = 40–70%) and mineral sites (SOM < 40%). SOM accumulation rates were largely the same in the three soil classes during the past century (p < 0.05); however, SIM accumulation rates in the intermediate and mineral sites were approximately 5 and 20 times greater, respectively, than rates in the organic sites. Despite this substantial difference in total mass accumulation rates, accretion rates were not statistically different between soil classes (p < 0.05). Our analysis revealed that the rate of SOM accumulation is the best predictor of accretion rates, while the rate of SIM accumulation primarily predicts soil dry bulk density. These findings indicate that SOM and SIM do not contribute additively to soil volume. This is contrary to findings from North American coastal wetlands broadly, suggesting a unique characteristic of carbonate platform mangrove soils that lack a regular, substantive supply of terrigenous SIM. Overall, accretion rates in the FL sites and a Yucatan site on the Caribbean Sea are maintaining pace with regional rates of SLR over the past 100-year and 50-year timespans, whereas the sites in Celestun Lagoon, MX (located on the Gulf of Mexico) exhibit an accretion deficit. Estimates of regional SLR rates range from 4.6 to 12.2 mm yr− 1 by the year 2060. Based on accretion rates observed in the past century, some of these sites may be able to keep pace with the lower SLR estimate, but there is no evidence that any of these sites can match the higher rate.

Sediment and carbon deposition vary among vegetation assemblages in a coastal salt marsh - Kelleway, Jeffrey J.; Saintilan, Neil; Macreadie, Peter I.; Baldock, Jeffrey A.; Ralph, Peter J. (Biogeosciences, 2017)
Coastal salt marshes are dynamic, intertidal ecosystems that are increasingly being recognised for their contributions to ecosystem services, including carbon (C) accumulation and storage. The survival of salt marshes and their capacity to store C under rising sea levels, however, is partially reliant upon sedimentation rates and influenced by a combination of physical and biological factors. In this study, we use several complementary methods to assess short-term (days) deposition and medium-term (months) accretion dynamics within a single marsh that contains three salt marsh vegetation types common throughout southeastern (SE) Australia. br br We found that surface accretion varies among vegetation assemblages, with medium-term (19 months) bulk accretion rates in the upper marsh rush (Juncus) assemblage (1.74g ±g 0.13g mmg yrg '1) consistently in excess of estimated local sea-level rise (1.15g mmg yrg '1). Accretion rates were lower and less consistent in both the succulent (Sarcocornia, 0.78g ±g 0.18g mmg yrg '1) and grass (Sporobolus, 0.88g ±g 0.22g mmg yrg '1) assemblages located lower in the tidal frame. Short-term (6 days) experiments showed deposition within Juncus plots to be dominated by autochthonous organic inputs with C deposition rates ranging from 1.14g ±g 0.41g mgg Cg cmg '2g dg '1 (neap tidal period) to 2.37g ±g 0.44g mgg Cg cmg '2g dg '1 (spring tidal period), while minerogenic inputs and lower C deposition dominated Sarcocornia (0.10g ±g 0.02 to 0.62g ±g 0.08g mgg Cg cmg '2g dg '1) and Sporobolus (0.17g ±g 0.04 to 0.40g ±g 0.07g mgg Cg cmg '2g dg '1) assemblages. br br Elemental (Cg :g N), isotopic (?13C), mid-infrared (MIR) and 13C nuclear magnetic resonance (NMR) analyses revealed little difference in either the source or character of materials being deposited among neap versus spring tidal periods. Instead, these analyses point to substantial redistribution of materials within the Sarcocornia and Sporobolus assemblages, compared to high retention and preservation of organic inputs in the Juncus assemblage. By combining medium-term accretion quantification with short-term deposition measurements and chemical analyses, we have gained novel insights into above-ground biophysical processes that may explain previously observed regional differences in surface dynamics among key salt marsh vegetation assemblages. Our results suggest that Sarcocornia and Sporobolus assemblages may be particularly susceptible to changes in sea level, though quantification of below-ground processes (e.g. root production, compaction) is needed to confirm this.

Short-term microbial respiration in an arid zone mangrove soil is limited by availability of gallic acid, phosphorus and ammonium - Davies, Tegan K.R.; Lovelock, Catherine E.; Pettit, Neil E.; Grierson, Pauline F. (Soil Biology and Biochemistry, 2017)
Microbial activity in soils of oligotrophic, arid zone mangroves is likely strongly limited by carbon (C) and nutrient availability, where even small changes in microbial activity could result in significant shifts in ecosystem functioning. We hypothesised that microbial respiration in arid mangrove ecosystems is primarily limited by supply of labile C sources. We measured short-term respiration responses to addition of glucose, citric acid, gallic acid, phosphate, ammonium (NH4+), nitrate (NO3−), urea and glutamic acid to mangrove soils from different tidal positions and soil depths in the laboratory using an adaptation of the MicroResp™ procedure (μg CO2-C g soil−1 hr−1). We also measured short-term respiration responses to added glucose, gallic acid, phosphate, ammonium and urea in the field using an infrared gas analyser (g CO2 m−2 hr−1). Both laboratory and field measurements indicated microbial communities were limited by gallic acid, phosphate and ammonium. Respiration rates were enhanced in both the laboratory and the field after addition of gallic acid but not glucose, suggesting adaptations of the arid microbial community to more complex C sources. Addition of phosphate alone and in combination with other substrates enhanced respiration more than ten-fold in the laboratory. In the field, nutrient addition (ammonium and/or phosphate) generally induced greater respiration responses in the surface soils (0–1 cm) compared to subsurface (>1 cm), which we attribute to more nutrient-limited autotrophic microbes in the surface soils. Addition of phosphate also induced slightly higher activity in the low intertidal fringing forests compared to high intertidal scrub forests. Our results contrast with studies of more productive tropical mangrove systems and demonstrate the critical role of microorganisms in maintaining organic matter turnover and nutrient supply in a relatively pristine and water-limited environment.

Small-scale variability in geomorphological settings influences mangrove-derived organic matter export in a tropical bay - Signa, Geraldina; Mazzola, Antonio; Kairo, James; Vizzini, Salvatrice (Biogeosciences, 2017)
Organic matter (OM) exchanges between adjacent habitats affect the dynamics and functioning of coastal systems, as well as the role of the different primary producers as energy and nutrient sources in food webs. Elemental (C, N, C:N) and isotope (δ13C) signatures and fatty acid (FA) profiles were used to assess the influence of geomorphological setting in two climatic seasons on the export and fate of mangrove OM across a tidally influenced tropical area, Gazi Bay (Kenya). The main results indicate that tidal transport, along with riverine runoff, plays a significant role in the distribution of mangrove organic matter. In particular, a marked spatial variability in the export of organic matter from mangroves to adjacent habitats was due to the different settings of the creeks flowing into the bay. Kinondo Creek acted as a mangrove retention site, where export of mangrove material was limited to the contiguous intertidal area, while Kidogoweni Creek acted as a "flow-throug" system, from which mangrove material spreads into the bay, especially in the rainy season. This pattern was evident from the isotopic signature of primary producers, which were more 13C-depleted in the Kinondo Creek and nearby, due to the lower dilution of the dissolved inorganic carbon (DIC) pool, typically depleted as an effect of intense mangrove mineralisation. Despite the trapping efficiency of the seagrass canopy, suspended particulate OM showed the important contribution of mangroves across the whole bay, up to the coral reef, as an effect of the strong ebb tide. Overall, mixing model outcomes indicated a widespread mixed contribution of both allochthonous and autochthonous OM sources across Gazi Bay. Moreover, FAs indicated a notable contribution of brown macroalgae and bacteria in both sediment and suspended pools. These results suggest that ecological connectivity in Gazi Bay is strongly influenced by geomorphological setting, which may have far-reaching consequences for the functioning of the whole ecosystem and the local food webs.

Soil C quantities of mangrove forests, their competing land uses, and their spatial distribution in the coast of Honda Bay, Philippines - Castillo, Jose Alan A.; Apan, Armando A.; Maraseni, Tek Narayan; Salmo, Severino G. (Geoderma, 2017)
Mangrove forests provide many ecosystem goods and services and they contain large amount of carbon (C) especially in their soil. Yet, their global area is still declining owing to conversion to non-forest land uses. While studies have been conducted on mangrove soil C stocks, our knowledge on how C stocks of mangrove forests compare with those of non-forest land uses that replaced them is still limited. This knowledge is crucial in land use planning and decision-making in the coastal zone. Site-scale mapping and assessments of mangrove soil C stocks and the land uses that replaced them are also limited. The aim of this study was to quantify and compare the soil C stocks in mangrove forests and their competing non-forest land uses (represented by aquaculture pond, coconut plantation, salt pond and cleared mangrove), estimate soil C loss arising from conversion, and model the soil C stock distribution in the entire study site. On the average, the soil C stock of mangrove forests was 851.9 ± 87 MgC ha− 1 while that of their non-forest competing land uses was less than half at 365.1 ± 31 MgC ha− 1. Closed canopy mangrove was highest at 1040 ± 104 MgC ha− 1, followed by open canopy mangrove (640 ± 131 MgC ha− 1) while aquaculture, salt pond and cleared mangrove had comparable C stocks (454 ± 32, 401 ± 9, 413 ± 25 MgC ha− 1, respectively) and coconut plantation had the least (42 ± 0.7 MgC ha− 1). Overall, the reduction in soil C stock (soil C loss) due to land use conversion in mangrove ranged from 398 to 809 MgC ha− 1 (mean: 486.8 MgC ha− 1) or a decline of 57% in soil C stock, on the average. It was possible to model the site-scale spatial distribution of soil C stocks and predict their values with 85% overall certainty using the Ordinary Kriging approach. Results from this study could help inform current discussions on Blue Carbon and REDD + as well as policy and program development that advance research on soil C conservation and ecosystem services in coastal forested wetlands.

Soil greenhouse gas fluxes in tropical mangrove forests and in land uses on deforested mangrove lands - Castillo, Jose Alan A.; Apan, Armando A.; Maraseni, Tek N.; Salmo, Severino G. (Catena, 2017)
Mangrove forests are important carbon sinks in the tropics, yet tropical mangrove deforestation and land use conversion still persists. Reporting of greenhouse gas (GHG) emissions from natural and anthropogenic sources in wetlands are important in regional and national emissions inventories. However, very few studies have been conducted to measure on the GHG fluxes in coastal wetlands, particularly in mangrove forest and non-forest land uses in deforested mangroves. We investigated the soil fluxes of CO2, CH4 and N2O in mangrove forest and non-forest land uses on deforested mangrove areas (i.e. abandoned aquaculture ponds, coconut plantations, abandoned salt ponds, and cleared mangroves) in the coasts of Honda Bay, Philippines. Results showed that the emissions of CO2 and CH4 were higher by 2.6 and 6.6 times in mangrove forests (110 and 0.6 kg CO2e ha − 1 day − 1, respectively) while N2O emissions were lower by 34 times compared to the average of non-forest land uses (1.3 kg CO2e ha − 1 day − 1). CH4 and N2O emissions accounted for 0.59% and 0.04% of the total emissions in mangrove forest as compared to 0.23% and 3.07% for non-forest land uses, respectively. Site-scale soil GHG flux distribution could be mapped with 75% to 83% accuracy using Ordinary Kriging. Unlike mangroves that can offset all GHG emissions through CO2 uptake from photosynthesis, the non-forest land uses cannot offset their emissions on-site as they are usually devoid of vegetation. Our results could be utilised in higher tier national GHG inventories, to refine regional and global estimates of GHG emissions in mangrove wetlands, and improve policy on coastal wetlands conservation.

Technical review of opportunities for including blue carbon in the Australian Government’s Emissions Reduction Fund - Kelleway, Jeff; Serrano, O.; Baldock, J.; Cannard, T.; Lavery, P.; Lovelock, C.E.; Macreadie, P.; Masqué, P.; Saintilan; N, Steven ADL (CSIRO , Australia, 2017)
… new growth of mangrove biomass organic carbon (Corg) pools and mangrove/tidal marsh … Corg stores within blue carbon ecosystems, has not yet developed blue carbon strategies to …

Temporal variability in the importance of hydrologic, biotic, and climatic descriptors of dissolved oxygen dynamics in a shallow tidal-marsh creek - Nelson, Natalie G.; Muñoz-Carpena, Rafael; Neale, Patrick J.; Tzortziou, Maria; Megonigal, J. Patrick (Water Resources Research, 2017)
Due to strong abiotic forcing, dissolved oxygen (DO) in shallow tidal creeks often disobeys the conventional explanation of general aquatic DO cycling as biologically regulated. In the present work, we seek to quantify the relative importance of abiotic (hydrologic and climatic), and biotic (primary productivity as represented by chlorophyll-a) descriptors of tidal creek DO. By fitting multiple linear regression models of DO to hourly chlorophyll-a, water quality, hydrology, and weather data collected in a tidal creek of a Chesapeake Bay marsh (Maryland, USA), temporal shifts (summer-early winter) in the relative importance of tidal creek DO descriptors were uncovered. Moreover, this analysis identified an alternative approach to evaluating tidal stage as a driver of DO by dividing stage into two DO-relevant variables: stage above and below bankfull depth. Within the hydrologic variable class, stage below bankfull depth dominated as an important descriptor, thus highlighting the role of pore water drainage and mixing as influential processes forcing tidal creek DO. Study findings suggest that tidal creek DO dynamics are explained by a balance of hydrologic, climatic, and biotic descriptors during warmer seasons due to many of these variables (i.e., chlorophyll-a, water temperature) acting as tracers of estuarine-marsh water mixing; conversely, in early winter months when estuarine and marsh waters differ less distinctly, hydrologic variables increase in relative importance as descriptors of tidal creek DO. These findings underline important distinctions in the underlying mechanisms dictating DO variability in shallow tidal marsh-creek environments relative to open water estuarine systems.

The contrasting effects of nutrient enrichment on growth, biomass allocation and decomposition of plant tissue in coastal wetlands - Hayes, Matthew A.; Jesse, Amber; Tabet, Basam; Reef, Ruth; Keuskamp, Joost A.; Lovelock, Catherine E. (Plant and Soil, 2017)
Aims: Eutrophication of coastal waters can have consequences for the growth, function and soil processes of coastal wetlands. Our aims were to assess how nutrient enrichment affects growth, biomass allocation and decomposition of plant tissues of a common and widespread mangrove, Avicennia marina, and how eutrophication drives changes in below-ground carbon sequestration. Methods: We assessed this through the measurement of above- and belowground growth and decomposition rates of plants and plant tissue in unenriched or nutrient enriched treatments. Results: Nutrient enrichment increased biomass allocation above-ground compared to below-ground in seedlings but not in fully developed, mature trees where we observed the opposite pattern. Experiments to assess root decomposition found that 40–50% of biomass was lost within six months with little change between 12 and 18 months, indicating a high potential for accumulation of organic matter over time. We estimate root-derived carbon sequestration rates of 53, 250 and 94 g C m−2 year−1 for unenriched control, N and P enriched treatments, respectively. Conclusions: These results show coastal eutrophication can be beneficial and detrimental to ecosystem function of coastal plants. Eutrophication stimulates root growth in fully developed trees, increasing organic matter input to soils. Our data suggests that organic matter accumulation will increase in areas with high nutrient availability where root growth is increased and rates of decomposition are low.

The effects of elevated CO2 and eutrophication on surface elevation gain in a European salt marsh - Reef, Ruth; Spencer, Tom; Mӧller, Iris; Lovelock, Catherine E.; Christie, Elizabeth K.; McIvor, Anna L.; Evans, Ben R.; Tempest, James A. (Global Change Biology, 2017)
Salt marshes can play a vital role in mitigating the effects of global environmental change by dissipating incident storm wave energy and, through accretion, tracking increasing water depths consequent upon sea level rise. Atmospheric CO2 concentrations and nutrient availability are two key variables that can affect the biological processes that contribute to marsh surface elevation gain. We measured the effects of CO2 concentrations and nutrient availability on surface elevation change in intact mixed-species blocks of UK salt marsh using six open-top chambers receiving CO2-enriched (800 ppm) or ambient (400 ppm) air. We found more rapid surface elevation gain in elevated CO2 conditions: an average increase of 3.4 mm over the growing season relative to ambient CO2. Boosted regression analysis to determine the relative influence of different parameters on elevation change identified that a 10% reduction in microbial activity in elevated CO2-grown blocks had a positive influence on elevation. The biomass of Puccinellia maritima also had a positive influence on elevation, while other salt marsh species (e.g. Suaeda maritima) had no influence or a negative impact on elevation. Reduced rates of water use by the vegetation in the high CO2 treatment could be contributing to elevation gain, either directly through reduced soil shrinkage or indirectly by decreasing microbial respiration rates due to lower redox levels in the soil. Eutrophication did not influence elevation change in either CO2 treatment despite doubling aboveground biomass. The role of belowground processes (transpiration, root growth and decomposition) in the vertical adjustment of European salt marshes, which are primarily minerogenic in composition, could increase as atmospheric CO2 concentrations rise and should be considered in future wetland models for the region. Elevated CO2 conditions could enhance resilience in vulnerable systems such as those with low mineral sediment supply or where migration upwards within the tidal frame is constrained.

The potential to integrate blue carbon into MPA design and management - Howard, Jennifer; McLeod, Elizabeth; Thomas, Sebastian; Eastwood, Erin; Fox, Matthew; Wenzel, Lauren; Pidgeon, Emily (Aquatic Conservation: Marine and Freshwater Ecosystems, 2017)
Oceans and coasts provide a wide array of services to humans, including climate regulation, food security, and livelihoods. Managing them well is vital to human well-being as well as the maintenance of marine biodiversity and ocean-dependent economies. Carbon sequestration and storage is increasingly recognized as a valuable service provided by coastal vegetation. Carbon sequestered and stored by mangrove forests, tidal marshes, and seagrass meadows is known as ‘blue’ carbon. These habitats capture and store carbon within the plants themselves and in the sediment below them. When the habitats are destroyed, much of their carbon is released back to the atmosphere and ocean contributing to global climate change. Therefore, blue carbon ecosystem protection is becoming a greater priority in marine management and is an area of interest to scientists, policy makers, coastal communities, and the private sector including those that contribute to ecosystem degradation but also those that are looking to reduce their carbon footprint. A range of policy and management responses aim to reduce coastal ecosystem loss, including the establishment of marine protected areas (MPAs). This paper explores how MPA design, location, and management could be used to protect and increase carbon sequestration and ensure integrity of carbon storage through conservation and restoration activities. While additional research is necessary to validate the proposed recommendations, this paper describes much needed first steps and highlights the potential for blue carbon finance mechanisms to provide sustainable funding for MPAs.

The role of surface elevation in the rehabilitation of abandoned aquaculture ponds to mangrove forests, Sulawesi, Indonesia - Oh, R. R.Y.; Friess, D. A.; Brown, B. M. (Ecological Engineering, 2017)
Intertidal mangrove forests are declining rapidly in Southeast Asia due to diverse threats such as urbanisation, agriculture and aquaculture. Mangrove rehabilitation programmes designed to compensate for such declines are largely unsuccessful as they fail to match environmental conditions to species-specific tolerance thresholds for different mangrove vegetation species. This study investigated the importance of surface elevation (related to tidal inundation period) in influencing the colonisation and establishment of mangroves in a rehabilitation site in Sulawesi, Indonesia. A topographic survey of 29 abandoned aquaculture ponds was conducted to map the surface elevations before and shortly after rehabilitation. A vegetation survey was conducted in a neighbouring reference forest to quantify the surface elevation envelopes of established mangroves, and in the rehabilitated site to predict where successful vegetation establishment would occur, and to guide remedial works to make surface elevations suitable for establishment. Surface elevations in aquaculture ponds ranged between −2.158 m and 2.411 m WGS 84. 651 mangrove individuals across 13 species had established naturally in ponds within six months after rehabilitation, and were restricted to elevations of −1.511 m to 0.228 m WGS 84. Seedlings/saplings from both ponds and reference forests had established at comparable surface elevation ranges of −1.511 m to 0.228 m WGS 84 and −1.255 m to 0.073 m WGS 84. The elevation envelope occupied by seedlings in aquaculture ponds was widest for Avicennia rumphiana (−1.085 m to −0.218 m WGS 84) and in reference forests, Rhizophora mucronata (−0.850 m to −0.503 m WGS 84). This study highlights the importance of intertidal surface elevation and its control on inundation hydroperiod as a key, spatially explicit threshold to seedling colonisation establishment. The rehabilitation of appropriate surface elevations is a crucial first step in successful mangrove rehabilitation.

The spatial distribution of soil organic carbon in tidal wetland soils of the continental United States - Hinson, Audra L.; Feagin, Rusty A.; Eriksson, Marian; Najjar, Raymond G.; Herrmann, Maria; Bianchi, Thomas S.; Kemp, Michael; Hutchings, Jack A.; Crooks, Steve; Boutton, Thomas (Global Change Biology, 2017)
Tidal wetlands contain large reservoirs of carbon in their soils and can sequester carbon dioxide (CO2) at a greater rate per unit area than nearly any other ecosystem. The spatial distribution of this carbon influences climate and wetland policy. To assist with international accords such as the Paris Climate Agreement, national-level assessments such as the United States (U.S.) National Greenhouse Gas Inventory, and regional, state, local, and project-level evaluation of CO2 sequestration credits, we developed a geodatabase (CoBluCarb) and high-resolution maps of soil organic carbon (SOC) distribution by linking National Wetlands Inventory data with the U.S. Soil Survey Geographic Database. For over 600,000 wetlands, the total carbon stock and organic carbon density was calculated at 5-cm vertical resolution from 0 to 300 cm of depth. Across the continental United States, there are 1,153–1,359 Tg of SOC in the upper 0–100 cm of soils across a total of 24 945.9 km2 of tidal wetland area, twice as much carbon as the most recent national estimate. Approximately 75% of this carbon was found in estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. The greatest pool of SOC was found within the Atchafalaya/Vermilion Bay complex in Louisiana, containing about 10% of the U.S. total. The average density across all tidal wetlands was 0.071 g cm−3 across 0–15 cm, 0.055 g cm−3 across 0–100 cm, and 0.040 g cm−3 at the 100 cm depth. There is inherent variability between and within individual wetlands; however, we conclude that it is possible to use standardized values at a range of 0–100 cm of the soil profile, to provide first-order quantification and to evaluate future changes in carbon stocks in response to environmental perturbations. This Tier 2-oriented carbon stock assessment provides a scientific method that can be copied by other nations in support of international requirements.

Wadden Sea Quality Status Report - Seagrass - Dolch, T; Folmer, E. O; Frederiksen, M. S; Herlyn, M.; van Katwijk, M. M.; Kolbe, K; Krause-Jensen, D; Schmedes, P; Westerbeek, E. P (Wadden Sea Quality Status Report 2017, 2017)
In December 1999 a new Wadden Sea Quality Status Report left the printer. The main conclusions, related to the implementation of the common trilateral Targets, are given. INTRODUCTION The last Wadden Sea Quality Status Report of the 1990s was finalized shortly before the end of the decade. After the "Development Report" of 1991 and the "1993 Quality Status Report" it is the third time that an integrated assessment report of the Wadden Sea has been published. Some 60 persons have contributed to the QSR, many on a voluntary basis. The analysis of the chemical data was, like for the previous two reports, done by the Dutch Institute for Coastal and Marine Management (RIKZ). The work was coordinated by the Quality Status Report Group, a subgroup of the Trilateral Monitoring and Assessment Group (TMAG). With its 260 pages the book is more comprehensive than its predecessors. It contains chapters on protection and management, human use, climate, marine chemistry and biology. For the first time dunes, beaches, estuaries and the offshore zone are addressed. This is because, at the Leeuwarden Conference in 1994, these habitats had become part of the trilateral cooperation. The chapter on Marine Chemistry covers the period 1985-1996, which is a sufficiently long period to allow for statistical analyses of trends. Also in Chapter 5, Biology, several long time series are assessed, amongst others for chlorophyll and macrozoobenthos. Also, in this chapter, for the first time data from the Demersal Young Fish Survey (DYFS) are presented. The overall assessment part of the QSR has been structured according to the common Targets as adopted at the Leeuwarden Conference and evaluates progress in the implementation of the Targets. Also, methodological considerations about how Targets can be evaluated are included. The conclusions and recommendations of the QSR will be discussed in the course of this year and the results of this dicussion will be submitted to the Wadden Sea Senior Officials in the framework of the preparation of the 9th Governmental Wadden Sea Conference (Denmark, November 2001). Some of the main conclusions are given below. QUALITY OF WATER, SEDIMENT AND BIOTA NUTRIENTS AND EUTROPHICATION The Target of "A Wadden Sea which can be regarded as a eutrophication non-problem area" relates to the agreements within the Ospar framework about dividing the Ospar area into non-eutrophication problem areas, potential eutrophication problem areas and eutrophication problem areas. For the Wadden Sea, criteria to differentiate between these three categories have been elaborated in a trilateral project, the results of which will become available this spring (see also Van Beusekom, this issue) could not yet be used for the evaluation of the Target. Phosphate levels in water have decreased significantly in most parts of the Wadden Sea whereas this is not the case for nitrate. Also chlorophyll levels showed no decrease. As reasons for the remaining high primary production several factors are mentioned namely increased input of organic matter from the adjacent North Sea, delivery of phosphorus from the sediment and the fact that nitrogen is the main limiting factor for primary production. The N to P ratio has increased in some areas, most notably in the western Wadden Sea. The duration of Phaeocystis blooms in the Marsdiep has, however, not decreased. The blooming intensity of Phaeocystis at Norderney, expressed as number of colonies per liter, decreased in the period 1993-1996, coinciding with decreasing dissolved N and P concentrations. The proliferation of potentially toxic algal species has not increased in the first half of the 1990s. A long-term evaluation of macrozoobenthos data from five locations in the Wadden Sea made clear that macrozoobenthos is, to a certain extent, regulated by winter severity and that, with the exception of Balgzand, no clear cause-effect relationships exists with primary productivity or eutrophic state. The observed increase since 1988 in macrozoobenthos biomass in the coastal zone off Norderney was related to mild meteorological conditions in winter. NATURAL MICROPOLLUTANTS For natural micropollutants the Target "natural background concentrations" has been agreed upon. Concentrations of most heavy metals in sediment are approaching background levels. An exception is mercury which still is three to ten times higher than background. All sediment metal concentrations are below ecotoxicological assessment criteria (EAC) ranges as developed by Ospar. Also metal concentrations in blue mussel have decreased but are still, with the exception of zinc, above background levels. Polycylic Aromatic Hydrocarbons (PAHs) concentrations in sediment are within the range of background levels and below EAC XENOBIOTIC SUBSTANCES The Target for xenobiotic or man-made substances is that levels should be such as resulting from zero discharge. Data for PCBs, HCB, HCH and TBT have been evaluated. Concentrations of PCBs in sediment and HCB and HCH in bird eggs show a steady decrease. TBT, however, is a reason for concern. Levels in sediment of up to 1000 times EAC have been recorded. THE TIDAL AREA Two categories of Targets apply to the Tidal Area, namely Targets for the geomorphology and Targets for the Biology. It is concluded that, as a result of human interference, most notably fixed coastal constructions, but also fisheries, dredging sand extraction and gas extraction, the ability of the system to compensate for sea level rise may have decreased. Also, the settling conditions for fine-grained sediment may have become worse.The Target of an increased area and a more natural development of natural mussel beds, eelgrass meadows and Sabellaria reefs has not been reached. The decline in number and size of mature beds of the blue mussel and seagrass meadows has continued in this decade. The decrease of these structure-building communities may also influence hydrology and sedimentology in the Tidal Area. Because our present understanding of the hydrological and geomorphological processes and their interactions, together with the role of mussel beds and seagrass meadows, is still insufficient, there is an urgent need for further research on the interactions between sediment composition, disturbances and subsequent biotic developments. SALT MARSHES The Targets for salt marshes are to increase the area of natural salt marshes and improve the natural vegetation structure of artificial salt marshes. Much has been achieved in the past ten years with regard to improving the natural situation in salt marshes by the reduction, or phasing out, of grazing and artificial drainage. The outbanking of summer polders has, so far, only been applied in the Dutch Wadden Sea. This practice not only increases the salt marsh area, but could also be favorable for creating new fresh-salt transitions and for maintaining the sediment balance of the Tidal Area. A precise comparison of the situation regarding the natural situation of salt marshes in the different parts of the Wadden Sea is presently not possible because of a lack of actual data and of common criteria. The last trilateral survey of salt marshes was carried out in 1986. It is therefore recommended to initiate a new survey on the basis of harmonized criteria. The erosion of salt marshes does not yet seem to have increased as a result of sea level rise, bottom subsidence and higher wave energy. BEACHES AND DUNES For beaches and dunes it is the Target to increase the natural dynamic situation and the presence of a complete natural vegetation succession. The status of the dunes in the Wadden Sea Area has been, and still is, determined by conservative measures of coastal protection which preserve directly (planting of marram grass) or indirectly (building of sand dikes, groynes etc.) the zoning patterns. As a result, there is a relatively high percentage of int

A marine heatwave drives massive losses from the world's largest seagrass carbon stocks - Arias-Ortiz, A.; Serrano, O.; Masqué, P.; Lavery, P. S.; Mueller, U.; Kendrick, G. A.; Rozaimi, M.; Esteban, A.; Fourqurean, J. W.; Marbà, N.; Mateo, M. A.; Murray, K.; et al. (Nature Climate Change, 2018)
Seagrass ecosystems contain globally significant organic carbon (C) stocks. However, climate change and increasing frequency of extreme events threaten their preservation. Shark Bay, Western Australia, has the largest C stock reported for a seagrass ecosystem, containing up to 1.3% of the total C stored within the top metre of seagrass sediments worldwide. On the basis of field studies and satellite imagery, we estimate that 36% of Shark Bay's seagrass meadows were damaged following a marine heatwave in 2010/2011. Assuming that 10 to 50% of the seagrass sediment C stock was exposed to oxic conditions after disturbance, between 2 and 9 Tg CO2 could have been released to the atmosphere during the following three years, increasing emissions from land-use change in Australia by 4-21% per annum. With heatwaves predicted to increase with further climate warming, conservation of seagrass ecosystems is essential to avoid adverse feedbacks on the climate system.

A remote sensing-based model of tidal marsh aboveground carbon stocks for the conterminous United States - Byrd, Kristin B.; Ballanti, Laurel; Thomas, Nathan; Nguyen, Dung; Holmquist, James R.; Simard, Marc; Windham-Myers, Lisamarie (ISPRS Journal of Photogrammetry and Remote Sensing, 2018)
Remote sensing based maps of tidal marshes, both of their extents and carbon stocks, have the potential to play a key role in conducting greenhouse gas inventories and implementing climate mitigation policies. Our objective was to generate a single remote sensing model of tidal marsh aboveground biomass and carbon that represents nationally diverse tidal marshes within the conterminous United States (CONUS). We developed the first calibration-grade, national-scale dataset of aboveground tidal marsh biomass, species composition, and aboveground plant carbon content (%C) from six CONUS regions: Cape Cod, MA, Chesapeake Bay, MD, Everglades, FL, Mississippi Delta, LA, San Francisco Bay, CA, and Puget Sound, WA. Using the random forest machine learning algorithm, we tested whether imagery from multiple sensors, Sentinel-1 C-band synthetic aperture radar, Landsat, and the National Agriculture Imagery Program (NAIP), can improve model performance. The final model, driven by six Landsat vegetation indices and with the soil adjusted vegetation index as the most important (n = 409, RMSE = 310 g/m2, 10.3% normalized RMSE), successfully predicted biomass for a range of marsh plant functional types defined by height, leaf angle and growth form. Model results were improved by scaling field-measured biomass calibration data by NAIP-derived 30 m fraction green vegetation. With a mean plant carbon content of 44.1% (n = 1384, 95% C.I. = 43.99%–44.37%), we generated regional 30 m aboveground carbon density maps for estuarine and palustrine emergent tidal marshes as indicated by a modified NOAA Coastal Change Analysis Program map. We applied a multivariate delta method to calculate uncertainties in regional carbon densities and stocks that considered standard error in map area, mean biomass and mean %C. Louisiana palustrine emergent marshes had the highest C density (2.67 ± 0.004 Mg/ha) of all regions, while San Francisco Bay brackish/saline marshes had the highest C density of all estuarine emergent marshes (2.03 ± 0.004 Mg/ha). Estimated C stocks for predefined jurisdictional areas ranged from 1023 ± 39 Mg in the Nisqually National Wildlife Refuge in Washington to 507,761 ± 14,822 Mg in the Terrebonne and St. Mary Parishes in Louisiana. This modeling and data synthesis effort will allow for aboveground C stocks in tidal marshes to be included in the coastal wetland section of the U.S. National Greenhouse Gas Inventory. With the increased availability of free post-processed satellite data, we provide a tractable means of modeling tidal marsh aboveground biomass and carbon at the global extent as well.

Accuracy assessment of sentinel 2 image-derived leaf area index (LAI) of plant canopies and other land use/cover types in mangrove areas - Apan, Armando A.; Castillo, Jose Alan A.; Narayan Maraseni, Tek; Salmo, Severino G. (Proceedings - 39th Asian Conference on Remote Sensing: Remote Sensing Enabling Prosperity, ACRS 2018, 2018)
Leaf area index (LAI) quantifies the amount of foliage area per unit ground surface area. A dimensionless quantity (i.e. LAI = leaf area / ground area, m2 / m2), it is an important variable to predict photosynthetic primary production and for monitoring vegetation dynamics. The aim of this study was to assess the accuracy of Sentinel 2 image-derived LAI of plant canopies and other land use/cover types in tropical mangrove areas in the Philippines. This is part of a bigger study on mapping of above-ground biomass and soil carbon of mangrove forests. Using hand-held CI-110 Plant Canopy Imager, field-level LAI measurements were made between June-July 2015, in mangrove areas from 90 sample sites located in Honda Bay, Palawan, Philippines. A regression analysis was conducted between the a) Sentinel 2 (Level-1C, acquired in April 2016) image-derived LAI values, and b) field-collected LAI measurements. The regression analysis was accomplished using the traditional linear regression and new machine learning algorithms from the WEKA software. The accuracy of prediction was analysed using root mean square error (RMSE) and agreement (r) of predicted and observed values from leave-one-out cross-validation method. The results show that the field collected LAI data ranges from 0 - 2.71 (mean = 0.86), while the Sentinel 2 image-derived LAI values range from 0.19 - 4.32 (mean = 1.64). The regression models had 0.9419 correlation/agreement of observed and predicted value for linear regression; and had 0.9435 for using the support vector machine algorithm. The corresponding RMSE obtained were 0.3350 (linear regression) and 0.3424 (support vector machine), demonstrating a high prediction accuracy although the two datasets' LAI values were nine months apart. This study validates the good accuracy of the Sentinel 2 image-derived LAI values, indicating their usefulness for selected applications.

Annual Growth Rings in Two Mangrove Species from the Sundarbans, Bangladesh Demonstrate Linkages to Sea-Level Rise and Broad-Scale Ocean-Atmosphere Variability - Maxwell, Justin T.; Harley, Grant L.; Rahman, Abdullah F. (Wetlands, 2018)
Worldwide, mangroves are a wetland biome that has both ecological and societal importance. Across the coastal region of the Bay of Bengal, the Sundarbans is the largest continual mangrove forest in the world. One way to examine growth trends in tree species is with tree-ring analysis, or dendrochronology. However, tropical applications of dendrochronology are often met with limited success because not many tropical tree species form consistently annual growth rings. Here, we aim to [1] examine if two common mangrove species in the Sundarbans, Heritiera fomes and Sonneratia apetala, produce annual growth rings and [2] better understand the environmental and climatic drivers of mangrove radial growth. We successfully developed species chronologies from S. apetala and H. fomes and found species-specific correlations with seasonal precipitation. S. apetala growth significantly correlates with climate drivers including the Madden-Julian Oscillation the El Nino-Southern Oscillation, and the Indian Ocean Dipole. Our findings show that growth rings from mangroves that experience distinct changes in seasonal climate can be used as indicators of species health and productivity.

Assessing the contribution of porewater discharge in carbon export and CO2 evasion in a mangrove tidal creek (Can Gio, Vietnam) - Taillardat, Pierre; Willemsen, Pim; Marchand, Cyril; Friess, Daniel A.; Widory, David; Baudron, Paul; Truong, Van Vinh; Nguyễn, Thanh Nho; Ziegler, Alan D. (Journal of Hydrology, 2018)
Although mangrove forests are efficient natural carbon sinks, most of the atmospheric carbon dioxide (CO2) fixed by its vegetation is believed to be exported via tidal exchange, rather than stored in the vegetative biomass and sediment. However, the magnitude of tidal export is largely unknown because direct measurements are scarce. We deployed a novel experimental design that combined automated high-resolution measurements of hydrodynamic, hydrogeochemical and biogeochemical parameters during the dry season in a mangrove tidal creek in the Can Gio Mangrove Forest in Vietnam. The objective was to quantify the tide-controlled water, porewater, DIC and DOC exchange, and estimate the CO2 evasion throughout tidal cycles contrasted by amplitude. Data from three 25-h time series showed a clear peak of DIC, DOC, pCO2, and 222Rn at low tide, particularly during tidal cycles of large amplitude, which directly relate to porewater discharge. Our mass balance models revealed that the tidal creek was a net exporter of dissolved carbon to coastal waters, with an important contribution (38%) coming from DIC in porewater discharge. Porewater exchange varied from 3.1 ± 1.6 to 7.1 ± 2.4 cm day−1. DIC exchange ranged from 352 ± 34 to 678 ± 79 mmolC m−2 day−1; DOC exchange, 20.6 ± 1.9 to 67.7 ± 7.9 mmol C m−2 day−1; and CO2 evasion, 69.9 ± 10.5 to 173.7 ± 26.1 mmolC m−2 day−1. These estimates were in the high range of previous carbon assessments and were explained by (i) the monitoring station being located at equal distance from the head and the mouth of the creek, which minimized carbon degradation and losses associated to transport in water; and (ii) the site being a highly productive mangrove within South East Asia.

Blue Carbon Accounting for Carbon Markets - Needelman, Brian A.; Emmer, Igino M.; Oreska, Matthew P. J.; Megonigal, J. Patrick (A Blue Carbon Primer, 2018)
Boca Raton, FL CRC Press

Blue Carbon Opportunities for Mangroves of Mexico - Adame, Maria Fernanda; Birdsey, Richard; Silveira, Jorge Herrera (A Blue Carbon Primer, 2018)

Carbon dynamics and inconstant porewater input in a mangrove tidal creek over contrasting seasons and tidal amplitudes - Taillardat, Pierre; Ziegler, Alan D.; Friess, Daniel A.; Widory, David; Truong Van, Vinh; David, Frank; Thành-Nho, Nguyễn; Marchand, Cyril (Geochimica et Cosmochimica Acta, 2018)
Constraining the contribution of mangrove-derived carbon in tidal creeks is fundamental to understanding the fate of mangrove primary production and the role of mangroves as coastal carbon sinks. Porewater measurements and 24-h time series in a mangrove tidal creek were conducted during the dry and wet season, and over contrasting tidal ranges at the Can Gio Biosphere Reserve, Vietnam. Surface water carbon concentrations (dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), partial pressure of carbon dioxide (pCO2)) and their respective δ13C values were correlated with radon, suggesting that porewater input drives mangrove-derived carbon in the tidal creek. Based on three complementary mixing models, porewater input contributed to about 30% of the water volume and 46% to 100% of DOC and DIC pools in the tidal creek at low tide, with variabilities between seasons and tidal amplitudes. The creek carbon pool was 88% DIC, 6% DOC, and 6% particulate organic carbon (POC). The pCO2 values during the wet season (2973–16,495 μatm) were on average 5-fold higher than during the dry season (584–2946 μatm). This was explained by a potential greater mineralization attributed to higher organic matter availability and residual humidity that stimulate bacterial activity, and by a potential tidal dilution changing the pCO2/DIC ratio as suggested by the Revelle factor. Consequently, average CO2 evasion from the creek was estimated at 327–427 mmolC m−2 d−1 during the wet season and 92–213 mmolC m−2 d−1 during the dry season, using two independent approaches. Tidal amplitude seemed to influence porewater input and its carbon loads, with a higher contribution during frequent and high tidal amplitudes (symmetric). However, the highest input occurred in a tidal cycle which was preceded by tidal cycle of low amplitude (asymmetric). We explain this ambiguity by the influence of both, rapid water turnover intensifying porewater exchange, and long water residence time enhancing carbon load in porewater.

Carbon isotope fractionation in the mangrove Avicennia marina has implications for food web and blue carbon research - Kelleway, Jeffrey J.; Mazumder, Debashish; Baldock, Jeffrey A.; Saintilan, Neil (Estuarine, Coastal and Shelf Science, 2018)
The ratio of stable isotopes of carbon (δ13C) is commonly used to track the flow of energy among individuals and ecosystems, including in mangrove forests. Effective use of this technique requires understanding of the spatial variability in δ13C among primary producer(s) as well as quantification of the isotopic fractionations that occur as C moves within and among ecosystem components. In this experiment, we assessed δ13C variation in the cosmopolitan mangrove Avicennia marina across four sites of varying physico-chemical conditions across two estuaries. We also compared the isotopic values of five distinct tissue types (leaves, woody stems, cable roots, pneumatophores and fine roots) in individual plants. We found a significant site effect (F3, 36 = 15.78; P < 0.001) with mean leaf δ13C values 2.0‰ more depleted at the lowest salinity site compared to the other locations. There was a larger within-plant fractionation effect, however, with leaf samples (mean ± SE = −29.1 ± 0.2) more depleted in 13C than stem samples (−27.1 ± 0.1), while cable root (−25. 8 ± 0.1), pneumatophores (−25.7 ± 0.1) and fine roots (−26.0 ± 0.2) were more enriched in 13C relative to both aboveground tissue types (F4, 36 = 223.45; P < 0.001). The within-plant δ13C fractionation we report for A. marina is greater than that reported in most other ecosystems. This has implications for studies of estuarine carbon cycling. The consistent and large size of the fractionation from leaf to woody stem (∼2.0‰) and mostly consistent fractionation from leaf to root tissues (>3.0‰) means that it may now be possible to partition the individual contributions of various mangrove tissues to estuarine food webs. Similarly, the contributions of mangrove leaves, woody debris and belowground sources to blue carbon stocks might also be quantified. Above all, however, our results emphasize the importance of considering appropriate mangrove tissue types when using δ13C to trace carbon cycling in estuarine systems.

Climate regulation: Salt marshes and blue carbon - Johnson, Beverly J.; Lovelock, Catherine E.; Herr, Dorothée (The Wetland Book: I: Structure and Function, Management, and Methods, 2018)
Carbon sequestered and stored in, or released from, salt marshes, mangroves, and seagrass ecosystems is often referred to as coastal "blue carbon." The term was first used in 2009 as a means of highlighting the significance of carbon sequestration and storage in these highly productive coastal ecosystems, largely to the policy and carbon finance communities.

Coastal Wetland Responses to Warming - Megonigal, J. Patrick; Chapman, Samantha; Langley, Adam; Crooks, Stephen; Dijkstra, Paul; Kirwan, Matt (A Blue Carbon Primer, 2018)
Most carbon (C) stored in coastal wetlands lies belowground, yet the critical belowground responses of roots and microbial respiration to warming are far more difficult to assess than the aboveground responses. Coastal wetlands have been recognized as important C sinks, and therefore the response of C cycling to climate change in tidal wetlands is largely unexplored. Warming is expected to influence the aboveground and belowground feedback loops that regulate soil C sequestration, elevation gain, methane emissions, and hydrologic export of C and nitrogen. Few experimental manipulations in wetlands have tested hypotheses about the effects of warming on ecological interactions. Numerical models are one approach to forecasting temperature effects on tidal marsh elevation and C sequestration. The potential of warming and ensuing sea level rise to alter plant community composition represents a large uncertainty for predicting future ecosystem C dynamics in tidal marshes and tidal forests.

Comment on Geoengineering with seagrasses: Is credit due where credit is given? - Oreska, Matthew P.J.; McGlathery, Karen J.; Emmer, Igino M.; Needelman, Brian A.; Emmett-Mattox, Stephen; Crooks, Stephen; Megonigal, J. Patrick; Myers, Doug (Environmental Research Letters, 2018)
In their recent review, 'Geoengineering with seagrasses: is credit due where credit is given?,' Johannessen and Macdonald (2016) invoke the prospect of carbon offset-credit over-allocation by the Verified Carbon Standard as a pretense for their concerns about published seagrass carbon burial rate and global stock estimates. Johannessen and Macdonald (2016) suggest that projects seeking offset-credits under the Verified Carbon Standard methodology VM0033: Methodology for Tidal Wetland and Seagrass Restoration will overestimate long-term (100 yr) sediment organic carbon (SOC) storage because issues affecting carbon burial rates bias storage estimates. These issues warrant serious consideration by the seagrass research community; however, VM0033 does not refer to seagrass SOC 'burial rates' or 'storage.' Projects seeking credits under VM0033 must document greenhouse gas emission reductions over time, relative to a baseline scenario, in order to receive credits. Projects must also monitor changes in carbon pools, including SOC, to confirm that observed benefits are maintained over time. However, VM0033 allows projects to conservatively underestimate project benefits by citing default values for specific accounting parameters, including CO2 emissions reductions. We therefore acknowledge that carbon crediting methodologies such as VM0033 are sensitive to the quality of the seagrass literature, particularly when permitted default factors are based in part on seagrass burial rates. Literature-derived values should be evaluated based on the concerns raised by Johannessen and Macdonald (2016), but these issues should not lead to credit over-allocation in practice, provided VM0033 is rigorously followed. These issues may, however, affect the feasibility of particular seagrass offset projects.

Conservation of blue carbon ecosystems for climate change mitigation and adaptation - Serrano, Oscar; Kelleway, Jeffrey J.; Lovelock, Catherine; Lavery, Paul S. (Coastal Wetlands: An Integrated Ecosystem Approach, 2018)
Emission of greenhouse gases, including carbon dioxide (CO2), has been the main cause of climate change and global warming since the mid-20th century. Blue carbon (BC) ecosystems, which include tidal marshes, mangroves, and seagrass meadows, play a key role in climate change mitigation and adaptation. Despite occupying only 0.2% of the ocean surface, they contribute 50% of carbon burial in marine sediments, equivalent to the sequestration of 1%-2% of current global CO2 emissions from fossil fuel combustion. Conversely, damage to these ecosystems risks the release of that carbon back to the atmosphere. Conserving and restoring BC ecosystems not only maintains CO2 sequestration capacity but also services essential for climate change adaptation along coasts, including prevention of shoreline erosion. However, BC ecosystems rank among the most threatened ecosystems on earth. Urgent action is needed to prevent further degradation, to avoid additional greenhouse emissions, as well as restoring degraded habitats to recover their climate change mitigation potential.

Dinámica de la cobertura del suelo y las existencias de carbono en los manglares de El Salvador - Cifuentes-Jara, Miguel; Rivera, Carlos; Magaña, Javier; Velásquez, Sergio; Danilo, Torres (Programa regional de cambio climático, 2018)

Does Nutrient Availability Regulate Seagrass Response to Elevated CO2? - Campbell, Justin E.; Fourqurean, James W. (Ecosystems, 2018)
Future increases in oceanic carbon dioxide concentrations (CO2(aq)) may provide a benefit to submerged plants by alleviating photosynthetic carbon limitation. However, other environmental factors (for example, nutrient availability) may alter how seagrasses respond to CO2(aq) by regulating the supply of additional resources required to support growth. Thus, questions remain in regard to how other factors influence CO2(aq) effects on submerged vegetation. This study factorially manipulated CO2(aq) and nutrient availability, in situ, within a subtropical seagrass bed for 350 days, and examined treatment effects on leaf productivity, shoot density, above- and belowground biomass, nutrient content, carbohydrate storage, and sediment organic carbon (Corg). Clear, open-top chambers were used to replicate CO2(aq) forecasts for the year 2100, whereas nutrient availability was manipulated via sediment amendments of nitrogen (N) and phosphorus (P) fertilizer. We provide modest evidence of a CO2 effect, which increased seagrass aboveground biomass. CO2(aq) enrichment had no effect on nutrient content, carbohydrate storage, or sediment Corg content. Nutrient addition increased leaf productivity and leaf N content, however did not alter above- or belowground biomass, shoot density, carbohydrate storage, or Corg content. Treatment interactions were not significant, and thus NP availability did not influence seagrass responses to elevated CO2(aq). This study demonstrates that long-term carbon enrichment may alter the structure of shallow seagrass meadows, even in relatively nutrient-poor, oligotrophic systems.

Estuarine , Coastal and Shelf Science Mangrove mortality in a changing climate : An overview - Sippo, James Z; Lovelock, Catherine E; Santos, Isaac R; Sanders, Christian J; Maher, Damien T (2018)

Expanding Greenland seagrass meadows contribute new sediment carbon sinks - Marbà, Núria; Krause-Jensen, Dorte; Masqué, Pere; Duarte, Carlos M. (Scientific Reports, 2018)
The loss of natural carbon sinks, such as seagrass meadows, contributes to grenhouse gas emissions and, thus, global warming. Whereas seagrass meadows are declining in temperate and tropical regions, they are expected to expand into the Arctic with future warming. Using paleoreconstruction of carbon burial and sources of organic carbon to shallow coastal sediments of three Greenland seagrass (Zostera marina) meadows of contrasting density and age, we test the hypothesis that Arctic seagrass meadows are expanding along with the associated sediment carbon sinks. We show that sediments accreted before 1900 were highly 13C depleted, indicative of low inputs of seagrass carbon, whereas from 1940’s to present carbon burial rates increased greatly and sediment carbon stocks were largely enriched with seagrass material. Currently, the increase of seagrass carbon inputs to sediments of lush and dense meadows (Kapisillit and Ameralik) was 2.6 fold larger than that of sparse meadows with low biomass (Kobbefjord). Our results demonstrate an increasing important role of Arctic seagrass meadows in supporting sediment carbon sinks, likely to be enhanced with future Arctic warming.

Global controls on carbon storage in mangrove soils - Rovai, A.S.; Twilley, R.R.; Castañeda-Moya, E.; Riul, P.; Cifuentes-Jara, M.; Manrow-Villalobos, M.; Horta, P.A.; Simonassi, J.C.; Fonseca, A.L.; Pagliosa, P.R. (Nature Climate Change, 2018)
Global-scale variation in mangrove ecosystem properties has been explained using a conceptual framework linking geomorphological processes to distinct coastal environmental settings (CES) for nearly 50 years. However, these assumptions have not been empirically tested at the global scale. Here, we show that CES account for global variability in mangrove soil C:N:P stoichiometry and soil organic carbon (SOC) stocks. Using this ecogeomorphology framework, we developed a global model that captures variation in mangrove SOC stocks compatible with distinct CES. We show that mangrove SOC stocks have been underestimated by up to 50% (a difference of roughly 200 Mg ha-1) in carbonate settings and overestimated by up to 86% (around 400 Mg ha-1) in deltaic coastlines. Moreover, we provide information for 57 nations that currently lack SOC data, enabling these and other countries to develop or evaluate their blue carbon inventories.

Habitat characteristics provide insights of carbon storage in seagrass meadows - Mazarrasa, Inés; Samper-Villarreal, Jimena; Serrano, Oscar; Lavery, Paul S.; Lovelock, Catherine E.; Marbà, Núria; Duarte, Carlos M.; Cortés, Jorge (Marine Pollution Bulletin, 2018)
Seagrass meadows provide multiple ecosystem services, yet they are among the most threatened ecosystems on earth. Because of their role as carbon sinks, protection and restoration of seagrass meadows contribute to climate change mitigation. Blue Carbon strategies aim to enhance CO2 sequestration and avoid greenhouse gasses emissions through the management of coastal vegetated ecosystems, including seagrass meadows. The implementation of Blue Carbon strategies requires a good understanding of the habitat characteristics that influence Corg sequestration. Here, we review the existing knowledge on Blue Carbon research in seagrass meadows to identify the key habitat characteristics that influence Corg sequestration in seagrass meadows, those factors that threaten this function and those with unclear effects. We demonstrate that not all seagrass habitats have the same potential, identify research priorities and describe the implications of the results found for the implementation and development of efficient Blue Carbon strategies based on seagrass meadows.

Human Impacts on Blue Carbon Ecosystems - Lovelock, Catherine E.; Friess, Daniel A.; Kauffman, J. Boone; Fourqurean, James W. (A Blue Carbon Primer, 2018)
Chapter 3:Human Impacts on Blue Carbon Ecosystems. 17-24 Lovelock, Catherine E. Friess, Daniel A. Kauffman, J. Boone Fourqurean, James W.

Influence of Coastal Submarine Groundwater Discharges on Seagrass Communities in a Subtropical Karstic Environment - Kantún-Manzano, C. A.; Herrera-Silveira, J. A.; Arcega-Cabrera, F. (Bulletin of Environmental Contamination and Toxicology, 2018)
The influence of coastal submarine groundwater discharges (SGD) on the distribution and abundance of seagrass meadows was investigated. In 2012, hydrological variability, nutrient variability in sediments and the biotic characteristics of two seagrass beds, one with SGD present and one without, were studied. Findings showed that SGD inputs were related with one dominant seagrass species. To further understand this, a generalized additive model (GAM) was used to explore the relationship between seagrass biomass and environment conditions (water and sediment variables). Salinity range (21–35.5 PSU) was the most influential variable (85%), explaining why H. wrightii was the sole plant species present at the SGD site. At the site without SGD, GAM could not be performed since environmental variables could not explain a total variance of > 60%. This research shows the relevance of monitoring SGD inputs in coastal karstic areas since they significantly affect biotic characteristics of seagrass beds.

Investigating the use of Alos Prism data in detecting mangrove succession through canopy height estimation - Aslan, Aslan; Rahman, Abdullah F.; Robeson, Scott M. (Ecological Indicators, 2018)
Mangroves have been massively degraded and deforested throughout the world, despite their known ecological and economic values. This study demonstrates the use of ALOS Global Digital Surface Model World (AW3D30) DSM dataset acquired between 2006 and 2011 to map canopy height of different succession stages of mangroves. We employed our previously developed canopy height model for assessing mangrove canopy height in three sites that vary in latitudinal position and mangrove degradation levels, ranging from relatively pristine mangrove ecosystems in Mimika Papua, Indonesia and Sundarbans, Bangladesh to severely degraded mangrove ecosystems in the Mahakam Delta, Indonesia. The study demonstrates good agreement between modeled and measured canopy height from these three sites as indicated by small mean absolute errors of 3.38 m at Mimika, 2.54 m at Sundarbans, and 2.89 m in the Mahakam Delta site. These findings further showed that, in the absence of synthetic aperture radar (SAR) based elevation data (such as SRTM and TanDEM-X), the ALOS PRISM data can be used to map mangrove heights (or in combination with SAR-based elevation data). Our results also pointed out that the ALOS data can differentiate the variability of canopy height estimation between an intact mangrove and severely degraded mangrove ecosystem.

Iron deficiency in seagrasses and macroalgae in the red sea is unrelated to latitude and physiological performance - Anton, Andrea; Hendriks, Iris E.; Marbà, Núria; Krause-Jensen, Dorte; Garcias-Bonet, Neus; Duarte, Carlos M. (Frontiers in Marine Science, 2018)
Iron can limit primary production in shallow marine systems, especially in tropical waters characterized by carbonated sediments, where iron is largely trapped in a non-available form. The Red Sea, an oligotrophic ecosystem characterized by a strong N-S latitudinal nutrient gradient, is a suitable setting to explore patterns in situ of iron limitation in macrophytes and their physiological performance under different iron regimes. We assessed the interactions between environmental gradients and physiological parameters of poorly-studied Red Sea macrophytes. Iron concentration, chlorophyll a concentration, blade thickness, and productivity of 17 species of macrophytes, including seven species of seagrasses and 10 species of macroalgae, were measured at 21 locations, spanning 10 latitude degrees, along the Saudi Arabian coast. Almost 90% of macrophyte species had iron concentrations below the levels indicative of iron sufficiency and more than 40% had critically low iron concentrations, suggesting that iron is a limiting factor of primary production throughout the Red Sea. We did not identify relationships between tissue iron concentration, chlorophyll a concentration and physiological performance of the 17 species of seagrass and macroalgae. There was also no latitudinal pattern in any of the parameters studied, indicating that the South to North oligotrophication of the Red Sea is not reflected in iron concentration, chlorophyll a concentration or productivity of Red Sea macrophytes.

Menilai Penggunaan Data Penginderaan Jauh untuk Memetakan Mangrove - Argasetiawan; Donato, Daniel C.; Kauffman, J. Boone; Murdiyarso, Daniel; Kurnianto, Sofyan; Stidham, Melanie; Kanninen, Markku; Mauko, Imanuel Christian; Setiohardjo, Nicodemus Mardanus; Noach, Fredrik Paulus; Karizal, Inal; Sardiana, I; et al. (TOPIK TERPILIH dalam SISTEM KEKUATAN dan PENGinderaan JAUH, 2018)
Mangrove merupakan salah satu sumberdaya pesisir penting ditinjau dari fungsi ekonomis dan ekologisnya. Fungsi tersebut telah dibahas secara luas oleh banyak ahli, sehingga data mangrove dan perubahannya dari waktu ke waktu sangat dibutuhkan terutama oleh para perencana dan pengambil keputusan mengenai sumberdaya dan pembangunan pesisir. Untuk memenuhi kebutuhan tersebut perlu dilakukan pemetaan tegakan mangrove secara akurat dan perubahannya dari waktu ke waktu. Kemajuan teknik penginderaan jauh memberikan peluang besar untuk pemetaan mangrove meskipun memiliki kelemahan. Selain itu, tegakan mangrove relatif mudah diidentifikasi karena jenis vegetasi ini sangat khas dibandingkan dengan tutupan pantai lainnya, sehingga dapat dengan mudah dikenali dan digambarkan dari sebagian besar citra satelit. Permasalahan muncul ketika pemetaan mangrove harus dilakukan secara nasional di wilayah yang sangat luas seperti Indonesia. Masalah berkisar dari teknis, keuangan hingga pengelolaan data. Makalah ini akan membahas peluang dan tantangan penerapan teknik penginderaan jauh untuk pemetaan mangrove di Indonesia berdasarkan pengalaman Pusat Survei Sumber Daya Laut, Badan Koordinasi Survei dan Pemetaan Nasional (BAKOSURTANAL) dalam pemetaan mangrove Indonesia tahun 2009. Kata

National Policy Opportunities to Support Blue Carbon Conservation - Sutton-Grier, Ariana E.; Brody, Carly; Kunz, Michael; Herr, Dorothee; García, Elisa López; Wylie, Lindsay; Rosette, Minerva; Kairo, James G. (A Blue Carbon Primer, 2018)
The international climate community is increasingly recognizing the role of natural systems in climate change mitigation, including the role of coastal wetlands as effective long-term carbon (C) sinks. The Dominican Republic’s current national climate change policy is aligned with national development strategies and sector strategies. Legislation is based on the international conventions and agreements ratified by the Dominican Government, such as the UN Convention on Climate Change Framework and the Kyoto Protocol. The National Council for Climate Change will manage the Measurement, Reporting, and Verification (MRV) mechanism for blue C. The MRV mechanism is used in international agreements on climate change and refers to states’ actions to collect data on emissions and mitigation actions and publish this information in reports and inventories. Indonesia’s blue C ecosystems are among the most threatened, with high levels of mangrove deforestation, cleared to make room for aquaculture or converted into plantations, often for palm oil.

Nekton communities as indicators of habitat functionality in Philippine mangrove plantations - Salmo, Severino G.; Tibbetts, Ian R.; Duke, Norman C. (Marine and Freshwater Research, 2018)
In the present study, we investigated the changes to nekton communities with increasing mangrove forest age and relationships between nekton and the mangrove vegetation, mangrove sediments and environmental variables. The nekton community was assessed as a potential indicator for evaluating habitat functionality of mangrove planting programs. In all, 99 species from 52 families were captured, including crabs, shrimp, squid and fish. The crustacean assemblage was dominated by Portunidae and Penaeidae, whereas the fish assemblage was dominated by Atherinidae, Apogonidae, Hemirhamphidae, Tetraodontidae, Congridae, Sphyraenidae, Murraenidae, Ambassidae, Gerreidae, Clupeidae, Platycephalidae, Gobiidae, Mullidae and Plotosidae, with these families accounting for 90% of all individuals collected. The species composition, abundance and biomass of the nekton community were not significantly correlated with mangrove vegetation and sediment variables, but were significantly associated with environmental variables, particularly proximity to reef and tidal inundation. The lack of correlations suggests that the whole nekton assemblage was not a useful indicator in evaluating the progress of restoring habitat functionality in these planted mangroves. However, a significant interaction with mangrove vegetation was found for non-fish components of the nekton. As such, crustaceans, particularly of the Portunidae and Penaeidae families, were useful indicators for determining the habitat functionality of planted mangroves.

Predators shape sedimentary organic carbon storage in a coral reef ecosystem - Atwood, Trisha B.; Madin, Elizabeth M.P.; Harborne, Alastair R.; Hammill, Edd; Luiz, Osmar J.; Ollivier, Quinn R.; Roelfsema, Chris M.; Macreadie, Peter I.; Lovelock, Catherine E. (Frontiers in Ecology and Evolution, 2018)
Trophic cascade theory predicts that predator effects should extend to influence carbon cycling in ecosystems. Yet, there has been little empirical evidence in natural ecosystems to support this hypothesis. Here, we use a naturally-occurring trophic cascade to provide evidence that predators help protect sedimentary organic carbon stocks in coral reef ecosystems. Our results show that predation risk altered the behavior of herbivorous fish, whereby it constrained grazing to areas close to the refuge of the patch reefs. Macroalgae growing in "riskier" areas further away from the reef were released from grazing pressure, which subsequently promoted carbon accumulation in the sediments underlying the macroalgal beds. Here we found that carbon stocks furthest away from the reef edge were ~24% higher than stocks closest to the reef. Our results indicate that predators and herbivores play an important role in structuring carbon dynamics in a natural marine ecosystem, highlighting the need to conserve natural predator-prey dynamics to help maintain the crucial role of marine sediments in sequestering carbon.

Predicting floodplain inundation and vegetation dynamics in arid wetlands - Sandi, Steven G.; Saco, Patricia M.; Kuczera, George; Wen, Li; Saintilan, Neil; Rodriguez, Jose F. (E3S Web of Conferences, 2018)
The Macquarie Marshes is a freshwater wetland system located in semiarid Australia. The ecological importance of this site has been recognized under the Ramsar convention. Plant associations in the marshes has shown a complex dynamic where some wetland vegetation patches have transitioned to terrestrial vegetation during severe drought, but also quickly responded to increased inflows due to record and near record rainfall accompanied by water releases from an upstream reservoir. Management decisions regarding the environmental flows require the use of predictive tools in order to assess the response of the vegetation. We have developed a vegetation response model that couples hydrodynamic modelling of the northern Macquarie Marshes with watering requirements of different plant associations and vegetation succession rules. The model simulates floods in the wetland during a series of years, after which patches of vegetation are analysed according to water depth, percent exceedance time and frequencies of inundation. During the simulated period, the patch can have adequate watering conditions, or it can have critical conditions that would lead to a succession to another type of vegetation. The predicted vegetation is reintroduced in the model, providing feedbacks for the next simulation period. In this contribution, we implemented the model to simulate changes of wetland understory during the period 1991 to 2014.

Reducing risk in reserve selection using Modern Portfolio Theory: Coastal planning under sea-level rise - Runting, Rebecca K.; Beyer, Hawthorne L.; Dujardin, Yann; Lovelock, Catherine E.; Bryan, Brett A.; Rhodes, Jonathan R. (Journal of Applied Ecology, 2018)
Climate change is expected to impact many species and ecosystem services, although it is difficult to predict when and how these impacts may arise. Due to this uncertainty, it is difficult to plan management actions, such as designating protected areas, intended to adapt to climate change impacts. The danger of ignoring uncertainty is that resulting plans may fail to achieve conservation objectives, yet this is not usually incorporated in conservation planning. Recent studies have accounted for uncertainty by applying Modern Portfolio Theory—an approach for risk-sensitive resource allocation used in the finance sector—to conservation planning. However, these approaches are not directly applicable to many conservation planning problems that typically include discrete site selection, multiple conservation objectives and a consideration of connectivity. We extend previous applications of Modern Portfolio Theory by incorporating these additional conservation planning requirements in the context of designing a reserve system and apply it to conserving coastal wetlands and associated ecosystem services under uncertain rates of sea-level rise. This allows us to identify an optimal set of properties to preserve, while maintaining connectivity for landward migration of wetlands and accounting for risk. We compare spatial plans that resulted from our risk-sensitive approach to reserve selection that ignored risk to determine whether, and how, explicitly accounting for risk alters planning outcomes. We demonstrate that incorporating sea-level rise, but ignoring uncertainty, is a high-risk strategy, even when planning for the worst-case sea-level rise scenario. In contrast, diversifying site selection through Modern Portfolio Theory can ensure the supply of ecosystem services by reducing the risk of failure across all sea-level rise scenarios. Synthesis and applications. Climate change will continue to drive profound changes to socio-ecological systems that are difficult to predict. In this context, risk reduction in spatial planning is a neglected but essential strategy for avoiding comprehensive failure and improving the long-term effectiveness of conservation efforts. Modern Portfolio Theory, as presented here to account for the characteristics of real-world conservation planning problems, provides a rigorous way forward in dealing explicitly with risk for many conservation planning exercises.

Remote sensing of wetland types: Mangroves - Lucas, Richard; Fatoyinbo, Lola; Simard, Marc; Rebelo, Lisa Maria (The Wetland Book: I: Structure and Function, Management, and Methods, 2018)
Mangroves are characteristics of coastlines and occur primarily in the tropics and subtropical but extend to temperate regions. Remote sensing radar and optical and lidar data can be used to provide information on mangrove extent and also biophysical characteristics. Optical data are the most useful for differentiating species type, while radar and lidar data can be used, either singularly or in combination, to retrieve the three-dimensional structure (canopy height profiles, cover, and stem number density). Data from these sensors also provide information on changes in extent and biophysical properties, which can be applied at local to global levels. Lower frequency L-band radar data are particularly useful given their ability to operate regardless of weather and illumination conditions and significant efforts are being made to map the changing extent of mangroves at a global level using these data. Examples of capability are provided for Brazil, Australia, and South America.

Response to experimental warming in northern eelgrass populations: Comparison across a range of temperature adaptations - Beca-Carretero, P.; Olesen, B.; Marbà, N.; Krause-Jensen, D. (Marine Ecology Progress Series, 2018)
Global warming may exert diverging effects on eelgrass (Zostera marina L.) populations originating from the northern versus the central part of the distribution range and on populations growing at saturating versus limiting light. We experimentally examined growth and physiological temperature responses of 3 eelgrass populations adapted to different temperature regimes in subarctic Greenland (2 populations) and in Denmark (1 population). Shoots were incubated at 5 different temperatures (10, 15, 20, 25 and 28°C) for 15 to 16 d at a saturating irradiance (200 µmol m?2 s?1) and one of the populations was also incubated at a limited irradiance of 50 µmol m?2 s?1. All populations exhibited optimum temperatures of 20 to 25°C for photosynthesis and growth under saturating light, while light limitation reduced the optimum by 5 to 10°C. When compared at their respective in situ summer temperature (i.e. 10, 15 and 20°C), all populations exhibited similar relative growth rates, indicating a capacity for local adaptation. The 2 subarctic populations exhibited higher activation energy for growth and, hence, greater responsiveness to warming than the centrally located population. However, subarctic populations were also more sensitive to extreme high temperatures, showing faster increases in respiration rates and declines in photosynthesis. Sensitivity to warming varied across light conditions with light-limited plants being most vulnerable to extreme temperatures, causing a negative carbon budget. In conclusion, projected warming would stimulate the performance of subarctic eelgrass populations but could eventually compromise populations in the center of the distribution range, which currently grow close to their temperature optimum.

Reviews and syntheses: 210Pb-derived sediment and carbon accumulation rates in vegetated coastal ecosystems - Setting the record straight - Arias-Ortiz, Ariane; Masqué, Pere; Garcia-Orellana, Jordi; Serrano, Oscar; Mazarrasa, Inés; Marbá, Núria; Lovelock, Catherine E.; Lavery, Paul S.; Duarte, Carlos M. (Biogeosciences, 2018)
Vegetated coastal ecosystems, including tidal marshes, mangroves and seagrass meadows, are being increasingly assessed in terms of their potential for carbon dioxide sequestration worldwide. However, there is a paucity of studies that have effectively estimated the accumulation rates of sediment organic carbon (Corg), also termed blue carbon, beyond the mere quantification of Corg stocks. Here, we discuss the use of the 210Pb dating technique to determine the rate of Corg accumulation in these habitats. We review the most widely used 210Pb dating models to assess their limitations in these ecosystems, often composed of heterogeneous sediments with varying inputs of organic material, that are disturbed by natural and anthropogenic processes resulting in sediment mixing and changes in sedimentation rates or erosion. Through a range of simulations, we consider the most relevant processes that impact the 210Pb records in vegetated coastal ecosystems and evaluate how anomalies in 210Pb specific activity profiles affect sediment and Corg accumulation rates. Our results show that the discrepancy in sediment and derived Corg accumulation rates between anomalous and ideal 210Pb profiles is within 20% if the process causing such anomalies is well understood. While these discrepancies might be acceptable for the determination of mean sediment and Corg accumulation rates over the last century, they may not always provide a reliable geochronology or historical reconstruction. Reliable estimates of Corg accumulation rates might be difficult at sites with slow sedimentation, intense mixing and/or that are affected by multiple sedimentary processes. Additional tracers or geochemical, ecological or historical data need to be used to validate the 210Pbderived results. The framework provided in this study can be instrumental in reducing the uncertainties associated with estimates of Corg accumulation rates in vegetated coastal sediments.

Rural livelihoods and mangrove degradation in south-west Madagascar: Lime production as an emerging threat - Scales, Ivan R.; Friess, Daniel A.; Glass, Leah; Ravaoarinorotsihoarana, Lalao (ORYX, 2018)
Mangroves are heavily threatened globally, with fuelwood harvesting and charcoal production a growing threat in low-income nations. However, the socio-ecological dynamics of mangroves are poorly understood, especially the roles of poverty and wealth in shaping resource use. This is particularly the case with Madagascar's mangroves, which contribute 2% of global mangrove cover. We report on the use of and threats to mangroves in the Bay of Assassins in south-west Madagascar. We document the production of sokay, a sea-shell based lime produced in mangrove wood kilns and used as a render on houses to improve their durability. Lime rendered houses are considered a status symbol. Growth in the use of lime is related to a rise in income in some households, which is partly a result of the increased commodification of marine products such as octopus, seaweed and sea cucumber. These products have experienced rapid commercialization over the last decade, with fishers now supplying global markets. We also document evidence of the emergence of larger-scale lime production. The growth of lime production has major ramifications for mangrove cover. We have observed a worrying development in mangrove harvesting patterns tied to lime production, where mangrove ecosystems are cleared instead of selectively cut. We consider the implications of our findings for broader debates about the relationship between conservation, poverty and natural resource use. We highlight research priorities and discuss the policy implications of our research, especially the need for the integrated management of ecosystems.

Seagrass Organic Carbon Stocks Show Minimal Variation Over Short Time Scales in a Heterogeneous Subtropical Seascape - Samper-Villarreal, Jimena; Mumby, Peter J.; Saunders, Megan I.; Roelfsema, Chris; Lovelock, Catherine E. (Estuaries and Coasts, 2018)
Blue carbon initiatives require accurate monitoring of carbon stocks. We examined sources of variability in seagrass organic carbon (Corg) stocks, contrasting spatial with short temporal scales. Seagrass morphology and sediment Corg stocks were measured from biomass and shallow sediment cores collected in Moreton Bay, Australia. Samples were collected between 2012 and 2013, from a total of 77 sites that spanned a gradient of water turbidity. Environmental measures of water quality between 2000 and 2013 revealed strong seasonal fluctuations from summer to winter, yet seagrass biomass exhibited no temporal variation. There was no temporal variability in Corg stocks, other than below ground biomass stocks were slightly higher in June 2013. Seagrass locations were grouped into riverine, coastal, and seagrass loss locations and short temporal variability of Corg stocks was analysed within these categories to provide clearer insights into temporal patterns. Above ground Corg stocks were similar between coastal and riverine meadows. Below ground Corg stocks were highest in coastal meadows, followed by riverine meadows. Sediment Corg stocks within riverine meadows were much higher than at coastal meadows and areas of seagrass loss, with no difference in sediment Corg stocks between these last two categories. Riverine seagrass meadows, of higher turbidity, had greater total Corg stocks than meadows in offshore areas irrespective of time. We suggest that Corg stock assessment should prioritise sampling over spatial gradients, but repeated monitoring over short time scales is less likely to be warranted if environmental conditions remain stable.

Sediment stocks of carbon, nitrogen, and phosphorus in Danish eelgrass meadows - Kindeberg, Theodor; Ørberg, Sarah B.; Röhr, Maria Emilia; Holmer, Marianne; Krause-Jensen, Dorte (Frontiers in Marine Science, 2018)
Seagrass ecosystems provide an array of ecosystem services ranging from habitat provision to erosion control. From a climate change and eutrophication mitigation perspective, the ecosystem services include burial and storage of carbon and nutrients in the sediments. Eelgrass (Zostera marina) is the most abundant seagrass species along the Danish coasts, and while its function as a carbon and nutrient sink has been documented in some areas, the spatial variability of these functions, and the drivers behind them, are not well understood. Here we present the first nationwide study on eelgrass sediment stock of carbon (Cstock), nitrogen (Nstock), and phosphorus (Pstock). Stocks were measured in the top 10 cm of eelgrass meadows spanning semi-enclosed estuaries (inner and outer fjords) to open coasts. Further, we assessed environmental factors (level of exposure, sediment properties, level of eutrophication) from each area to evaluate their relative importance as drivers of the spatial pattern in the respective stocks. We found large spatial variability in sediment stocks, representing 155-4413 g C m-2, 24-448 g N m-2, and 7-34 g P m-2. Cstock and Nstock were significantly higher in inner fjords compared to outer fjords and open coasts. Cstock, Nstock, and Pstock showed a significantly positive relationship with the silt-clay content in the sediments. Moreover, Cstock was also significantly higher in more eutrophied areas with high concentrations of nutrients and chlorophyll a (chl a) in the water column. Conversely, silt-clay content was not related to nutrients or chl a, suggesting a spatial dependence of the importance of these factors in driving stock sizes and implying that local differences in sediment properties and eutrophication level should be included when evaluating the storage capacity of carbon, nitrogen, and phosphorus in Danish eelgrass meadows. These insights provide guidance to managers in selecting priority areas for carbon and nutrient storage for climate- and eutrophication mitigation initiatives.

Short-distance barriers affect genetic variability of Rhizophora mangle L. in the Yucatan Peninsula - Cisneros-de la Cruz, Diana J.; Martínez-Castillo, Jaime; Herrera-Silveira, Jorge; Yáñez-Espinosa, Laura; Ortiz-García, Matilde; Us-Santamaria, Roberth; Andrade, José L. (Ecology and Evolution, 2018)
The environmental variability at local scale results in different physiognomic types of mangrove forest. However, this variability has never been considered in studies of mangrove genetic variability. This study analyzed the genetic and morphological variability and structure of Rhizophora mangle at regional and local scales in the Yucatan Peninsula. Thirteen mangrove populations (eight scrub and five tall), located in seven sites, were sampled, and their morphological variability and relationship with the availability of phosphorus and salinity were analyzed. The diversity and genetic structure were estimated at different hierarchical levels with nine microsatellites, also Bayesian inference and Principal Coordinates Analysis were used. We found a great morphological variability of R. mangle that responded to local environmental variability and not to the precipitation gradient of the peninsula. The genetic diversity found in the peninsula was greater than that reported for other populations in Mexico and was grouped into two regions: the Gulf of Mexico and the Caribbean Sea. At a local scale, tall and scrub mangroves had significant genetic differentiation suggesting that ecological barriers promote genetic differentiation within sites. These results need to be considered in future population genetic studies and for mangrove management and conservation.

Subtidal benthic recruitment in a sub-Arctic glacial fjord system: Temporal and spatial variability and potential drivers - Ørberg, Sarah B.; Krause-Jensen, Dorte; Meire, Lorenz; Sejr, Mikael K. (Polar Biology, 2018)
Increasing glacial discharge may influence future recruitment patterns and growth rates of marine benthos in glacial fjords as changes in surface-water temperature and salinity as well as an increase in ice-scouring events. We deployed settling plates at three spatial and temporal scales in a sub-Arctic glacial fjord system to quantify spatial and temporal variation in the recruitment rates and early growth of subtidal marine benthos, and to determine potential drivers of recruitment. We found significant spatial variation in recruitment of benthos (flora and fauna) at both the small (20 m) and large (> 30 km) scale, indicating that both abiotic and biotic factors may be important. We observed that substrate modification by bushy macroalgae facilitated Mytilus spp. settlement, yet limited Semibalanus balanoides recruitment, underlining that timing in settlement of different species is important in structuring benthic communities. Spatial variation in physical parameters, such as temperature and salinity, likely affected growth and recruitment patterns of benthos (S. balanoides). Finally, we found large spatial and temporal variation in kelp recruitment varying from none to 5866 ind. m−2, with an annual production of more than 6000 g dw m−2 year−1. This large growth potential of kelp suggests recruitment as a bottleneck in kelp population dynamics. Conclusively, variation in sub-Arctic benthic recruitment and growth patterns may respond to changes in temperature and salinity, yet further effort is needed to elucidate potential drivers of benthic recruitment in a fast changing Arctic environment.

The Calcium Carbonate Cycle in Seagrass Ecosystems - Kennedy, Hilary; Fourqurean, James W.; Papadimitriou, Stathys (A Blue Carbon Primer, 2018)
Seagrass meadows are commonly associated with carbonate-rich soils in the sub-tropics and tropics, where the functional traits of seagrasses and the ecosystem supported by seagrass meadows facilitate the growth of calcareous organisms that contribute to the accumulation of detrital carbonate particles in the soil. This chapter outlines processes in seagrass ecosystems that contribute to calcium carbonate (CaCO3) production and accumulation in the underlying soils and how the relative rates of the organic carbon and the CaCO3 cycles affect chemical changes in the water column that determine the direction of the air-sea carbon dioxide exchange. The biogenic production of CaCO3 in seagrass ecosystems generally leads to local CaCO3 deposition and accumulation of CaCO3 stocks. The accumulation rate of CaCO3 soils underlying seagrass meadows has rarely been directly measured, with most current estimates derived from calculated rates of epiphyte production or from soil stocks of CaCO3 and soil accumulation rate, or from the alkalinity anomaly method from benthic incubations and seawater transects.

The effect of heterogeneous soil bulk density on root growth of field-grown mangrove species - Ola, Anne; Schmidt, Susanne; Lovelock, Catherine E. (Plant and Soil, 2018)
Background and aims: Mangroves harbour large organic carbon (C) reservoirs in their soils that are important in the global C cycle. The below-ground biomass of mangrove trees is a major contributor to these organic C stocks. Root system development tends to be highly plastic in response to environmental conditions such as soil bulk density (BD). Hence, this study aimed to assess the role of soil BD on mangrove root growth. Methods: Root in-growth bags filled with root-free soil ranging in BD from 0.2 to 1.2 g cm−3 were buried in the soil of three mangrove species. Results: Root image analysis indicated that BD had a significant positive effect on root length and root biomass suggesting trees increase biomass allocation to roots and enhance root elongation, possibly to increase the acquisition of water and nutrients in dense soils. However, the responses to variation in BD were species-specific which was attributed to differences in species growth rates and the background soil conditions. Conclusion: Soil BD affects mangrove root growth with dense patches likely to have increased root growth and organic C sequestration potential compared to less dense soil patches.

The role of consumers in structuring seagrass communities: Direct and indirect mechanisms - Nowicki, Robert J.; Fourqurean, James W.; Heithaus, Michael R. (Seagrasses of Australia: Structure, Ecology and Conservation, 2018)
Seagrass ecosystems were traditionally assumed to be structured by competition as well as by "bottom up forces" such as resource availability and disturbance. However, a wealth of new evidence demonstrates that exertion of "top down control" by animals may be widespread. The strength and direction of top down control is context dependent, however, and varies with properties of organisms, the community, and the physical environment. Consumers can facilitate, consume, or destroy primary producers, aid or inhibit seagrass reproduction, or alter bottom up processes with implications for the properties and persistence of seagrass ecosystems. Studies in Australian ecosystems have been critical in helping to elucidate the role of consumers in seagrass ecosystems. Specifically, work investigating the roles of megaherbivores and apex predators and the pioneering of novel experimental approaches which allow for cage-free manipulations of mesograzers have substantially furthered our understanding of top-down control. At the broadest scale, megagrazers are likely to dominate grazing pathways in Australian tropical and subtropical seagrass ecosystems, while macrograzers and mesograzers do so in temperate seagrass ecosystems. However, while we have learned much about mechanisms through which top-down control can operate and its effects on seagrass ecosystems, predicting which grazing pathways dominate at smaller spatial scales, and net herbivore effects on seagrasses in specific ecosystems remains challenging due to context dependence and the highly complex nature of species interactions. Anthropogenic impacts further complicate these relationships. Australian seagrass habitats possess unusual properties, including relatively intact populations of megafauna, remote and pristine locations, and distinctive oceanographic features which allow these habitats to provide unique insights of top down control in seagrass ecosystems.

Tree biomass quantity, carbon stock and canopy correlates in mangrove forest and land uses that replaced mangroves in Honda Bay, Philippines - Castillo, Jose Alan A.; Apan, Armando A.; Maraseni, Tek Narayan; Salmo, Severino G. (Regional Studies in Marine Science, 2018)
Mangrove forests are important carbon (C) sinks in the tropics that are threatened by tropical deforestation and land use conversion, especially in Southeast Asia. Yet quantitative estimates are limited on the biomass (i.e. aboveground, belowground, downed woody debris) and tree C stocks of secondary, and converted mangroves in Southeast Asia. While some related studies have been conducted in Latin America and Central Asia, there is a need to assess different geographical areas and regional ecosystems, as well as to consider the impacts of mangrove conversion to other land use types. In this study, tree biomass and tree C stocks of secondary mangrove forests and four types of land uses that replaced intact mangrove forests (abandoned aquaculture pond, abandoned salt pond, coconut plantation, and cleared mangroves) in the coast of Honda Bay, Philippines were quantified. Their relationships with selected canopy variables were evaluated. Our measurements revealed that mean tree biomass (±SE) of intact mangroves ranged from 22.4 ± 9.0 to 178.1 ± 32.0 Mg ha−1, which store 10–80 MgC ha−1 (mean: 47.9 ± 5.1 MgC ha−1). Leaf Area Index correlated with mangrove tree biomass C stock (r=0.67, p<0.05). In contrast, the biomass and tree C stock of the replacement land uses ranged from 0.1 ± 0 Mg ha−1 and 0.12 ± 0.1 MgC ha−1, respectively, in the abandoned aquaculture ponds to 12.0 ± 4.0 Mg ha−1 and 5.7 ± 1.5 MgC ha−1 in coconut plantation. Our results indicate the importance of mangroves in storing considerable amounts of C in tree biomass in the coastal area, and the C losses (46.5 Mg C ha−1 or 97% decline) in tree C stocks from conversion of mangroves to other land uses.

Valoración económica de los servicios ecosistémicos provistos por los manglares del Golfo de Nicoya - Hernández-Blanco, M; Costanza, R; Cifuentes-Jara, M (Conservación Internacional, 2018)
Los bosques de manglar han sido el ecosistema estuarino más estudiado en el Golfo de Nicoya, con una cobertura total de 20,739 ha. Debido a la naturaleza de bien público de muchos de los servicios ecosistémicos del manglar, no existen mercados para ellos y existe un potencial limitado para gestionarlos con los mercados convencionales. Y debido a las dificultades para estimar el valor de estos servicios no comercializados, los manglares a menudo están subvalorados en el análisis de costo-beneficio de la conservación en comparación a los usos comerciales del suelo, lo que provoca su degradación y pérdida. En este estudio se aplicó un enfoque híbrido para estimar el valor de los servicios ecosistémicos de los bosques de manglar en el Golfo de Nicoya, utilizando la transferencia de beneficios tradicional y la transferencia de beneficios modificada por expertos para 11 servicios ecosistémicos. Además se realizaron estudios primarios para 3 servicios ecosistémicos (pesca, regulación del clima y protección costera), incluyendo el uso de modelos de INVEST en combinación con la transferencia de beneficios. Usando la transferencia de beneficios tradicional, se estimó el valor económico de 11 servicios ecosistémicos de estos manglares en $812 millones por año (mediana = $88 millones por año), y el valor promedio total de los servicios ecosistémicos proporcionados por la extensión total de manglares en Costa Rica en $1.5 mil millones por año (mediana = $160 millones/año).

Water quality of inlets’ water bodies in a growing touristic barrier reef Island “Isla Holbox” at the Yucatan Peninsula - Rubio-Cisneros, N. T.; Herrera-Silveira, J.; Morales-Ojeda, S.; Moreno-Báez, M.; Montero, J.; Pech-Cárdenas, M. (Regional Studies in Marine Science, 2018)
Holbox Island faces issues related to the availability of freshwater and living space given the increasing coastal migration and tourism development in the region. We report the water quality of 12 tidal inlets (which are geomorphological features of barrier islands), which neighbor hotels. Because no previous studies of tidal inlets exist on Holbox, we used reference published values of water quality and unpublished water values collected at 43 sampling sites throughout the Yalahau Lagoon. Analyses of water quality variables and the trophic index (TRIX) were measured. Inlets sites salinity values ranged from 11 to 36 psu. Average values for nitrates (0.83 μmol l−1), and nitrites (0.14 μmol l−1), at inlets, had lower values in the fronts season. Soluble reactive phosphate (48.8μmol l−1), and silicate (78.6 μmol l−1) were higher at inlets during rains and chlorophyll-α (29.7 mg/m3) was more top at inlets during fronts. TRIX values for inlets ranged between 2 and 6, indicating low water quality in most inlets associated with hotel sites. Seasonal changes in soluble reactive phosphate and chlorophyll-α at inlets suggests these could be receiving sewage water discharges from human activities. Besides inlet's higher water residence time and slower water interchange rate can favor the accumulation of pollutants. Results demonstrate that water quality issues exist on Holbox and need management actions to prevent the decay of coastal ecosystem services. These are necessary for positive feedback between local communities’ wellbeing and successful tourism development in the region.

A general framework for propagule dispersal in mangroves - Van der Stocken, Tom; Wee, Alison K.S.; De Ryck, Dennis J.R.; Vanschoenwinkel, Bram; Friess, Daniel A.; Dahdouh-Guebas, Farid; Simard, Marc; Koedam, Nico; Webb, Edward L. (Biological Reviews, 2019)
Dispersal allows species to shift their distributions in response to changing climate conditions. As a result, dispersal is considered a key process contributing to a species' long-term persistence. For many passive dispersers, fluid dynamics of wind and water fuel these movements and different species have developed remarkable adaptations for utilizing this energy to reach and colonize suitable habitats. The seafaring propagules (fruits and seeds) of mangroves represent an excellent example of such passive dispersal. Mangroves are halophytic woody plants that grow in the intertidal zones along tropical and subtropical shorelines and produce hydrochorous propagules with high dispersal potential. This results in exceptionally large coastal ranges across vast expanses of ocean and allows species to shift geographically and track the conditions to which they are adapted. This is particularly relevant given the challenges presented by rapid sea-level rise, higher frequency and intensity of storms, and changes in regional precipitation and temperature regimes. However, despite its importance, the underlying drivers of mangrove dispersal have typically been studied in isolation, and a conceptual synthesis of mangrove oceanic dispersal across spatial scales is lacking. Here, we review current knowledge on mangrove propagule dispersal across the various stages of the dispersal process. Using a general framework, we outline the mechanisms and ecological processes that are known to modulate the spatial patterns of mangrove dispersal. We show that important dispersal factors remain understudied and that adequate empirical data on the determinants of dispersal are missing for most mangrove species. This review particularly aims to provide a baseline for developing future research agendas and field campaigns, filling current knowledge gaps and increasing our understanding of the processes that shape global mangrove distributions.

A species-specific individual-based simulation model of mixed mangrove forest stands - Estacio, Ian; Quinton, Khristoffer Ryan; Macatulad, Edgardo; Salmo, Severino (SIMULTECH 2019 - Proceedings of the 9th International Conference on Simulation and Modeling Methodologies, Technologies and Applications, 2019)
A species-specific spatially explicit individual-based model has been developed to simulate the development of mixed mangrove forest stands featuring eight species. The model is a forest stand model that forecasts mangrove forest development in a 50 m x 50 m plot by simulating the recruitment, growth, and mortality of individual mangrove trees. Species-specific growth rates, shade responses, and salinity responses of each species were incorporated to observe differences in forest structure given different salinity conditions. The model used a modified Field of Neighborhood (FON) approach that considers species-specific responses to shading and a salinity response function that considers the species-specific salinity upper boundary value of optimum growth and maximum porewater salinity of a mangrove. Simulation results of 300 years given salinity conditions in a specific site in Katunggan It Ibajay (KII) showed matching dominant species in the site. Simulation results of 500 years given extreme low and high salinity values showed consistent forest dynamics where above-ground biomass and tree count approach certain limit values as the forest stand matures. Simulation results also of 300 years given salinity values ranging from 1 – 37 ppt showed the different dominant species for different salinity conditions.

Aerial root physiology: Reaching for the sky or down to earth? - Rasmussen, Amanda; Dobrijevic, Daisy P.; Ola, Anne; Ishaya, Findimila Dio; Lovelock, Catherine E. (Annual Plant Reviews Online, 2019)
Aerial roots have evolved in plants from diverse ecosystems, many facing specific environmental challenges associated with their natural or agricultural setting. In coastal species exposed to wind and waves, including mangroves, soft anoxic substrates have resulted in highly developed aerial root systems. In the rainforest, aerial roots of hemi-epiphytic figs enable life to begin higher in the canopy while climbing plants, such as ivy and Monsteras, depend on structurally very different aerial roots to climb vertical substrates. Maize, globally one of the three most important cereals, develops aerial roots presumably reducing lodging in high winds. In each of these cases, the dominant hypothesized role for aerial roots is to provide support and enabling greater heights to be reached. But do aerial roots of these plant groups also contribute to resource uptake and movement? This article explores the current knowledge of aerial root physiology and structure from each of these interesting and challenging environmental conditions and discusses how understanding these adaptations and niche requirements has value for improving crops, protecting our coastlines, improving our urban green spaces, and managing biodiversity conservation.

Assessing nutrient dynamics in mangrove porewater and adjacent tidal creek using nitrate dual-stable isotopes: A new approach to challenge the Outwelling Hypothesis? - Taillardat, Pierre; Ziegler, Alan D.; Friess, Daniel A.; Widory, David; David, Frank; Ohte, Nobuhito; Nakamura, Takashi; Evaristo, Jaivime; Thanh-Nho, Nguyen; Van Vinh, Truong; Marchand, Cyril (Marine Chemistry, 2019)
The importance of mangrove-derived material in sustaining coastal food webs (i.e. the Outwelling Hypothesis) is often invoked in support of mangroves conservation. Biogeochemical cycling, particularly nitrogen (N) and phosphorus (P) in mangrove ecosystems, however, is poorly understood because of high spatial heterogeneity and temporal variability of sources, sinks, and transformation pathways. Here we show that the distribution of N and P are intimately related to vegetation distribution, tidal cycles, and seasonality. We examined the dynamics of N and P in sediments and in a tidal creek of the Can Gio Mangrove Forest, Vietnam. Our objectives were to (1) determine the spatial distribution of dissolved inorganic nitrogen and phosphorus in the mangrove forest along a Rhizophora-Avicennia-mudflat transect; and (2) identify the respective inputs and transformation pathways of N and P in the water column via 24-h time series measurements in a tidal creek. Sediment porewater had N-NH4+ and N-NO3− concentrations <11 μM, except in the mudflat where N-NH4+ was as high as 162 μM. This difference was likely due to N-NH4+ uptake by trees in the vegetated areas and suggests that mangrove sediments can be a zone of NH4+ production via ammonification of organic nitrogen. In all stands, P-PO43− concentrations were three-fold higher during the wet season, with a maximum of 34.4 μM. This can be explained by enhanced microbial activity during the rainy season. The phosphorus seasonal trend was also observed in the creek water but with a maximum P-PO43− value of 4.3 μM only. In the tidal creek, N-NH4+ was highly variable (0 to 51 μM), with the higher values measured at low tide and related to porewater discharge from the mudflat. Our data suggest that mangroves act both as a sink of dissolved inorganic nutrients via vegetation uptake and a source of ammonium from unvegetated mudflat porewater towards the tidal creek. The dual stable isotopes approach (δ15NNO3 & δ18ONO3) revealed that this ammonium was later nitrified within the water column. Moreover, the approach showed that some nitrate originated from the river-estuarine system during rising tides. The export of ammonium from mangrove porewater is presumably entirely consumed before exiting the tidal creek, thereby limiting the spatial extent of mangrove Outwelling. Nevertheless, our multi-isotope approach leads us to conclude that nutrients recycling via mangrove-derived organic matter mineralization may play a fundamental role in sustaining coastal food web.

Asynchronous nitrogen supply and demand produce nonlinear plant allocation responses to warming and elevated CO2 - Noyce, Genevieve L.; Kirwan, Matthew L.; Rich, Roy L.; Megonigal, J. Patrick (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Terrestrial ecosystem responses to climate change are mediated by complex plant–soil feedbacks that are poorly understood, but often driven by the balance of nutrient supply and demand. We actively increased aboveground plant-surface temperature, belowground soil temperature, and atmospheric CO2 in a brackish marsh and found nonlinear and nonadditive feedbacks in plant responses. Changes in root-to-shoot allocation by sedges were nonlinear, with peak belowground allocation occurring at +1.7 °C in both years. Above 1.7 °C, allocation to root versus shoot production decreased with increasing warming such that there were no differences in root biomass between ambient and +5.1 °C plots in either year. Elevated CO2 altered this response when crossed with +5.1 °C, increasing root-to-shoot allocation due to increased plant nitrogen demand and, consequently, root production. We suggest these nonlinear responses to warming are caused by asynchrony between the thresholds that trigger increased plant nitrogen (N) demand versus increased N mineralization rates. The resulting shifts in biomass allocation between roots and shoots have important consequences for forecasting terrestrial ecosystem responses to climate change and understanding global trends.

Australian vegetated coastal ecosystems as global hotspots for climate change mitigation - Serrano, Oscar; Lovelock, Catherine E.; B. Atwood, Trisha; Macreadie, Peter I.; Canto, Robert; Phinn, Stuart; Arias-Ortiz, Ariane; Bai, Le; Baldock, Jeff; Bedulli, Camila; Carnell, Paul; Connolly, Rod M.; et al. (Nature Communications, 2019)
Policies aiming to preserve vegetated coastal ecosystems (VCE; tidal marshes, mangroves and seagrasses) to mitigate greenhouse gas emissions require national assessments of blue carbon resources. Here, we present organic carbon (C) storage in VCE across Australian climate regions and estimate potential annual CO2 emission benefits of VCE conservation and restoration. Australia contributes 5–11% of the C stored in VCE globally (70–185 Tg C in aboveground biomass, and 1,055–1,540 Tg C in the upper 1 m of soils). Potential CO2 emissions from current VCE losses are estimated at 2.1–3.1 Tg CO2-e yr-1, increasing annual CO2 emissions from land use change in Australia by 12–21%. This assessment, the most comprehensive for any nation to-date, demonstrates the potential of conservation and restoration of VCE to underpin national policy development for reducing greenhouse gas emissions.

Blue carbon in coastal landscapes: a spatial framework for assessment of stocks and additionality - Rogers, K.; Macreadie, P. I.; Kelleway, J. J.; Saintilan, N. (Sustainability Science, 2019)
Efforts to incorporate blue carbon, the carbon associated with marine ecosystems, into carbon accounting and carbon markets are increasing. To fully leverage the capacity of marine ecosystems to sequester carbon requires information to guide prioritisation of coastal landscapes for conservation and regeneration. A comprehensive landscape-scale assessment of mangrove and saltmarsh blue carbon requires information regarding vegetation cover, sedimentological and geomorphological factors. This information should also be integrated with socio-economic factors that alter natural processes of blue carbon accumulation and storage. The purpose of this study was to provide a framework for undertaking a first-pass assessment of blue carbon storage, preservation, generation and permanency in coastal landscapes, and to incorporate socio-economic factors that will influence blue carbon storage in coastal landscapes. This was achieved using readily available datasets that were analysed using a raster-based approach to develop a proxy indication of biophysical and socio-economic factors relevant for mangrove and saltmarsh blue carbon. The approach demonstrated that large catchments were associated with areas highly suitable for blue carbon storage, preservation, generation and permanency. Small catchments associated with mature barrier estuaries had the highest proportional area that provides potential blue carbon ecosystem services and climate mitigation benefits. The qualitative approach used does not replace high-resolution quantitative assessments of blue carbon storage, flux and detailed site-specific assessment of socio-economic factors that may influence blue carbon services; however, it can be used to guide prioritisation of blue carbon landscapes for further assessment prior to conservation and/or regeneration.

Blue carbon potential of coastal wetland restoration varies with inundation and rainfall - Negandhi, Karita; Edwards, Grant; Kelleway, Jeffrey J.; Howard, Dean; Safari, David; Saintilan, Neil (Scientific Reports, 2019)
There is a growing interest in how the management of ‘blue carbon’ sequestered by coastal wetlands can influence global greenhouse gas (GHG) budgets. A promising intervention is through restoring tidal exchange to impounded coastal wetlands for reduced methane (CH 4 ) emissions. We monitored an impounded wetland’s GHG flux (CO 2 and CH 4 ) prior to and following tidal reinstatement. We found that biogeochemical responses varied across an elevation gradient. The low elevation zone experienced a greater increase in water level and an associated greater marine transition in the sediment microbial community (16 S rRNA) than the high elevation zone. The low elevation zone’s GHG emissions had a reduced sustained global warming potential of 264 g m −2 yr −1 CO 2 -e over 100 years, and it increased to 351 g m −2 yr −1 with the removal of extreme rain events. However, emission benefits were achieved through a reduction in CO 2 emissions, not CH 4 emissions. Overall, the wetland shifted from a prior CH 4 sink (−0.07 to −1.74 g C m −2 yr −1 ) to a variable sink or source depending on the elevation site and rainfall. This highlights the need to consider a wetland’s initial GHG emissions, elevation and future rainfall trends when assessing the efficacy of tidal reinstatement for GHG emission control.

Building coastal resilience for disaster risk reduction and climate change adaptation through green-gray infrastructure - Bruins, Janet; Corwin, Emily; Pangilinan, Jocel; Pidgeon, Emily; Taylor, Stewart; Ng, Kit (International Conference on Sustainable Infrastructure 2019: Leading Resilient Communities through the 21st Century - Proceedings of the International Conference on Sustainable Infrastructure 2019, 2019)
Extreme weather events brought about by climate change have caused devastating impacts on communities in many parts of the world; affecting people's lives and infrastructure in an unprecedented manner. Extreme weather events are the most prominent risk facing humanity and 2017 was the most costly hurricane season on record. As extreme weather events increase in both intensity and frequency it is critical that preemptive solutions to mitigate disasters are found. Nowhere is this more true than in the Philippines where 62% of the country's population lives in coastal zones. The scale of devastation caused by Typhoon Haiyan in 2013 revealed a high degree of vulnerability among coastal and small island communities in a region regularly hit by tropical cyclones. The situation is expected to worsen with more frequent extreme events compounded by sea level rise. Conservation International (CI) in collaboration with Bechtel Corporation's Building Resilient Communities Program is piloting a new approach for coastal protection at two sites in the province of Iloilo, Philippines. The project integrates ecological solutions with engineering structures, providing green-gray infrastructure to alleviate the impact of extreme weather events. By blending green and gray techniques the environment becomes more adaptable and resilient than either technique applied alone. The concept designs, planned for implementation in 2019, use civil engineering techniques to establish and support the rehabilitation of mangrove communities. The long-term benefits of rehabilitating coastal mangrove forests in the region will mitigate climate change impacts and support community adaptation strategies.

Carbon and Nitrogen Concentrations, Stocks, and Isotopic Compositions in Red Sea Seagrass and Mangrove Sediments - Garcias-Bonet, Neus; Delgado-Huertas, Antonio; Carrillo-de-Albornoz, Paloma; Anton, Andrea; Almahasheer, Hanan; Marbà, Núria; Hendriks, Iris E.; Krause-Jensen, Dorte; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Coastal vegetated ecosystems are intense global carbon (C) sinks; however, seagrasses and mangroves in the Central Red Sea are depleted in organic C (Corg). Here, we tested whether Corg depletion prevails across the whole Red Sea, or if sediment Corg and nitrogen (N) stocks reflect the latitudinal productivity gradient of the Red Sea. We assessed Corg and N concentrations, stocks, isotopic compositions (δ13C and δ15N), and the potential contribution of primary producers to the organic matter accumulation in seagrass and mangrove sediments along the Eastern coast of the Red Sea. Sediment Corg concentration was higher in mangroves than seagrasses, while N concentrations were similar, resulting in higher C/N ratios in mangrove than seagrass sediments. Mangrove Corg stocks (integrated over the top 10 cm) were two-fold higher than those of seagrasses, respectively. N concentrations and stocks decreased from south to north in seagrass sediments matching the productivity gradient while Corg concentrations and stocks were uniform. The δ15N decreased from south to north in seagrass and mangrove sediments, reflecting a shift from nitrate and nitrite as N sources in the south, to N2 fixation towards the north. Stable isotope mixing models showed that seagrass leaves and macroalgae blades were the major contributors to the organic matter accumulation in seagrass sediments; while mangrove leaves were the major contributors in mangrove sediments. Overall, vegetated sediments in the Red Sea tend to be carbonate-rich and depleted in Corg and N, compared to coastal habitats elsewhere. Specifically, mean Corg stocks in Red Sea seagrass and mangrove sediments (7.2 ± 0.4 and 14.5 ± 1.4 Mg C ha-1, respectively) are lower than previously reported mean global values. This new information of Blue Carbon resources in the Red Sea provides a background for Blue Carbon programs in the region while also helping to balance global estimates.

Carbon sequestration and fluxes of restored mangroves in abandoned aquaculture ponds - Sidik, Frida; Fernanda Adame, Maria; Lovelock, Catherine E. (Journal of the Indian Ocean Region, 2019)
There has been a growing interest in restoring mangroves to reduce and offset carbon (C) emissions, but it is still unknown whether restored mangroves provide ‘blue carbon’ services similar to natural ones. This study aimed to determine if 10 year-old restored mangroves in abandoned aquaculture ponds in Perancak Estuary, Bali have similar net primary productivity (NPP) and C sequestration to those of intact mangroves. Tidal re-instatement in the ponds has occurred and facilitated mangrove regeneration and sediment accumulation. We found that NPP were similar between natural and restored mangroves. Soil C sequestration in restored mangroves was similar to the natural mangroves, but the soil respiration (CO2 efflux) was lower. The source of C in mangrove sediments was mainly of mangrove origin, confirming the role of NPP in sediment C sequestration. We suggest that many components of the carbon cycle of the mangroves have been restored within 10 years since the reestablishment of the mangrove.

Climate Change in Areas of the Gulf of Mexico With High Freshwater Input – A Review of Impacts and Potential Mitigation - Day, J.W.; Lara Dominguez, A.L.; Herrera-Silveira, J.; Paul Kemp, G. (JAINA Costas y Mares ante el Cambio Climático, 2019)
The Gulf of Mexico currently spans the transition from tropical to temperate coastal ecosystems but this is changing as the northern Gulf undergoes tropicalization and the entire Gulf will become tropical in this century. The objective of this paper was to review information on climate change impacts on coastal ecosystems with high freshwater input for the Gulf of Mexico and review mitigation measures for dealing with climate change. There are two high freshwater discharge areas, one surrounding the Mississippi River in the north central Gulf and one in the southern Gulf, which is associated with the Grijalva-Usumacinta River and adjacent rivers and ground water discharge from the Yucatan Peninsula. Both of these areas are characterized by extensive coastal wetlands, and in the southern Gulf, submerged aquatic vegetation. These coastal ecosystems support important natural resources, have high petroleum production, and important maritime trade. Climate change will impact both of these areas strongly. Sea level is projected to increase by a meter or more by 2100 and there will be more strong hurricanes that will be larger, have more intense rainfall, will move slower, and the rate of intensification will increase. In the north, peak Mississippi River discharge is projected to increase by 10 to 60%. In the southern Gulf, it is projected that precipitation and freshwater discharge will decrease associated with the Mesoamerican climate hotspot. Coastal management to accommodate climate change should mimic ecosystem functioning. Specific actions include protection of natural areas, full use of freshwater and sediment resources, maintain con-nections between freshwater input and coastal systems, allow inland migration of coastal wetlands, and careful management of land use changes. Keywords: Gulf of Mexico, climate change impacts, coastal ecossytems.

Community structure and distribution of benthic Bacteria and Archaea in a stratified coastal lagoon in the Southern Gulf of Mexico - Cadena, Santiago; Aguirre-Macedo, M. Leopoldina; Cerqueda-García, Daniel; Cervantes, Francisco J.; Herrera-Silveira, Jorge A.; García-Maldonado, José Q. (Estuarine, Coastal and Shelf Science, 2019)
Coastal lagoons are important aquatic systems with strong physicochemical gradients, where the participation of microorganisms in biogeochemical cycles has been well recognised; however, to date, the microbial diversity and distribution in these environments remains under-investigated. Here, three distinguished regions (oligohaline, marine and the mixing) of a transitional coastal lagoon were explored to characterise the structure and composition of benthic microbial communities through 16S rRNA gene Illumina-sequencing, for both Bacteria and Archaea domains. Principal coordinate analysis showed differences in the community structure according to the analysed zones. PERMANOVA analysis evidenced that, of the measured variables, sample zonation and salinity were the main environmental factors explaining the variance of the prokaryotic assemblages. Differentially abundant microbial taxa were detected for each region of the lagoon by LEfSe analysis. Representative members of anaerobic methanogens/methanotrophs (Methanosaetaceae, ANME 1-b and WSA2) were enriched in the oligohaline sediments, while the coastal marine zone had a community represented mainly by Sandaracinaceae, Aminicenantes and Thaumarchaeota (Group-C3). The sediments in the mixing zone had higher abundance of Flavobacteriaceae, Syntrophobacteraceae and uncultured Thermoplasmatales, Bathyarchaeota and Lokiarchaeota. This study expands the available information of the composition and distribution of uncultured Bacteria and Archaea in transitional coastal lagoons, contributing to a systematic understanding of the functioning of these ecosystems.

Connected macroalgal-sediment systems: blue carbon and food webs in the deep coastal ocean - Queirós, Ana Moura; Stephens, Nicholas; Widdicombe, Stephen; Tait, Karen; McCoy, Sophie J.; Ingels, Jeroen; Rühl, Saskia; Airs, Ruth; Beesley, Amanda; Carnovale, Giorgia; Cazenave, Pierre; Dashfield, Sarah; et al. (Ecological Monographs, 2019)
Macroalgae drive the largest CO2 flux fixed globally by marine macrophytes. Most of the resulting biomass is exported through the coastal ocean as detritus and yet almost no field measurements have verified its potential net sequestration in marine sediments. This gap limits the scope for the inclusion of macroalgae within blue carbon schemes that support ocean carbon sequestration globally, and the understanding of the role their carbon plays within distal food webs. Here, we pursued three lines of evidence (eDNA sequencing, Bayesian Stable Isotope Mixing Modeling, and benthic-pelagic process measurements) to generate needed, novel data addressing this gap. To this end, a 13-month study was undertaken at a deep coastal sedimentary site in the English Channel, and the surrounding shoreline of Plymouth, UK. The eDNA sequencing indicated that detritus from most macroalgae in surrounding shores occurs within deep, coastal sediments, with detritus supply reflecting the seasonal ecology of individual species. Bayesian stable isotope mixing modeling [C and N] highlighted its vital role in supporting the deep coastal benthic food web (22–36% of diets), especially when other resources are seasonally low. The magnitude of detritus uptake within the food web and sediments varies seasonally, with an average net sedimentary organic macroalgal carbon sequestration of 8.75 g C·m−2·yr−1. The average net sequestration of particulate organic carbon in sediments is 58.74 g C·m−2·yr−1, the two rates corresponding to 4–5% and 26–37% of those associated with mangroves, salt marshes, and seagrass beds, systems more readily identified as blue carbon habitats. These novel data provide important first estimates that help to contextualize the importance of macroalgal-sedimentary connectivity for deep coastal food webs, and measured fluxes help constrain its role within global blue carbon that can support policy development. At a time when climate change mitigation is at the foreground of environmental policy development, embracing the full potential of the ocean in supporting climate regulation via CO2 sequestration is a necessity.

Decreasing carbonate load of seagrass leaves with increasing latitude - Mazarrasa, Inés; Marbà, Núria; Krause-Jensen, D.; Kennedy, Hilary; Santos, Rui; Lovelock, Catherine E.; Duarte, Carlos M. (Aquatic Botany, 2019)
Seagrass meadows play a significant role in the formation of carbonate sediments, serving as a substrate for carbonate-producing epiphyte communities. The magnitude of the epiphyte load depends on plant structural and physiological parameters, related to the time available for epiphyte colonization. Yet, the carbonate accumulation is likely to also depend on the carbonate saturation state of seawater (Ω) that tends to decrease as latitude increases due to decreasing temperature and salinity. A decrease in carbonate accumulation with increasing latitude has already been demonstrated for other carbonate producing communities. The aim of this study was to assess whether there was any correlation between latitude and the epiphyte carbonate load and net carbonate production rate on seagrass leaves. Shoots from 8 different meadows of the Zostera genus distributed across a broad latitudinal range (27 °S to up to 64 °N) were sampled along with measurements of temperature and Ω. The Ω within meadows significantly decreased as latitude increased and temperature decreased. The mean carbonate content and load on seagrass leaves ranged from 17% DW to 36% DW and 0.4–2.3 mg CO3 cm−2, respectively, and the associated mean carbonate net production rate varied from 0.007 to 0.9 mg CO3 cm−2 d-1. Mean carbonate load and net production rates decreased from subtropical and tropical, warmer regions towards subpolar latitudes, consistent with the decrease in Ω. These results point to a latitudinal variation in the contribution of seagrass to the accumulation of carbonates in their sediments which affect important processes occurring in seagrass meadows, such as nutrient cycling, carbon sequestration and sediment accretion.

Deep penetration of kelps offshore along the west coast of Greenland - Krause-Jensen, Dorte; Sejr, Mikael K.; Bruhn, Annette; Rasmussen, Michael B.; Christensen, Peter Bondo; Hansen, Jørgen L.S.; Duarte, Carlos M.; Bruntse, Grethe; Wegeberg, Susse (Frontiers in Marine Science, 2019)
Until recently, Arctic kelp forests were so understudied that they did not even appear in global kelp forest maps. An increasing focus on Arctic coastal ecosystems has documented extended kelp forests along Arctic coastlines but the distribution of the forests is still not well documented and opens up for surprises. Here, we report kelp depth limits deeper than 61 m (median: 38.4 m, 10-90% percentiles: 10.8-54.4 m) in the Disko Bay region, Greenland, at latitudes of 67-70°N. We compiled, for comparison, existing records of kelp depth limits in high latitude (50°N) regions (median: 17.7 m, 10-90% percentiles: 9.0-38.1 m), which underline that the Disko Bay kelps hold a depth-record for this region. The deepest kelps were located at offshore sites beyond the Disko Island and the main coast. The clear waters offshore with euphotic zones (1% of surface irradiance) extending to 67 m depth provide, along with deep rocky seafloors and low density of sea urchins, the basis for these deep kelps. The sites were ice-covered for 77-133 days year-1, which is beyond the length of the polar night (30-60 days year-1) in the region, suggesting a potential for further depth penetration of kelp forests in a future with longer open water periods and more light potentially reaching the seafloor.

Detecting inundation thresholds for dryland wetland vulnerability - Sandi, Steven G.; Saco, Patricia M.; Saintilan, Neil; Wen, Li; Riccardi, Gerardo; Kuczera, George; Willgoose, Garry; Rodríguez, José F. (Advances in Water Resources, 2019)
Dryland wetlands receiving periodical floods are of key importance for ecological resilience. The inundation regime (i.e., frequency, duration, depth, and timing of inundation), is one of the major factors that determine the suitability of local conditions for specific wetland species. During droughts, inundation conditions can reach a threshold after which wetland vegetation could transition to dryland vegetation. This study analyses the response of vegetation to hydrologic variability in an arid wetland in Australia over a period of 22 years (including the Millennium drought) in order to identify inundation thresholds for transitions. We use numerical modelling, field observations and remote sensing data to relate continuous detailed simulations of the inundation regime with the response of patches of Common reed, Water couch and River red gum, three key vegetation associations in the study site. We focus in patches that were affected by the drought and presented dryland vegetation invasion as well as reference patches that remained healthy throughout the drought. On each patch, we compare annual and inter-annual simulated inundation regimes to the minimum inundation conditions that can support the specific vegetation, and we compute the percentage area of the patch that verifies minimum inundation for each year. We define this area percentage as minimum inundation index. This index is analysed in conjunction with Landsat derived information on green vegetation coverage (green Seasonal Fractional Cover) for the selected patches. We found that the minimum inundation index and inter annual frequency are able to describe the vegetation dynamics of the patches, which can be characterised by two distinct response modes that depend on a threshold value of the minimum inundation index. Inundation below the threshold noticeably leads to degraded vegetation, but the vegetation can recover quickly if this threshold is later maintained for one or two years. Values below the threshold for more extended periods (drought) result in a gradual decrease of wetland vegetation to almost complete disappearance after four years and subsequent dryland vegetation invasion.

Effect of land-use and land-cover change on mangrove blue carbon: A systematic review - Sasmito, Sigit D.; Taillardat, Pierre; Clendenning, Jessica N.; Cameron, Clint; Friess, Daniel A.; Murdiyarso, Daniel; Hutley, Lindsay B. (Global Change Biology, 2019)
Mangroves shift from carbon sinks to sources when affected by anthropogenic land-use and land-cover change (LULCC). Yet, the magnitude and temporal scale of these impacts are largely unknown. We undertook a systematic review to examine the influence of LULCC on mangrove carbon stocks and soil greenhouse gas (GHG) effluxes. A search of 478 data points from the peer-reviewed literature revealed a substantial reduction of biomass (82% ± 35%) and soil (54% ± 13%) carbon stocks due to LULCC. The relative loss depended on LULCC type, time since LULCC and geographical and climatic conditions of sites. We also observed that the loss of soil carbon stocks was linked to the decreased soil carbon content and increased soil bulk density over the first 100 cm depth. We found no significant effect of LULCC on soil GHG effluxes. Regeneration efforts (i.e. restoration, rehabilitation and afforestation) led to biomass recovery after ~40 years. However, we found no clear patterns of mangrove soil carbon stock re-establishment following biomass recovery. Our findings suggest that regeneration may help restore carbon stocks back to pre-disturbed levels over decadal to century time scales only, with a faster rate for biomass recovery than for soil carbon stocks. Therefore, improved mangrove ecosystem management by preventing further LULCC and promoting rehabilitation is fundamental for effective climate change mitigation policy.
Keywords: Paris Agreement; carbon emissions; carbon stocks; climate change mitigation; coastal wetlands; meta-analysis; restoration

Effect of seagrass on current speed: Importance of flexibility vs. shoot density - Fonseca, Mark S.; Fourqurean, James W.; Koehl, M. A.R. (Frontiers in Marine Science, 2019)
Water flow through seagrass beds transports nutrients, affects sediment stability and chemistry, and imposes hydrodynamic forces on shoots that alter canopy configuration. Past studies done under diverse conditions yielded conflicting results about the effects of shoot density on flow through seagrass bed canopies. We used eelgrass, Zostera marina, to study how the density of flexible shoots affect the hydrodynamics of seagrass beds in unidirectional water flow. By exposing randomly-arranged shoots of uniform length to current velocities controlled in a flume, the effects of shoot density and distance downstream from the bed edge could be determined without confounding factors. Comparison of velocity profiles within beds to those upstream of beds showed that flow was slower in the beds. However, shoot density, downstream distance, and current velocity did not affect the percent reduction in flow velocity in a bed. Turbulence enhances mixing of substances carried in the water. Here, turbulence intensity (index of the importance of turbulent velocity fluctuations relative to average current velocity) was lower when ambient flow was faster, but was not affected by shoot density or downstream position, Drag (hydrodynamic force on a shoot that bends it over in the flow direction) provides another measure of how the canopy affects flow experienced by a shoot. Drag was not affected by current velocity, shoot density, or downstream position in the bed. Gaps between shoots can enhance light and flow penetration into the canopy, but when shoots are bent over by flow, they can cover gaps. Faster ambient currents caused greater gap closure, which at each current speed was greater for high shoot densities. Thus, canopy gap closure did not correlate with percent flow reduction in grass beds or with drag on individual shoots, both of which were independent of shoot density and ambient current velocity. Since changing shoot density does not affect the flow in a grass bed exposed to a given ambient current, our results are inconsistent with the hypothesis that the high shoot densities observed in grass beds in habitats exposed to rapid flow are due to a direct, adaptive response of the grass to the flow environment.

Effects of crab burrows on sediment characteristics in a Ceriops australis-dominated mangrove forest - Gillis, Lucy Gwen; Snavely, Elise; Lovelock, Catherine; Zimmer, Martin (Estuarine, Coastal and Shelf Science, 2019)
The presence of mangrove trees and crab burrows potentially contribute to localized variation in sediment elevation and affect sediment characteristics in these ecosystems, but the interacting effects of trees and burrows are largely unknown. Using a field study and artificial burrow experiment, we investigated variation in sediment redox potential, organic matter content, carbon to nitrogen ratios and activities of microbial communities related to presence and absence of trees and burrows. The presence of mangrove trees of the species Ceriops australis decreased the redox potential of the sediment, which may favor organic matter preservation, but no significant differences were observed in percent organic matter in sediment next to trees versus distant from trees. The effects of C. australis on sediment redox conditions were counteracted by the presence of crab burrows in deeper (20 cm) sediments. The utilization of a variety of carbon sources by microbial communities varied between the surface of crab burrow walls and bulk sediment, indicating crab burrow-induced changes in microbial communities, whereas the presence of C. australis did not affect community-wide microbial activity patterns and did not interact with the effects of crab burrows. The novel artificial crab burrow-mimics replicated these results, where organic matter and carbon to nitrogen ratios did not change over the experiment course whilst redox did. Differences in carbon-utilization by microbial communities between artificial burrow walls and bulk sediment mimicked those between natural crab burrow walls and bulk sediment. Hence, in the environmental settings of this study, it was the presence of burrow structures rather than crabs that induced changes in microbial communities.

Evaluation of Mangrove Forest Change and Fragmentation in Mahakam Delta, East Kalimantan for Coastal Management - Kauffman, J. Boone; Adame, Maria Fernanda; Arifanti, Virni Budi; Schile-Beers, Lisa M.; Bernardino, Angelo F.; Bhomia, Rupesh K.; Donato, Daniel C.; Feller, Ilka C.; Ferreira, Tiago O.; Jesus Garcia, Maria del Carmen; MacKenzie, Richard A.; Megonigal, J. Patrick; et al. (Remote Sensing, 2019)
A global net loss of 12 percent of mangrove forests has occurred from 1975 to 2005, with present extent estimated at about 1,670,000 ha. The major causes of deforestation calculated across all the maps for the region were agriculture (81 percent), aquaculture (12 percent), and urban development (2 percent). Mangrove conversion for aquaculture development also occurred in Mahakam Delta and became a major cause of deforestation in this region. The aim of this research was to map mangrove zonation in Mahakam Delta, to identify change and fragmentation in Mahakam Delta, and to plan as well as evaluate the change in Mahakam Delta for restoring mangrove ecosystems. The method for mangrove zonation mapping was visual interpretation of remote sensing data. Remote sensing data that was used included Landsat imagery acquired on 1989, 1997, 2004, 2009 and 2015. To evaluate the changes, we used image subtraction method and morphological image processing method to obtain mangrove forest change and fragmentation respectively. The result includes six mangrove zonation classes :Avicennia spp., Nypa fruticans, Heriteira littoralis and Oncosperma tigillarium as a transition zone, tropical rain forest, aquaculture, and barren land. The mapping accuracy for 2015 is 94.1%. The percentage mangrove forest change into aquaculture in 1989, 1997, 2004, 2009 and 2015 is 2%, 15.7%, 58.9%, 58.4%, and 53.8%, respectively. Major change occurred between 1997 to 2004, which included a 40% change of mangrove in delta or 64,529.40 hectares. Nevertheless, fragmentation in mangrove forest still increases until 7,958.97 hectares or with 333 patches in 2015. Coastal management planning in Mahakam Delta involves mangrove ecology, economy, and community. Suitable management programs apply the integration system mangrove-aquaculture in existing or abandoned pond, or known as silvofisheries system. Rehabilitation can be conducted by mangrove planting in pond areas, with recommended locations consisting of four villages in Mahakam Delta. The selection of the locations considered human resource factors, accessibility, and nurseries.

Fingerprinting blue carbon: Rationale and tools to determine the source of organic carbon in marine depositional environments - Geraldi, Nathan R.; Ortega, Alejandra; Serrano, Oscar; Macreadie, Peter I.; Lovelock, Catherine E.; Krause-Jensen, Dorte; Kennedy, Hilary; Lavery, Paul S.; Pace, Michael L.; Kaal, Joeri; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Blue carbon is the organic carbon in oceanic and coastal ecosystems that is captured on centennial to millennial timescales. Maintaining and increasing blue carbon is an integral component of strategies to mitigate global warming. Marine vegetated ecosystems (especially seagrass meadows, mangrove forests, and tidal marshes) are blue carbon hotspots and their degradation and loss worldwide have reduced organic carbon stocks and increased CO2 emissions. Carbon markets, and conservation and restoration schemes aimed at enhancing blue carbon sequestration and avoiding greenhouse gas emissions, will be aided by knowing the provenance and fate of blue carbon. We review and critique current methods and the potential of nascent methods to track the provenance and fate of organic carbon, including: bulk isotopes, compound-specific isotopes, biomarkers, molecular properties, and environmental DNA (eDNA). We find that most studies to date have used bulk isotopes to determine provenance, but this approach often cannot distinguish the contribution of different primary producers to organic carbon in depositional marine environments. Based on our assessment, we recommend application of multiple complementary methods. In particular, the use of carbon and nitrogen isotopes of lipids along with eDNA have a great potential to identify the source and quantify the contribution of different primary producers to sedimentary organic carbon in marine ecosystems. Despite the promising potential of these new techniques, further research is needed to validate them. This critical overview can inform future research to help underpin methodologies for the implementation of blue carbon focused climate change mitigation schemes.

Global carbon and biomass implications of mangrove land use change 2000-2016 - Goldberg, L; Fatoyinbo, T; Lagomasino, D; Lee, S K; ... (…, 2019)
Mangrove forests are highly productive coastal carbon sinks, while also providing a range of economic and ecological services to neighboring coastal communities. High mangrove loss rates in many regions have continued into the 21st century, though a lack of understanding …

Global Mangrove Distribution, Aboveground Biomass, and Canopy Height - Simard, M.; Fatoyinbo, T.; Smetanka, C.; Rivera-monroy, V.H., Castaneda-mova, E.; Thomas, N.; Van der stocken, T.; Rivera-Monroy, V.H.; Castaneda, E.; Thomas, N.; Van der stocken, T.; Rivera-monroy, V.H., Castaneda-mova, E.; Thomas, N.; et al. (Oak Ridge National Laboratory (ORNL) Distributed Active Archive Center (DAAC), 2019)
This dataset characterizes the global distribution, biomass, and canopy height of mangrove-forested wetlands based on remotely sensed and in situ field measurement data. Estimates of 1) mangrove aboveground biomass (AGB), 2) maximum canopy height (height of the tallest tree), and 3) basal-area weighted height (individual tree heights weighted in proportion to their basal area) for the nominal year 2000 were derived across a 30-meter resolution global mangrove ecotype extent map using remotely-sensed canopy height measurements and region-specific allometric models. Results were validated with in situ canopy height measurements and aboveground biomass estimates from field plots distributed across three continents. Maps of the three data products are provided for each of 116 countries. Spatially explicit maps of mangrove canopy height and AGB derived from space-borne remote sensing data and in situ measurements can be used to assess local-scale geophysical and environmental conditions that may regulate forest structure and carbon cycle dynamics. Maps revealed a wide range of canopy heights, including maximum values (> 62 m) that surpass maximum heights of other forest types. There are 348 data files in GeoTIFF format (.tif) with this dataset representing three data products for each of 116 countries.

Global-scale dispersal and connectivity in mangroves - Stocken, Tom Van Der; Carroll, Dustin; Menemenlis, Dimitris; Simard, Marc; Koedam, Nico (2019)

Groundwater enhances above-ground growth in mangroves - Hayes, Matthew A.; Jesse, Amber; Welti, Nina; Tabet, Basam; Lockington, David; Lovelock, Catherine E. (Journal of Ecology, 2019)
Groundwater flow through coastal wetlands plays an important role in the maintenance of productivity of intertidal ecosystems. Groundwater can reduce salinity and increase nutrient availability which can enhance plant growth and alter plant biomass allocation patterns. Here, we used stable isotopes of oxygen and hydrogen to assess how groundwater influences below-ground and above-ground growth in the widespread mangrove species Avicennia marina. We found source water within tree stems varied seasonally, with non-saline water use higher in the wet season when rainwater availability was highest compared to the dry season. Stems with higher proportional contribution of non-saline water had increased above-ground growth but no effect on below-ground growth. Below-ground growth was however influenced by nutrient availability across the intertidal zone which was higher in the high- compared to the low-intertidal zone. Synthesis. This study shows that mangroves use non-saline groundwater and rainwater when available rather than saline water sources. Groundwater flows into the intertidal stimulates organic matter accumulation in above-ground biomass suggesting the availability of non-saline water sources, such as groundwater and rainfall, are important for the growth and productivity of mangrove forests.

High-resolution mapping of biomass and distribution of marsh and forested wetlands in southeastern coastal Louisiana - Thomas, Nathan; Simard, Marc; Castañeda-Moya, Edward; Byrd, Kristin; Windham-Myers, Lisamarie; Bevington, Azure; Twilley, Robert R. (International Journal of Applied Earth Observation and Geoinformation, 2019)

Historical seagrass abundance of Florida Bay, USA, based on a foraminiferal proxy - Collins, Laurel S.; Cheng, Jie; Hayek, Lee Ann C.; Fourqurean, James W.; Buzas, Martin A. (Journal of Paleolimnology, 2019)
A foraminiferal proxy for seagrass abundance was developed, tested and used to construct a record of seagrass variability for Florida Bay, USA, since its initial flooding ~ 3800 cal years BP. Of 76 species recorded in the Bay, 13 seagrass-associated foraminifera were identified based on previously observed occurrences in seagrass beds of the region. Species that occurred more in seagrass beds than in other sediments were designated seagrass-associated foraminifera (SAF). SAF from six cores taken in four areas were tested against a large, well-studied seagrass die-off that began in 1987. SAF percentages of total foraminiferal assemblages declined in 1986 ( 210 Pb age, ± 2 years) with no recovery as of 2001 (the youngest core age), and discriminant analysis showed that SAF assemblages in 1970–1985 and 1986–2001 differed significantly. Results agree with observations of the decline in seagrass coverage, supporting SAF as a seagrass proxy for investigating earlier assemblages preserved in the cores. After anthropogenic influence began ~ 1880, the largest overall decreases in SAF percentages occurred in 1934–1940 ( 210 Pb ages, ± 5 years), possibly from decreased salinities due to three intense hurricanes that hit South Florida, and in 1987–2002 during the seagrass die-off. SAF assemblages in the oldest core record were significantly different over the four intervals of (1) initial flooding ~ 3800 cal years BP, (2) pristine conditions until ~ 1880 when agriculture and canal construction began, (3) anthropogenic and climatic influences 1880–1986, and (4) the 1987–2002 seagrass die-off. Historically, SAF assemblages indicate that this die-off resulted in extremely low coverage (comparable to inundation and development of the benthic ecosystem > 2500 cal years BP), probably a result of cumulative anthropogenic disturbance combined with natural events. This is the first study using foraminifera as a proxy to reconstruct the seagrass history of an area. The research introduced a new approach for developing a seagrass proxy_ we identified species that are more abundant in seagrass beds than in other sediments, and tested them together as a proxy against a previously documented seagrass die-off.

Impacts and adaptation options for estuarine vegetation in a large city - Rogers, Kerrylee; Mogensen, Laura A.; Davies, Peter; Kelleway, Jeffrey; Saintilan, Neil; Withycombe, Geoff (Landscape and Urban Planning, 2019)
Climate change adaptation options for natural systems are particularly challenging in high density urban settings. We model the vulnerability of estuarine vegetation (mangroves, saltmarshes and Casuarina forest) to sea-level rise in Australia's most populous city, Sydney, and conduct a detailed assessment of impacts and adaptation options for a densely urbanised estuary, the Cooks River. Our modelling demonstrates a range of opportunities for the preservation and, in some cases, expansion of estuarine vegetation area under sea-level rise, though this is largely dependent on the degree of flexibility applied in the management of existing open space. Mangrove area increases under a high sea-level rise scenario, more so than under a low sea-level rise scenario, due to opportunities for landward colonisation. However, this would require estuarine vegetation expansion and land-use conversion of recreational, industrial or private land. Sediment nourishment emerges as a potentially cost-efficient means of preserving wetlands. The mix of wetland types is likely to change without active management, with higher proportion of mangrove and substantially less saltmarsh under all scenarios. Implementation of living shorelines, as opposed to hard defensive structures, could be incentivised. This could be achieved by planning concessions, ‘payment for ecosystem services’ such as managing ‘blue carbon’ values, and zoning controls that promote visual amenity and ecological adaptation.

Important contribution of macroalgae to oceanic carbon sequestration - Ortega, Alejandra; Geraldi, Nathan R.; Alam, Intikhab; Kamau, Allan A.; Acinas, Silvia G.; Logares, Ramiro; Gasol, Josep M.; Massana, Ramon; Krause-Jensen, Dorte; Duarte, Carlos M. (Nature Geoscience, 2019)
The role of macroalgae in Blue Carbon assessments has been controversial, partially due to uncertainties about the fate of exported macroalgae. Available evidence suggests that macroalgae are exported to reach the open ocean and the deep sea. Nevertheless, this evidence lacks systematic assessment. Here, we provide robust evidence of macroalgal export beyond coastal habitats. We used metagenomes and metabarcodes from the global expeditions Tara Oceans and Malaspina 2010 Circumnavigation. We discovered macroalgae worldwide at up to 5,000 km from coastal areas. We found 24 orders, most of which belong to the phylum Rhodophyta. The diversity of macroalgae was similar across oceanic regions, although the assemblage composition differed. The South Atlantic Ocean presented the highest macroalgal diversity, whereas the Red Sea was the least diverse region. The abundance of macroalgae sequences attenuated exponentially with depth at a rate of 37.3% km−1, and only 24% of macroalgae available at the surface were expected to reach the seafloor at a depth of 4,000 m. Our findings indicate that macroalgae are exported across the open and the deep ocean, suggesting that macroalgae may be an important source of allochthonous carbon, and their contribution should be considered in Blue Carbon assessments.

In the blind-spot of governance – Stakeholder perceptions on seagrasses to guide the management of an important ecosystem services provider - Ruiz-Frau, Ana; Krause, Torsten; Marbà, Núria (Science of the Total Environment, 2019)
Seagrass ecosystems have been identified as important marine ecosystem service (ES) providers, they contribute to coastal protection, fisheries provision and mitigate climate change among others. Yet, they are declining globally at alarming rates. While the ecological dimensions of this social-ecological system have been well studied, its associated social aspects remain largely unexplored. Here, we show how the analysis of stakeholders' perceptions on seagrass ES, their drivers of change, links to wellbeing and governance structures can provide a path towards a more sustainable management. Stakeholders identified seagrass regulatory ES as crucial for the maintenance of social and economic wellbeing and the potential causes and consequences associated to seagrass decline. Power imbalances, an over-compartmentalized legislation and a generalized lack of awareness were highlighted as key aspects to redress in order to achieve a more just governance system. Stakeholders' empirical evidence on the importance of particular ES and on negative drivers of change can also provide an understanding of areas where financial investment would gather wider public support and therefore be more successfully implemented. We showed how the different dimensions highlighted through stakeholders' perspectives can contribute to the consecution of a more inclusive sustainable management, a crucial aspect in the maintenance of seagrass ecosystems.

Integrating imaging spectrometer and synthetic aperture radar data for estimating wetland vegetation aboveground biomass in coastal Louisiana - Jensen, Daniel; Cavanaugh, Kyle C.; Simard, Marc; Okin, Gregory S.; Castañeda-Moya, Edward; McCall, Annabeth; Twilley, Robert R. (Remote Sensing, 2019)
Aboveground biomass (AGB) plays a critical functional role in coastal wetland ecosystem stability, with high biomass vegetation contributing to organic matter production, sediment accretion potential, and the surface elevation's ability to keep pace with relative sea level rise. Many remote sensing studies have employed either imaging spectrometer or synthetic aperture radar (SAR) for AGB estimation in various environments for assessing ecosystem health and carbon storage. This study leverages airborne data from NASA's Airborne Visible/Infrared Imaging Spectrometer-Next Generation (AVIRIS-NG) and Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) to assess their unique capabilities in combination to estimate AGB in coastal deltaic wetlands. Here we develop AGB models for emergent herbaceous and forested wetland vegetation in coastal Louisiana. In addition to horizontally emitted, vertically received (HV) backscatter, SAR parameters are expressed by the Freeman-Durden polarimetric decomposition components representing volume and double-bounce scattering. The imaging spectrometer parameters include normalized difference vegetation index (NDVI), reflectance from 290 visible-shortwave infrared (VSWIR) bands, the first derivatives from those bands, or partial least squares (PLS) x-scores derived from those data. Model metrics and cross-validation indicate that the integrated models using the Freeman-Durden components and PLS x-scores improve AGB estimates for both wetland vegetation types. In our study domain over Louisiana'sWax Lake Delta (WLD), we estimated a mean herbaceous wetland AGB of 3.58 Megagrams/hectare (Mg/ha) and a total of 3551.31 Mg over 9.92 km2, and a mean forested wetland AGB of 294.78 Mg/ha and a total of 27,499.14 Mg over 0.93 km2. While the addition of SAR-derived values to imaging spectrometer data provides a nominal error decrease for herbaceous wetland AGB, this combination significantly improves forested wetland AGB prediction. This integrative approach is particularly effective in forested wetlands as canopy-level biochemical characteristics are captured by the imaging spectrometer in addition to the variable structural information measured by the SAR.

Land cover changes reduce net primary production in tropical coastal peatlands of West Kalimantan, Indonesia - Basuki, Imam; Kauffman, J. B.; Peterson, James; Anshari, Gusti; Murdiyarso, Daniel (Mitigation and Adaptation Strategies for Global Change, 2019)
Tropical peat swamp forests are carbon-rich ecosystems that have been threatened by high rates of land use change (LUC). Despite the ecosystem’s shifts from sequestering carbon (C) to emitting carbon, few studies have quantified the changes in ecosystem productivity associated with LUC in tropical peatlands. This study quantified net primary production (NPP) in intact peat swamp forests (PSF), logged forests (LPSF), early seral sites (ES), and smallholder oil palm plantations (OP) in a peat dome of West Kalimantan, Indonesia. All sites were dominated by peat forest prior to deforestation. The NPP of intact forests was 13.2 Mg C ha −1  year −1 making it among the world’s most productive terrestrial ecosystems, exceeding that of many tropical rainforests and similar to the most productive mangrove ecosystems (12.9 Mg C ha −1  year −1 ). Land cover change resulted in large shifts in NPP. Logged forest and early seral sites were < 11.1 Mg C ha −1  year −1 . The NPP of oil palm plantations was 3.7 Mg C ha −1  year −1 . Aboveground NPP was recorded at 10.5 Mg C ha −1  year −1 in forests, exceeding the NPP of LPSF, ES, and OP (8.9, 5.1, and 3.5 Mg C ha −1  year −1 , respectively). Early seral sites (5.7 Mg C ha −1  year −1 ) were estimated to have the highest belowground NPP (p = 0.05). Root productivity in PSF, LPSF, and OP was 2.7, 2.1, and 0.2 Mg C ha −1  year −1 , respectively. Land use change and forest degradation have reduced the productivity of tropical peatlands.

Land tenure considerations are key to successful mangrove restoration - Lovelock, Catherine E.; Brown, Benjamin M. (Nature Ecology and Evolution, 2019)

Landscape Evolution of a Fluvial Sediment-Rich Avicennia marina Mangrove Forest: Insights from Seasonal and Inter-annual Surface-Elevation Dynamics - Swales, A.; Reeve, G.; Cahoon, D. R.; Lovelock, C. E. (Ecosystems, 2019)
Mangrove forests are vulnerable to accelerated sea-level rise associated with climate warming because they occupy a relatively narrow zone on the mid-to-upper-intertidal flats. The fate of these ecosystems largely depends on their capacity to accrete sediment at a rate sufficient to maintain their elevation relative to sea level. We investigated the role of biophysical processes and feedbacks controlling surface-elevation dynamics in a fluvial sediment-rich Avicennia marina mangrove forest (New Zealand) at seasonal-to-inter-annual timescales (over 9 years) using the Rod Surface Elevation Table method. We found that sediment accretion in the forest was not measurably enhanced by episodic and short-lived storm discharges from rivers nor by elevated sea levels during storms. Critically, the coupling of frequent onshore winds and resulting resuspension of intertidal muds, with the fortnightly cycle of spring tide inundation, controlled sediment delivery and resulting accretion rates of 13 to 47 mm y−1. In turn, net surface-elevation trends of 0 to 28 mm y−1 were dominated by the physical processes of sediment accretion and shallow subsidence due to seasonal desiccation and resulting compaction of the infrequently inundated forest platform (4 to 16 mm y−1). Our data suggest that monthly and seasonal variation in tidally controlled hydroperiod and sediment delivery rather than episodic storm events are important for the maintenance of mangrove elevation within the intertidal zone.

Legal barriers and enablers for reintroducing tides: An Australian case study in reconverting ponded pasture for climate change mitigation - Bell-James, Justine; Lovelock, Catherine E. (Land Use Policy, 2019)
Across the globe, areas of the floodplain have been converted to agricultural use – often at the expense of natural ecosystems. In Australia, coastal wetlands have been transformed to ‘ponded pasture’ for cattle grazing which has resulted in a loss of saline wetlands, increased methane emissions, and impacts on species like fish and birds. Reconversion of these areas to saline wetlands is a potential climate change mitigation strategy, but given they occur at the intersection of private and public ownership regimes, some specific legal issues must be considered. This article provides an analysis of the legal enablers and barriers associated with reconverting ponded pastures or other hydrologically modified coastal land to saline wetlands for climate change mitigation, using Queensland, Australia as a case study. While projects are clearly possible, some of the key factors to consider in order to reduce legal risk and liability include: whether the law permits reflooding and what permits are required; clarifying land and carbon rights, which may require negotiation with the state government; and understanding the liabilities for potential impacts on adjacent land and biota.

Mangrove blue carbon in the Verde Island Passage - Salmo, Severino G (Archium Ateneo, 2019)
Coastal communities are deeply dependent on coastal ecosystems while being especially vulnerable to climate change. Intense typhoons, storm surge, and habitat loss due to coral bleaching are among the impacts that threaten their lives and livelihoods. These will only …

Mangrove cover and cover change analysis in the transboundary area of Kenya and Tanzania during 1986–2016 - Mungai, Fredrick; Kairo, James; Mironga, John; Kirui, Bernard; Mangora, Mwita; Koedam, Nico (Journal of the Indian Ocean Region, 2019)
Mangrove forests are among the most threatened ecosystems on earth. Some of these forests traverse national boundaries complicating their management due to differences in governance structures between countries. To improve the management of transboundary species regular monitoring is essential. Remotely sensed data were used to estimate forest cover and analyze conditions of mangroves in the proposed transboundary conservation area (TBCA) between Kenya and Tanzania. Image analysis was performed using unsupervised and supervised classification methods. The transboundary mangroves cover an estimated 11,906 ha; 55% being in Kenya, 45% in Tanzania. Ceriops tagal, Avicennia marina, and Rhizophora mucronata species co-dominate the mangroves of the transboundary area. The hotspot for loss and degradation of mangrove in the TBCA is Vanga in Kenya with a loss of 27 ha/yr. Harvesting of mangrove wood products have contributed to the loss of mangroves in the transboundary area. TBCA formation could play a critical role in ensuring sustainable mangrove resources utilization.

Mangroves and saltmarshes of Moreton Bay - Lovelock, C.E; Accad, A; Dowling, R; Duke, N; Yip, S.L; Ronan, M (Moreton Bay Quandamooka & Catchment: Past, present and future (The Morton Bay Foundation), 2019)
A custodial ethic, Indigenous values towards water in Moreton Bay and Catchments…………………………………………………………………………….…29-44

Mikoko Pamoja: A Demonstrably Effective Community-Based Blue Carbon Project in Kenya - Kairo, James G.; Hamza, A. J.; Wanjiru, C. (A Blue Carbon Primer: The State of Coastal Wetland Carbon Science, Practice and Policy, 2019)
Mikoko Pamoja is being executed in Gazi Bay area of the southern coast of Kenya, about 55km south of Mombasa in Kwale County. Community projects to be supported through Mikoko Pamoja are decided annually through village-level consultative meetings. Mikoko Pamoja is meeting the demand of 73% of 4,000 resident population by supplying water through water points or connecting water pipes directly into people’s houses. Mikoko Pamoja has improved education, water and sanitation systems, as well as the management of mangrove ecosystem in Gazi Bay. Mangrove forests in Kenya provide a range of ecosystem goods and services. A typical zonation of mangrove in Kenya starts with Sonneratia alba on the seaward margin, followed by large Avicennia and Rhizophora mucronata. Mangrove forests develop and sustain above- and belowground carbon (C) pools. Communication of the value of blue C in both economic terms and in terms of ecosystem services provided by mangrove habitats was key to community uptake of Mikoko Pamoja.

Mitigation and Adaptation Strategies for Global Change Land cover changes reduce net primary production in tropical coastal peatlands of - Basuki, Imam; Kauffman, J.B.; Peterson, James; Anshari, Gusti Z; Murdiyarso, Daniel (Mitigation and Adaptation Strategies for Global Change, 2019)
Tropical peat swamp forests are carbon-rich ecosystems that have been threatened by high rates of land use change (LUC). Despite the ecosystem's shifts from sequestering carbon (C) to emitting carbon, few studies have quantified the changes in ecosystem productivity associated with LUC in tropical peatlands. This study quantified net primary production (NPP) in intact peat swamp forests (PSF), logged forests (LPSF), early seral sites (ES), and smallholder oil palm plantations (OP) in a peat dome of West Kalimantan, Indonesia. All sites were dominated by peat forest prior to deforestation. The NPP of intact forests was 13.2 Mg C ha −1 year −1 making it among the world's most productive terrestrial ecosystems, exceeding that of many tropical rainforests and similar to the most productive mangrove ecosystems (12.9 Mg C ha −1 year −1). Land cover change resulted in large shifts in NPP. Logged forest and early seral sites were < 11.1 Mg C ha −1 year −1 . The NPP of oil palm plantations was 3.7 Mg C ha −1 year −1 . Aboveground NPP was recorded at 10.5 Mg C ha −1 year −1 in forests, exceeding the NPP of LPSF, ES, and OP (8.9, 5.1, and 3.5 Mg C ha −1 year −1 , respectively). Early seral sites (5.7 Mg C ha −1 year −1) were estimated to have the highest belowground NPP (p = 0.05). Root productivity in PSF, LPSF, and OP was 2.7, 2.1, and 0.2 Mg C ha −1 year −1 , respectively. Land use change and forest degradation have reduced the productivity of tropical peatlands. Mitig Adapt Strateg Glob Change https:

Natural and Regenerated Saltmarshes Exhibit Similar Soil and Belowground Organic Carbon Stocks, Root Production and Soil Respiration - Santini, Nadia S.; Lovelock, Catherine E.; Hua, Quan; Zawadzki, Atun; Mazumder, Debashish; Mercer, Tim R.; Muñoz-Rojas, Miriam; Hardwick, Simon A.; Madala, Bindu Swapna; Cornwell, William; Thomas, Torsten; Marzinelli, Ezequiel M.; et al. (Ecosystems, 2019)
Saltmarshes provide many valuable ecosystem services including storage of a large amount of ‘blue carbon’ within their soils. To date, up to 50% of the world’s saltmarshes have been lost or severely degraded primarily due to a variety of anthropogenic pressures. Previous efforts have aimed to restore saltmarshes and their ecosystem functions, but the success of these efforts is rarely evaluated. To fill this gap, we used a range of metrics, including organic carbon stocks, root production, soil respiration and microbial communities to compare natural and a 20-year restoration effort in saltmarsh habitats within the Sydney Olympic Park in New South Wales, Australia. We addressed four main questions: (1) Have above- and belowground plant biomass recovered to natural levels? (2) Have organic carbon stocks of soils recovered? (3) Are microbial communities similar between natural and regenerated saltmarshes? and (4) Are microbial communities at both habitats associated to ecosystem characteristics? For both soil organic carbon stocks and belowground biomass, we found no significant differences between natural and regenerated habitats (F(1,14) = 0.47, p = 0.5; F(1,42) = 0.08, p = 0.76). Aboveground biomass was higher in the natural habitat compared to the regenerated habitat (F(1,20) = 27.3, p < 0.0001), which may result from a site-specific effect: protection from erosion offered by a fringing mangrove forest in the natural habitat but not the regenerated habitat. Our microbial community assessment indicated that restored and natural saltmarsh habitats were similar at a phylum level, with the exception of a higher proportion of Proteobacteria in the rhizosphere of saltmarshes from the regenerated habitat (p < 0.01). Abundance of both Desulfuromonas and Geobacter was associated with high carbon and nitrogen densities in soils indicating that these genera may be key for the recovery of ecosystem characteristics in saltmarshes. Our restored and natural saltmarsh soils store at 30 cm depth similar levels of organic carbon: 47.9 Mg OC ha−1 to 64.6 Mg OC ha−1. Conservation of urban saltmarshes could be important for ‘blue carbon’ programmes aimed at mitigating atmospheric carbon dioxide.

Net heterotrophy and carbonate dissolution in two subtropical seagrass meadows - Van Dam, Bryce R.; Lopes, Christian; Osburn, Christopher L.; Fourqurean, James W. (Biogeosciences, 2019)
The net ecosystem productivity (NEP) of two seagrass meadows within one of the largest seagrass ecosystems in the world, Florida Bay, was assessed using direct measurements over consecutive diel cycles during a short study in the fall of 2018. We report significant differences between NEP determined by dissolved inorganic carbon (NEPDIC) and by dissolved oxygen (NEPDO), likely driven by differences in air-water gas exchange and contrasting responses to variations in light intensity. We also acknowledge the impact of advective exchange on metabolic calculations of NEP and net ecosystem calcification (NEC) using the "open-water" approach and attempt to quantify this effect. In this first direct determination of NEPDIC in seagrass, we found that both seagrass ecosystems were net heterotrophic, on average, despite large differences in seagrass net above-ground primary productivity. NEC was also negative, indicating that both sites were net dissolving carbonate minerals. We suggest that a combination of carbonate dissolution and respiration in sediments exceeded seagrass primary production and calcification, supporting our negative NEP and NEC measurements. However, given the limited spatial (two sites) and temporal (8 d) extent of this study, our results may not be representative of Florida Bay as a whole and may be season-specific. The results of this study highlight the need for better temporal resolution, accurate carbonate chemistry accounting, and an improved understanding of physical mixing processes in future seagrass metabolism studies.

Night and day: Shrinking and swelling of stems of diverse mangrove species growing along environmental gradients - Vilas, Maria P.; Adams, Matthew P.; Ball, Marilyn C.; Meynecke, Jan Olaf; Santini, Nadia S.; Swales, Andrew; Lovelock, Catherine E. (PLoS ONE, 2019)
Tree stems swell and shrink daily, which is thought to reflect changes in the volume of water within stem tissues. We observed these daily patterns using automatic dendrometer bands in a diverse group of mangrove species over five mangrove forests across Australia and New Caledonia. We found that mangrove stems swelled during the day and shrank at night. Maximum swelling was highly correlated with daily maxima in air temperature. Variation in soil salinity and levels of tidal inundation did not influence the timing of stem swelling over all species. Medium-term increases in stem circumference were highly sensitive to rainfall. We defoliated trees to assess the role of foliar transpiration in stem swelling and shrinking. Defoliated trees showed maintenance of the pattern of daytime swelling, indicating that processes other than canopy transpiration influence the temporary stem diameter increments, which could include thermal swelling of stems. More research is required to understand the processes contributing to stem shrinking and swelling. Automatic Dendrometer Bands could provide a useful tool for monitoring the response of mangroves to extreme climatic events as they provide high-frequency, long-term, and large-scale information on tree water status.

Nitrogen status regulates morphological adaptation of marsh plants to elevated CO2 - Lu, Meng; Herbert, Ellen R.; Langley, J. Adam; Kirwan, Matthew L.; Megonigal, J. Patrick (Nature Climate Change, 2019)
Coastal wetlands provide valuable ecosystem services that are increasingly threatened by anthropogenic activities1. The atmospheric carbon dioxide (CO2) concentration has increased from 280 ppm to 404 ppm since the Industrial Revolution and is projected to exceed 900 ppm by 2100 (ref. 2). In terrestrial ecosystems, elevated CO2 typically stimulates C3 plant photosynthesis and primary productivity leading to an increase in plant size3. However, compared with woody plants or crops4, the morphological responses of clonal non-woody plants to elevated CO2 have rarely been examined. We show that 30 years of experimental CO2 enrichment in a brackish marsh increased primary productivity and stem density but decreased stem diameter and height of the dominant clonal species Schoenoplectus americanus. Smaller, denser stems were associated with the expansion of roots and rhizomes to alleviate nitrogen (N) limitation as evidenced by high N immobilization in live tissue and litter, high tissue C:N ratio and low available porewater N. Changes in morphology and tissue chemistry induced by elevated CO2 were reversed by N addition. We demonstrate that morphological responses to CO2 and N supply in a clonal plant species influences the capacity of marshes to gain elevation at rates that keep pace with rising sea levels.

Participatory planning of a community-based payments for ecosystem services initiative in Madagascar's mangroves - Rakotomahazo, Cicelin; Ravaoarinorotsihoarana, Lalao Aigrette; Randrianandrasaziky, Dolce; Glass, Leah; Gough, Charlotte; Boleslas Todinanahary, Gildas Georges; Gardner, Charlie J. (Ocean and Coastal Management, 2019)
Although the dynamics of coastal resources are largely determined by the impacts of human users, spatially-explicit social data are rarely systematically integrated into coastal management planning in data-poor developing states. In order to plan a community-based mangrove payments for ecosystem services initiative in southwest Madagascar, we used two participatory approaches; public participation geographic information systems and concept modelling workshops – with 10 coastal communities to investigate the dynamics and spatial distribution of the mangrove resources they use. In each village we conducted participatory mapping of land and resource use with different livelihood groups using printed satellite images, and concept modelling workshops to develop concept models of the mangrove social-ecological system (including the identification of threats and underlying drivers, and proposals for targeted management strategies). Each community then proposed mangrove zoning consisting of strict conservation zones, sustainable use zones and restoration zones. Following validation and ground-truthing, the proposed zones and management strategies formed the basis of the zoning and management plan for the mangrove. Participatory approaches proved a simple and reliable way to gather spatial data and better understand the relationships between the mangrove and those who use it. Moreover, participation stimulated mangrove users to consider resource trends, the impacts of their activities, and required management actions, promoting a collective ‘buy-in’ for the project. Since participation extended beyond research to the development of management zones, rules and strategies, we believe that community ownership of the project has been strengthened and the chances of successfully conserving the mangrove improved.

Post-disturbance carbon stocks and rates of sequestration: Implications on "blue carbon" estimates in Philippine mangroves - Salmo Iii, Severino G; Lois, Eunice; Gianan, D (Philippine Science Letters, 2019)
angrove forest is one of the "blue carbon" ecosystems recognized for its high sequestration and long-term storage of carbon. While reports on blue carbon in mangroves are increasing, studies on the post-disturbance carbon stocks and rates of sequestration are still lacking in the Philippines. In this study, we assessed the stocks and rates of carbon sequestration in mangroves that were disturbed by typhoon and converted to aquaculture ponds. Carbon stocks were measured from the biomass and sediment compartments from typhoon-impacted sites (composed of natural and planted stands) and from mangrove-colonized abandoned fishponds. Using a stock-change approach, the rates of carbon sequestration were estimated at intra-annual and post-disturbance levels. Results showed wide variation in total carbon stocks and ranged from 168.96 to 355.70 Mg/ha (of which the biomass comprised 8.20 ± 4.18 % and the sediment with 92.84 ± 3.56 %). These values are 40-60 % lower than some SE Asian mangroves. Across sites, the post-disturbance rates of carbon sequestration (mean: 17.17 ± 0.57 Mg C/ha/yr) are similar with some studies and are within range from stands that are similarly recovering from disturbance. Our results indicate that disturbances contribute to changes in stocks and rates of carbon sequestration. Mangroves that colonized fishponds, although with relatively slower rates, have more stable carbon recovery. A more pro-active approach on the rehabilitation of abandoned fishponds (rather than leaving it to natural colonization process) is suggested to enhance carbon sequestration in Philippine mangroves.

Recent trend reversal for declining European seagrass meadows - de los Santos, Carmen B.; Krause-Jensen, Dorte; Alcoverro, Teresa; Marbà, Núria; Duarte, Carlos M.; van Katwijk, Marieke M.; Pérez, Marta; Romero, Javier; Sánchez-Lizaso, José L.; Roca, Guillem; Jankowska, Emilia; Pérez-Lloréns, José Lucas; et al. (Nature Communications, 2019)
Seagrass meadows, key ecosystems supporting fisheries, carbon sequestration and coastal protection, are globally threatened. In Europe, loss and recovery of seagrasses are reported, but the changes in extent and density at the continental scale remain unclear. Here we collate assessments of changes from 1869 to 2016 and show that 1/3 of European seagrass area was lost due to disease, deteriorated water quality, and coastal development, with losses peaking in the 1970s and 1980s. Since then, loss rates slowed down for most of the species and fast-growing species recovered in some locations, making the net rate of change in seagrass area experience a reversal in the 2000s, while density metrics improved or remained stable in most sites. Our results demonstrate that decline is not the generalised state among seagrasses nowadays in Europe, in contrast with global assessments, and that deceleration and reversal of declining trends is possible, expectingly bringing back the services they provide.

Role of carbonate burial in Blue Carbon budgets - Saderne, V.; Geraldi, N. R.; Macreadie, P. I.; Maher, D. T.; Middelburg, J. J.; Serrano, O.; Almahasheer, H.; Arias-Ortiz, A.; Cusack, M.; Eyre, B. D.; Fourqurean, J. W.; Kennedy, H.; et al. (Nature Communications, 2019)
Calcium carbonates (CaCO 3 ) often accumulate in mangrove and seagrass sediments. As CaCO 3 production emits CO 2 , there is concern that this may partially offset the role of Blue Carbon ecosystems as CO 2 sinks through the burial of organic carbon (C org ). A global collection of data on inorganic carbon burial rates (C inorg , 12% of CaCO 3 mass) revealed global rates of 0.8 TgC inorg yr −1 and 15–62 TgC inorg yr −1 in mangrove and seagrass ecosystems, respectively. In seagrass, CaCO 3 burial may correspond to an offset of 30% of the net CO 2 sequestration. However, a mass balance assessment highlights that the C inorg burial is mainly supported by inputs from adjacent ecosystems rather than by local calcification, and that Blue Carbon ecosystems are sites of net CaCO 3 dissolution. Hence, CaCO 3 burial in Blue Carbon ecosystems contribute to seabed elevation and therefore buffers sea-level rise, without undermining their role as CO 2 sinks.

Role of Eelgrass in the Coastal Filter of Contrasting Baltic Sea Environments - Asmala, Eero; Gustafsson, Camilla; Krause-Jensen, Dorte; Norkko, Alf; Reader, Heather; Staehr, Peter A.; Carstensen, Jacob (Estuaries and Coasts, 2019)
Coastal ecosystems act as filters of nutrients from land to the open sea. We investigated the role of eelgrass (Zostera marina) metabolism in the coastal filter transforming nitrogen, phosphorus, and organic carbon. Field campaigns following identical methodologies were carried out at two contrasting coastal locations: the mesohaline and nutrient-rich Roskilde Fjord, Denmark, and the mesotrophic brackish Tvärminne archipelago, Finland. Over the 24-h in situ benthic incubations, we measured oxygen concentrations continuously and assessed changes in DOM characteristics and net fluxes of carbon, nitrogen, and phosphorus. Ecosystem metabolism modeled on the basis of the O2 data showed that the systems were either net heterotrophic (Roskilde Fjord; − 1.6 and − 2.4 g O2 m−2 day−1 in eelgrass meadow and bare sand, respectively) or had balanced primary production and respiration (Tvärminne; 0.0 and 0.2 g O2 m−2 day−1). Overall, initial nutrient stoichiometry was a key factor determining benthic–pelagic fluxes of nutrients, which exacerbated the deviations from Redfield ratios of N and P, indicating an efficient use of the limiting nutrient. A net diel uptake of dissolved inorganic N was observed at both locations (− 2.3 μmol l−1 day−1 in Roskilde Fjord and − 0.1 μmol l−1 day−1 in Tvärminne). Despite minor changes in dissolved organic carbon concentrations during the incubations, a marked increase of fluorescent DOM was observed at both locations, suggesting rapid heterotrophic processing of the DOM pool. Our results underline that the biogeochemical role of eelgrass in the coastal filter is not inherent, but strongly dependent on the environmental conditions.

SDG 14: Life below water-Impacts on mangroves - Friess, Daniel A.; Aung, Toe Toe; Huxham, Mark; Lovelock, Catherine; Sasmito, Sigit (Sustainable Development Goals: Their Impacts on Forests and People, 2019)

Sea Level Rise and Implications for Low-Lying Islands, Coasts and Communities. In: IPCC Special Report on the Ocean and Cryosphere in a Changing Climate - Oppenheimer, M.; Glavovic, B.C.; Hinkel, J.; van de Wal, R.; Magnan, A.K.; Abd-Elgawad, A.; Cai, R.; Cifuentes-Jara, M.; DeConto, R.M.; Ghosh, T.; Hay, J.; Isla, F.; et al. (The Ocean and Cryosphere in a Changing Climate, 2019)
The release of carbon dioxide (CO 2) and other greenhouse gases (GHGs) due to human activity is increasing global average surface air temperatures, disrupting weather patterns, and acidifying the ocean (1). Left unchecked, the continued growth of GHG emissions could cause global average temperatures to increase by another 4°C or more by 2100 and by 1.5 to 2 times as much in many midcontinent and far northern locations (1). Although our understanding of the impacts of climate change is increasingly and disturbingly clear, there is still debate about the proper course for U.S. policy-a debate that is very much on display during the current presidential transition. But putting near-term politics aside, the mounting economic and scientific evidence leave me confident that trends toward a clean-energy economy that have emerged during my presidency will continue and that the economic opportunity for our country to harness that trend will only grow. This Policy Forum will focus on the four reasons I believe the trend toward clean energy is irreversible. ECONOMIES GROW, EMISSIONS FALL The United States is showing that GHG mitigation need not conflict with economic growth. Rather, it can boost efficiency , productivity, and innovation. Since 2008, the United States has experienced the first sustained period of rapid GHG emissions reductions and simultaneous economic growth on record. Specifically, CO2 emissions from the energy sector fell by 9.5% from 2008 to 2015, while the economy grew by more than 10%. In this same period, the amount of energy consumed per dollar of real gross domestic product (GDP) fell by almost 11%, the amount of CO 2 emitted per unit of energy consumed declined by 8%, and CO 2 emitted per dollar of GDP declined by 18% (2). The importance of this trend cannot be understated. This "decoupling" of energy sector emissions and economic growth should put to rest the argument that combatting climate change requires accepting lower growth or a lower standard of living. In fact, although this decoupling is most pronounced in the United States, evidence that economies can grow while emissions do not is emerging around the world. The International Energy Agency's (IEA's) preliminary estimate of energy-related CO2 emissions in 2015 reveals that emissions stayed flat compared with the year before , whereas the global economy grew (3). The IEA noted that "There have been only four periods in the past 40 years in which CO 2 emission levels were flat or fell compared with the previous year, with three of those-the early 1980s, 1992, and 2009-being associated with global economic weakness. By contrast, the recent halt in emissions growth comes in a period of economic growth." At the same time, evidence is mounting that any economic strategy that ignores carbon pollution will impose tremendous costs to the global economy and will result in fewer jobs and less economic growth over the long term. Estimates of the economic damages from warming of 4°C over preindustrial levels range from 1% to 5% of global GDP each year by 2100 (4). One of the most frequently cited economic models pins the estimate of annual damages from warming of 4°C at ~4% of global GDP (4-6), which could lead to lost U.S. federal revenue of roughly $340 billion to $690 billion annually (7). Moreover, these estimates do not include the possibility of GHG increases triggering catastrophic events, such as the accelerated shrinkage of the Greenland and Antarctic ice sheets, drastic changes in ocean currents, or sizable releases of GHGs from previously frozen soils and sediments that rapidly accelerate warming. In addition, these estimates factor in economic damages but do not address the critical question of whether the underlying rate of economic growth (rather than just the level of GDP) is affected by climate change, so these studies could substantially understate the potential damage of climate change on the global macroe-conomy (8, 9). As a result, it is becoming increasingly clear that, regardless of the inherent uncertainties in predicting future climate and weather patterns, the investments needed to reduce emissions-and to increase resilience and preparedness for the changes in climate that can no longer be avoided will be modest in comparison with the benefits from avoided climate-change damages. This means, in the coming years, states, localities, and businesses will need to continue making these critical investments, in addition to taking common-sense steps to disclose climate risk to taxpayers,

Seagrass sedimentary deposits as security vaults and time capsules of the human past - Krause-Jensen, Dorte; Serrano, Oscar; Apostolaki, Eugenia T.; Gregory, David J.; Duarte, Carlos M. (Ambio, 2019)
Seagrass meadows form valuable ecosystems, but are considered to have low cultural value due to limited research efforts in this field. We provide evidence that seagrass deposits play a hitherto unrealized central role in preserving valuable submerged archaeological and historical heritage across the world, while also providing an historical archive of human cultural development over time. We highlight three case studies showing the significance of seagrass in protecting underwater cultural heritage in Denmark, the Mediterranean and Australia. Moreover, we present an overview of additional evidence compiled from the literature. We emphasize that this important role of seagrasses is linked to their capacity to form thick sedimentary deposits, accumulating over time, thereby covering and sealing submerged archaeological heritage. Seagrass conservation and restoration are key to protecting this buried heritage while also supporting the role of seagrass deposits as carbon sinks as well as the many other important ecosystem functions of seagrasses.

Soil Structure and Its Relationship to Shallow Soil Subsidence in Coastal Wetlands - Xiong, Yanmei; Ola, Anne; Phan, Sang Minh; Wu, Jingtao; Lovelock, Catherine E. (Estuaries and Coasts, 2019)
Accelerating sea-level rise poses a threat to mangroves and salt marshes. Sediment accretion on the soil surface and belowground root production is proposed to increase soil elevation enabling these intertidal habitats to maintain their position relative to mean sea level. However, shallow soil subsidence is frequently observed, which may cancel out or even outweigh the positive effects of surface accretion and root production on soil elevation gains. The processes that lead to shallow soil subsidence have not often been investigated. Here, we used computed tomography (CT) imaging to determine the volume of coarse pores in the top 20 cm of 30-cm-deep soil cores collected from mangroves and salt marshes within Moreton Bay, eastern Australia. The four field sites have long-term observations of variation in soil surface elevation gain, surface accretion rate, and shallow subsidence rate using the rod surface elevation table-marker horizon (RSET-MH) method. Over our sites, we found that the rates of shallow soil subsidence were positively related to the volume of soil coarse pores and soil clay and silt content rather than to the volume of fine pores or total porosity or other soil properties. In turn, the volume of soil coarse pores was positively related to the volume of animal burrows and root mass. Fine-pore volume and total porosity of soils were negatively associated with soil bulk density, which was in turn negatively related to soil organic matter content. Our results indicate influences of differently sized soil pores in shallow soil subsidence and suggest that animal burrowing may play a role in shallow soil subsidence.

Species composition, abundance and fishing methods of small-scale fisheries in the seagrass meadows of Gazi Bay, Kenya - Musembi, Peter; Fulanda, Bernerd; Kairo, James; Githaiga, Michael (Journal of the Indian Ocean Region, 2019)
Fisheries are important sources of livelihoods to coastal communities. In the tropics fishing is conducted from mangroves, seagrass meadows to coral reefs. Studies on fisheries in the tropics have focused on coral reef fisheries, with little attention to seagrass meadows and mangroves. Using creel survey and in-depth interviews, this study assessed species composition, abundance and exploitation methods of fisheries from the seagrass meadows of Gazi Bay, Kenya. Eighty-five species were recorded with 8 species accounting for 75.7% of the total catch dominated by Leptoscarus vaigiensis, accounting for 30.9% of the total catch. Five dominant gears were observed: basket traps, hook and stick, handlines, nets and spear-guns. Basket traps were the most dominant accounting for 75.1% of the total catch by volume. These results underscore the value of the seagrass meadows to supporting fisheries. Gear management measures should be implemented for sustainability of the seagrass habitat and associated fisheries.

The atmospheric carbon sequestration potential of man-made tidal lagoons - Piano, Marco; Papadimitriou, Stathys; Roche, Ronan; Bowers, David; Kennedy, Paul; Kennedy, Hilary (Continental Shelf Research, 2019)
Understanding sequestration of carbon by coastal ecosystems is central to addressing the role they play in climate change mitigation. To quantify this process, accurate measurements of CO2 fluctuation, coupled with variations in residence time of coastal water-bodies are required. Nearshore ecosystems, including coastal lagoons, may provide an effective sink for atmospheric carbon dioxide, particularly those containing productive biota such as seagrass. However, the rate and pattern of carbon sequestration in seagrass meadows across a range of environmental settings is still poorly constrained. In this study, we utilize a robust physical tidal model, along with biogeochemical dissolved inorganic carbon (DIC) assessment, to estimate water residence time and net sequestration of atmospheric CO2 in an intertidal lagoon containing a seagrass (Zostera noltii) meadow. Total alkalinity and pH measurements taken from advected water mass exchanged with the open ocean at inlet boundaries are used to calculate DIC and pCO2. A predictive model of hydrodynamics provides good approximation of mean water residence time to within 6 h (±3 s.d). Results indicate that during the daytime study period the lagoon is a sink for carbon, having a mean net ecosystem productivity (NEP) of 3.0 ± 0.4 mmol C m−2 hr−1. An equivalent diel NEP range of between 15.23 and −9.24 mmol C m−2 d−1 is calculated based on reported shallow water pelagic respiration rates. Moreover, approximately 4% of DIC availability occurs from atmospheric CO2 transfer to lagoon water. However, a negative diel rate of −82 ± 81 mmol C m−2 d−1 is found, assuming overnight respiration ascertained from converted Zostera noltii O2 utilization. We hypothesize that analogous regional nearshore ecosystems provide baseline study sites suitable to elucidate the carbon capture potential of planned, nearby tidal range energy schemes.

The Ecology and Management of Temperate Mangroves - Morrisey, Donald J.; Swales, Andrew; Dittmann, Sabine; Morrison, Mark A.; Lovelock, Catherine E.; Beard, Catherine M. (Oceanography and Marine Biology, 2019)
Previous reviews of mangrove biology focused on the more extensive and diverse tropical examples, with those of temperate regions generally relegated to a footnote. Temperate mangroves are distinctive in several ways, most obviously by the lower diversity of tree species. Their occurrence in relatively developed countries has created different issues for mangrove management from those in the tropics. Mangroves in several temperate areas are currently expanding, due to changes in river catchments, in contrast to their worldwide decline. Information derived from the greater body of research from tropical regions has sometimes been applied uncritically to the management of temperate mangroves. The growing body of information on the ecology of temperate mangroves is reviewed, with emphasis on productivity, response to anthropogenically enhanced rates of sediment accumulation, and potential effects of climate change. There is no unique marine or estuarine fauna in temperate mangroves, but the poorly known terrestrial fauna includes mangrove-dependent species. Although productivity generally declines with increasing latitude, there is overlap in the range of reported values between temperate and tropical regions and considerable within-region variation. This, and variation in other ecologically important factors, makes it advisable to consider management of temperate mangroves on a case-by-case basis, for example, when responding to expansion of mangroves at a particular location.

The future of Blue Carbon science - Macreadie, Peter I.; Anton, Andrea; Raven, John A.; Beaumont, Nicola; Connolly, Rod M.; Friess, Daniel A.; Kelleway, Jeffrey J.; Kennedy, Hilary; Kuwae, Tomohiro; Lavery, Paul S.; Lovelock, Catherine E.; Smale, Dan A.; et al. (Nature Communications, 2019)
The term Blue Carbon (BC) was first coined a decade ago to describe the disproportionately large contribution of coastal vegetated ecosystems to global carbon sequestration. The role of BC in climate change mitigation and adaptation has now reached international prominence. To help prioritise future research, we assembled leading experts in the field to agree upon the top-ten pending questions in BC science. Understanding how climate change affects carbon accumulation in mature BC ecosystems and during their restoration was a high priority. Controversial questions included the role of carbonate and macroalgae in BC cycling, and the degree to which greenhouse gases are released following disturbance of BC ecosystems. Scientists seek improved precision of the extent of BC ecosystems; techniques to determine BC provenance; understanding of the factors that influence sequestration in BC ecosystems, with the corresponding value of BC; and the management actions that are effective in enhancing this value. Overall this overview provides a comprehensive road map for the coming decades on future research in BC science.

The role of reactive iron in long-term carbon sequestration in mangrove sediments - Dicen, Gerald P.; Navarrete, Ian A.; Rallos, Roland V.; Salmo, Severino G.; Garcia, Maria Carmela A. (Journal of Soils and Sediments, 2019)
Purpose: Despite occupying only 0.5% of the global coastal ocean, mangroves play a disproportionately large role in the capture and retention of atmospheric carbon dioxide as organic carbon (OC) in its sediments. However, the capacity of mangrove sediments to store high amounts of OC has never been explained mechanistically. This study elucidates the role of reactive iron (Fe R ) in long-term carbon sequestration in mangrove sediments. Materials and methods: Sediment samples of up to 1 m in depth were collected from six selected mangrove areas across the Philippines. The samples were characterized using X-ray diffraction (XRD) and X-ray fluorescence (XRF). A citrate-bicarbonate-dithionite reduction procedure was employed to extract Fe R from the sediments. The OC concentration and δ 13 C signatures before and after Fe R extraction were determined using a dichromate oxidation technique and isotope ratio mass spectrometry (IRMS), respectively. Results and discussion: XRD diffractograms showed that the mangrove sediment samples varied in terms of mineralogical characteristics, which reflected their different parent materials. It was found that the OC concentration increased exponentially (OC = 8.38e 0.37FeR ; R 2 = 0.88; p < 0.0001) with increasing Fe R concentration. δ 13 C signatures of Fe R -associated OC revealed that Fe R preferentially preserved terrestrial over marine-derived organic matter. Finally, Fe R was estimated to coprecipitate with up to 5.44 × 10 12  g OC in mangrove sediments per year. Conclusions: The findings of this study suggest that Fe R is responsible for the preservation of OC, thus making mangrove sediments a “giant rusty sponge” for carbon. This mechanistic understanding of the long-term carbon storage in mangrove sediments could help draft better strategies for blue carbon initiatives that include the mangrove ecosystems.

The value of small mangrove patches - Sills, Jennifer; Curnick, David J; Pettorelli, Nathalie; Amir, A Aldrie; Balke, Thorsten; Barbier, Edward B; Crooks, Stephen; Dahdouh-Guebas, Farid; Duncan, Clare; Endsor, Charlie; Friess, Daniel A; Quarto, Alfredo; et al. (Science, 2019)
![Figure][1] Since 2016, when this photo was taken, much of Kulhudhuffushi island's small mangrove patch has been destroyed. PHOTO: EYEWELL PORTRAIT Mangroves provide crucial services to humanity, including food, coastal protection, fisheries support, and carbon sequestration ([ 1 ][2]). However, up to 35% of mangrove area has been lost since the 1980s, primarily due to coastal development ([ 2 ][3]). Mangroves are protected under a plethora of international agreements, and they are key to meeting commitments of the Paris Climate Agreement and mitigating the impacts of a changing climate on coastal communities ([ 3 ][4]). Despite warnings about the ramifications of losing mangroves ([ 4 ][5]), conversion and degradation still occur ([ 5 ][6]), especially for smaller mangrove patches. The global disdain for small mangrove patches is exemplified by the 2017 decision by the Maldivian government to construct a new local airport on the regionally significant mangrove patch (12 ha) on Kulhudhuffushi island ([ 6 ][7]). This decision was made despite the socioeconomic importance of the mangrove to the local community, the viable alternative solutions that were identified ([ 6 ][7]), the island's high risk for cyclones and tsunamis ([ 6 ][7]), and the substantial funding the Maldives received for climate change mitigation and adaptation [e.g., ([ 7 ][8])]. Despite assurances that only 30% of the mangrove would be directly affected by this project, nearly 70% may have already been destroyed ([ 8 ][9]). The loss of relatively small patches of mangrove may seem less concerning than large-scale deforestation. However, these patches are especially important to low-lying island nations vulnerable to climate change and sea-level rise ([ 1 ][2]). Their interconnectedness with adjacent habitats, such as coral reefs, allows them to provide substantial ecosystem services relative to their size ([ 9 ][10]). The continued loss of mangrove patches further fragments mangrove habitat, which creates barriers to species movement and dispersal ([ 10 ][11]). The loss also drastically erodes local coastal resilience and pushes key mangrove ecosystems toward collapse. Given the recent Intergovernmental Panel on Climate Change's projections ([ 11 ][12]), we simply cannot afford to lose more mangrove forests, irrespective of their size. We call on governments to move away from policy decisions that prioritize large areas and short-term local political gains and instead adopt a more holistic long-term vision ([ 12 ][13]), whereby the value of smaller mangrove patches is better appreciated and safeguarded. 1. [↵][14]1. S. Y. Lee et al ., Glob. Ecol. Biogeogr. 23, 726 (2014). [OpenUrl][15] 2. [↵][16]1. B. A. Polidoro et al ., PLOS ONE 5, 10.1371/journal.pone.0010095 (2010). 3. [↵][17]1. P. Taillardat, 2. D. A. Friess, 3. M. Lupascu , Biol. Lett. 14, 20180251 (2018). [OpenUrl][18][CrossRef][19][PubMed][20] 4. [↵][21]1. N. C. Duke et al ., Science 317, 41 (2007). [OpenUrl][22][CrossRef][23][PubMed][24][Web of Science][25] 5. [↵][26]1. S. E. Hamilton, 2. D. Casey , Glob. Ecol. Biogeogr. 25, 729 (2016). [OpenUrl][27] 6. [↵][28]1. Z. Hameed , “Environmental Impact Assessment for the airport development project at Haa Dhaal Kulhudhuffushi” (2017). 7. [↵][29]Green Climate Fund (2018); [www.mv.undp.org/content/maldives/en/home/operations/projects/environment_and_energy/GreenClimateFund.html][30]. 8. [↵][31]Transparency Maldives (2018); <http://transparency.mv/2018/09/joint-press-statement-we-call-on-the-authorities-to-ensure-the-protection-of-the-kulhudhuffushi-mangrove/>. 9. [↵][32]1. S. J. Pitmann <!-- --> 1. E. B. Barbier , in Seascape Ecology, S. J. Pitmann, Ed. (Wiley-Blackwell, NY, 2017), pp. 465–481. 10. [↵][33]1. L. Triest , Aquat. Bot. 89, 138 (2008). [OpenUrl][34][CrossRef][35] 11. [↵][36]1. V. Masson-Delmotte et al. <!-- --> 1. O. Hoegh-Guldberg et al ., in “Global warming of 1.5°C,” V. Masson-Delmotte et al., Eds. (2018); [www.ipcc.ch/sr15/][37]. 12. [↵][38]1. A. A. Amir , Science 359, 1342 (2018). [OpenUrl][39][FREE Full Text][40] [1]: pending:yes [2]: #ref-1 [3]: #ref-2 [4]: #ref-3 [5]: #ref-4 [6]: #ref-5 [7]: #ref-6 [8]: #ref-7 [9]: #ref-8 [10]: #ref-9 [11]: #ref-10 [12]: #ref-11 [13]: #ref-12 [14]: #xref-ref-1-1 "View reference 1 in text" [15]: {openurl}?query=rft.jtitle%253DGlob.%2BEcol.%2BBiogeogr.%26rft.volume%253D23%26rft.spage%253D726%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [16]: #xref-ref-2-1 "View reference 2 in text" [17]: #xref-ref-3-1 "View reference 3 in text" [18]: {openurl}?query=rft.jtitle%253DBiol.%2BLett.%26rft_id%253Dinfo%253Adoi%252F10.1098%252Frsbl.2018.0251%26rft_id%253Dinfo%253Apmid%252F30355678%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [19]: /lookup/external-ref?access_num=10.1098/rsbl.2018.0251&link_type=DOI [20]: /lookup/external-ref?access_num=30355678&link_type=MED&atom=%2Fsci%2F363%2F6424%2F239.atom [21]: #xref-ref-4-1 "View reference 4 in text" [22]: {openurl}?query=rft.jtitle%253DScience%26rft.volume%253D317%26rft.spage%253D41%26rft_id%253Dinfo%253Adoi%252F10.1126%252Fscience.317.5834.41b%26rft_id%253Dinfo%253Apmid%252F17615322%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [23]: /lookup/external-ref?access_num=10.1126/science.317.5834.41b&link_type=DOI [24]: /lookup/external-ref?access_num=17615322&link_type=MED&atom=%2Fsci%2F363%2F6424%2F239.atom [25]: /lookup/external-ref?access_num=000247776700016&link_type=ISI [26]: #xref-ref-5-1 "View reference 5 in text" [27]: {openurl}?query=rft.jtitle%253DGlob.%2BEcol.%2BBiogeogr.%26rft.volume%253D25%26rft.spage%253D729%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [28]: #xref-ref-6-1 "View reference 6 in text" [29]: #xref-ref-7-1 "View reference 7 in text" [30]: http://www.mv.undp.org/content/maldives/en/home/operations/projects/environment_and_energy/GreenClimateFund.html [31]: #xref-ref-8-1 "View reference 8 in text" [32]: #xref-ref-9-1 "View reference 9 in text" [33]: #xref-ref-10-1 "View reference 10 in text" [34]: {openurl}?query=rft.jtitle%253DAquat.%2BBot.%26rft.volume%253D89%26rft.spage%253D138%26rft_id%253Dinfo%253Adoi%252F10.1016%252Fj.aquabot.2007.12.013%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [35]: /lookup/external-ref?access_num=10.1016/j.aquabot.2007.12.013&link_type=DOI [36]: #xref-ref-11-1 "View reference 11 in text" [37]: http://www.ipcc.ch/sr15/ [38]: #xref-ref-12-1 "View reference 12 in text" [39]: {openurl}?query=rft.jtitle%253DScience%26rft.stitle%253DScience%26rft.aulast%253DAmir%26rft.auinit1%253DA.%2BA.%26rft.volume%253D359%26rft.issue%253D6382%26rft.spage%253D1342%26rft.epage%253D1343%26rft.atitle%253DMitigate%2Brisk%2Bfor%2BMalaysia%2527s%2Bmangroves%26rft_id%253Dinfo%253Adoi%252F10.1126%252Fscience.aas9139%26rft_id%253Dinfo%253Apmid%252F29567699%26rft.genre%253Darticle%26rft_val_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Ajournal%26ctx_ver%253DZ39.88-2004%26url_ver%253DZ39.88-2004%26url_ctx_fmt%253Dinfo%253Aofi%252Ffmt%253Akev%253Amtx%253Actx [40]: /lookup/ijlink/YTozOntzOjQ6InBhdGgiO3M6MTQ6Ii9sb29rdXAvaWpsaW5rIjtzOjU6InF1ZXJ5IjthOjQ6e3M6ODoibGlua1R5cGUiO3M6NDoiRlVMTCI7czoxMToiam91cm5hbENvZGUiO3M6Mzoic2NpIjtzOjU6InJlc2lkIjtzOjE1OiIzNTkvNjM4Mi8xMzQyLWIiO3M6NDoiYXRvbSI7czoyMjoiL3NjaS8zNjMvNjQyNC8yMzkuYXRvbSI7fXM6ODoiZnJhZ21lbnQiO3M6MDoiIjt9

Toward a coordinated global observing system for seagrasses and marine macroalgae - Duffy, J. Emmett; Benedetti-Cecchi, Lisandro; Trinanes, Joaquin; Muller-Karger, Frank E.; Ambo-Rappe, Rohani; Boström, Christoffer; Buschmann, Alejandro H.; Byrnes, Jarrett; Coles, Robert G.; Creed, Joel; Cullen-Unsworth, Leanne C.; Diaz-Pulido, Guillermo; et al. (Frontiers in Marine Science, 2019)
In coastal waters around the world, the dominant primary producers are benthic macrophytes, including seagrasses and macroalgae, that provide habitat structure and food for diverse and abundant biological communities and drive ecosystem processes. Seagrass meadows and macroalgal forests play key roles for coastal societies, contributing to fishery yields, storm protection, biogeochemical cycling and storage, and important cultural values. These socio-economically valuable services are threatened worldwide by human activities, with substantial areas of seagrass and macroalgal forests lost over the last half-century. Tracking the status and trends in marine macrophyte cover and quality is an emerging priority for ocean and coastal management, but doing so has been challenged by limited coordination across the numerous efforts to monitor macrophytes, which vary widely in goals, methodologies, scales, capacity, governance approaches, and data availability. Here, we present a consensus assessment and recommendations on the current state of and opportunities for advancing global marine macrophyte observations, integrating contributions from a community of researchers with broad geographic and disciplinary expertise. With the increasing scale of human impacts, the time is ripe to harmonize marine macrophyte observations by building on existing networks and identifying a core set of common metrics and approaches in sampling design, field measurements, governance, capacity building, and data management. We recommend a tiered observation system, with improvement of remote sensing and remote underwater imaging to expand capacity to capture broad-scale extent at intervals of several years, coordinated with stratified in situ sampling annually to characterize the key variables of cover and taxonomic or functional group composition, and to provide ground-truth. A robust networked system of macrophyte observations will be facilitated by establishing best practices, including standard protocols, documentation, and sharing of resources at all stages of workflow, and secure archiving of open-access data. Because such a network is necessarily distributed, sustaining it depends on close engagement of local stakeholders and focusing on building and long-term maintenance of local capacity, particularly in the developing world. Realizing these recommendations will produce more effective, efficient, and responsive observing, a more accurate global picture of change in vegetated coastal systems, and stronger international capacity for sustaining observations.

Toward the Ultrasonic Sensing of Organic Carbon in Seagrass-Bearing Sediments - Venegas, G. R.; Rahman, A. F.; Lee, K. M.; Ballard, M. S.; Wilson, P. S. (Geophysical Research Letters, 2019)
Ten percent of all organic carbon (Corg) absorbed by the ocean each year is stored in seagrass-bearing sediments. The preservation of these carbon stores is considered a vital method to mitigate climate change. Seagrass-bearing sediments have been correlated with sediment geophysical properties yet have not been related to sediment acoustic properties. For this purpose, sediment cores were collected from a Thalassia testudinum seagrass meadow in South Texas, USA, where geophysical, acoustical, and Corg properties were measured. It is hypothesized that when deposits of Corg adsorb onto mineral surfaces and are stored in pore spaces, compliant layers between grain contacts and the formation of an organic-rich suspension reduce sediment stiffness. Results from this seagrass meadow demonstrated a strong correlation between sediment P wave modulus and Corg and show promise toward the development of an in situ ultrasonic sediment probe to more rapidly quantify and monitor seagrass carbon stores.

A national approach to greenhouse gas abatement through blue carbon management - Kelleway, Jeffrey J.; Serrano, Oscar; Baldock, Jeffrey A.; Burgess, Rachel; Cannard, Toni; Lavery, Paul S.; Lovelock, Catherine E.; Macreadie, Peter I.; Masqué, Pere; Newnham, Mark; Saintilan, Neil; Steven, Andrew D.L. (Global Environmental Change, 2020)
There is increasing interest in protecting, restoring and creating ‘blue carbon’ ecosystems (BCE; mangroves, tidal marshes and seagrasses) to sequester atmospheric CO2-C and thereby contribute to climate change mitigation. While a growing number of countries aspire to report greenhouse gas emission and carbon sequestration changes from these ecosystems under voluntary international reporting requirements, few countries have domestic policy frameworks that specifically support the quantification and financing of carbon emission abatement through BCE management. Australia, as home to approximately 5–11% of global blue carbon stocks, has a substantial interest in the development of blue carbon policy. Here we assess the potential inclusion of blue carbon within Australia's Emissions Reduction Fund, emphasizing issues and approaches that have global relevance. We used a participatory workshop of scientific experts and carbon industry stakeholders to identify blue carbon management actions that would meet the requirements of the Fund. In total, twelve actions were assessed for their greenhouse gas emission abatement potential and the ability to measure abatement reliably, using a combination of available data and qualitative and quantitative methods, including expert knowledge. We identify and discuss the five most relevant and promising activities, encompassing the protection, restoration and creation of mangroves, tidal marshes and seagrasses. On a per area basis, mean abatement intensity of organic carbon (Corg) was highest for the (re)introduction of tidal flow resulting in establishment of mangrove (13–15 Mg Corg ha−1 yr−1) and tidal marsh (6–8 Mg Corg ha−1 yr−1), followed by land use planning for sea-level rise for the creation of new mangrove habitat (8 Mg Corg ha−1 yr−1). The avoided disturbance of existing mangroves, tidal marshes and seagrasses has the twofold benefit of avoiding remineralisation of existing stocks, plus the future annual abatement associated with the net sequestration of atmospheric CO2-C as Corg with the continued functioning of these BCE. Our approach offers a template that uses best available information to identify options for carbon abatement through management of coastal landscapes, and details current knowledge gaps and important technical aspects that need to be considered for implementation in carbon crediting schemes.

Almacenes de carbono en Pastos marinos de la Reserva de la Biosfera “ Los Petenes ”, México - Cota-Lucero, Tania Cecilia; Mendoza-Martínez, J. E.; Herrera-Silveira, J. A. (Estado actual del concociemitnp del ciclo del Carbono y sus interacciones en México, 2020)
Seagrasses form extensive meadows whose importance lies in the structural and trophic functions they perform. Meadows through of photosynthesis capture CO2 and transform it into organic carbon that accumulates in biomass (leaves, rhizomes and roots) and sediments. This stored carbon is known as blue carbon. In Mexico, there are 9 species distributed in the coastal zone and their populations are threatened mainly by anthropogenic impacts. Despite the decrease in their populations, information on their condition and their role as carbon stores both in living tissue and in local sediments is scarce. Therefore, the objective of the present study was to estimate the organic carbon stored in biomass of the seagrass that are distributed in the Los Petenes Biosphere Reserve, these estimates were made by means of biomass samples collected in the field and the carbon was calculated indirectly. Regarding the carbon storage, the reserve presents an average of 2.19 ± 0.18 Mg C ha-1, higher than other zones in Mexico. This carbon is equivalent to the retention of CO2eq emissions of 1.24 TgCO2eq from the ocean and the atmosphere. The results of the present study indicate that the Reserve is an area with a high carbon store in Mexico both for its extension and for the biomass generated, where the belowrground tissue provides the highest biomass. Therefore, the Reserve must maintain its current state of conservation

Assessment of Hurricane Irma Impacts on South Florida Seagrass Communities Using Long-Term Monitoring Programs - Wilson, Sara S.; Furman, Bradley T.; Hall, Margaret O.; Fourqurean, James W. (Estuaries and Coasts, 2020)
Hurricanes are some of the largest environmental drivers of change in coastal systems. We investigated the impacts of Hurricane Irma on benthic macrophyte communities in Florida Bay (FB) and the Florida Keys National Marine Sanctuary (FKNMS), USA. Spatiotemporal analyses were performed at multiple hierarchical levels (site, zone, region) to identify potential changes in the Braun-Blanquet (BB) densities of total seagrass (TSG) and total calcareous green macroalgae (TCAL) post-disturbance and to determine whether changes were attributable to hurricane impacts or normal seasonal and inter-annual variability. There were significant decreases in TSG in one of five zones in FKNMS and in one of six zones in FB, but no change in TCAL was recorded in either system. TSG in the Lower Keys Bayside declined from a mean BB score of 2.6 to 1.2, resulting from storm-induced erosion, whereas TSG in coastal FB declined from 1.05–2.4 to 0.36–2.0, likely due to prolonged hyposalinity and low dissolved oxygen following stormwater drainage. Overall, impacts to South Florida benthic macrophyte communities from Hurricane Irma were not catastrophic and were limited in spatial extent. Our results suggest that coastal areas hit by a storm with heavy winds are more likely to sustain direct physical impacts to the benthos, whereas estuarine areas with longer residence times are more at risk of the indirect effects of stormwater runoff and retention. Our analyses placed putative hurricane impacts within the context of recent variability and historical system baselines through the use of long-term monitoring data coordinated by multiple governmental and academic entities.

Assessment of typhoon impacts and post-typhoon recovery in Philippine mangroves: Lessons and challenges for adaptive management - Salmo, Severino G. (Dynamic Sedimentary Environments of Mangrove Coasts, 2020)
The extent and state of ecosystem health of Philippine mangroves are affected by the occurrences of typhoons (ca. 20 per year). While severe damages (and sometimes even total forest collapse) are commonly reported, there are some cases where mangroves are less damaged and easily recovered implying that some mangroves are either highly vulnerable or resilient. Most studies on effects of typhoons in mangroves (including post-typhoon recovery) are mainly focused on vegetation but rarely on changes in sediment and faunal composition and activities. Also, these studies are mostly short-term and rapid (<1 year) with suboptimal experimental designs because of the lack of baseline data and systematic assessment. In this study, a 15-year synthesis of impacts of typhoon and post-typhoon recovery in selected mangrove sites in the Philippines was discussed and compared with other typhoon-disturbed tropical/subtropical mangroves. The study covered pre- and post-typhoon changes in vegetation, sediment, and faunal assemblages and activities including the assessment of possible recovery and identification of recovery indicators. The study provides an overview of interrelationships of vegetation, sediment (including nutrients), and faunal assemblages and activities as a more integrative approach in damage and recovery assessments. Lastly, the implications of the study on research needs (e.g., systematic and sustained monitoring) and policy and management programs (e.g., effective conservation and restoration programs) for Philippine mangroves were discussed.

Blue Carbon – climate adaptation, CO2 uptake and sequestration of carbon in Nordic blue forests - Results from the Nordic Blue Carbon Project - Frigstad, H; Gundersen, Hege; Andersen, Guri S.; Borgersen, Gunhild; Kvile, Kristina O.; Krause-Jensen, Dorte; Boström, Christoffer; Bekkby, Trine; D'Auriac, Marc Angles; Ruus, Anders; Thormar, Jonas; Asdal, Kaya; et al. (TemaNord, 2020)
Purpose: Earth faces an urgent need for climate change mitigation, and carbon storage is discussed as an option. Approaches for assessing the benefit of temporary carbon storage in relation to carbon footprinting exist, but many are based on a 100-year accounting period, disregarding impacts after this time. The aim of this paper is to assess the consequences of using such approaches that disregard the long timescale on which complete removal of atmospheric CO2 occurs. Based on these findings, an assessment is made on what are relevant timescales to consider when including the value of temporary carbon storage in carbon footprinting. Methods: Implications of using a 100-year accounting period is evaluated via a literature review study of the global carbon cycle, as well as by analysing the crediting approaches that are exemplified by the PAS 2050 scheme for crediting temporary carbon storage. Results and discussion: The global carbon cycle shows timescales of thousands of years for the transport of carbon from the atmosphere to pools beyond the near-surface layers of the Earth, from where it will not readily be re-emitted as a response to change in near-surface conditions. Compared to such timescales, the use of the 100-year accounting period appears hard to justify. We illustrate how the use of the 100-year accounting period can cause long-term global warming impacts to be hidden by short-term storage solutions that may not offer real long-term climate change mitigation. Obtaining long-term climatic benefits is considered to require storage of carbon for at least thousand years. However, it has been proposed that there may exist tipping points for the atmospheric CO2 concentration beyond which irreversible climate changes occur. To reduce the risk of passing such tipping points, fast mitigation of the rise in atmospheric greenhouse gas concentration is required and in this perspective, shorter storage times may still provide climatic benefits. Conclusions: Both short- and long-term perspectives should be considered when crediting temporary carbon storage, addressing both acute effects on the climate and the long-term climate change. It is however essential to distinguish between short- and long-term mitigation potential by treating them separately and avoid that short-term mitigation is used to counterbalance long-term climate change impacts from burning of fossil fuels. © 2012 Springer-Verlag Berlin Heidelberg.

Blue carbon from the past forecasts the future - Lovelock, Catherine E. (Science, 2020)

Blue Restoration – Building Confidence and Overcoming Barriers - Stewart-Sinclair, Phoebe J.; Purandare, Jemma; Bayraktarov, Elisa; Waltham, Nathan; Reeves, Simon; Statton, John; Sinclair, Elizabeth A.; Brown, Benjamin M.; Shribman, Zoë I.; Lovelock, Catherine E. (Frontiers in Marine Science, 2020)
Marine coastal (or “blue”) ecosystems provide valuable services to humanity and the environment, but global loss and degradation of blue ecosystems necessitates ecological restoration. However, blue restoration is an emerging field and is still relatively experimental and small-scale. Identification of the key barriers to scaling-up blue restoration will enable targeted problem solving and increase the likelihood of success. Here we describe the environmental, technical, social, economic, and political barriers to restoration of blue ecosystems, including saltmarsh, mangroves, seagrass, shellfish reefs, coral reefs, and kelp forests. We provide managers, practitioners, and decision-makers with solutions to construct barrier-informed blue restoration plans and illustrate these solutions through the use of case studies where barriers were overcome. We offer a way forward to build confidence in blue restoration for society, government, and restoration practitioners at larger and more ambitious scales.

Channel network structure determines genetic connectivity of landward–seaward Avicennia marina populations in a tropical bay - Triest, Ludwig; Van der Stocken, Tom; Allela Akinyi, Abbie; Sierens, Tim; Kairo, James; Koedam, Nico (Ecology and Evolution, 2020)
Mangrove ecosystems along the East African coast are often characterized by a disjunct zonation pattern of seaward and landward Avicennia marina trees. This disjunct zonation may be maintained through different positions in the tidal frame, yielding different dispersal settings. The spatial configuration of the landscape and coastal processes such as tides and waves is expected to largely influence the extent of propagule transport and subsequent regeneration. We hypothesized that landward sites would keep a stronger genetic structure over short distances in comparison with enhanced gene flow among regularly flooded seaward fringes. We tested this hypothesis from densely vegetated A. marina transects of a well-documented mangrove system (Gazi Bay, Kenya) and estimated local gene flow and kinship-based fine-scale genetic structure. Ten polymorphic microsatellite markers in 457 A. marina trees revealed no overall significant difference in levels of allele or gene diversities between sites that differ in hydrological proximity. Genetic structure and connectivity of A. marina populations however indicated an overall effect of geographic distance and revealed a pronounced distinction between channels and topographic setting. Migration models allowed to infer gene flow directionality among channels, and indicated a bidirectional steppingstone between seaward and nearest located landward stands. Admixed gene pools without any fine-scale structure were found within the wider and more exposed Kidogoweni channel, suggesting open systems. Elevated kinship values and structure over 5 to 20 m distance were only detected in two distant landward and seaward transects near the mouth of the Mkurumuji River, indicating local retention and establishment. Overall, our findings show that patterns of A. marina connectivity are explained by hydrological proximity, channel network structure, and hydrokinetic energy, rather than just their positioning as disjunct landward or seaward zones.

Comparison of sediment-plate methods to measure accretion rates in an estuarine mangrove forest (New Zealand) - Swales, Andrew; Lovelock, Catherine E. (Estuarine, Coastal and Shelf Science, 2020)
Sedimentation is a fundamental process in aquatic receiving environments, including vegetated habitats such as mangroves. Selection of appropriate methods to measure sedimentation depends on time scales of interest, due to the variable nature of this process. Our study considers the appropriateness of methods to measure sediment accretion over time scales of months to years in estuarine mangroves. Sediment accretion has commonly been measured using marker horizons, sediment erosion pins and buried plates. Bioturbation and erosion can make application of these methods problematic. Here, sediment accretion rates for porous plastic-mesh and impervious ceramic plates of two sizes (0.023 and 0.16 m2) were compared. Replicate plates of each type were installed on the substrate surface at nine Rod Surface Elevation Table (RSET) sites distributed along a shore-normal sedimentation gradient. The plates were progressively buried by sedimentation (17–41 mm yr−1). Measurements were made at seasonal to annual intervals over a seven-year period (2012–2019). Comparison of accretion rates on the plastic-mesh with both types of ceramic plates, showed strong positive correlations (r2 > 0.96, with slopes close to unity, mean 0.95, range = 0.68–1.09). Sediment accretion rates measured on the large and small ceramic plates were not measurably different from rates for the plastic mesh. These results show that sediment accretion rates were spatially homogenous at sub-metre to metre scales in the mangroves and sediment accretion rates did not measurably vary between different sediment-plate methods. The sediment-plate method has a number of advantages over marker horizons for long-term measurements of sediment accretion, particularly where bioturbation alters the sediment profile. Mesh plates are easily maintained and provide a cost-effective, flexible, precise and reproducible alternative to sediment marker horizons and solid plates for long-term monitoring sediment accretion in mangroves and unvegetated intertidal habitats. Future studies, including those employing RSET, should consider incorporating mesh-plate measurements of sediment accretion.

Coring and compaction: Best practice in blue carbon stock and burial estimations - Smeaton, Craig; Barlow, Natasha L.M.; Austin, William E.N. (Geoderma, 2020)
A comparison of gouge and hammer coring techniques in intertidal wetland soils highlights a significant effect of soil compaction of up to 28% associated with the widely applied hammer coring method employed in Blue Carbon research. Hammer coring reduces the thickness of the soil profile and increases the dry bulk density, which results in an overestimation of the soil OC stock of up to 22%. In saltmarshes with multiple different soil units, we show that hammer coring is unsuitable for the calculation of OC stocks and should be avoided in favour of Russian or gouge cores. Compaction changes both soil dry bulk density and porosity and we show that resultant radiometric chronologies are compromised, almost doubling mass accumulation rates. While we show that the OC (%) content of these sediments is largely unchanged by coring method, the implication for OC burial rates are profound because of the significant effect of hammer coring on the calculation of soil mass accumlation rates.

Economic and social constraints on reforestation for climate mitigation in Southeast Asia - Zeng, Yiwen; Sarira, Tasya Vadya; Carrasco, L Roman; Chong, Kwek Yan; Friess, Daniel A; Ser, Janice; Lee, Huay; Taillardat, Pierre; Worthington, Thomas A; Zhang, Yuchen; Koh, Lian Pin (Nature Climate Change, 2020)

Ecosystem services and disservices of mangrove forests and salt marshes - Friess, Daniel A.; Yando, Erik S.; Alemu I, Jahson B.; Wong, Lynn Wei; Soto, Sasha D.; Bhatia, Natasha (Oceanography and Marine Biology, 2020)
Coastal wetlands such as mangrove forests and salt marshes provide a range of important benefits to people, broadly defined as ecosystem services. These include provisioning services such as fuelwood and food, regulating services such as carbon sequestration and wave attenuation, and various tangible and intangible cultural services. However, strong negative perceptions of coastal wetlands also exist, often driven by the perceived or actual ecosystem disservices that they also produce. These can include odour, a sense of danger, and their real or perceived role in vector and disease transmission (e.g. malaria). This review provides an introduction to the ecosystem services and disservices concepts and highlights the broad range of services and chdisservices provided by mangrove forests and salt marshes. Importantly, we discuss the key implications of ecosystem services and disservices for the management of these coastal ecosystems. Ultimately, a clear binary does not exist between ecosystem services and disservices; an ecosystem service to one stakeholder can be viewed as a disservice to another, or a service can change seasonally into a disservice, and vice versa. It is not enough to only consider the beneficial ecosystem services that coastal wetlands provide: instead, we need to provide a balanced view of coastal wetlands that incorporates the complexities that exist in how humans relate to and interact with them.

Evaluating Current and Future Sensor-Specific Biomass Calibration in the Tallest Mangrove Forest on Earth - Stovall, Atticus E.L.; Lagomasino, David; Lee, Seung Kuk; Simard, Marc; Thomas, Nathan M.; Trettin, Carl; Fatoyinbo, Temilola (International Geoscience and Remote Sensing Symposium (IGARSS), 2020)
High-resolution global-scale estimates of aboveground biomass density will soon be available from a suite of spaceborne LiDAR and radar missions. The 2016-2017 AfriSAR campaign was specifically designed to evaluate a suite of sensors for estimating biomass in a range of tropical forest environments. Here, we compare the calibration and biomass estimates from 5 different active sensors - ALOS Global Digital Surface Model (DSM), Shuttle Radar Topography Mission (SRTM), Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR), NASA Land Vegetation Ice Sensor (LVIS), and TanDEM-X (TDX) - in the tallest known mangrove forest on Earth - Pongara National Park, Gabon. We leverage this comparison to evaluate the implications for future satellite missions that are aimed at improving global estimates of forest carbon storage. Our findings are directly relevant for space-borne missions estimating terrestrial carbon storage - GEDI, ICESat-2, NISAR, BIOMASS, Tandem-X, and Tandem-L - highlighting the specific uncertainty and bias that can be expected in several global biomass products in mangrove ecosystems.

Global declines in human-driven mangrove loss - Goldberg, Liza; Lagomasino, David; Thomas, Nathan; Fatoyinbo, Temilola (Global Change Biology, 2020)
Global mangrove loss has been attributed primarily to human activity. Anthropogenic loss hotspots across Southeast Asia and around the world have characterized the ecosystem as highly threatened, though natural processes such as erosion can also play a significant role in forest vulnerability. However, the extent of human and natural threats has not been fully quantified at the global scale. Here, using a Random Forest-based analysis of over one million Landsat images, we present the first 30 m resolution global maps of the drivers of mangrove loss from 2000 to 2016, capturing both human-driven and natural stressors. We estimate that 62% of global losses between 2000 and 2016 resulted from land-use change, primarily through conversion to aquaculture and agriculture. Up to 80% of these human-driven losses occurred within six Southeast Asian nations, reflecting the regional emphasis on enhancing aquaculture for export to support economic development. Both anthropogenic and natural losses declined between 2000 and 2016, though slower declines in natural loss caused an increase in their relative contribution to total global loss area. We attribute the decline in anthropogenic losses to the regionally dependent combination of increased emphasis on conservation efforts and a lack of remaining mangroves viable for conversion. While efforts to restore and protect mangroves appear to be effective over decadal timescales, the emergence of natural drivers of loss presents an immediate challenge for coastal adaptation. We anticipate that our results will inform decision-making within conservation and restoration initiatives by providing a locally relevant understanding of the causes of mangrove loss.
Keywords: Landsat; climate change; commodities; deforestation; mangrove; shoreline erosion

Global trends in mangrove forest fragmentation - Bryan-Brown, Dale N.; Connolly, Rod M.; Richards, Daniel R.; Adame, Fernanda; Friess, Daniel A.; Brown, Christopher J. (Scientific Reports, 2020)
Fragmentation is a major driver of ecosystem degradation, reducing the capacity of habitats to provide many important ecosystem services. Mangrove ecosystem services, such as erosion prevention, shoreline protection and mitigation of climate change (through carbon sequestration), depend on the size and arrangement of forest patches, but we know little about broad-scale patterns of mangrove forest fragmentation. Here we conduct a multi-scale analysis using global estimates of mangrove density and regional drivers of mangrove deforestation to map relationships between habitat loss and fragmentation. Mangrove fragmentation was ubiquitous; however, there are geographic disparities between mangrove loss and fragmentation; some regions, like Cambodia and the southern Caribbean, had relatively little loss, but their forests have been extensively fragmented. In Southeast Asia, a global hotspot of mangrove loss, the conversion of forests to aquaculture and rice plantations were the biggest drivers of loss (>50%) and fragmentation. Surprisingly, conversion of forests to oil palm plantations, responsible for >15% of all deforestation in Southeast Asia, was only weakly correlated with mangrove fragmentation. Thus, the management of different deforestation drivers may increase or decrease fragmentation. Our findings suggest that large scale monitoring of mangrove forests should also consider fragmentation. This work highlights that regional priorities for conservation based on forest loss rates can overlook fragmentation and associated loss of ecosystem functionality.

Harnessing Big Data to Support the Conservation and Rehabilitation of Mangrove Forests Globally - Worthington, Thomas A; Andradi-Brown, Dominic A; Bhargava, Radhika; Buelow, Christina; Bunting, Pete; Duncan, Clare; Fatoyinbo, Lola; Friess, Daniel A; Goldberg, Liza; Hilarides, Lammert; Lagomasino, David; Landis, Emily; et al. (2020)
Mangrove forests are found on sheltered coastlines in tropical, subtropical, and some warm temperate regions. These forests support unique biodiversity and provide a range of benefits to coastal communities, but as a result of large-scale conversion for aquaculture, agriculture, and urbanization, mangroves are considered increasingly threatened ecosystems. Scientific advances have led to accurate and comprehensive global datasets on mangrove extent, structure, and condition, and these can support evaluation of ecosystem services and stimulate greater conservation and rehabilitation efforts. To increase the utility and uptake of these products, in this Perspective we provide an overview of these recent and forthcoming global datasets and explore the challenges of translating these new analyses into policy action and on-the-ground conservation. We describe a new platform for visualizing and disseminating these datasets to the global science community, non-governmental organizations, government officials, and rehabilitation practitioners and highlight future directions and collaborations to increase the uptake and impact of large-scale mangrove research.
Keywords: conservation; ecosystem services; mangrove; policy action; rehabilitation; remote sensing

Hurricane Sandy Effects on Coastal Marsh Elevation Change - Yeates, Alice G.; Grace, James B.; Olker, Jennifer H.; Guntenspergen, Glenn R.; Cahoon, Donald R.; Adamowicz, Susan; Anisfeld, Shimon C.; Barrett, Nels; Benzecry, Alice; Blum, Linda; Christian, Robert R.; Grzyb, Joseph; et al. (Estuaries and Coasts, 2020)
High-magnitude storm events such as Hurricane Sandy are powerful agents of geomorphic change in coastal marshes, potentially altering their surface elevation trajectories. But how do a storm’s impacts vary across a large region spanning a variety of wetland settings and storm exposures and intensities. We determined the short-term impacts of Hurricane Sandy at 223 surface elevation table–marker horizon stations in estuarine marshes located across the northeast region of the United States by comparing post-storm surface elevation change with pre-storm elevation trends. We hypothesized that the storm’s effect on marsh elevation trends would be influenced by position relative to landfall (right or left) and distance from landfall. The structural equation model presented predicts that marshes located to the left of landfall were more likely to experience an elevation gain greater than expected, and this positive deviation from pre-storm elevation trends tended to have a greater magnitude than those experiencing negative deviations (elevation loss), potentially due to greater sediment deposition. The magnitude of negative deviations from elevation change in marshes to the right of landfall was greater than for positive deviations, with a greater effect in marshes within 200 km of landfall, potentially from the extent and magnitude of storm surge. Overall, results provide an integrated picture of how storm characteristics combined with the local wetland setting are important to a storm’s impact on surface elevation, and that the surface elevation response can vary widely among sites across a region impacted by the same storm.

Improving mangrove above-ground biomass estimates using LiDAR - Salum, Rafaela B.; Souza-Filho, Pedro Walfir M.; Simard, Marc; Silva, Carlos Alberto; Fernandes, Marcus E.B.; Cougo, Michele F.; do Nascimento, Wilson; Rogers, Kerrylee (Estuarine, Coastal and Shelf Science, 2020)
Tree height is a key parameter to accurately quantify above ground biomass (AGB) of trees. Approaches that integrate airborne light detection and ranging (LiDAR) with mapped extents of forests may improve estimation of mangrove heights by providing considerably more measurements of mangrove tree heights than can be achieved using field-based measurements alone. In this study, we present a validated method for quantifying mangrove AGB that was demonstrated for a mangrove forest at Guarás Island, Brazil. The application of LiDAR to estimate mangrove height was confirmed by correlating 89 tree heights measured in the field with LiDAR-derived mangrove heights, resulting in highly robust relationships for Avicennia germinans, Laguncularia racemosa and Rhizophora mangle (R2 = 0.90–0.97, RMSE of 1.24–0.67 m and RMSE% of 11.26%–25.97%). These relationships were used to calibrate a LiDAR-derived canopy height model (CHM) and develop robust relationships between the calibrated-CHM and field-based estimates of AGB (R2 = 0.85–0.92, RMSE of 3.1 kg–42.53 kg, RMSE% of 20.66%–43.81%). This relationship was then applied to the CHM whilst accounting for tree density to estimate mangrove AGB. Total mangrove AGB per hectare was estimated to be 246.90 t ha−1, corresponding closely with previous mangrove AGB measurements within the region. This study found that mangrove height and AGB are statistically related and these relationships can be applied to allometric equations for specific species to improve mangrove AGB estimates. This study demonstrates the capacity for LiDAR-derived tree heights to replace traditional approaches to estimating AGB and improving estimates of mangrove blue carbon storage. Application of LiDAR to determine tree heights will be particularly useful where mangrove is extensive and/or remote.

Indian Sundarbans mangrove forest considered endangered under Red List of Ecosystems, but there is cause for optimism - Sievers, Michael; Chowdhury, Mahua Roy; Adame, Maria Fernanda; Bhadury, Punyasloke; Bhargava, Radhika; Buelow, Christina; Friess, Daniel A.; Ghosh, Anwesha; Hayes, Matthew A.; McClure, Eva C.; Pearson, Ryan M.; Turschwell, Mischa P.; et al. (Biological Conservation, 2020)
Accurately evaluating ecosystem status is vital for effective conservation. The Red List of Ecosystems (RLE) from the International Union for the Conservation of Nature (IUCN) is the global standard for assessing the risk of ecosystem collapse. Such tools are particularly needed for large, dynamic ecosystem complexes, such as the Indian Sundarbans mangrove forest. This ecosystem supports unique biodiversity and the livelihoods of millions, but like many mangrove forests around the world is facing substantial pressure from a range of human activities. Holistic, standardised and quantitative environment risk assessment frameworks are essential here, because previous assessments have either been qualitative in nature, or have generally considered single threats in isolation. We review these threats and utilise the RLE framework to quantitatively assess the risk of ecosystem collapse. Historical clearing and diminishing fish populations drove a status of Endangered (range: Vulnerable to Endangered), and ongoing threats including climate change and reduced freshwater supply may further impact this ecosystem. However, considering recent change, the outlook is more optimistic. Mangrove extent has stabilised, and analysis of mangrove condition highlights that only a small proportion of the forest is degraded. Using the RLE provides an authoritative avenue for further protection and recognition of the issues facing this UNESCO World Heritage Site. We also identify knowledge and data gaps in the Sundarbans that are likely common to coastal systems globally. By articulating these and presenting opportunities and recommendations, we aim to further the conservation goals of the IUCN and the implementation of its new assessment framework.

Inferences on the role of coral bleaching or seasonality on cross-habitat movement of nekton assemblages in adjacent coral reef, seagrass, and mangrove habitats - Salmo, Severino G.; Altomonte, John Charles A. (Bulletin of Marine Science, 2020)
We investigated shifts in nekton assemblages in coral reef, seagrass, and mangrove habitats that coincided with a coral bleaching event in June 2016. The study was conducted in May 2016 (prebleaching), July 2016 (bleaching), October 2016 (4-mo postbleaching), and February 2017 (7-mo postbleaching) in relatively undisturbed coastal areas in Busuanga, Palawan, western Philippines. We used triangular trap nets to capture nekton samples from each habitat. In coral reef and mangrove habitats, there were increases in nekton abundance and biomass from the prebleaching to the bleaching period. After the bleaching event, however, there were reductions in nekton abundance and biomass at the coral reefs until 7-mo postbleaching. Species composition changed at all sites where shifts in dominant species, habitat affinity, and trophic category were observed. The postbleaching increase in nekton abundance in mangroves coincided with the decreased nekton abundance in the coral reef, suggesting a cross-habitat movement, likely due to the reduced suitability and/or food in the bleached coral reef. The changes in the nekton assemblage may also have been due to seasonal fluctuations in environmental parameters, especially salinity. Our study presents evidence of the possible role of coral bleaching or seasonal changes on cross-habitat movements of nekton assemblages, which can be inferred as an indicator of disturbance. The presence of adjacent vegetated habitats may provide refuge for the affected nekton assemblage of the coral reef.

Land use impacts on benthic bioturbation potential and carbon burial in Brazilian mangrove ecosystems - Bernardino, Angelo F.; Sanders, Christian J.; Bissoli, Lorena B.; Gomes, Luiz Eduardo de O.; Kauffman, J. Boone; Ferreira, Tiago O. (Limnology and Oceanography, 2020)
The potential of Blue Carbon as an integral part of global climate change adaptation and mitigation strategies requires quantification of drivers and rates of organic carbon (OC) burial and storage. However, there is limited recognition of how land use impacts benthic assemblages, their bioturbation potential, and OC burial in mangrove forests and tidal flats. Here we evaluated the effects of mangrove deforestation on benthic bioturbation potential (BPc), sediment accretion rates (SARs), and OC and total nitrogen (TN) burial in mangrove soils and tidal flat sediments from three estuaries in tropical Brazil. SARs based on 210Pb dating varied significantly among undisturbed estuaries (2.1–18.6 mm yr−1) and the OC and TN burial rates were respectively 46% and 16% higher than global averages. The cleared mangrove sites had a twofold lower SAR, 40-fold lower OC burial, and over 100-fold lower TN burial when compared to undisturbed forests, revealing the pervasive impacts of land use. Variation in benthic assemblage structure and BPc among sites suggests that the composition and activity of macrofaunal communities may facilitate OC burial in some cases, yet the global extent and significance of bioturbation requires further study. Our work reveals a strong spatial variability in C burial in undisturbed mangrove forests and a decreased capacity of mangroves to accumulate C and sediments due to land use effects.

Linking climatic-driven iron toxicity and water stress to a massive mangrove dieback - Sippo, James Z.; Santos, Isaac R.; Sanders, Christian J.; Gadd, Patricia; Hua, Quan; Lovelock, Catherine; Santini, Nadia S.; Johnston, Scott G.; Harada, Yota; Reithmeir, Gloria; Maher, Damien T. (Biogeosciences Discussions, 2020)
Dendritic cells (DCs) are the sentinels of the immune system. New disruptive technologies have identified novel populations and challenged long-held beliefs on the relationship between the DC lineages. Nutt and Chopin examine DC differentiation from a transcriptional perspective and describe the factors that program the DC network.

Major drivers of coastal aquaculture expansion in Southeast Asia - Akber, Md Ali; Aziz, Ammar Abdul; Lovelock, Catherine (Ocean and Coastal Management, 2020)
Coastal aquaculture is socially, culturally and economically important in Southeast Asia, but its expansion in the last fifty years has had negative environmental and social consequences. Through analyses of detailed accounts of the expansion of coastal aquaculture, we aimed to increase knowledge of the factors underlying this expansion to guide future policies for sustainable management of the coastal zone. Using a systematic review of ninety studies, we found that increased aquaculture development and economic opportunities were the most frequently identified proximate drivers of coastal aquaculture expansion, while factors associated with location (e.g. availability of mangrove land), institutional policies and economy (e.g. capital investment and market demand) had lesser influence. However, complex combinations of the underlying factors were also important. For example, the influence of policies that stimulated aquaculture development was often associated with combinations of locational, institutional, economic, technological and social factors. Strategies aimed at enhancing expansion of sustainable coastal aquaculture and mangrove conservation should focus on government policy interventions, including those that support mangrove silvo-aquaculture.

Managing sediment dynamics through reintroduction of tidal flow for mangrove restoration in abandoned aquaculture ponds - Sidik, Frida; Kusuma, Denny Wijaya; Priyono, Bayu; Proisy, Christophe; Lovelock, Catherine E. (Dynamic Sedimentary Environments of Mangrove Coasts, 2020)
The geomorphology of mangrove ecosystems is strongly influenced by hydrodynamic factors. Mangrove growth is conditional on water and sediment budgets at the coastal interface. This basic ecological principle has been ignored in many mangrove restoration or rehabilitation programs, leading to failures in the design of successful and cost-effective ecosystem restoration and rehabilitation. This chapter highlights how restoring tidal flows can adequately supply sediments to the mangrove system and stimulate its recovery in abandoned aquaculture ponds, where hydrology was previously constrained by pond walls. Tidal flows transport sediments that accumulate in the pond, causing an increase in soil surface elevation; a key factor in both helping minerogenic mangroves maintain their elevation in the face of sea level rise and improving the local blue carbon balance through carbon accumulation. In a number of cases, tidal flow also facilitates the dispersal of mangrove propagules over the site, contributing to subsequent mangrove development. As restoring the hydrological regime is most likely to have positive contributions to the early development of mangroves in abandoned ponds, it should be considered as a “nature-inspired” alternative to plantation programs. Our work suggests that such “passive” mangrove restoration strategies are to be preferred as they provide better opportunities for blue carbon abatement and increase resilience of coasts to rising sea levels and biodiversity loss.

Mangrove blue carbon in the face of deforestation, climate change, and restoration - Friess, Daniel A.; Krauss, Ken W.; Taillardat, Pierre; Adame, Maria Fernanda; Yando, Erik S.; Cameron, Clint; Sasmito, Sigit D.; Sillanpää, Mériadec (Annual Plant Reviews Online, 2020)
Coastal wetlands have disproportionately high carbon densities, known as blue carbon, compared to most terrestrial ecosystems. Mangroves and their blue carbon stocks are at risk globally from land-use and land-cover change (LULCC) activities such as aquaculture, alongside biophysical disturbances such as sea-level rise and cyclones. Global estimates of carbon emissions from mangrove loss have been previously unable to differentiate between the variable impacts of different drivers of loss. This article discusses the impacts that different LULCC activities and biophysical disturbances have on carbon stocks (biomass and soil) and greenhouse gas fluxes (CO2 and CH4). The dynamics of carbon stocks and fluxes depends on the type of LULCC; aquaculture often results in biomass and soil carbon removal, and some forms of agriculture can substantially increase methane emissions. Natural disturbances have mixed impacts on mangrove carbon; sea-level rise will drown some mangroves and their carbon stocks but provide opportunities for new carbon accumulation, while cyclones can have immediate negative impacts on stocks but positive impacts on sequestration during recovery. Mangrove rehabilitation practices can actively restore carbon stocks and reduce greenhouse gas emissions from previous land uses. It is critical to consider the type of LULCC when estimating carbon emissions due to mangrove loss or rehabilitation. Mangrove blue carbon is now high on the international conservation policy agenda, and a better understanding of how carbon stocks and fluxes respond to anthropogenic and biophysical disturbance may provide better incentives for mangrove conservation and sustainable management.

Mangrove blue carbon stocks and dynamics are controlled by hydrogeomorphic settings and land-use change - Sasmito, Sigit D.; Sillanpää, Mériadec; Hayes, Matthew A.; Bachri, Samsul; Saragi-Sasmito, Meli F.; Sidik, Frida; Hanggara, Bayu B.; Mofu, Wolfram Y.; Rumbiak, Victor I.; Hendri; Taberima, Sartji; Suhaemi; et al. (Global Change Biology, 2020)
Globally, carbon-rich mangrove forests are deforested and degraded due to land-use and land-cover change (LULCC). The impact of mangrove deforestation on carbon emissions has been reported on a global scale; however, uncertainty remains at subnational scales due to geographical variability and field data limitations. We present an assessment of blue carbon storage at five mangrove sites across West Papua Province, Indonesia, a region that supports 10% of the world's mangrove area. The sites are representative of contrasting hydrogeomorphic settings and also capture change over a 25-years LULCC chronosequence. Field-based assessments were conducted across 255 plots covering undisturbed and LULCC-affected mangroves (0-, 5-, 10-, 15- and 25-year-old post-harvest or regenerating forests as well as 15-year-old aquaculture ponds). Undisturbed mangroves stored total ecosystem carbon stocks of 182–2,730 (mean ± SD: 1,087 ± 584) Mg C/ha, with the large variation driven by hydrogeomorphic settings. The highest carbon stocks were found in estuarine interior (EI) mangroves, followed by open coast interior, open coast fringe and EI forests. Forest harvesting did not significantly affect soil carbon stocks, despite an elevated dead wood density relative to undisturbed forests, but it did remove nearly all live biomass. Aquaculture conversion removed 60% of soil carbon stock and 85% of live biomass carbon stock, relative to reference sites. By contrast, mangroves left to regenerate for more than 25 years reached the same level of biomass carbon compared to undisturbed forests, with annual biomass accumulation rates of 3.6 ± 1.1 Mg C ha−1 year−1. This study shows that hydrogeomorphic setting controls natural dynamics of mangrove blue carbon stocks, while long-term land-use changes affect carbon loss and gain to a substantial degree. Therefore, current land-based climate policies must incorporate landscape and land-use characteristics, and their related carbon management consequences, for more effective emissions reduction targets and restoration outcomes.

Mangrove Mapping with the Freeman-Durden Polarimetric Decomposition and Insar Coherence from ALOS-2 - Liao, Tien Hao; Simard, Marc; Marshak, Charlie; Denbina, Michael; Thomas, Nathan (International Geoscience and Remote Sensing Symposium (IGARSS), 2020)
We map mangrove extents in Pongara National Park, Gabon using the Freeman-Durden Decomposition and InSAR Coherence derived from ALOS-2 imagery. Specifically, we obtain a land cover map derived from both this polarimetric decomposition and a 14-day repeat-pass coherence. Our classification model and results are highly interpretable based on a depth 2 decision tree. We further illustrate the correlation between InSAR coherence and height obtaining rough mangrove height estimates from TanDEM-X data. From our results, we observe that repeat-pass interferometric coherence provides invaluable information about mangrove extents and coastal forests. The clear identification of mangrove extents presents a significant opportunity for NISAR, which will provide 12-day repeat pass images over coastal areas globally.

Mangrove trees survive partial sediment burial by developing new roots and adapting their root, branch and stem anatomy - Okello, Judith Auma; Kairo, James Gitundu; Dahdouh-Guebas, Farid; Beeckman, Hans; Koedam, Nico (Trees - Structure and Function, 2020)
Key message: Large sedimentation events resulting in partial burial may negatively affect mangrove trees’ growth and survival. However, mangroves can adapt to respond dynamically within months to sediment burial, attributes which confer resilience. Abstract: Mangrove forests are generally sites of sediment deposition at the coast facilitated by the unique root structure of the trees, thus serving to help the system keep pace with rising sea level. However, at high levels it can cause anoxia in sediments and consequently tree mortality. This study evaluates the morphological and anatomical response of bark and roots of three mangrove tree species (Avicennia marina, Ceriops tagal and Rhizophora mucronata), commonly found along the Kenya coast and around the Indian Ocean, to partial burial by sediment. This was done through simulation of natural and rapid sedimentation in an experiment involving 15, 30 and 45 cm burial levels. Partial sediment burial resulted in an increase in root density which also aided survival particularly in C. tagal, where 5 of the 17 buried trees that did not form new roots in the 45 cm treatment died. Air lacunae in the root cortex became larger in pneumatophores following burial, while the ray parenchyma and cylinder of secondary xylem showed increased widths in cable roots of C. tagal. There was also an induction of the phellogen which produced more outer tissue in the buried section of stems in all three studied species (two fold increase in A. marina and C. tagal and fourfold in R. mucronata). The results suggest that the observed morpho-anatomical adaptations could lead to enhanced performance or recovery of biological processes in the burial-affected trees.

Organic carbon burial and sources in soils of coastal mudflat and mangrove ecosystems - Sasmito, Sigit D.; Kuzyakov, Yakov; Lubis, Ali Arman; Murdiyarso, Daniel; Hutley, Lindsay B.; Bachri, Samsul; Friess, Daniel A.; Martius, Christopher; Borchard, Nils (Catena, 2020)
Mangrove organic carbon is primarily stored in soils, which contain more than two-thirds of total mangrove ecosystem carbon stocks. Despite increasing recognition of the critical role of mangrove ecosystems for climate change mitigation, there is limited understanding of soil organic carbon sequestration mechanisms in undisturbed low-latitude mangroves, specifically on organic carbon burial rates and sources. This study assessed soil organic carbon burial rates, sources and stocks across an undisturbed coastal mudflat and mangrove hydrogeomorphological catena (fringe mangrove and interior mangrove) in Bintuni Bay, West Papua Province, Indonesia. 210Pb radionuclide sediment dating, and mixing model of natural stable isotope signatures (δ 13C and δ15N) and C/N ratio were used to estimate organic carbon burial rates and to quantify proportions of allochthonous (i.e., upland terrestrial forest) and autochthonous (i.e., on-site mangrove forest) organic carbon in the top 50 cm of the soil. Burial rates were in the range of 0.21–1.19 Mg C ha−1 yr−1. Compared to the fringe mangroves, organic carbon burial rates in interior mangroves were almost twice as high. Primary productivity of C3 upland forest vegetation and mangroves induced soil organic carbon burial in interior mangroves and this was consistent with the formation of the largest organic carbon stocks (179 ± 82 Mg C ha−1). By contrast, organic carbon stored in the fringe mangrove (68 ± 11 Mg C ha−1) and mudflat (62 ± 10 Mg C ha−1) soils mainly originated from upland forests (allochthonous origin). These findings clearly indicate that carbon sequestered and cycling in mangrove and terrestrial forest ecosystems are closely linked, and at least a part of carbon losses (e.g., erosion) from terrestrial forests is buried in mangrove ecosystems.

Organic Carbon Stocks of Mexican Montane Habitats: Variation Among Vegetation Types and Land-Use - Santini, Nadia S.; Villarruel-Arroyo, Alfredo; Adame, María Fernanda; Lovelock, Catherine E.; Nolan, Rachael H.; Gálvez-Reyes, Nancy; González, Edgar J.; Olivares-Resendiz, Betzabeth; Mastretta-Yanes, Alicia; Piñero, Daniel (Frontiers in Environmental Science, 2020)
Montane ecosystems occur throughout the world, and harbor many endemic species. They also provide key ecological services, including the catchment of water resources and the storage of organic carbon. These ecosystems are vulnerable to global climate change and increasing human pressures, including forestry and their conversion to arable land. In the extensive and biodiverse Mexican montane regions, ongoing deforestation and conversion to arable lands has led to diminished ecosystem health and services. Here, we undertook a comprehensive evaluation of carbon stocks within Mexican montane habitats in the Flora and Fauna Conservation Area of Nevado de Toluca. This aimed to integrate these habitats into Mexican and global census of forest carbon, the first step needed to convert on carbon credit markets to incentivize conservation of this region by local communities. Our study evaluated both, living biomass and belowground soil organic carbon in sites within forests, alpine grasslands and converted arable land. We addressed the following questions: (1) What are the organic carbon stocks, including the soil component, of our studied montane habitats? (2) What are the avoided CO2 emissions from maintaining natural forests and preventing conversion to arable land? And (3) Within our study area, are organic carbon stocks in the soil correlated to carbon stocks in aboveground living biomass? We found whole ecosystem organic carbon stocks ranged from 68 Mg OC ha–1 in unburnt alpine grasslands to 668 Mg OC ha–1 in Abies religiosa forests. By avoiding conversion of the A. religiosa forests to arable lands, we show that emissions of 1,122 to 1,671 Mg CO2 ha–1 are avoided. Notably, the belowground soil organic carbon stock comprised ≥ 40% of the total ecosystem organic carbon stock. We recommend soil organic carbon stocks should be included within Mexican and global forestry carbon stock inventories, and should be considered within voluntary carbon-credit markets used to incentivize the conservation of Mexican montane habitats.

Past and Present Utilization of Mangrove Resources in Eastern Africa and Drivers of Change - Hamza, Amina Juma; Esteves, Luciana S.; Cvitanovic, Marin; Kairo, James (Journal of Coastal Research, 2020)
Hamza, A.J.; Esteves, L.S.; Cvitanovic, M., and Kairo, J., 2020. Past and present utilization of mangrove resources in Eastern Africa and drivers of change In: Malvárez, G. and Navas, F. (eds.), Global Coastal Issues of 2020. Journal of Coastal Research, Special Issue No. 95, pp. 39-44. Coconut Creek (Florida), ISSN 0749-0208. Mangroves offer natural coastal protection and are carbon sinks, playing a key role in mitigating climate change impacts. Despite their recognized importance as the main livelihood of many coastal communities in developing countries, mangroves are being lost at fast rates impacting overwhelmingly the poorest people. The pressures of changing climate and human activities urge a better understanding of the drivers leading to mangrove loss and degradation and the effects on coastal communities. A systematic literature search was undertaken to review the current understanding of how mangroves have been used through time in Kenya and identify the key drivers of change. Results from 32 articles identified extraction of wood for construction and fuel as the major use of mangrove in Kenya. Direct needs of mangrove resources are the major cause of changes in the mangrove areas and this is due to lack of harvesting plans. The paper emphasizes the need to identify ways in which changes in mangroves can become opportunities to improve coastal communities living conditions.

Plant species determine tidal wetland methane response to sea level rise - Mueller, Peter; Mozdzer, Thomas J.; Langley, J. Adam; Aoki, Lillian R.; Noyce, Genevieve L.; Megonigal, J. Patrick (Nature Communications, 2020)
Blue carbon (C) ecosystems are among the most effective C sinks of the biosphere, but methane (CH4) emissions can offset their climate cooling effect. Drivers of CH4 emissions from blue C ecosystems and effects of global change are poorly understood. Here we test for the effects of sea level rise (SLR) and its interactions with elevated atmospheric CO2, eutrophication, and plant community composition on CH4 emissions from an estuarine tidal wetland. Changes in CH4 emissions with SLR are primarily mediated by shifts in plant community composition and associated plant traits that determine both the direction and magnitude of SLR effects on CH4 emissions. We furthermore show strong stimulation of CH4 emissions by elevated atmospheric CO2, whereas effects of eutrophication are not significant. Overall, our findings demonstrate a high sensitivity of CH4 emissions to global change with important implications for modeling greenhouse-gas dynamics of blue C ecosystems.

Plasticity in the Above- and Below-Ground Development of Mangrove Seedlings in Response to Variation in Soil Bulk Density - Ola, Anne; Staples, Timothy L.; Robinson, Nicole; Lovelock, Catherine E. (Estuaries and Coasts, 2020)
Mangroves store large amounts of organic carbon (C) in their soils and are important in the global C cycle. These C stocks have been attributed to the below-ground productivity of mangroves, yet there is limited knowledge about the environmental factors that influence mangrove root growth. Thus, this study aimed to assess the role of variation in soil bulk density (BD) on the early development of mangroves. Seedlings of four mangrove species were grown in a pot-experiment in soils with a BD ranging from 0.2 to 1.2 g cm−3. Nine functional above- and below-ground plant traits were measured. Above- and below-ground traits of mangrove seedlings were influenced by variation in soil BD, but the effect was species specific. The reaction norms for most plant traits of Bruguiera gymnorrhiza and Rhizophora stylosa suggested a growth optimum at a specific soil BD (0.6 and 0.4 g cm−3, respectively), whilst the reaction norm of Avicennia marina was highly variable among traits, and Ceriops australis showed a very limited response. Moreover, A. marina was the most plastic species above-ground, while R. stylosa was the most plastic species below-ground. Ceriops australis was the least plastic species. Hence, soil BD is an environmental factor that influences mangrove root traits and seedling establishment, and may therefore affect mangrove species distributions and ecosystem C stocks.

Predicting flow and vegetation status in floodplain wetlands during drought - Sandi, S. G.; Rodriguez, J. F.; Saco, P. M.; Kuczera, G.; McDonough, K. R.; Wen, L.; Saintilan, N.; Riccardi, G. (River Flow 2020 - Proceedings of the 10th Conference on Fluvial Hydraulics, 2020)
Floodplain vegetation of semiarid and arid areas of Australia is dependent on the water availability. In some lower floodplains, the complex interaction between flow and the low gradient topography form unique wetland sites that serve as invaluable refugia for a diverse range of fauna. The biodiversity of these sites is then dependent on the deliveries of environmental water, which competes with other water uses such as crop irrigation and human consumption. In the Murray Darling Basin (MDB), water-sharing plans are developed by regulatory authorities to outline the delivery of environmental flow to different ecological assets. Although environmental water deliveries are targeted to produce the best outcomes for vegetation and other habitat services, definition of water releases and monitoring of these outcomes can be aided by the use of predicting tools that would allow assessing vegetation status. We have developed a detailed hydrodynamic model integrated with vegetation response functions to provide estimates of the expected state of the vegetation. Here we analyze the current state of vegetation in the Macquarie Marshes, a wetland site located on the Macquarie River floodplain, in NSW. Inflows into the site are controlled by water releases from a dam upstream. Recently, drought has affected the region and limited the availability of environmental water as defined in the water-sharing plan. We use our model to evaluate the wetland habitat services by simulating the overall condition of the vegetation and by identifying critical areas within the site.

Priorities and Motivations of Marine Coastal Restoration Research - Bayraktarov, Elisa; Brisbane, Shantala; Hagger, Valerie; Smith, Carter S.; Wilson, Kerrie A.; Lovelock, Catherine E.; Gillies, Chris; Steven, Andrew D.L.; Saunders, Megan I. (Frontiers in Marine Science, 2020)
Active restoration is becoming an increasingly important conservation intervention to counteract the degradation of marine coastal ecosystems. Understanding what has motivated the scientific community to research the restoration of marine coastal ecosystems and how restoration research projects are funded is essential if we want to scale-up restoration interventions to meaningful extents. Here, we systematically review and synthesize data to understand the motivations for research on the restoration of coral reefs, seagrass, mangroves, saltmarsh, and oyster reefs. We base this analysis off a published database of marine restoration studies, originally designed to estimate the cost and feasibility of marine coastal restoration, derived from mostly scientific studies published in peer-reviewed and some gray literature. For the present study, the database was updated with fields aimed at assessing the motivations, outcomes, and funding sources for each project. We classify restoration motivations into five categories: biotic, experimental, idealistic, legislative, and pragmatic. Moreover, we evaluate the variables measured and outcomes reported by the researchers and evaluate whether projects adhered to the Society for Ecological Restoration's (SER) standards for the practice of ecological restoration. The most common motivation of the scientific community to study restoration in marine coastal ecosystems was experimental i.e., to seek experimental data to answer ecological research questions or improve restoration approach, as expected since mostly peer-reviewed literature was evaluated here. There were differences in motivations among the five coastal ecosystems. For instance, biodiversity enhancement was the most common case for a biotic motivation in mangrove restoration projects. The most common metrics evaluated were growth/productivity, survivorship, habitat function, physical attributes, and reproduction. For most ecosystems, ecological outcomes were frequently reported, with socio-economic implications of the restoration rarely mentioned, except for mangroves. Projects were largely funded by governmental grants with some investment from private donations, non-governmental organizations, and the involvement of volunteers. Our findings and database provide critical data to align future research of the scientific community with the real social, economic and policy needs required to scale-up marine coastal restoration projects.

Protecting irrecoverable carbon in Earth’s ecosystems - Goldstein, Allie; Turner, Will R.; Spawn, Seth A.; Anderson-Teixeira, Kristina J.; Cook-Patton, Susan; Fargione, Joseph; Gibbs, Holly K.; Griscom, Bronson; Hewson, Jennifer H.; Howard, Jennifer F.; Ledezma, Juan Carlos; Page, Susan; et al. (Nature Climate Change, 2020)
Avoiding catastrophic climate change requires rapid decarbonization and improved ecosystem stewardship. To achieve the latter, ecosystems should be prioritized by responsiveness to direct, localized action and the magnitude and recoverability of their carbon stores. Here, we show that a range of ecosystems contain ‘irrecoverable carbon’ that is vulnerable to release upon land use conversion and, once lost, is not recoverable on timescales relevant to avoiding dangerous climate impacts. Globally, ecosystems highly affected by human land-use decisions contain at least 260 Gt of irrecoverable carbon, with particularly high densities in peatlands, mangroves, old-growth forests and marshes. To achieve climate goals, we must safeguard these irrecoverable carbon pools through an expanded set of policy and finance strategies.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Dahdouh-Guebas, Farid; Ajonina, Gordon N.; Amir, A. Aldrie; Andradi-Brown, Dominic A.; Aziz, Irfan; Balke, Thorsten; Barbier, Edward B.; Cannicci, Stefano; Cragg, Simon M.; Cunha-Lignon, Marília; Curnick, David J.; Duarte, Carlos M.; et al. (Frontiers in Marine Science, 2020)

Reconstructing extreme climatic and geochemical conditions during the largest natural mangrove dieback on record - Sippo, James Z.; Santos, Isaac R.; Sanders, Christian J.; Gadd, Patricia; Hua, Quan; Lovelock, Catherine E.; Santini, Nadia S.; Johnston, Scott G.; Harada, Yota; Reithmeir, Gloria; Maher, Damien T. (Biogeosciences, 2020)
A massive mangrove dieback event occurred in 2015-2016 along ~ 1000km of pristine coastline in the Gulf of Carpentaria, Australia. Here, we use sediment and wood chronologies to gain insights into geochemical and climatic changes related to this dieback. The unique combination of low rainfall and low sea level observed during the dieback event had been unprecedented in the preceding 3 decades. A combination of iron (Fe) chronologies in wood and sediment, wood density and estimates of mangrove water use efficiency all imply lower water availability within the dead mangrove forest. Wood and sediment chronologies suggest a rapid, large mobilization of sedimentary Fe, which is consistent with redox transitions promoted by changes in soil moisture content. Elemental analysis of wood cross sections revealed a 30-to 90-fold increase in Fe concentrations in dead mangroves just prior to their mortality. Mangrove wood uptake of Fe during the dieback is consistent with large apparent losses of Fe from sediments, which potentially caused an outwelling of Fe to the ocean. Although Fe toxicity may also have played a role in the dieback, this possibility requires further study. We suggest that differences in wood and sedimentary Fe between living and dead forest areas reflect sediment redox transitions that are, in turn, associated with regional variability in groundwater flows. Overall, our observations provide multiple lines of evidence that the forest dieback was driven by low water availability coinciding with a strong El Niño-Southern Oscillation (ENSO) event and was associated with climate change.

Respective contribution of urban wastewater and mangroves on nutrient dynamics in a tropical estuary during the monsoon season - Taillardat, Pierre; Marchand, Cyril; Friess, Daniel A.; Widory, David; David, Frank; Ohte, Nobuhito; Nakamura, Takashi; Van Vinh, Truong; Thanh-Nho, Nguyen; Ziegler, Alan D. (Marine Pollution Bulletin, 2020)
Estuaries of Southeast Asia are increasingly impacted by land-cover changes and pollution. Here, our research objectives were to (1) determine the origins of nutrient loads along the Can Gio estuary (Vietnam) and (2) identify the processes that affect the nutrient pools during the monsoon. We constructed four 24-h time-series along the salinity gradient measuring nutrient concentrations and stable isotopes values. In the upper estuary, urban effluents from Ho Chi Minh City were the main input of nutrients, leading to dissolved oxygen saturation <20%. In the lower estuary, ammonium and nitrite concentration peaks were explained by mangrove export. No contribution from aquaculture was detected, as it represents <0.01% of the total river discharge. Along the salinity gradient, nutrient inputs were rapidly consumed, potentially by phytoplankton while nitrate dual-stable isotopes indicated that nitrification occurred. Thus, even in a large and productive estuary, urban wastewater can affect nutrient dynamics with potentially important ecological risks.

Role of vegetated coastal ecosystems as nitrogen and phosphorous filters and sinks in the coasts of Saudi Arabia - Saderne, V.; Cusack, M.; Serrano, O.; Almahasheer, H.; Krishnakumar, P. K.; Rabaoui, L.; Qurban, M. A.; Duarte, C. M. (Environmental Research Letters, 2020)
Vegetated coastal ecosystems along the Red Sea and Arabian Gulf coasts of Saudi Arabia thrive in an extremely arid and oligotrophic environment, with high seawater temperatures and salinity. Mangrove, seagrass and saltmarsh ecosystems have been shown to act as efficient sinks of sediment organic carbon, earning these vegetated ecosystems the moniker 'blue carbon' ecosystems. However, their role as nitrogen and phosphorus (N and P) sinks remains poorly understood. In this study, we examine the capacity of blue carbon ecosystems to trap and store nitrogen and phosphorous in their sediments in the central Red Sea and Arabian Gulf. We estimated the N and P stocks (in 0.2 m thick-sediments) and accumulation rates (for the last century based on 210Pb and for the last millennia based on 14C) in mangrove, seagrass and saltmarsh sediments from eight locations along the coast of Saudi Arabia (81 cores in total). The N and P stocks contained in the top 20 cm sediments ranged from 61 g N m-2 in Red Sea seagrass to 265 g N m-2 in the Gulf saltmarshes and from 70 g P m-2 in Red Sea seagrass meadows and mangroves to 58 g P m-2 in the Gulf saltmarshes. The short-term N and P accumulation rates ranged from 0.09 mg N cm-2 yr-1 in Red Sea seagrass to 0.38 mg N cm-2 yr-1 in Gulf mangrove, and from 0.027 mg P cm-2 yr-1 in the Gulf seagrass to 0.092 mg P cm-2 yr-1 in Red Sea mangroves. Short-term N and P accumulation rates were up to 10-fold higher than long-term accumulation rates, highlighting increasing sequestration of N and P over the past century, likely due to anthropogenic activities such as coastal development and wastewater inputs.

Seagrass fatty acid profiles as a sensitive indicator of climate settings across seasons and latitudes - Beca-Carretero, Pedro; Guihéneuf, Freddy; Krause-Jensen, Dorte; Stengel, Dagmar B. (Marine Environmental Research, 2020)
Zostera marina is a dominant meadow-forming seagrass in temperate regions in the northern hemisphere. Here, fatty acid content and composition, and pigmentation, in leaves were evaluated across temporal (April, July, November −2015 and January-2016) and latitudinal (Greenland to southern Spain) environmental gradients. Content of total fatty acids (TFA) in samples collected in Ireland during warmer periods (summer) was 2–3 times lower than in winter and exhibited a lower proportion of polyunsaturated fatty acids (PUFAs), which have high high-nutritional value relative to saturated fatty acids (SAFA). The latitudinal comparison (Greenland to southern Spain) revealed a clear reduction in the proportion n-3 PUFAs and an increase in n-6 PUFA and SAFA, which correlated with the rise in temperature towards southern locations, which correlated with the rise in temperature towards south. Results indicate that future warming may negatively affect its lipid nutritional value. These results demonstrate the capacity of seagrasses to adjust their lipid composition to achieve optimal membrane functionality, suggesting the potential use of FA as an eco-physiological indicator of global change conditions. The results also suggest that future warming may negatively affect the lipid nutritional value of seagrasses.

Short-lived effects of nutrient enrichment on Avicennia germinans decomposition in a saltmarsh-mangrove ecotone - Simpson, L. T.; Lovelock, C. E.; Cherry, J. A.; Feller, I. C. (Estuarine, Coastal and Shelf Science, 2020)
Rates of litter decomposition, an important component of the global carbon (C) cycle, often depend on litter quality and decomposer activity, which can then drive differences in C sequestration and storage in ecosystems. Nutrient enrichment may alter C storage in wetlands through its effects on litter quality. We investigated the effects of long-term nitrogen (N) and phosphorus (P) enrichment on Avicennia germinans litter quality and above- and belowground decomposition rates in a saltmarsh-mangrove ecotone in St. Augustine, Florida, U.S.A. Senescent leaf litter collected from Control, +N-, and +P-fertilized shrubs was placed in litterbags for use in a reciprocal transplant experiment, with each litter treatment placed on the soil adjacent to each fertilized shrub (Control, +N, and +P). Leaf litterbags were collected at 0, 14, 30, 60 and 180 days, while roots collected from a common, unfertilized location were incubated belowground at each shrub for 180 and 365 days to determine mass loss and decay rates. Nutrient enrichment did not alter %N, C:N, or %lignin in treatment leaves, and there were subsequently no significant differences in decay rates of treatment leaves, likely due to the homogeneity of litter quality. Initial decay rates (30 and 60 days) were significantly higher in +N and +P fertilized soils compared to controls, but by 180 days decay rates had stabilized to 0.009 ± 0.0003 k day−1. Labile fractions were rapidly decomposed and net immobilization of litter was favored after 60 days of incubation irrespective of nutrient treatments. Additionally, belowground root decomposition with roots from unfertilized plants did not vary across nutrient treatments. Thus, nutrient enrichment of A. germinans did not alter litter quality considerably or increase decomposition in the longer term, and therefore, we do not expect a substantial decline in sediment C sequestration as a result of eutrophication in this mangrove system.

Structural characterisation of mangrove forests achieved through combining multiple sources of remote sensing data - Lucas, Richard; Van De Kerchove, Ruben; Otero, Viviana; Lagomasino, David; Fatoyinbo, Lola; Omar, Hamdan; Satyanarayana, Behara; Dahdouh-Guebas, Farid (Remote Sensing of Environment, 2020)
Temporal information on mangrove extent, age, structure and biomass provides an important contribution towards understanding the role of these ecosystems in terms of the services they provide (e.g., in relation to storage of carbon, conservation biodiversity), particularly given the diversity of influences of human activity and natural events and processes. Focusing on the Matang Mangrove Forest Reserve (MMFR) in Perak Province, Peninsular Malaysia, this study aimed to retrieve comprehensive information on the biophysical properties of mangroves from spaceborne optical and Synthetic Aperture Radar (SAR) to support better understanding of their dynamics in a managed setting. For the period 1988 to 2016 (29 years), forest age was estimated on at least an annual basis by combining time-series of Landsat-derived Normalised Difference Moisture Index (NDMI) and Japanese L-band Synthetic Aperture Radar (SAR) data. The NDMI was further used to retrieve canopy cover (%). Interferometric Shuttle Radar Topographic Mission (SRTM) X/C-band (2000), TanDEM-X-band (2010–2016) and stereo WorldView-2 stereo (2016) data were evaluated for their role in estimating canopy height (CH), from which above ground biomass (AGB, Mg ha−1) was derived using pre-established allometry. Whilst both L-band HH and HV data increased with AGB after about 8–10 years of growth, retrieval was compromised by mixed scattering from varying amounts of dead woody debris following clearing and wood material within regenerating forests, thinning of trees at ~15 and 20 years, and saturation of L-band SAR data after approximately 20 years of growth. Reference was made to stereo Phantom-3 DJI stereo imagery to support estimation of canopy cover (CC) and validation of satellite-derived CH. AGB estimates were compared with ground-based measurements. Using relationships with forest age, both CH and AGB were estimated for each date of Landsat or L-band SAR observation and the temporal trends in L-band SAR were shown to effectively track the sequences of clearing and regeneration. From these, four stages of the harvesting cycle were defined. The study provided new information on the biophysical properties and growth dynamics of mangrove forests in the MMFR, inputs for future monitoring activities, and methods for facilitating better characterisation and mapping of mangrove areas worldwide.

Structure and biomass accumulation of natural mangrove forest at Gazi Bay, Kenya - KAIRO, JAMES G.; GITHAIGA, MICHAEL NJOROGE; KOTUT, KIPLAGAT; KARIUKI, FRANCIS (International Journal of Bonorowo Wetlands, 2020)
Abstract. Githaiga MN, Kotut K, Kariuki F, Kairo JG. 2019. Structure and biomass accumulation of natural mangrove forest at Gazi Bay, Kenya. Bonorowo Wetlands 9: 18-32. The goal of this study was to determine the forest structure and estimate biomass accumulation above and below ground in the mangrove forest of Gazi Bay. The western, middle, and eastern forest blocks of the Gazi Bay mangrove forest were investigated for forest structure, whereas the western forest block was determined for biomass accumulation. To calculate below-ground biomass accumulation, in-growth cores of 80 cm long, 20 cm broad, and 60 cm deep were employed. Above-ground biomass accumulation was calculated using data on tree height and stem diameter at breast height (DBH-130). Leaf phenology was observed by tagging shoots. At the start, environmental variables were measured every four months for a year across four mangrove species zones. The linear regeneration sampling approach was used to determine the composition and distribution pattern of natural regeneration (LRS). Salinity revealed a strong negative connection with above-ground biomass accumulation among the soil environment characteristics studied. Sonneratia alba had the highest biomass accretion rate of 10.5 1.9 t ha-1 yr-1 among the four forest zones. Rhizophora mucronata (8.5 0.8 t ha-1 yr-1), Avicennia marina (5.2 1.8 t ha-1 yr-1), and Ceriops tagal (2.6 1.5 t ha-1 yr-1) were the next most abundant species. Above-ground and below-ground biomass accumulation differed significantly among zones (F (3, 8) = 5.42, p = 0.025) and (F (3, 8) = 16.03, p = 0 001), respectively. There was a significant difference in total biomass accumulation across zones (F (3, 8) =15.56, p = 0.001). For the entire forest, a root : shoot biomass accumulation ratio of 2 : 5 was calculated. This study's findings provide more accurate estimates of mangrove carbon capture and storage, which can be used in carbon credit discussions in the emerging carbon market.

Submarine groundwater discharge along the northern coast of the Yucatán Peninsula - Murgulet, Dorina; Douglas, Audrey; Herrera Silveira, Jorge; Mariño Tapia, Ismael; Valle-Levinson, Arnoldo (2020)

The google earth engine mangrove mapping methodology (Geemmm) - Yancho, J. Maxwell M.; Jones, Trevor Gareth; Gandhi, Samir R.; Ferster, Colin; Lin, Alice; Glass, Leah (Remote Sensing, 2020)
Mangroves are found globally throughout tropical and sub-tropical inter-tidal coastlines. These highly biodiverse and carbon-dense ecosystems have multi-faceted value, providing critical goods and services to millions living in coastal communities and making significant contributions to global climate change mitigation through carbon sequestration and storage. Despite their many values, mangrove loss continues to be widespread in many regions due primarily to anthropogenic activities. Accessible, intuitive tools that enable coastal managers to map and monitor mangrove cover are needed to stem this loss. Remotely sensed data have a proven record for successfully mapping and monitoring mangroves, but conventional methods are limited by imagery availability, computing resources and accessibility. In addition, the variable tidal levels in mangroves presents a unique mapping challenge, particularly over geographically large extents. Here we present a new tool—the Google Earth Engine Mangrove Mapping Methodology (GEEMMM)—an intuitive, accessible and replicable approach which caters to a wide audience of non-specialist coastal managers and decision makers. The GEEMMM was developed based on a thorough review and incorporation of relevant mangrove remote sensing literature and harnesses the power of cloud computing including a simplified image-based tidal calibration approach. We demonstrate the tool for all of coastal Myanmar (Burma)—a global mangrove loss hotspot—including an assessment of multi-date mapping and dynamics outputs and a comparison of GEEMMM results to existing studies. Results—including both quantitative and qualitative accuracy assessments and comparisons to existing studies—indicate that the GEEMMM provides an accessible approach to map and monitor mangrove ecosystems anywhere within their global distribution.

The interplay between vegetation and water in mangroves: new perspectives for mangrove stand modelling and ecological research - Peters, Ronny; Walther, Marc; Lovelock, Catherine; Jiang, Jiang; Berger, Uta (Wetlands Ecology and Management, 2020)
It is commonly accepted that vegetation patterns and water supply mutually define each other. In mangroves, soil water salinity and the corresponding osmotic potential are the main drivers of plant water supply. Below-ground processes thus may be key for the structure and dynamics of mangrove stands. Nevertheless, existing simulation models describing mangrove forest dynamics do not quantify the water uptake of the single plant from the soil and traditionally neglect any feedback of the vegetation on the water availability, but instead use empirical, statistical models for plant competition affecting growth. We provide a brief review on the state of the art of mangrove forest models with an emphasis on how below-ground processes are regarded. We follow mainly two directions: (1) phenomenological concepts for competition for below-ground resources and (2) assessing the impact of salinity and water supply on the vegetation and possible feedback mechanisms from the vegetation to the below-ground conditions. We hypothesise that a coupled vegetation-groundwater model would avail us to better understand the dynamics and properties of mangrove systems, their capability to persist or rehabilitate under stressful hydrological conditions, as well as their response to environmental changes related to the groundwater system and transport. The benefits of such a joint approach would (i) constitute an intrinsic below-ground competition description close to the governing processes and (ii) concurrently exploit secondary, constraining information from vegetation patterns to derive a new concept to acquire knowledge on subsurface heterogeneity and parametrisation. The aim of this paper is to lay the theoretical groundwork and guidelines for future modellers to follow in the creation of a more realistic mangrove model coupling above- and below-ground processes. The proposed modelling approach has the potential to be useful for a broad audience based particularly in forest sciences and plant ecology in general, but also for hydrodynamic modelling (e.g. subsurface flow and transport detected by vegetation patterns as above-ground proxy).

Thirty-Year Repeat Measures of Mangrove Above- and Below-Ground Biomass Reveals Unexpectedly High Carbon Sequestration - Lamont, Karen; Saintilan, Neil; Kelleway, Jeffrey J.; Mazumder, Debashish; Zawadzki, Atun (Ecosystems, 2020)
Mangrove ecosystems store large quantities of organic carbon for long periods of time. This study explores organic carbon stock change through the first comparative study of radiometric analysis and repeat field measures over a multi-decadal period in a mangrove system. Examining one tall gallery forest of Avicennia marina, and an adjacent interior scrub mangrove of mixed Avicennia marina and Aegiceras corniculatum, radiometric analysis estimated a soil organic carbon accumulation rate of 4.3 ± 0.6 Mg C ha−1 y−1 in the tall gallery forest and 2.2 ± 0.5 Mg C ha−1 y−1 in a stunted mangrove. Repeat measures of root carbon separated by 30 years estimated an increase of 5.06 Mg C ha−1 y−1 in the tall forest and 6.63 Mg C ha−1 y−1 in the stunted forest—suggesting an underestimate of carbon accumulation by radiometric dating of 15% and 67% in the tall and stunted forest, respectively. A higher carbon stock in the interior forest was attributed to root mass increase, associated with landward mangrove encroachment. Extrapolated to the entire region of NSW we estimate that mangrove encroachment has contributed at least about 1.8 Tg C sequestration over the 70 years for which this has been observed in New South Wales, Australia.

Tropical seagrass Halophila stipulacea shifts thermal tolerance during Mediterranean invasion - Wesselmann, Marlene; Anton, Andrea; Duarte, Carlos M.; Hendriks, Iris E.; Agustí, Susana; Savva, Ioannis; Apostolaki, Eugenia T.; Marbà, Núria (Proceedings of the Royal Society B: Biological Sciences, 2020)
Exotic species often face new environmental conditions that are different from those that they are adapted to. The tropical seagrass Halophila stipulacea is a Lessepsian migrant that colonized the Mediterranean Sea around 100 years ago, where at present the minimum seawater temperature is cooler than in its native range in the Red Sea. Here, we tested if the temperature range in which H. stipulacea can exist is conserved within the species or if the exotic populations have shifted their thermal breadth and optimum due to the cooler conditions in the Mediterranean. We did so by comparing the thermal niche (e.g. optimal temperatures, and upper and lower thermal limits) of native (Saudi Arabia in the Red Sea) and exotic (Greece and Cyprus in the Mediterranean Sea) populations of H. stipulacea. We exposed plants to 12 temperature treatments ranging from 8 to 40°C for 7 days. At the end of the incubation period, we measured survival, rhizome elongation, shoot recruitment, net population growth and metabolic rates. Upper and lower lethal thermal thresholds (indicated by 50% plant mortality) were conserved across populations, but minimum and optimal temperatures for growth and oxygen production were lower for Mediterranean populations than for the Red Sea one. The displacement of the thermal niche of exotic populations towards the colder Mediterranean Sea regime could have occurred within 175 clonal generations.

UN Decade on Ecosystem Restoration 2021–2030—What Chance for Success in Restoring Coastal Ecosystems? - Waltham, Nathan J.; Elliott, Michael; Lee, Shing Yip; Lovelock, Catherine; Duarte, Carlos M.; Buelow, Christina; Simenstad, Charles; Nagelkerken, Ivan; Claassens, Louw; Wen, Colin K.C.; Barletta, Mario; Connolly, Rod M.; et al. (Frontiers in Marine Science, 2020)

Variation in Seagrass Carbon Stocks Between Tropical Estuarine and Marine Mangrove-Fringed Creeks - Juma, Gabriel A.; Magana, Adiel M.; Michael, Githaiga N.; Kairo, James G. (Frontiers in Marine Science, 2020)
Seagrass and associated blue carbon ecosystems are important carbon sinks, and hence understanding their spatial and temporal variability is vital in appreciating their potential roles in climate change mitigation and adaptation. The Indo-Pacific region has the highest seagrass biodiversity, yet little focus has been made to compare seagrass habitat extent and carbon dynamics with their temperate counterparts. The present study assessed habitat characteristics and seagrass species distribution, diversity, and carbon storage in Eastern (marine) and Western (estuarine) mangrove-fringed creeks of Gazi Bay, Kenya. Data on species composition, canopy cover, biomass, and sediment organic carbon were collected in 80 plots of 0.25 × 0.25 m laid along transects established perpendicular to the waterline. Five species formation, viz., Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, and Thalassidendron ciliatum, were encountered as either single or mixed stands. There was a significant difference in total seagrass biomass between creeks (p < 0.01), with the Eastern creek recording a mean of 10.2 ± 0.6 Mg C ha–1 while the Western creek recording 4.3 ± 0.3 Mg C ha–1. In addition, sediment carbon to 1-m depth varied significantly (p < 0.01) between species in the two creeks and ranged from 98 to 302 Mg C ha–1, with the Eastern and Western creeks recording means of 258 ± 90 and 107 ± 21 Mg C ha–1, respectively. The total carbon stock from 50 ha of seagrasses in the Eastern creek was 13,420 Mg C, whereas in the 70 ha of the Western creek it was 7,769 Mg C. The study shows that seagrass community attributes such as species composition and productivity can vary dramatically over a small spatial extent due to differences in biophysical conditions and caution estimations of site-specific carbon stocks using generalized global values.

Vulnerability of mangrove ecosystems to climate change effects: The case of the Yucatan Peninsula - Cinco-Castro, Siuling; Herrera-Silveira, Jorge (Ocean and Coastal Management, 2020)
Climate change adds an additional pressure on mangrove health, and the present study evaluated mangroves' vulnerability to sea level rises at four sites (Los Petenes, Celestun, Cancun, and Mahahual) on the Yucatan Peninsula, Mexico. Exposure, sensitivity, and adaptive capacity were evaluated on a scale from 1 to 5 to identify characteristics that cause the mangrove vulnerability. Mangroves in sites with different characteristics had different vulnerabilities, despite having similar exposure. The best-conserved mangroves had low vulnerability and were in good health because of their sensitivity, whereas mangroves affected by human activity were more vulnerable in terms of sensitivity and adaptive capacity. Overall, Mahahual had the highest vulnerability (3.0) because of its low tidal range (~5 cm), changes in precipitation (−25 mm year−1), poor ecological conditions (low basal area without positive changes), low resilience of adjacent ecosystems (poor condition of coral reefs and seagrass meadows), and poor mangrove protection. This vulnerability assessment method identifies factors that affect vulnerability and can be used to develop management strategies that decrease mangrove vulnerability to climate change by reducing sensitivity and increasing the adaptive capacity of the ecosystem and the surrounding communities.

Widespread mangrove damage resulting from the 2017 Atlantic mega hurricane season - Taillie, P.J.; Roman-Cuesta, R.; Lagomasino, D.; Cifuentes-Jara, M.; Fatoyinbo, T.; Ott, L.E.; Poulter, B. (Environmental Research Letters, 2020)
Comprised of 17 named tropical storms, 6 of which were major hurricanes, the 2017 Atlantic hurricane season ranked as one of the most damaging and costly hurricane seasons on record. In addition to socio-economic impacts, many previous studies have shown that important coastal ecosystems like mangroves are shaped by severe storms. However, little is known about how the cumulative effects of storms over entire hurricane seasons affect mangroves across large regions. We used satellite imagery from the entire Caribbean and Gulf of Mexico region to show that 2017 resulted in disproportionate mangrove damage compared to baseline responses over the previous 8 years. Specifically, we observed 30 times more mangrove damage, via a reduction in the normalized difference vegetation index (NDVI), during 2017 compared to any of the eight previous hurricane seasons, and most (72%) of this damage persisted throughout the 7 month post-hurricane season period as indicated by no NDVI recovery. Furthermore, wind speed, rainfall, and canopy height data showed that mangrove damage primarily resulted from high maximum wind speeds, but flooding (cumulative rainfall), previous storm history, and mangrove structure (canopy height) were also important predictors of damage. While mangroves are known to be resilient to hurricane impacts, our results suggest that increasingly frequent mega-hurricane seasons in the Caribbean region will dramatically alter mangrove disturbance dynamics.
Keywords: coastal wetlands; disturbance; forest; remote sensing; tropical cyclone

A question of standards: Adapting carbon and other PES markets to work for community seagrass conservation - Shilland, Robyn; Grimsditch, Gabriel; Ahmed, Mohamed; Bandeira, Salomão; Kennedy, Hilary; Potouroglou, Maria; Huxham, Mark (Marine Policy, 2021)
Seagrass meadows deliver multiple ecosystem services that are of particular importance to resource-poor coastal communities, yet they are rapidly declining globally. The Payments for Ecosystem Services (PES) approach has been used to fund the protection of other ‘Blue Carbon’ Ecosystems (BCE), yet seagrass has been incorporated in just one PES project worldwide. Some of the ecosystem services delivered by seagrass have the potential for inclusion under a PES framework but multiple challenges currently make this difficult, particularly under community-based management. PES programmes typically focus on carbon as the tradable service, but scientific uncertainties regarding seagrass carbon are likely to remain significant barriers to using carbon as the sole commodity under current carbon trading standards and market conditions. It is recommended here that project developers demonstrate the multiple ecosystem services delivered by seagrass meadows, along with their importance to coastal communities, in the planning and marketing of seagrass PES projects. Moreover, they should consider approaches that incorporate seagrass meadows into other blue carbon certified projects. The capacities of the communities that rely most heavily on seagrass are generally very limited. Consequently, demanding high levels of scientific certainty over carbon stocks and flows will exclude most of these communities. Standards, buyers and policy makers should consider building community capacity in the technical and marketing requirements of voluntary carbon standards. The voluntary carbon market has the flexibility to pioneer certified seagrass carbon, potentially leading to the inclusion of seagrass carbon in formal policy instruments, such as Nationally Determined Contributions (NDCs).

Accelerated Sea-Level Rise Limits Vegetation Capacity to Sequester Soil Carbon in Coastal Wetlands: A Study Case in Southeastern Australia - Sandi, S. G.; Rodriguez, J. F.; Saco, P. M.; Saintilan, N.; Riccardi, G. (Earth's Future, 2021)
Estimates of global carbon stocks in coastal wetlands reveal that these are some of the most efficient carbon-sequestering environments in the world, which has prompted a renewed interest in conservation and restoration programs as an opportunity for greenhouse gas abatement. Accumulation of carbon in coastal wetlands is linked to diverse factors such as the type of vegetation, geomorphic setting, and sediment supply. Feedbacks between these factors and the tidal flow conditions drive the dynamics of carbon accumulation rates. Climate change-induced sea-level rise has been shown to increase the vulnerability to submergence of saltmarsh and mangroves in coastal wetlands, even if accommodation and landward colonization are possible. These potential losses of wetland vegetation combined with the reduced productivity of newly colonized areas will directly affect the capacity of the wetlands to sequester carbon from sediments and root growth. Here, we implement an eco-geomorphic model to simulate vegetation dynamics, soil carbon accumulation, and changes in soil carbon stock for a restored mangrove-saltmarsh wetland experiencing accelerated sea-level rise. We evaluate model outcomes for existing conditions and two different management scenarios aimed at mitigating sea-level rise effects and conserve wetland vegetation. Even though some management measures can result in partial conservation of wetland vegetation, they do not necessarily result in the best option for soil carbon capture. Our results suggest that accelerated sea-level can trigger accelerated wetland colonization resulting in wetland areas with limited opportunities for soil carbon capture from sediment and root mineralization, an issue that has not been considered in previous studies.

Accommodating complexities: Enhancing understanding of the impacts of sea-level rise. A commentary on Kerrylee Rogers’ ‘Accommodation space as a framework for assessing the response of mangroves to relative sea-level rise’. - Lovelock, Catherine E. (Singapore Journal of Tropical Geography, 2021)

Application of feature selection methods and machine learning algorithms for saltmarsh biomass estimation using Worldview-2 imagery - Rasel, Sikdar M.M.; Chang, Hsing Chung; Ralph, Timothy J.; Saintilan, Neil; Diti, Israt Jahan (Geocarto International, 2021)
Assessing large scale plant productivity of coastal marshes is essential to understand the resilience of these systems to climate change. Two machine learning approaches, random forest (RF) and support vector machine (SVM) regression were tested to estimate biomass of a common saltmarshes species, salt couch grass (Sporobolus virginicus). Reflectance and vegetation indices derived from 8 bands of Worldview-2 multispectral data were used for four experiments to develop the biomass model. These four experiments were, Experiment-1: 8 bands of Worldview-2 image, Experiment-2: Possible combination of all bands of Worldview-2 for Normalized Difference Vegetation Index (NDVI) type vegetation indices, Experiment-3: Combination of bands and vegetation indices, Experiment-4: Selected variables derived from experiment-3 using variable selection methods. The main objectives of this study are (i) to recommend an affordable low cost data source to predict biomass of a common saltmarshes species, (ii) to suggest a variable selection method suitable for multispectral data, (iii) to assess the performance of RF and SVM for the biomass prediction model. Cross-validation of parameter optimizations for SVM showed that optimized parameter of ɛ-SVR failed to provide a reliable prediction. Hence, ν-SVR was used for the SVM model. Among the different variable selection methods, recursive feature elimination (RFE) selected a minimum number of variables (only 4) with an RMSE of 0.211 (kg/m2). Experiment-4 (only selected bands) provided the best results for both of the machine learning regression methods, RF (R 2= 0.72, RMSE= 0.166 kg/m2) and SVR (R 2= 0.66, RMSE = 0.200 kg/m2) to predict biomass. When a 10-fold cross validation of the RF model was compared with a 10-fold cross validation of SVR, a significant difference (p = <0.0001) was observed for RMSE. One to one comparisons of actual to predicted biomass showed that RF underestimates the high biomass values, whereas SVR overestimates the values; this suggests a need for further investigation and refinement.

Biogeochemical and plant trait mechanisms drive enhanced methane emissions in response to whole-ecosystem warming - Noyce, Genevieve L.; Patrick Megonigal, J. (Biogeosciences, 2021)
Climate warming perturbs ecosystem carbon (C) cycling, causing both positive and negative feedbacks on greenhouse gas emissions. In 2016, we began a tidal marsh field experiment in two vegetation communities to investigate the mechanisms by which whole-ecosystem warming alters C gain, via plant-driven sequestration in soils, and C loss, primarily via methane (CH4) emissions. Here, we report the results from the first 4 years. As expected, warming of 5.1 °C more than doubled CH4 emissions in both plant communities. We propose this was caused by a combination of four mechanisms: (i) a decrease in the proportion of CH4 consumed by CH4 oxidation, (ii) more C substrates available for methanogenesis, (iii) reduced competition between methanogens and sulfate-reducing bacteria, and (iv) indirect effects of plant traits. Plots dominated by Spartina patens consistently emitted more CH4 than plots dominated by Schoenoplectus americanus, indicating key differences in the roles these common wetland plants play in affecting anaerobic soil biogeochemistry and suggesting that plant composition can modulate coastal wetland responses to climate change.

Calcification-driven CO2emissions exceed "blue Carbon" sequestration in a carbonate seagrass meadow - Van Dam, Bryce R.; Zeller, Mary A.; Lopes, Christian; Smyth, Ashley R.; Böttcher, Michael E.; Osburn, Christopher L.; Zimmerman, Tristan; Pröfrock, Daniel; Fourqurean, James W.; Thomas, Helmuth (Science Advances, 2021)
Long-term "Blue Carbon"burial in seagrass meadows is complicated by other carbon and alkalinity exchanges that shape net carbon sequestration. We measured a suite of such processes, including denitrification, sulfur, and inorganic carbon cycling, and assessed their impact on air-water CO2 exchange in a typical seagrass meadow underlain by carbonate sediments. Eddy covariance measurements reveal a consistent source of CO2 to the atmosphere at an average rate of 610 ± 990 μmol m-2 hour-1 during our study and 700 ± 660 μmol m-2 hour-1 (6.1 mol m-2 year-1) over an annual cycle. Net alkalinity consumption by ecosystem calcification explains >95% of the observed CO2 emissions, far exceeding organic carbon burial and anaerobic alkalinity generation. We argue that the net carbon sequestration potential of seagrass meadows may be overestimated if calcification-induced CO2 emissions are not accounted for, especially in regions where calcification rates exceed net primary production and burial.

Carbon Stocks from Peat Swamp Forest and Oil Palm Plantation in Central Kalimantan , Indonesia - Novita, Nisa; Kauffman, J Boone; Hergoualc, Kristell; Murdiyarso, Daniel; Tryanto, Dede Hendry; Jupesta, Joni (Springer International Publishing, 2021)
Keywords: Tropical peat forest,Land-use change,Oil palm,Indo

Carbon storage in the coastal Swamp Oak Forest Wetlands of Australia - Kelleway, Jeffrey J.; Adame, Maria Fernanda; Gorham, Connor; Bratchell, Jennifer; Serrano, Oscar; Lavery, Paul S.; Owers, Christopher J.; Rogers, Kerrylee; Nagel-Tynan, Zachary; Saintilan, Neil (Wetland Carbon and Environmental Management, 2021)
Coastal Swamp Oak Forests (CSOF) dominated by the species Casuarina glauca are an Endangered Ecological Community under state and Commonwealth legislation in Australia. These forests have suffered significant historic declines due to changes in land use and hydrological modification. Although they have a limited contemporary extent (~320 to over 500 km 2 ) along the east coast of Australia, CSOF represent part of a much larger range of supratidal forested wetlands in Australia, which include wetlands vegetated by the more broadly distributed genus Melaleuca. For the first time, in this chapter we estimated aboveground and 1 m-depth belowground organic carbon (C org ) stocks in CSOF (mean ± SD: 143 ± 61 Mg C org /ha and 241 ± 136 Mg C org /ha, respectively) across six study sites in temperate and subtropical Australia. Variations in aboveground C org stock are explained by differences in the stature and structure of forests, while belowground C org stocks appear more reflective of within- and among-estuary variations in geomorphic evolution. These early findings show that C org stocks in CSOF are within the range of values reported for mangrove, saltmarsh and seagrass ecosystems. Our data provide a foundation for future research efforts to determine the carbon sequestration potential of CSOF, and their amenability to management interventions which seek to reverse past losses and contribute to climate change mitigation.

Century-long records reveal shifting challenges to seagrass recovery - Krause-Jensen, Dorte; Duarte, Carlos M.; Sand-Jensen, Kaj; Carstensen, Jacob (Global Change Biology, 2021)
Global losses over the 20th century placed seagrass ecosystems among the most threatened ecosystems in the world, with eutrophication, and associated deterioration of the submarine light environment identified as the main driver. Growing appreciation of the ecological and societal benefits of healthy seagrass meadows has stimulated efforts to protect and restore them, largely focused on reducing nutrient input to coastal waters. Here we analyze a unique data set spanning 135 years on eelgrass (Zostera marina), the dominant seagrass of the northern hemisphere. We show that meadows in the Western Baltic Sea exhibited major declines relative to historic (1890–1910) reference due to the wasting disease in the 1930s followed by eutrophication peaking in the 1980s, but have only shown modest improvement despite major eutrophication mitigation, halving nitrogen input since the 1980s. Across the past century, we identified generally shallower colonization depths of eelgrass for a given submarine light penetration and, hence, increased apparent light requirements. This suggests that eelgrass recovery is limited by additional stressors. Our study indicates that bottom trawling and intense recent warming (0.5°C per decade, 1985–2018), which impact on deeper and shallower meadows, respectively, suppress eelgrass from fully recovering from eutrophication. Warming is most severe in shallow turbid waters, while clear-water areas offer eelgrass refugia from warming in deeper, cooler waters; but trawling can prevent eelgrass from reaching these refugia. Efforts to reduce nutrient input and thereby improve water clarity have been instrumental in avoiding a catastrophic loss of eelgrass ecosystems. However, local-scale future management must, in addition, reduce bottom trawling to facilitate eelgrass reaching deeper, cooler refugia, and increase resilience toward realized and further warming. Warming needs to be limited by meeting global climate change mitigation goals.

Comparative Assessment of Natural, Colonized and Planted Mangroves Disturbed by Lahar Deposition in Sasmuan, Pampanga, Philippines - Joson, Ma Patricia; Comia, Mark Joseph; Cureg, Ma Klarice; Navarrete, Ian A.; Salmo, Severino G. (Science and Engineering Journal, 2021)
The lahar deposition from the eruption of Mt. Pinatubo in 1991 altered the mangrove mudflat in Sasmuan, Pampanga. Here, we assessed and compared the vegetation and sediment characteristics of mangroves composed of pre-eruption natural stands, post-eruption colonized stands (ca. 20 yr-old), and post-eruption planted stands (ca. 7 yr-old). Our results revealed that coarse sediments dominated more relative to the fine fractions, which may be related to the massive lahar deposition in the mudflat areas. In natural stands, the organic matter (OM) decreased at 80 to 100 cm depth that coincided with high coarse content but increased from 80 cm to surface implying post-disturbance OM accumulation. Both the colonized and planted stands have similar low OM at the bottom than the natural stands. Similar patterns were observed with bulk density (BD). The natural and colonized stands have comparable vegetation and sediment characteristics implying that mangroves subjected to post-disturbance colonization process may have similar attributes with a pre-disturbance stand in ca. 20 yrs. Although the deposition of lahar materials altered the growth of pre-eruption mangrove stands, the aeration and accretion provided by coarse fractions (on a usually asphyxiated and inundated sediment) may have facilitated mangrove colonization that led to the development of the colonized stands. To our knowledge, our study was the first to report the impacts of lahar in Philippine mangroves.

Comprehensive comparison of airborne and spaceborne SAR and LiDAR estimates of forest structure in the tallest mangrove forest on earth - Stovall, Atticus E.L.; Fatoyinbo, Temilola; Thomas, Nathan M.; Armston, John; Ebanega, Médard Obiang; Simard, Marc; Trettin, Carl; Obiang Zogo, Robert Vancelas; Aken, Igor Akendengue; Debina, Michael; Me Kemoe, Alphna Mekui; Assoumou, Emmanuel Ondo; et al. (Science of Remote Sensing, 2021)
A recent suite of new global-scale satellite sensors and regional-scale airborne campaigns are providing a wealth of remote sensing data capable of dramatically advancing our current understanding of the spatial distribution of forest structure and carbon stocks. However, a baseline for forest stature and biomass estimates has yet to be established for the wide array of available remote sensing products. At present, it remains unclear how the estimates from these sensors compare to one another in terrestrial forests, with a clear dearth of studies in high carbon density mangrove ecosystems. In the tallest mangrove forest on Earth (Pongara National Park, Gabon), we leverage the data collected during the AfriSAR campaign to evaluate 17 state-of-the-art sensor data products across the full range of height and biomass known to exist globally in mangrove forest ecosystems, providing a much-needed baseline for sensor performance. Our major findings are: (Houghton, Hall, Goetz) height estimates are not consistent across products, with opposing trends in relative and absolute errors, highlighting the need for an adaptive approach to constraining height estimates (Panet al., 2011); radar height estimates had the lowest calibration error and bias, with further improvements using LiDAR fusion (Bonan, 2008); biomass variability and uncertainty strongly depends on forest stature, with variation across products increasing with canopy height, while relative biomass variation was highest in low-stature stands (Le Quéréet al., 2017); a remote sensing product's sensitivity to variations in canopy structure is more important than the absolute accuracy of height estimates (Mitchardet al., 2014); locally-calibrated area-wide totals are more representative than generalized global biomass models for high-precision biomass estimates. The findings presented here provide critical baseline expectations for height and biomass predictions across the full range of mangrove forest stature, which can be directly applied to current (TanDEM-X, GEDI, ICESat-2) and future (NISAR, BIOMASS) global-scale forest monitoring missions.

Conceptualizing ecosystem degradation using mangrove forests as a model system - Yando, Erik S.; Sloey, Taylor M.; Dahdouh-Guebas, Farid; Rogers, Kerrylee; Abuchahla, Guilherme M.O.; Cannicci, Stefano; Canty, Steven W.J.; Jennerjahn, Tim C.; Ogurcak, Danielle E.; Adams, Janine B.; Connolly, Rod M.; Diele, Karen; et al. (Biological Conservation, 2021)
The status and potential degradation of an ecosystem is often difficult to identify, quantify, and characterize. Multiple, concurrent drivers of degradation may interact and have cumulative and confounding effects, making mitigation and rehabilitation actions challenging to achieve. Ecosystem status assessments generally emphasize areal change (gains/losses) as a primary indicator; however, this over-simplifies complex ecosystem dynamics and ignores metrics that would better assess ecosystem quality. Consideration of multiple indicators is necessary to characterize and/or anticipate ecosystem degradation and appropriately identify factors causing changes. We utilize mangrove forests as a model system due to their distribution across a wide range of geographic settings, their position in the inherently dynamic coastal zone, and the multiple natural and anthropogenic pressures they face. We present a conceptual framework to: i) examine drivers of ecosystem degradation and characterize system status, and ii) delineate the roles of biogeographic and geomorphic variability, site history and typology, and references. A complementary workflow is proposed for implementing the conceptual framework. We demonstrate the universal applicability of our conceptual framework through a series of case studies that represent locations with differing drivers of degradation and biogeographic and geomorphic conditions. Our conceptual framework facilitates scientists, conservation practitioners, and other stakeholders in considering multiple aspects of ecosystems to better assess system status and holistically evaluate degradation. This is achieved by critically evaluating suitable comparisons and relevant elements in assessing a site to understand potential actions or the outcome of previously implemented management strategies.

Considering coasts: Adapting terrestrial models to characterize coastal wetland ecosystems - O'Meara, Theresa A.; Thornton, Peter E.; Ricciuto, Daniel M.; Noyce, Genevieve L.; Rich, Roy L.; Megonigal, J. Patrick (Ecological Modelling, 2021)
The Energy Exascale Earth System Model (E3SM) simulates fully coupled processes and interactions among water, energy, carbon and nutrient cycles. E3SM connects vegetation and soil dynamics through nutrient uptake, plant production, litterfall and decomposition as a function of abiotic parameters (e.g. temperature and moisture). However, E3SM is designed to characterize terrestrial ecosystems and connects land and open ocean systems using a single streamflow transport term, ignoring the complex dynamics of energy, water, carbon, and nutrients in coastal systems. The goals of our project were to: (1) Parameterize a point version of E3SM to capture coastal wetland habitats and (2) Determine marsh community responses to increased temperature and elevated CO2. We adapted a version of the E3SM land model, previously configured to represent forested bog hydrology to a coastal ecosystem using datasets from field experiments conducted at the Smithsonian Environmental Research Center's Global Change Research Wetland (GCReW). Tidal forcing in a marsh environment was simulated using a two-column system in which the columns are connected by lateral hydrologic flows. One column simulates interactions between vegetation and soil while a second column simulates variation in water level (both tidal and sea level rise). The updated model captures many aspects of the field experiments, showing that plant community responses to environmental change are non-linear, non-additive and different between plant types. Elevated CO2 treatments increased C3 plant biomass more than C4 (33% vs 17%). Temperature exacerbated CO2 responses in C3 plants (0 °C: 26%, 5.1 °C: 56%). We were more successful at characterizing C3 than C4 responses and simulating above rather than belowground biomass production. Next steps will include updates to key physiological parameters such as root:shoot carbon allocation and the addition of mechanistic feedbacks between vegetation and biogeochemical processes.

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Duarte de Paula Costa, Micheli; Lovelock, Catherine E.; Waltham, Nathan J.; Young, Mary; Adame, Maria F.; Bryant, Catherine V.; Butler, Don; Green, David; Rasheed, Michael A.; Salinas, Cristian; Serrano, Oscar; York, Paul H.; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Decomposition of mangrove roots depends on the bulk density they grew in - Ola, Anne; Lovelock, Catherine E. (Plant and Soil, 2021)
Aims: Mangroves hold large organic carbon (C) stocks in their soils. These C stocks are mainly attributed to the high productivity and slow decomposition of the below-ground biomass. Rates of decomposition are strongly influenced by edaphic factors including soil bulk density (BD). Hence, this study assessed the influence of soil BD on mangrove root material and its effect on decomposition. Methods: To determine the effect of the BD in which the plants were grown on decomposition rates (i.e. mass loss), four mangrove species were grown in soils of six different BD. The root material was then placed in litterbags and incubated in mangrove forest soil for three months. Additionally, the root material was analysed for nitrogen (N) and phosphorus (P), as well as lignin and cellulose content. Results: The soil BD experienced during root growth strongly affected mass loss, which decreased with increasing soil BD of the growth media. Decomposition also differed among species. Variation in mass loss was likely influenced by N levels, C:N ratios and lignin content of the root tissue. Conclusion: Variation in soil BD influences the C sequestration potential of mangroves, as BD affects the decomposability of mangrove root tissues.

Decomposition Rates of Surficial and Buried Organic Matter and the Lability of Soil Carbon Stocks Across a Large Tropical Seagrass Landscape - Howard, Jason L.; Lopes, Christian C.; Wilson, Sara S.; McGee-Absten, Vicki; Carrión, Claudia I.; Fourqurean, James W. (Estuaries and Coasts, 2021)
The paradigm for understanding the accumulation of organic carbon in vegetated coastal “blue carbon” habitats holds that burial of organic carbon (Corg) slows decomposition and leads to stability of carbon stocks. Further, it is generally assumed that the presence of the plant communities contributes to the buried organic matter and the stability of the carbon stocks. In this study, these assumptions were tested and the lability of soil organic carbon was examined as a function of environmental and plant community drivers. Samples of surficial sediment and seagrass community characteristics were collected at 93 locations across the ca. 15,000 km2 of seagrass beds in south Florida. Ramped pyrolysis was used to describe the relative lability of soil organic carbon across the landscape. Organic matter (OM) was lost at all temperatures from 180 to 600 °C, suggesting that even the relatively high combustion temperature of 550 °C underestimates OM content by ≈ 10% on average. Additionally, deployments of model substrates (canvas strips) were used to examine decomposition rates of buried and surficial organic material at a subset of these sites. On average, finer, muddier soils contained slightly higher Corg stocks than coarser sediment sites, but the relationships between sediment grain size and seagrass community structure was weak. The lability of soil organic carbon varied with sediment grain size; as much as 80% of the Corg was refractory in coarse-grained soils compared with less than 30% in muddy soils. In muddy soils, burial decreased cellulose decomposition rate by an average of 22–39% compared with surficial breakdown, but in coarse-grained soils, burial enhanced cellulose decomposition rate by at least 55%. Taken as a whole, this study suggests that burial does not enhance Corg storage in all blue carbon environments, and that soil C stores are only weakly correlated with seagrass biomass at the landscape scale.

Dissolved organic carbon sorption dynamics in tidal marsh soils - Pinsonneault, Andrew J.; Neale, Patrick J.; Tzortziou, Maria; Canuel, Elizabeth A.; Pondell, Christina R.; Morrissette, Hannah; Lefcheck, Jonathan S.; Megonigal, James Patrick (Limnology and Oceanography, 2021)
Coastal wetlands are significant sources of dissolved organic carbon (DOC) to adjacent waters and, consequently, exert a strong influence on the quantity and quality of DOC exported to the coastal oceans. Our understanding of the factors that control the exchange of DOC at the tidal marsh-estuarine interface, however, remains limited. We hypothesize that tidal marsh soils act as a regulator and that their physical characteristics, such as organic carbon content and mineral phase composition, are key controls on DOC exchange between soil surfaces and both surface and interstitial waters. To test this hypothesis, we generated traditional Langmuir sorption isotherms using anaerobic batch incubations of four tidal wetland soils, representing a range of soil organic carbon content (1.77% ± 0.12% to 36.2% ± 2.2%) and salinity regimes (freshwater to mixoeuhaline), across four salinity treatments. Results suggest that the maximum soil sorption capacity and DOC binding affinity increase and decrease with greater salinity, respectively, though the enhancement of maximum soil sorption capacity is somewhat mitigated in soils richer in poorly crystalline iron minerals. Initial natively sorbed organic carbon showed a significant positive correlation with soil specific surface area and K showed a moderate yet significant positive correlation with poorly crystalline iron mineral content. Taken together, these results point to a strong mineralogical control on tidal marsh sorption dynamics and a complex physicochemical response of those dynamics to salinity in tidal marsh soils.

Drivers of bacterial diversity along a natural transect from freshwater to saline subtropical wetlands - Chuvochina, Maria; Adame, Maria Fernanda; Guyot, Adrien; Lovelock, Catherine; Lockington, David; Gamboa-Cutz, Julieta N.; Dennis, Paul G. (Science of the Total Environment, 2021)
Tropical coastal wetlands provide a range of ecosystem services that are closely associated with microbially-driven biogeochemical processes. Knowledge of the main players and their drivers in those processes can have huge implications on the carbon and nutrient fluxes in wetland soils, and thus on the ecosystems services we derive from them. Here, we collected surface (0–5 cm) and subsurface (20–25 cm) soil samples along a transect from forested freshwater wetlands, to saltmarsh, and mangroves. For each sample, we measured a range of abiotic properties and characterised the diversity of bacterial communities using 16S rRNA gene amplicon sequencing. The alpha diversity of bacterial communities in mangroves exceeded that of freshwater wetlands, which were dominated by members of the Acidobacteria, Alphaproteobacteria and Verrucomicrobia, and associated with high soil pore-water concentrations of soluble reactive phosphorous, and nitrogen as nitrate and nitrite (N-NOX−). Bacterial communities in the saltmarsh were strongly stratified by depth and included members of the Actinobacteria, Chloroflexi, and Deltaproteobacteria. Finally, the mangroves were dominated by representatives of Deltaproteobacteria, mainly Desulfobacteraceae and Synthrophobacteraceae, and were associated with high salinity and soil pore-water concentrations of ammonium (N-NH4+). These communities suggest methane consumption in freshwater wetlands, and sulfate reduction in deep soils of marshes and in mangroves. Our work contributes to the important goal of describing reference conditions for specific wetlands in terms of both bacterial communities and their drivers. This information may be used to monitor change and assess wetland health and function.

Dynamics and fate of blue carbon in a mangrove–seagrass seascape: influence of landscape configuration and land-use change - Asplund, Maria E.; Dahl, Martin; Ismail, Rashid O.; Arias-Ortiz, Ariane; Deyanova, Diana; Franco, João N.; Hammar, Linus; Hoamby, Arielle I.; Linderholm, Hans W.; Lyimo, Liberatus D.; Perry, Diana; Rasmusson, Lina M.; et al. (Landscape Ecology, 2021)
Context: Seagrass meadows act as efficient natural carbon sinks by sequestering atmospheric CO2 and through trapping of allochthonous organic material, thereby preserving organic carbon (Corg) in their sediments. Less understood is the influence of landscape configuration and transformation (land-use change) on carbon sequestration dynamics in coastal seascapes across the land–sea interface. Objectives: We explored the influence of landscape configuration and degradation of adjacent mangroves on the dynamics and fate of Corg in seagrass habitats. Methods: Through predictive modelling, we assessed sedimentary Corg content, stocks and source composition in multiple seascapes (km-wide buffer zones) dominated by different seagrass communities in northwest Madagascar. The study area encompassed seagrass meadows adjacent to intact and deforested mangroves. Results: The sedimentary Corg content was influenced by a combination of landscape metrics and inherent habitat plant- and sediment-properties. We found a strong land-to-sea gradient, likely driven by hydrodynamic forces, generating distinct patterns in sedimentary Corg levels in seagrass seascapes. There was higher Corg content and a mangrove signal in seagrass surface sediments closer to the deforested mangrove area, possibly due to an escalated export of Corg from deforested mangrove soils. Seascapes comprising large continuous seagrass meadows had higher sedimentary Corg levels in comparison to more diverse and patchy seascapes. Conclusion: Our results emphasize the benefit to consider the influence of seascape configuration and connectivity to accurately assess Corg content in coastal habitats. Understanding spatial patterns of variability and what is driving the observed patterns is useful for identifying carbon sink hotspots and develop management prioritizations.

Economic valuation of the ecosystem services provided by the mangroves of the Gulf of Nicoya using a hybrid methodology - Hernández-Blanco, M.; Costanza, R.; Cifuentes-Jara, M. (Ecosystem Services, 2021)
Due to the public good nature of many of mangrove's ecosystem services, markets for them do not exist and there is limited potential to manage them with conventional markets. Moreover, because of the difficulties in estimating the value of these non-marketed services, mangroves are often undervalued in benefit cost analysis of conservation versus commercial land uses causing their degradation and loss. With the goal of supporting the current efforts of the government of Costa Rica to develop a new PES scheme that include these ecosystems, as well as other policy initiatives on wetlands conservation and restoration, we applied a hybrid approach to estimate the value of ecosystem services from mangrove forests in the Gulf of Nicoya. Our method consists of traditional benefit transfer and expert modified benefit transfer for 11 ecosystem services, and the application of more specific methods to estimate three of those ecosystem services (i.e. climate regulation, fisheries and coastal protection). Using traditional benefit transfer, we estimated the total economic value of ecosystem services of mangroves in the Gulf of Nicoya in $812 million per year (median=$88 million/year), and the total mean value of the ecosystem services provided by all the mangroves in Costa Rica as $1.5 billion per year (median=$160 million/year). By applying the expert modified benefit transfer we estimated that the mean total value of the mangrove forests of the Gulf of Nicoya is $470 million per year, and a median value of $75 million per year. Combining the three different valuation technics, we calculated the mean total value of the ecosystem services from mangrove forests in the Gulf of Nicoya in $408 million per year, and a median total value of $86 million. Considering the median total value of ecosystem services from mangroves, it represents 0.16% of the GDP in Costa Rica in 2015.
Keywords: Economic value; Ecosystem services; Mangroves; Natural capital

Ecosystem carbon losses following a climate-induced mangrove mortality in Brazil - Gomes, Luiz Eduardo de Oliveira; Sanders, Christian J.; Nobrega, Gabriel N.; Vescovi, Lucas C.; Queiroz, Hermano M.; Kauffman, J. Boone; Ferreira, Tiago O.; Bernardino, Angelo F. (Journal of Environmental Management, 2021)
Drought events may induce mangrove mortality and dieback events worldwide as a result of climate extremes. As mangroves sequester large quantities of carbon, quantifying the losses of these stocks following climate disturbances may guide wetland governance strategies globally. In Southeast Brazil, we determined the total ecosystem carbon stocks (TECS) of pristine mangroves that were up to 1851 Mg of carbon per hectare (Mg C ha−1), which are the highest stocks measured from South American and raising estimates of Brazil's mangrove TECS to 0.52 Pg C. A mangrove mortality event in the same estuary resulted in a 14.6 % decrease in TECS (270.5 Mg C ha−1) and loss of 20 % of mangrove soil carbon within less than 2-years. Carbon dioxide emissions from this impact were 992.8 Mg CO2e ha−1, which are slightly lower than emissions from land use disturbances on mangroves worldwide. Our results suggest that climate effects on mangroves can become significant sources of greenhouse gases globally.

Ecosystem type drives tea litter decomposition and associated prokaryotic microbiome communities in freshwater and coastal wetlands at a continental scale - Trevathan-Tackett, Stacey M.; Kepfer-Rojas, Sebastian; Engelen, Aschwin H.; York, Paul H.; Ola, Anne; Li, Jinquan; Kelleway, Jeffrey J.; Jinks, Kristin I.; Jackson, Emma L.; Adame, Maria Fernanda; Pendall, Elise; Lovelock, Catherine E.; et al. (Science of the Total Environment, 2021)
Wetland ecosystems are critical to the regulation of the global carbon cycle, and there is a high demand for data to improve carbon sequestration and emission models and predictions. Decomposition of plant litter is an important component of ecosystem carbon cycling, yet a lack of knowledge on decay rates in wetlands is an impediment to predicting carbon preservation. Here, we aim to fill this knowledge gap by quantifying the decomposition of standardised green and rooibos tea litter over one year within freshwater and coastal wetland soils across four climates in Australia. We also captured changes in the prokaryotic members of the tea-associated microbiome during this process. Ecosystem type drove differences in tea decay rates and prokaryotic microbiome community composition. Decomposition rates were up to 2-fold higher in mangrove and seagrass soils compared to freshwater wetlands and tidal marshes, in part due to greater leaching-related mass loss. For tidal marshes and freshwater wetlands, the warmer climates had 7–16% less mass remaining compared to temperate climates after a year of decomposition. The prokaryotic microbiome community composition was significantly different between substrate types and sampling times within and across ecosystem types. Microbial indicator analyses suggested putative metabolic pathways common across ecosystems were used to breakdown the tea litter, including increased presence of putative methylotrophs and sulphur oxidisers linked to the introduction of oxygen by root in-growth over the incubation period. Structural equation modelling analyses further highlighted the importance of incubation time on tea decomposition and prokaryotic microbiome community succession, particularly for rooibos tea that experienced a greater proportion of mass loss between three and twelve months compared to green tea. These results provide insights into ecosystem-level attributes that affect both the abiotic and biotic controls of belowground wetland carbon turnover at a continental scale, while also highlighting new decay dynamics for tea litter decomposing under longer incubations.

ENSO feedback drives variations in dieback at a marginal mangrove site - Hickey, S. M.; Radford, B.; Callow, J. N.; Phinn, S. R.; Duarte, C. M.; Lovelock, C. E. (Scientific Reports, 2021)
Ocean–atmosphere climatic interactions, such as those resulting from El Niño Southern Oscillation (ENSO) are known to influence sea level, sea surface temperature, air temperature, and rainfall in the western Pacific region, through to the north-west Australian Ningaloo coast. Mangroves are ecologically important refuges for biodiversity and a rich store of blue carbon. Locations such as the study site (Mangrove Bay, a World Heritage Site within Ningaloo Marine Park and Cape Range National Park) are at the aridity range-limit which means trees are small in stature, forests small in area, and are potentially susceptible to climate variability such as ENSO that brings lower sea level and higher temperature. Here we explore the relationship between mangrove dieback, and canopy condition with climatic variables and the Southern Oscillation Index (SOI)—a measure of ENSO intensity, through remote sensing classification of Landsat satellite missions across a 29 year period at a north-west Australian site. We find that the SOI, and seasonal mean minimum temperature are strongly correlated to mangrove green canopy (as indicator of live canopy) area. This understanding of climate variations and mangrove temporal heterogeneity (patterns of abundance and condition) highlights the sensitivity and dynamics of this mangrove forest and recommends further research in other arid and semi-arid tropical regions at mangrove range-limits to ascertain the extent of this relationship.

Estimating blue carbon sequestration under coastal management scenarios - Moritsch, Monica M.; Young, Mary; Carnell, Paul; Macreadie, Peter I.; Lovelock, Catherine; Nicholson, Emily; Raimondi, Peter T.; Wedding, Lisa M.; Ierodiaconou, Daniel (Science of the Total Environment, 2021)
Restoring and protecting “blue carbon” ecosystems - mangrove forests, tidal marshes, and seagrass meadows - are actions considered for increasing global carbon sequestration. To improve understanding of which management actions produce the greatest gains in sequestration, we used a spatially explicit model to compare carbon sequestration and its economic value over a broad spatial scale (2500 km of coastline in southeastern Australia) for four management scenarios: (1) Managed Retreat, (2) Managed Retreat Plus Levee Removal, (3) Erosion of High Risk Areas, (4) Erosion of Moderate to High Risk Areas. We found that carbon sequestration from avoiding erosion-related emissions (abatement) would far exceed sequestration from coastal restoration. If erosion were limited only to the areas with highest erosion risk, sequestration in the non-eroded area exceeded emissions by 4.2 million Mg CO2 by 2100. However, losing blue carbon ecosystems in both moderate and high erosion risk areas would result in net emissions of 23.0 million Mg CO2 by 2100. The removal of levees combined with managed retreat was the strategy that sequestered the most carbon. Across all time points, removal of levees increased sequestration by only an additional 1 to 3% compared to managed retreat alone. Compared to the baseline erosion scenario, the managed retreat scenario increased sequestration by 7.40 million Mg CO2 by 2030, 8.69 million Mg CO2 by 2050, and 16.6 million Mg CO2 by 2100. Associated economic value followed the same patterns, with large potential value loss from erosion greater than potential gains from conserving or restoring ecosystems. This study quantifies the potential benefits of managed retreat and preventing erosion in existing blue carbon ecosystems to help meet climate change mitigation goals by reducing carbon emissions.

Evaluation of Spatio-Temporal Dynamics of Guyana’s Mangroves Using SAR and GEE - Nedd, Gordon Ansel; Oyedotun, Temitope D.Timothy; Simard, Marc (Earth Systems and Environment, 2021)
Mangrove forests are vital in many ways to coastal communities. The forests prevent coastal erosion, produce nutrients and organic matter, serve as a sink for carbon, nitrogen, and phosphorus, maintain water quality, and support food production for habitat biodiversity. However, these systems are threatened by urban development and have sea-level rise as a result of climate change. Such is evident in Guyana coastal areas where there had been a reduction of mangroves coverage from approximately 80,000 ha in 1980 to 22,000 ha in 2010 and 26,115 ha in 2019. One of the measures to restrict the depletion of this vital ecosystem is through an aggressive programme of mangrove replanting and restoration by the Government of Guyana. To monitor and measure the spatio-temporal effectiveness of this management effort require effective and advanced technologies, which remote-sensing capabilities can provide. In this study, the synthetic aperture radar (SAR) imagery was used for the mapping of mangrove regeneration and dynamics. The producer’s accuracy of the mangrove classification for each year was 96%, 95%, 97%, 99%, and 99% in 1996, 2007, 2010, 2016, and 2019, respectively, and the users’ accuracy was 95%, 95%, 95%, 99%, and 99%, respectively, demonstrated that this can be used for the monitoring spatio-temporal response of mangroves. The analysis of diameter at breast height and the heights of the mangroves also show the spatial and temporal trend of gains and losses of biomass as derived from the allometric equations of the analysed SAR images. The findings show the effectiveness of the methodology used to monitor changes and to estimate the biomass. This study could be a useful guide for planning future coastal restoration projects at the sample study sites, assist in community resilience in the face of sea-level rise and climate change, and support policymakers in multi-policy coordination involving the management of the Guyana coastal retreat.

Factors Determining Seagrass Blue Carbon Across Bioregions and Geomorphologies - Mazarrasa, Inés; Lavery, Paul; Duarte, Carlos M.; Lafratta, Anna; Lovelock, Catherine E.; Macreadie, Peter I.; Samper-Villarreal, Jimena; Salinas, Cristian; Sanders, Christian J.; Trevathan-Tackett, Stacey; Young, Mary; Steven, Andy; et al. (Global Biogeochemical Cycles, 2021)
Seagrass meadows rank among the most significant organic carbon (Corg) sinks on earth. We examined the variability in seagrass soil Corg stocks and composition across Australia and identified the main drivers of variability, applying a spatially hierarchical approach that incorporates bioregions and geomorphic settings. Top 30 cm soil Corg stocks were similar across bioregions and geomorphic settings (min-max: 20–26 Mg Corg ha−1), but meadows formed by large species (i.e., Amphibolis spp. and Posidonia spp.) showed higher stocks (24–29 Mg Corg ha−1) than those formed by smaller species (e.g., Halodule, Halophila, Ruppia, Zostera, Cymodocea, and Syringodium; 12–21 Mg Corg ha−1). In temperate coastal meadows dominated by large species, soil Corg stocks mainly derived from seagrass Corg (72 ± 2%), while allochthonous Corg dominated soil Corg stocks in meadows formed by small species in temperate and tropical estuarine meadows (64 ± 5%). In temperate coastal meadows, soil Corg stocks were enhanced by low hydrodynamic exposure associated with high mud and seagrass Corg contents. In temperate estuarine meadows, soil Corg stocks were enhanced by high contributions of seagrass Corg, low to moderate solar radiation, and low human pressure. In tropical estuarine meadows formed by small species, large soil Corg stocks were mainly associated with low hydrodynamic energy, low rainfall, and high solar radiation. These results showcase that bioregion and geomorphic setting are not necessarily good predictors of soil Corg stocks and that site-specific estimates based on local environmental factors are needed for Blue Carbon projects and greenhouse gases accounting purposes.

Future carbon emissions from global mangrove forest loss - Adame, Maria F.; Connolly, Rod M.; Turschwell, Mischa P.; Lovelock, Catherine E.; Fatoyinbo, Temilola; Lagomasino, David; Goldberg, Liza A.; Holdorf, Jordan; Friess, Daniel A.; Sasmito, Sigit D.; Sanderman, Jonathan; Sievers, Michael; et al. (Global Change Biology, 2021)
Mangroves have among the highest carbon densities of any tropical forest. These ‘blue carbon’ ecosystems can store large amounts of carbon for long periods, and their protection reduces greenhouse gas emissions and supports climate change mitigation. Incorporating mangroves into Nationally Determined Contributions to the Paris Agreement and their valuation on carbon markets requires predicting how the management of different land-uses can prevent future greenhouse gas emissions and increase CO2 sequestration. We integrated comprehensive global datasets for carbon stocks, mangrove distribution, deforestation rates, and land-use change drivers into a predictive model of mangrove carbon emissions. We project emissions and foregone soil carbon sequestration potential under ‘business as usual’ rates of mangrove loss. Emissions from mangrove loss could reach 2391 Tg CO2 eq by the end of the century, or 3392 Tg CO2 eq when considering foregone soil carbon sequestration. The highest emissions were predicted in southeast and south Asia (West Coral Triangle, Sunda Shelf, and the Bay of Bengal) due to conversion to aquaculture or agriculture, followed by the Caribbean (Tropical Northwest Atlantic) due to clearing and erosion, and the Andaman coast (West Myanmar) and north Brazil due to erosion. Together, these six regions accounted for 90% of the total potential CO2 eq future emissions. Mangrove loss has been slowing, and global emissions could be more than halved if reduced loss rates remain in the future. Notably, the location of global emission hotspots was consistent with every dataset used to calculate deforestation rates or with alternative assumptions about carbon storage and emissions. Our results indicate the regions in need of policy actions to address emissions arising from mangrove loss and the drivers that could be managed to prevent them.
Keywords: Nationally Determined Contributions; blue carbon; carbon sequestration; climate change; coastal wetlands; erosion; greenhouse gases; tropical storms

Future-proofing conservation priorities for sea level rise in coastal urban ecosystems - Mazor, Tessa; Runting, Rebecca K.; Saunders, Megan I.; Huang, Danwei; Friess, Daniel A.; Nguyen, Nhung T.H.; Lowe, Ryan J.; Gilmour, James P.; Todd, Peter A.; Lovelock, Catherine E. (Biological Conservation, 2021)
Decision makers are calling for actionable science to protect coastal ecosystems from adverse impacts. Future sea level rise (SLR) is expected to alter the spatial configuration of coastal habitats and their services. Ensuring conservation efforts are in optimal areas can be achieved using systematic conservation planning, yet plans rarely address multiple goals and uncertainties. We developed and applied a novel multi-ecosystem approach for planning the conservation of coastal ecosystems under future SLR scenarios. Decision support tool Marxan was used to determine priority areas that incorporate habitat connectivity, SLR modelling scenarios and feasibility for conservation in urbanised Moreton Bay in Queensland, Australia, as a case-study. We found that planning based on present conditions will not adequately capture conservation priorities for the future, and has associated financial consequences. Priority conservation areas of Moreton Bay are not well aligned with current protected areas (<35%), with further misalignment for future scenarios. This study highlights the importance of a multi-ecosystem approach for protecting coastal habitats as well as leveraging the current management system. Our approach helps inform policy and guides conservation actions in urbanised coastal regions facing SLR.

Groundwater Quality in the Yucatan Peninsula: Insights from Stable Isotope and Metals Analysis - Arcega-Cabrera, F.; Sickman, J. O.; Fargher, L.; Herrera-Silveira, J.; Lucero, D.; Oceguera-Vargas, I.; Lamas-Cosío, E.; Robledo-Ardila, P. A. (Groundwater, 2021)
High surface water-groundwater connectivity characterizes watersheds underlain by karsts, increasing contaminant transport risks. However, karsts are highly complex, making research necessary to understand the transport of contaminants from the surface, through the aquifer, to discharge areas. In Yucatan, the lack of waste water treatment raises the risk of groundwater contamination. We monitored stable isotopes (δ18O-NO3 and δ15N-NO3), cadmium, and lead to document waste water contamination and transport during the rainy and dry seasons, using water samples collected along the Ring of Cenotes during each season. Specific conductance and pH showed no consistent seasonality, with conductance ranging from 0.5 to 55 mS/cm and pH ranging from 6.6 to 8.6 for most samples. Nitrate concentrations in the cenotes averaged 205 ± 260 μM and no seasonal pattern was observed. Cd and Pb concentrations were 0.1 to 37.9 μg/L and 0.2 to 243.2 μg/L, respectively. Nitrate stable isotope values were 2.6 to 27.2‰ for δ18O and 1.2 to 20.7‰ for δ15N. The statistical relationship between δ15N and δ18O, in dry season samples, indicated that denitrification was occurring. A scale measure for waste water recognition showed: (1) high variability among sites probably related with dry/rainy seasons and/or diverse anthropogenic activities; and (2) specific water quality variables that contribute to contamination at each site during each season. Importantly, our analyses indicate that in the area surrounding the Ring of Cenotes, waste water exhibits spatial and temporal patterns related to complex transport and dilution processes, as is the case in karsts in general.

High variance in community structure and ecosystem carbon stocks of Fijian mangroves driven by differences in geomorphology and climate - Cameron, Clint; Kennedy, Bridget; Tuiwawa, Senilolia; Goldwater, Nick; Soapi, Katy; Lovelock, Catherine E. (Environmental Research, 2021)
Mangrove ecosystems are particularly important for small island developing states of the Pacific, such as Fiji, which are at the forefront of the impacts of climate change. This is because of the ability of mangroves to mitigate storm surges and floods as well as their high carbon sequestration and storage capacity. However, there are few detailed studies on the spatial variation in mangrove structure and carbon stocks in Fiji, and this information is essential to support decision making by government and communities, enabling the development of effective mitigation and adaptation responses. We assessed mangrove forest structure in contrasting regions around Fiji's largest island, Viti Levu, within sites managed by indigenous (iTaukei) Fijians. Mangroves of the Ba, Nadroga-Navosa, and Rewa and Tailevu regions showed high variance in both structural complexity and ecosystem carbon stocks. Levels of variation were similar to that observed globally due to variable geomorphological and biophysical settings related to orographic rainfall, freshwater influx, tidal amplitude and cyclonic disturbances. High biomass, structurally complex forests occur on the wetter south-east coast (e.g. the Rewa Delta), while structurally uniform scrub mangroves dominate large areas of mangroves along the north-west (e.g. the Ba Delta) and west coast (e.g. the Tuva Delta). Mangroves of the Ba region displayed considerable damage from tropical cyclones, particularly in taller vegetation. All mangrove sites assessed were important reservoirs of carbon, with results when scaled to the spatial extent of mangroves in Fiji revealing that ecosystem carbon storage is disproportionate to area and equates to 73.3% of the carbon held within terrestrial rainforests, despite occupying just 7.3% of the total area. This underscores the importance of mangroves as valuable carbon sinks in Fiji and the need to develop incentives for improved conservation and restoration.

Identifying global and local drivers of change in mangrove cover and the implications for management - Maina, J. M.; Bosire, J. O.; Kairo, J. G.; Bandeira, S. O.; Mangora, M. M.; Macamo, C.; Ralison, H.; Majambo, G. (Global Ecology and Biogeography, 2021)
Background: Climate change and human activities continue to drive a widespread decline in global mangrove coverage, undermining their capacity to provide ecosystem benefits. While global and local scale drivers of change on mangroves are widely acknowledged, the relative importance and the exposure of mangroves to climatic, geomorphological, and direct human threats vary spatially. Understanding the role and relative importance of the multiscale and multiple threats to mangroves and how these vary spatially is fundamental for formulating a spatially adaptive approach to their management and conservation. Aim: Our study investigated the role of multiple threats on mangroves and the relative exposure. Location: Western Indian Ocean (WIO) region. Time period: Recent past (2002–2019 and future (2050–2060). Major taxa studied: Mangrove. Methods: Using satellite-derived indicators of mangrove condition aggregated over 19 years (2002 to 2019) and 14 proxies of climate, human activity, and geomorphology, we applied machine learning methods to determine the role and relative importance of the change drivers. Using outputs from this deductive statistical process, we applied inductive methods to map mangrove exposure spatially. Results: Model results highlight the importance of catchment erosion, human pressure, sea level, and macroclimate as the main drivers of the present-day ecological condition of mangroves in the WIO. Normalized difference vegetation index (NDVI) was more sensitive to the identified drivers than the vegetation condition index (VCI), with the relative importance of variables varying across the two vegetation indicators. Main conclusions: In anticipation of a stronger manifestation of climate change impacts, the resilience of mangroves in the WIO could be improved through adaptive management over time and space. Testing the efficacy of the essential biodiversity variables (EBV) is critical for understanding the mechanisms of ecosystem change and managing biodiversity change.

Impact of shrimp ponds on mangrove blue carbon stocks in Ecuador - Merecí-Guamán, Jéssica; Casanoves, Fernando; Delgado-Rodríguez, Diego; Ochoa, Pablo; Cifuentes-Jara, Miguel (Forests, 2021)
Mangrove forests play an important role in mitigating climate change but are threatened by aquaculture expansion. The inclusion of mangroves in climate change mitigation strategies requires measuring of carbon stocks and the emissions caused by land use change over time. This study provides a synthesis of carbon stocks in mangrove and shrimp ponds in the Gulf of Guayaquil. In this study area, we identified 134,064 ha of mangrove forest and 153,950 ha of shrimp farms. Two mangrove strata were identified according to their height and basal area: medium-statured mangrove (lower height and basal area) and tall mangrove (greater height and basal area). These strata showed statistical differences in aboveground carbon stocks. In both strata, the most abundant mangrove species was Rhizophora mangle. For both strata, trees had a maximum height (>30 m), and their density was greater than 827 ha−1 . Total ecosystem level carbon stocks (measured to 1 m soil depth) were 320.9 Mg C ha−1 in medium-statured mangroves and 419.4 Mg C ha−1 in tall mangroves. The differences are attributable to higher basal area, soil organic carbon concentrations and salinity, tidal range, origin of allochthonous material, and herbivory patterns. Mangrove soils represented >80% of the total ecosystem carbon. Ecosystem carbon stocks were lower (81.9 Mg C ha−1 ) in the shrimp farms, 50% less than in undisturbed mangroves. Our results highlight mangroves as tropical ecosystems with extremely high carbon storage; therefore, they play an important role in mitigating climate change. This research provides a better understanding of how carbon stocks in this gulf are found and can be used for design strategies to protect global natural carbon sinks.
Keywords: Carbon stocks; Climate change; Mangrove strata; Shrimp ponds; Soil carbon; Vegetated coastal ecosystem

Investing in Blue Natural Capital to Secure a Future for the Red Sea Ecosystems - Cziesielski, Maha J.; Duarte, Carlos M.; Aalismail, Nojood; Al-Hafedh, Yousef; Anton, Andrea; Baalkhuyur, Faiyah; Baker, Andrew C.; Balke, Thorsten; Baums, Iliana B.; Berumen, Michael; Chalastani, Vasiliki I.; Cornwell, Brendan; et al. (Frontiers in Marine Science, 2021)
For millennia, coastal and marine ecosystems have adapted and flourished in the Red Sea’s unique environment. Surrounded by deserts on all sides, the Red Sea is subjected to high dust inputs and receives very little freshwater input, and so harbors a high salinity. Coral reefs, seagrass meadows, and mangroves flourish in this environment and provide socio-economic and environmental benefits to the bordering coastlines and countries. Interestingly, while coral reef ecosystems are currently experiencing rapid decline on a global scale, those in the Red Sea appear to be in relatively better shape. That said, they are certainly not immune to the stressors that cause degradation, such as increasing ocean temperature, acidification and pollution. In many regions, ecosystems are already severely deteriorating and are further threatened by increasing population pressure and large coastal development projects. Degradation of these marine habitats will lead to environmental costs, as well as significant economic losses. Therefore, it will result in a missed opportunity for the bordering countries to develop a sustainable blue economy and integrate innovative nature-based solutions. Recognizing that securing the Red Sea ecosystems’ future must occur in synergy with continued social and economic growth, we developed an action plan for the conservation, restoration, and growth of marine environments of the Red Sea. We then investigated the level of resources for financial and economic investment that may incentivize these activities. This study presents a set of commercially viable financial investment strategies, ecological innovations, and sustainable development opportunities, which can, if implemented strategically, help ensure long-term economic benefits while promoting environmental conservation. We make a case for investing in blue natural capital and propose a strategic development model that relies on maintaining the health of natural ecosystems to safeguard the Red Sea’s sustainable development.

Landcover change in mangroves of Fiji: Implications for climate change mitigation and adaptation in the Pacific - Cameron, Clint; Maharaj, Anish; Kennedy, Bridget; Tuiwawa, Senilolia; Goldwater, Nick; Soapi, Katy; Lovelock, Catherine E. (Environmental Challenges, 2021)
Mangrove coverage in Fiji is among the highest of all Pacific island nations. These ecosystems store disproportionate amounts of carbon, provide critically important resources for communities, and protect coastal communities against the impacts of tropical cyclones. They are therefore vital in mitigating and adapting to the impacts of climate change. An improved understanding of both the scale and drivers of mangrove loss in Fiji can underpin sustainable management strategies and achieve climate change mitigation and adaptation goals. In this study we assessed mangrove cover, landcover change, and drivers of landcover change for Fiji between 2001 and 2018, as well as the impacts of landcover change on the structural characteristics of mangroves at selected sites on the Fijian island of Viti Levu. Results were then framed within the context of developing management responses, including the potential to develop forest carbon projects. We found Fiji's mangrove estate to be 65,243 ha, with a loss of 1135 ha between 2001 and 2018 and an annual rate of loss of 0.11%. Tropical cyclones accounted for 77% of loss (~870 ha), with highest losses along the northern coastlines of Viti Levu and Vanua Levu. Mangrove structural characteristics showed high variability in the level of damage incurred, with taller riverine and hinterland vegetation sustaining greater levels of damage than coastal fringing or scrub mangroves. There was no tropical cyclone damage evident along the southern coastline of Viti Levu, with small-scale harvesting the predominate driver of loss in this region. Because of the large effect of cyclone damage on mangroves in the region, small to medium scale restoration projects may be appropriate interventions to increase mangrove cover and carbon stocks. Where harvesting of mangroves occurs, improved management to avoid deforestation could also provide opportunities to maintain mangrove cover and carbon stocks.

Large conservation opportunities exist in >90% of tropic-subtropic coastal habitats adjacent to cities - Mazor, Tessa; Friess, Daniel A.; Todd, Peter A.; Huang, Danwei; Nguyen, Nhung T.H.; Saunders, Megan I.; Runting, Rebecca K.; Lowe, Ryan J.; Cartwright, Paula; Gilmour, James P.; Lovelock, Catherine E. (One Earth, 2021)
Coastal habitats have faced decades of loss caused by urbanization. Global recognition of the ecosystem services that coastal habitats provide has led to an emphasis on cities to adopt nature-based solutions (NBS). However, a broad assessment of urban areas and their potential to conserve remaining coastal habitat has not been undertaken. Here we apply spatial analytics to investigate 5,096 coastal urban areas in tropical and subtropical regions within the distribution of mangroves, tidal flats, seagrass meadows, and coral reefs, and find <50% of urban areas have natural coastal habitats within their extent. Large conservation opportunities for urban areas exist within an adjacent 50 km buffer zone where a significant proportion (93%) of urban-influenced coastal habitat lies and where 26% is currently protected. Potential high-conservation areas across the globe provide a unique opportunity to increase the resilience of urbanizing coasts and NBS for long-term socioeconomic and conservation goals.

Large-Scale High-Resolution Coastal Mangrove Forests Mapping Across West Africa With Machine Learning Ensemble and Satellite Big Data - Liu, Xue; Fatoyinbo, Temilola E.; Thomas, Nathan M.; Guan, Weihe Wendy; Zhan, Yanni; Mondal, Pinki; Lagomasino, David; Simard, Marc; Trettin, Carl C.; Deo, Rinki; Barenblitt, Abigail (Frontiers in Earth Science, 2021)
Coastal mangrove forests provide important ecosystem goods and services, including carbon sequestration, biodiversity conservation, and hazard mitigation. However, they are being destroyed at an alarming rate by human activities. To characterize mangrove forest changes, evaluate their impacts, and support relevant protection and restoration decision making, accurate and up-to-date mangrove extent mapping at large spatial scales is essential. Available large-scale mangrove extent data products use a single machine learning method commonly with 30 m Landsat imagery, and significant inconsistencies remain among these data products. With huge amounts of satellite data involved and the heterogeneity of land surface characteristics across large geographic areas, finding the most suitable method for large-scale high-resolution mangrove mapping is a challenge. The objective of this study is to evaluate the performance of a machine learning ensemble for mangrove forest mapping at 20 m spatial resolution across West Africa using Sentinel-2 (optical) and Sentinel-1 (radar) imagery. The machine learning ensemble integrates three commonly used machine learning methods in land cover and land use mapping, including Random Forest (RF), Gradient Boosting Machine (GBM), and Neural Network (NN). The cloud-based big geospatial data processing platform Google Earth Engine (GEE) was used for pre-processing Sentinel-2 and Sentinel-1 data. Extensive validation has demonstrated that the machine learning ensemble can generate mangrove extent maps at high accuracies for all study regions in West Africa (92%–99% Producer’s Accuracy, 98%–100% User’s Accuracy, 95%–99% Overall Accuracy). This is the first-time that mangrove extent has been mapped at a 20 m spatial resolution across West Africa. The machine learning ensemble has the potential to be applied to other regions of the world and is therefore capable of producing high-resolution mangrove extent maps at global scales periodically.

Late Holocene environmental change in Celestun Lagoon, Yucatan, Mexico - Hardage, Kyle; Street, Joseph; Herrera-Silveira, Jorge A.; Oberle, Ferdinand K. J.; Paytan, Adina (Journal of Paleolimnology, 2021)
Epikarst estuary response to hydroclimate change remains poorly understood, despite the well-studied link between climate and karst groundwater aquifers. The influence of sea-level rise and coastal geomorphic change on these estuaries obscures climate signals, thus requiring careful development of paleoenvironmental histories to interpret the paleoclimate archives. We used foraminifera assemblages, carbon stable isotope ratios (δ 13 C) and carbon:nitrogen (C:N) mass ratios of organic matter in sediment cores to infer environmental changes over the past 5300 years in Celestun Lagoon, Yucatan, Mexico. Specimens (> 125 µm) from modern core top sediments revealed three assemblages: (1) a brackish mangrove assemblage of agglutinated Miliammina and Ammotium taxa and hyaline Haynesina (2) an inner-shelf marine assemblage of Bolivina , Hanzawaia , and Rosalina, and (3) a brackish assemblage dominated by Ammonia and Elphidium . Assemblages changed along the lagoon channel in response to changes in salinity and vegetation, i.e. seagrass and mangrove. In addition to these three foraminifera assemblages, lagoon sediments deposited since 5300 cal yr BP are comprised of two more assemblages, defined by Archaias and Laevipeneroplis, which indicate marine Thalassia seagrasses, and Trichohyalus, which indicates restricted inland mangrove ponds. Our data suggest that Celestun Lagoon displayed four phases of development: (1) an inland mangrove pond (5300 BP) (2) a shallow unprotected coastline with marine seagrass and barrier island initiation (4900 BP) (3) a protected brackish lagoon (3000 BP), and (4) a protected lagoon surrounded by mangroves (1700 BP). Stratigraphic (temporal) changes in core assemblages resemble spatial differences in communities across the modern lagoon, from the southern marine sector to the northern brackish region. Similar temporal patterns have been reported from other Yucatan Peninsula lagoons and from cenotes (Nichupte, Aktun Ha), suggesting a regional coastal response to sea level rise and climate change, including geomorphic controls (longshore drift) on lagoon salinity, as observed today. Holocene barrier island development progressively protected the northwest Yucatan Peninsula coastline, reducing mixing between seawater and rain-fed submarine groundwater discharge. Superimposed on this geomorphic signal, assemblage changes that are observed reflect the most severe regional wet and dry climate episodes, which coincide with paleoclimate records from lowland lake archives (Chichancanab, Salpeten). Our results emphasize the need to consider coastal geomorphic evolution when using epikarst estuary and lagoon sediment archives for paleoclimate reconstruction and provide evidence of hydroclimate changes on the Yucatan Peninsula.
Keywords: Yucatan,Celestun,Paleoecology,Mangrove,Estuary,For

Limited relationships between mangrove forest structure and hydro-edaphic conditions in subtropical Queensland, Australia - Hill, Jack W.; Bourke, Lachlan A.; Horton, Ciara M.; Staples, Timothy L.; Lovelock, Catherine E. (Estuarine, Coastal and Shelf Science, 2021)
Mangroves are important ecosystems of the global subtropical zone providing a wide range of ecosystem services. They are sensitive to human disturbances and climate change. However, regional assessments of species composition, forest structure and soil characteristics, and knowledge of the environmental factors that contribute to regional variation in their characteristics are limited. We surveyed mangrove communities at seven island locations along 450 km of the sandy south-east Queensland coast. We found no latitudinal trends in richness of common species or their abundance, likely due to shared climatic conditions across our study range, however there was considerable variation in forest structure among and within the seven sites. Over all sites, analysis of soil characteristics identified four hydro-edaphic environmental categories differing in soil water content, dry bulk density, organic matter and porewater salinity, which also varied spatially among and within sites. There were few strong relationships among forest structure and hydro-edaphic categories, although relatively small trees and high stem densities tended to be associated with soils having high soil water content, high levels of soil organic matter and low bulk density, while forests with largest trees and lowest stem densities tended to be associated with soils with intermediate characteristics, indicative of regular inundation and drainage. The two most common species (Avicennia marina and Rhizophora stylosa) had very broad distributions over the four hydro-edaphic categories, although A. marina tended to be more strongly associated with soils with high water content where R. stylosa had a lower probability of occurrence. Bruguiera gymnorrhiza had high fidelity to locations with low porewater salinity influenced by groundwater. We conclude that hydrological conditions are key determinants of mangrove soil characteristics, but less important in determining forest structure in the subtropics. Our study provides a baseline from which future change in mangrove soils and forest structure can be detected.

Losses of Soil Organic Carbon with Deforestation in Mangroves of Madagascar - Arias-Ortiz, Ariane; Masqué, Pere; Glass, Leah; Benson, Lisa; Kennedy, Hilary; Duarte, Carlos M.; Garcia-Orellana, Jordi; Benitez-Nelson, Claudia R.; Humphries, Marc S.; Ratefinjanahary, Ismaël; Ravelonjatovo, Jaona; Lovelock, Catherine E. (Ecosystems, 2021)
Global mangrove deforestation has resulted in substantial CO2 emissions to the atmosphere, but the extent of emissions from soil organic carbon (C) loss remains difficult to assess. Here, we sampled five intact and five deforested mangrove plots from Tsimipaika Bay, Madagascar, to examine the loss of soil C in the 10 years since deforestation. We estimated tree biomass and analyzed grain size, 210Pb activities, organic C and total nitrogen (N) and their stable isotopes in soils as well as dissolved organic C in surface waters. Deforested soils revealed evidence of disturbance in the upper 14 g cm−2 (~40 cm) when compared to reference intact soils, indicated by lower porosity, higher dry bulk density, an order of magnitude higher soil mixing and loss of C and N despite no significant soil erosion. Although C loss from biomass was unequivocal and was estimated at 130 Mg C ha−1, the C loss from soils was more difficult to assess given the large heterogeneity of intact forest soils. We estimated that the loss of C due to mangrove clearing and soil exposure over 10 years was equivalent to about 20% of the upper meter soil C stock, and about 45% of the C stock accumulated during the last century. Soil C loss rate was 4.5 times higher than the C sequestration rate in reference intact soils. These results emphasize the importance of mangrove conservation for CO2 emissions mitigation, as they suggest that deforestation-C losses will take substantially longer to offset with mangrove restoration.

Macroecological patterns of forest structure and allometric scaling in mangrove forests - Rovai, Andre S.; Twilley, Robert R.; Castañeda-Moya, Edward; Midway, Stephen R.; Friess, Daniel A.; Trettin, Carl C.; Bukoski, Jacob J.; Stovall, Atticus E.L.; Pagliosa, Paulo R.; Fonseca, Alessandra L.; Mackenzie, Richard A.; Aslan, Aslan; et al. (Global Ecology and Biogeography, 2021)
Aim: Mangrove wetlands span broad geographical gradients, resulting in functionally diverse tree communities. We asked whether latitudinal variation, allometric scaling relationships and species composition influence mangrove forest structure and biomass allocation across biogeographical regions and distinct coastal morphologies. Location: Global. Time period: Present. Major taxa studied: Mangrove ecosystems. Methods: We built the largest field-based dataset on mangrove forest structure and biomass to date (c. 2,800 plots from 67 countries) to address macroecological questions pertaining to structural and functional diversity of mangroves spanning biogeographical and coastal morphology gradients. We used frequentist inference statistics and machine learning models to determine environmental drivers that control biomass allocation within and across mangrove communities globally. Results: Allometric scaling relationships and forest structural complexity were consistent across biogeographical and coastal morphology gradients, suggesting that mangrove biomass is controlled by regional forcings rather than by latitude or species composition. For instance, nearly 40% of the global variation in biomass was explained by regional climate and hydroperiod, revealing nonlinear thresholds that control biomass accumulation across broad geographical gradients. Furthermore, we found that ecosystem-level carbon stocks (average 401 ± 48 MgC/ha, covering biomass and the top 1 m of soil) varied little across diverse coastal morphologies, reflecting regional bottom-up geomorphic controls that shape global patterns in mangrove biomass apportioning. Main conclusions: Our findings reconcile views of wetland and terrestrial forest macroecology. Similarities in stand structural complexity and cross-site size–density relationships across multiscale environmental gradients show that resource allocation in mangrove ecosystems is independent of tree size and invariant to species composition or latitude. Mangroves follow a universal fractal-based scaling relationship that describes biomass allocation for several other terrestrial tree-dominated communities. Understanding how mangroves adhere to these universal allometric rules can improve our ability to account for biomass apportioning and carbon stocks in response to broad geographical gradients.
Keywords: aboveground biomass; allometric scaling relationships; biogeography; blue carbon; coastal environmental setting; ecosystem-level carbon; forest structure

Mangrove carbon stocks in Pongara National Park, Gabon - Trettin, Carl C.; Dai, Zhaohua; Tang, Wenwu; Lagomasino, David; Thomas, Nathan; Lee, Seung Kuk; Simard, Marc; Ebanega, Médard Obiang; Stoval, Atticus; Fatoyinbo, Temilola E. (Estuarine, Coastal and Shelf Science, 2021)
Mangroves are recognized for their valued ecosystem services to coastal areas, and the functional linkages between those services and ecosystem carbon stocks have been established. However, spatially explicit inventories are necessary to facilitate management and protection of mangroves, as well as providing a foundation for payment for ecosystem service programs such as REDD+. We conducted an inventory of carbon stocks in mangroves within Pongara National Park (PNP), Gabon using a stratified random sampling design based on forest canopy height derived from TanDEM-X remote sensing data. Ecosystem carbon pools, including aboveground and belowground biomass and necromass, and soil carbon to a depth of 2 m were assessed using measurements and samples from plots distributed among three canopy height classes within the park. There were two mangrove species within the inventory area in PNP, Rhizophora racemosa and R. harrisonii. R. harrisonii was predominant in the sparse, low-stature stands that dominated the west side of the park. In the east side of the park, both species occurred in tall-stature stands, with tree height often exceeding 30 m. Canopy height was an effective means to stratify the inventory area, as biomass was significantly different among the height classes. Despite those differences in aboveground biomass, the soil carbon density was not significantly different among height classes. Soils were the main component of the ecosystem carbon stock, accounting for over 84% of the total. The ecosystem carbon density ranged from 644 to 943 Mg C ha−1 among the three height classes. The ecosystem carbon stock within PNP is estimated to be 40,588 Gg C. The combination of pre-inventory information about stand conditions and their spatial distribution within the assessment area obtained from remote sensing data and a spatial decision support system were fundamental to implementing this relatively large-scale field inventory. This work exemplifies how mangrove carbon stocks can be quantified to augment national C reporting statistics, provide a baseline for projects involving monitoring, reporting and verification (i.e., MRV), and provide data on the forest composition and structure for sustainable management and conservation practices.

Mangroves in arid regions: Ecology, threats, and opportunities - Adame, M. F.; Reef, R.; Santini, N. S.; Najera, E.; Turschwell, M. P.; Hayes, M. A.; Masque, P.; Lovelock, C. E. (Estuarine, Coastal and Shelf Science, 2021)
Mangroves are one of the few woody ecosystems that grow in hot-arid climates. They can survive extreme conditions of low precipitation, high solar radiation, wide temperature fluctuations and hypersalinity. These unique mangroves have distinct geomorphology, hydrology, forest structure, tree physiology, and soil biogeochemistry. In this review, supported by field data from Australia and Mexico, we explore the characteristics of mangroves in arid climates of the world. These mangroves are mostly tide-dominated with freshwater flows restricted to groundwater and sporadic tropical storms. They form dense forests with stunted growth dominated mainly by trees of the genus Avicennia that co-occur with salt marshes in the high intertidal. Their soils have low nutrient and carbon concentrations, and high soil δ15 N and δ13C values compared to subhumid and humid mangroves. Mangroves in arid climates have relatively low human pressure due to sparse human settlements. Key threats to these mangroves, which often persist at the edge of their physiological tolerances, include extreme drought, reductions in groundwater inputs, altered hydrology, sea-level fluctuations and increases in nutrient loading. Restoration of mangroves in arid climates should focus on restoring their hydrology. Mangroves in arid zones are under-represented in global maps and assessment programs, as they may not be consistent with countries’ definition of “forests”. Improved global representation and understanding of the ecology of mangroves in arid climates could help sustain their valuable ecosystem services.

Manual for the ecological restoration of mangroves in the Mesoamerican Reef System and the Wider Caribbean - Teutli-hernández, Claudia; Herrera-silveira, Jorge A; Cisneros-de, Diana J; Arceo-carranza, Daniel; Canul-cabrera, Andrés; Robles-toral, Pedro Javier; Pérez-martínez, Oscar J; Sierra-oramas, Daniela; Zenteno, Karla; Us-, Heimi G (2021)

Manual para la Restauración Ecológica de Manglares del Sistema Arrecifal Mesoamericano y el Gran Caribe - Teutli-hernández, Claudia; Herrera-silveira, Jorge A; Cruz, Diana Cisneros-de; Comín, Francisco A; Arceo, Daniel; Pérez, Oscar (2021)

Monitoring post-disaster mangrove forest recoveries in lawaan-balangiga, eastern samar using time series analysis of moisture and vegetation indices - Ticman, K. V.; Salmo, S. G.; Cabello, K. E.; Germentil, M. Q.; Burgos, D. M.; Blanco, A. C. (International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences - ISPRS Archives, 2021)
The mangrove forests of Lawaan-Balangiga in Eastern Samar lost significant cover due to the Typhoon Haiyan that struck the region in 2013. The mangroves in the area have since shown signs of recovery in terms of growth and spatial coverage, but these widely varied with locations. This study aims to further examine the status of recovery of mangroves across different locations by analysing the time series trends of selected vegetation and moisture indices: Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), Modified Soil Adjusted Vegetation Index (MSAVI), and Normalized Difference Moisture Index (NDMI). These indices were extracted from Landsat 8 surface reflectance images, spanning 2014 to 2020, using Google Earth Engine (GEE). The time series analyses showed similar NDVI, MSAVI and NDMI values and trends after the 2013 typhoon event. The trend slopes also indicated high correlation (0.91-1.00) between and among the indices, with NDVI having the highest correlation with MSAVI (∼1.00). The study was able to corroborate the previous study on mangroves in Lawaan-Balangiga, by presenting positive trend results in the identified recovered areas. These trends, however, would still have to be validated by collecting and comparing biophysical parameters in the field. The next step of the research would be to identify the factors that contribute to the varying rates of recovery in the areas and to evaluate how this can affect the carbon sequestration rates of recovering mangroves.

Multi-sensor approach to leaf area index estimation using statistical machine learning models: A case on mangrove forests - Martinez, K. P.; Burgos, D. F.M.; Blanco, A. C.; Salmo, S. G. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
Leaf Area Index (LAI) is a quantity that characterizes canopy foliage content. As leaf surfaces are the primary sites of energy, mass exchange, and fundamental production of terrestrial ecosystem, many important processes are directly proportional to LAI. With this, LAI can be considered as an important parameter of plant growth. Multispectral optical images have been widely utilized for mangrove-related studies, such as LAI estimation. In Sentinel-2, for example, LAI can be estimated using a biophysical processor in SNAP or using various machine learning algorithms. However, multispectral optical images have disadvantages due to its weather-dependence and limited canopy penetration. In this study, a multi-sensor approach was implemented by using free multi-spectral optical images (Sentinel-2 ) and synthetic aperture radar (SAR) images (Sentinel-1) to perform Leaf Area Index (LAI) estimation. The use of SAR images can compensate for the abovementioned disadvantages and it then can pave the way for regular mapping and assessment of LAI, despite any weather conditions and cloud cover. In this study, generation of LAI models that explores linear, non-linear and decision trees modelling algorithms to incorporate Sentinel-1 derivatives and Sentinel-2 LAI were executed. The Random Forest model have exhibited the most robust model having the lowest RMSE of 0.2845. This result poses a concrete relationship of a biophysical entity derived from optical parameters to RADAR derivatives to which opens the opportunity of integrating both systems to compensate each disadvantages and produce a more efficient quantification of LAI.

National scale predictions of contemporary and future blue carbon storage - Young, Mary A.; Serrano, Oscar; Macreadie, Peter I.; Lovelock, Catherine E.; Carnell, Paul; Ierodiaconou, Daniel (Science of the Total Environment, 2021)
To help mitigate the impacts of climate change, many nature-based solutions are being explored. These solutions involve protection and restoration of ecosystems that serve as efficient carbon sinks, including vegetated coastal ecosystems (VCEs: tidal marshes, mangrove forests, and seagrass meadows) also known as ‘Blue Carbon’ ecosystems. In fact, many nations are seeking to manage VCEs to help meet their climate change mitigation targets through Nationally Determined Contributions (NDCs). However, incorporation of VCEs into NDCs requires national-scale estimates of contemporary and future blue carbon storage, which has not yet been achieved. Here we address this challenge using machine learning approaches to reliably map (with 62–72% accuracy) soil carbon stocks in VCEs based on geospatial data (topography, geomorphology, climate, and anthropogenic impacts), using Australia as a case study. The resulting maps of soil carbon stocks showed that there is a total of 951 Tg (±65 Tg) of carbon stock within Australian VCEs. Strong relationships between soil carbon stocks and climatic conditions (temperature, rainfall, solar radiation) allowed us to project future changes in carbon storage across all RCP scenarios for the years 2050 and 2090 to determine changes in environmental suitability for soil carbon stocks. Results show that soil carbon stocks in mangrove/tidal marsh ecosystems are likely to predominantly experience declines in carbon stocks under predicted climate change scenarios (19% of ecosystems area is predicted to have an increase in soil carbon stocks, while 38% of ecosystems area is predicted to have a decrease in soil carbon stocks), but a majority of seagrass area is likely to have increased soil carbon stocks (56% increase, 7% decrease). This approach is effective for developing robust national blue carbon inventories and revealing the capacity for blue carbon to help meet NDCs. The resulting spatially-explicit maps can also be used to pinpoint areas for successful blue carbon projects both now and in the future.

Nature-Based Engineering : A Review on Reducing Coastal Flood Risk With Mangroves - Gijsman, Rik; Horstman, Erik M; Wal, Daphne Van Der; Friess, Daniel A (2021)
Keywords: nature-based solutions, functionality, persistence

Partial canopy loss of mangrove trees: Mitigating water scarcity by physical adaptation and feedback on porewater salinity - Peters, Ronny; Lovelock, Catherine; López-Portillo, Jorge; Bathmann, Jasper; Wimmler, Marie Christin; Jiang, Jiang; Walther, Marc; Berger, Uta (Estuarine, Coastal and Shelf Science, 2021)
Trees species in the mangrove genus Avicennia can shed canopy parts when exposed to adverse environmental conditions, such as increases in porewater salinity. The individual-based model BETTINA enables the quantification of the tree's water use depending on its allometric characteristics. It thus provides a tool to model the equilibrium between plant size and density in a mangrove stand and porewater salinity. When the model is coupled with a simple water balance approach, the water use of trees corresponds to water uptake from the soil and, in combination with water fluxes, an increase of salinity in the root zone. Annual variations of the sea level, the tidal regime, groundwater inflow, and precipitation have an impact on the equilibrium of the combined system. Higher salinities lead to lower potential gradients and reduced water uptake of the plant. With a combined modelling approach (single tree model BETTINA with a simple water balance approach), we examined the dampening effects of consecutive partial canopy loss for the survival of the tree. We found that (i) the tree is able to decrease water demand and uptake and thus may reduce the tree's effect on soil water salinity, (ii) the reduced branch length leads to a reduced xylem flow resistance, and (iii) the reduction in height has a small positive effect on the water potential gradient between leaves and soil. Individual-based models can enhance our understanding of the regulating impact of the partial canopy loss on water balance in the combined plant-soil system.

Participatory Forestry Improves Mangrove Forest Management in Kenya - Kairu, A.; Kotut, K.; Mbeche, R.; Kairo, J. (International Forestry Review, 2021)
HIGHLIGHTS Stand densities and biomass were significantly higher in co-managed than in state-managed mangrove forests. Co-managed forest had significantly more merchantable pole density and significantly higher natural regeneration. Enhanced community patrols and surveillance has led to improved management of mangroves in the area. Sales of carbon credits from co-managed forests have served as a strong incentive for promoting mangrove rehabilitation, surveillance, and monitoring. Both co-managed and state-managed mangrove stands were characterized by high concentrations of small sized diameter and height classes signifying young forests under constant utilization. SUMMARY Participatory forestry has been recognized as a tool for improving tropical forest management. The current study assessed the impacts of participatory forest management (PFM) on the structure and regeneration of a mangrove forest at Gazi Bay, Kenya. Data were collected along belt transects perpendicular to the waterline in both co-managed and state-managed mangrove forests. Basal area and standing density were significantly higher in the co-managed mangrove forests (16 m2/ha and 4 341 tree/ha) as compared to the state forests (eastern block 10.3 m2/ha and 2 673 trees/ha; western block 6.2 m2/ha and 2 436 trees/ha). There were significantly higher (p = 0.0068) densities of merchantable poles in community-managed as compared to state-managed forests. Natural regeneration patterns in community-managed and state-managed forests were deemed adequate to support the recovery of both forests. The results demonstrate that community participation contributes to improved management of mangrove forests and is in agreement with the principles of sustainable forest management.

Participatory Forestry Improves Mangrove Forest Management in Kenya | La foresterie participative améliore la gestion des forets de mangrove au Kenya - Kairu, A.; Kotut, K.; Mbeche, R.; Kairo, J. (International Forestry Review, 2021)
HIGHLIGHTS Stand densities and biomass were significantly higher in co-managed than in state-managed mangrove forests. Co-managed forest had significantly more merchantable pole density and significantly higher natural regeneration. Enhanced community patrols and surveillance has led to improved management of mangroves in the area. Sales of carbon credits from co-managed forests have served as a strong incentive for promoting mangrove rehabilitation, surveillance, and monitoring. Both co-managed and state-managed mangrove stands were characterized by high concentrations of small sized diameter and height classes signifying young forests under constant utilization. SUMMARY Participatory forestry has been recognized as a tool for improving tropical forest management. The current study assessed the impacts of participatory forest management (PFM) on the structure and regeneration of a mangrove forest at Gazi Bay, Kenya. Data were collected along belt transects perpendicular to the waterline in both co-managed and state-managed mangrove forests. Basal area and standing density were significantly higher in the co-managed mangrove forests (16 m2/ha and 4 341 tree/ha) as compared to the state forests (eastern block 10.3 m2/ha and 2 673 trees/ha; western block 6.2 m2/ha and 2 436 trees/ha). There were significantly higher (p = 0.0068) densities of merchantable poles in community-managed as compared to state-managed forests. Natural regeneration patterns in community-managed and state-managed forests were deemed adequate to support the recovery of both forests. The results demonstrate that community participation contributes to improved management of mangrove forests and is in agreement with the principles of sustainable forest management.

Policy solutions to facilitate restoration in coastal marine environments - Shumway, Nicole; Bell-James, Justine; Fitzsimons, James A.; Foster, Rose; Gillies, Chris; Lovelock, Catherine E. (Marine Policy, 2021)
Restoration of coastal and marine ecosystems is essential to meet both national and global conservation targets and to counteract declines in coastal marine ecosystems. However, despite its status as a world leader in marine protection, Australia is lagging behind other countries in the implementation of coastal and marine restoration. Effective legislative frameworks that support the implementation of coastal and marine restoration as a management tool remains a key barrier to large-scale implementation of coastal and marine restoration in Australia and many other regions. We analyzed restoration projects and their policy frameworks in Australia, North America and Europe to identify the range of policy approaches for marine and coastal restoration. We then evaluated the legislative frameworks for coastal and marine restoration in two states in Australia (Queensland and New South Wales), to assess the current restoration permitting process and identify how different legislative and policy approaches could facilitate coastal and marine restoration projects. We identified two specific areas where improvements could be made to facilitate marine coastal restoration in Australia: increased transparency and better integration into coastal policy. Coastal and marine restoration in Australia is undertaken without appropriate and effective policy at the local, regional and national levels, which likely impedes its broader use as a management strategy. The policy and legislative changes and amendments outlined in this article can streamline the coastal and marine restoration process and thereby improve uptake of marine and coastal restoration in Australia.

Post-disaster assessment of mangrove forest recovery in lawaan-balangiga, eastern samar using ndvi time series analysis - Cabello, K. E.; Germentil, M. Q.; Blanco, A. C.; MacAtulad, E. G.; Salmo, S. G. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
In 2013, Typhoon Haiyan (Yolanda) struck the Eastern Philippines. Mangrove forests in the area were destroyed and were estimated to have at least 86% of damage. Some studies done on the typhoon-stricken mangroves had collected data such as measurements of mangrove trunk, height, roots, and seedlings to investigate the extent of damage and recovery. While these studies were proven to effectively identify mangrove gains and losses, these methods are only applicable in sites that are relatively accessible. This paper highlights the relevance of effective remote monitoring of mangrove forests that are vulnerable to typhoons including post-typhoon recovery. In this study, a Time Series Analysis using Google Earth Engine (GEE) was applied in assessing the damages and recovery of mangroves struck by Super Typhoon Haiyan in Lawaan and Balangiga, Samar (Eastern Philippines). The changes in mangrove extent followed the changes in NDVI; however, there were significant site-specific differences. Based on NDVI values, it was estimated that 83% of the mangrove area was damaged. After three years, regeneration from 2014-2017 was about 144%. Mangroves steadily developed but with a minimal change of 2.83% from 2017-2019. Most villages followed the general recovery trends in Lawaan and Balangiga. However, based on the time series analysis, some villages have minimal recovery than others. It suggests that the recovery of mangroves may be a function of the pre-typhoon mangrove extent and possibly vegetation condition. Even if there were new spaces for mangroves to colonize, some of the sites may not be conducive for plant regrowth.

Reconciling nature, people and policy in the mangrove social-ecological system through the adaptive cycle heuristic - Dahdouh-Guebas, Farid; Hugé, Jean; Abuchahla, Guilherme M.O.; Cannicci, Stefano; Jayatissa, Loku P.; Kairo, James G.; Kodikara Arachchilage, Sunanda; Koedam, Nico; Mafaziya Nijamdeen, Thanne W.G.F.; Mukherjee, Nibedita; Poti, Meenakshi; Prabakaran, Nehru; et al. (Estuarine, Coastal and Shelf Science, 2021)
While mangroves are increasingly described as social-ecological systems (SESs), performing SES research is so much more than merely documenting local resource utilisation patterns in case studies. The aim of this paper is to review and show how ecological, human and institutional resilience could be understood and fostered in an era of uncertainty, through the adaptive cycle (AC) heuristic. Uncertainties come in many forms and shapes: climate change, social and economic dynamics, natural disasters, political and institutional disruption and ever-increasing public demands for participation. Social-ecological studies form windows of experimentation that can provide insights beyond their case-specific context. In order to synthesise and structure the cumulative knowledge base arising from existing and future studies, the need for a suitable overarching framework arose. Here, the AC heuristic represents the connectedness between variables of the mangrove SES versus the mangrove's accumulated capital (natural, built, human and social). We posit that the AC heuristic can be used to interpret spatial and temporal changes (ecological, social, economic, political) in mangrove SESs and we exemplify it by using the 2004 Indian Ocean tsunami as well as a century-long silviculture case. The AC, combined with the SES scheme, allows integration of the spato-temporal dynamics and the multi-dimensional character of mangrove SESs. We also reviewed the ecosystem functions, services and disservices of mangrove SESs, linking each of them to SES capital and variable (fast or slow) attributes, which in turn are closely linked to the different axes and phases of the AC. We call upon mangrove scientists from the natural, applied, social and human sciences to join forces in fitting diversified empirical data from multiple case studies around the world to the AC heuristic. The aim is to reflect on and understand such complex dynamic systems with stakeholders having various (mutual) relationships at risk of breaking down, and to prepare for interactive adaptive planning for mangrove forests.

Resilience of trees and the vulnerability of grasslands to climate change in temperate Australian wetlands - Saintilan, Neil; Bowen, Sharon; Maguire, Owen; Karimi, Sara S.; Wen, Li; Powell, Megan; Colloff, Matthew J.; Sandi, S.; Saco, P.; Rodriguez, J. (Landscape Ecology, 2021)
Objectives: Observations from wetlands across the globe suggest a consistent pattern of woody encroachment into wetland grasslands, altering habitat structure and ecological function. The extent to which hydrological changes have contributed to woody invasion of wetland grasslands is unclear. Our objective was to compare rates of woody encroachment in Australian floodplain wetlands between wet and dry hydrological phases. We test the hypothesis that contraction of non-woody wetland vegetation (grasses and rushes) would be concentrated in dry phases, co-incident with recruitment of the River Red Gum Eucalyptuscamaldulensis lower in the floodplain. Methods: We conduct the first detailed mapping of habitat change in two of the largest forested wetlands in inland Australia, comparing wet and dry hydrological phases. Detailed photogrammetry, supported by extensive ground survey, allowed the interpretation of high resolution aerial photography to vegetation community level. Results: We found a consistent pattern of decline in non-woody vegetation, particularly amongst grasses utilising the C4 photosynthetic pathway. The C4 grasses Pseudoraphisspinescens and Paspalumdistichum showed steep declines in the Barmah Millewa and Macquarie Marshes respectively, being replaced by River Red Gum E. camaldulensis. C3 sedges proved more resilient in both systems. Conclusions: Our results suggest that a pattern of tree expansion into non-woody wetland vegetation, characteristic of wetlands across the globe, is a major habitat structural change in the Australian floodplain wetlands studied. Projected hydrological impacts of climate change are likely to further restrict wetland grass foraging habitat in these semi-arid floodplain wetlands.

Scalability and performance tradeoffs in quantifying relationships between elevation and tidal wetland plant communities - Holmquist, James R.; Schile-Beers, Lisa; Buffington, Kevin; Lu, Meng; Mozdzer, Thomas J.; Riera, Jefferson; Weller, Donald E.; Williams, Meghan; Megonigal, J. Patrick (Marine Ecology Progress Series, 2021)
Elevation is a major driver of plant ecology and sediment dynamics in tidal wetlands, so accurate and precise spatial data are essential for assessing wetland vulnerability to sea-level rise and making forecasts. We performed survey-grade elevation and vegetation surveys of the Global Change Research Wetland, a brackish microtidal wetland in the Chesapeake Bay estuary, Maryland (USA), to both intercompare unbiased digital elevation model (DEM) creation techniques and to describe niche partitioning of several common tidal wetland plant species. We identified a tradeoff between scalability and performance in creating unbiased DEMs, with more dataintensive methods such as kriging performing better than 3 more scalable methods involving postprocessing of light detection and ranging (LiDAR)-based DEMs. The LiDAR Elevation Correction with Normalized Difference Vegetation Index (LEAN) method provided a compromise between scalability and performance, although it underpredicted variability in elevation. In areas where native plants dominated, the sedge Schoenoplectus americanus occupied more frequently flooded areas (median: 0.22, 95% range: 0.09 to 0.31 m relative to North America Vertical Datum of 1988 [NAVD88]) and the grass Spartina patens, less frequently flooded (0.27, 0.1 to 0.35 m NAVD88). Non-native Phragmites australis dominated at lower elevations more than the native graminoids, but had a wide flooding tolerance, encompassing both their ranges (0.19, -0.05 to 0.36 m NAVD88). The native shrub Iva frutescens also dominated at lower elevations (0.20, 0.04 to 0.30 m NAVD88), despite being previously described as a high marsh species. These analyses not only provide valuable context for the temporally rich but spatially restricted data collected at a single well-studied site, but also provide broad insight into mapping techniques and species zonation.

Seagrass (Halophila stipulacea) invasion enhances carbon sequestration in the Mediterranean Sea - Wesselmann, Marlene; Geraldi, Nathan R.; Duarte, Carlos M.; Garcia-Orellana, Jordi; Díaz-Rúa, Rubén; Arias-Ortiz, Ariane; Hendriks, Iris E.; Apostolaki, Eugenia T.; Marbà, Núria (Global Change Biology, 2021)
The introduction and establishment of exotic species often result in significant changes in recipient communities and their associated ecosystem services. However, usually the magnitude and direction of the changes are difficult to quantify because there is no pre-introduction data. Specifically, little is known about the effect of marine exotic macrophytes on organic carbon sequestration and storage. Here, we combine dating sediment cores (210Pb) with sediment eDNA fingerprinting to reconstruct the chronology of pre- and post-arrival of the Red Sea seagrass Halophila stipulacea spreading into the Eastern Mediterranean native seagrass meadows. We then compare sediment organic carbon storage and burial rates before and after the arrival of H. stipulacea and between exotic (H. stipulacea) and native (C. nodosa and P. oceanica) meadows since the time of arrival following a Before-After-Control-Impact (BACI) approach. This analysis revealed that H. stipulacea arrived at the areas of study in Limassol (Cyprus) and West Crete (Greece) in the 1930s and 1970s, respectively. Average sediment organic carbon after the arrival of H. stipulacea to the sites increased in the exotic meadows twofold, from 8.4 ± 2.5 g Corg m−2year−1 to 14.7 ± 3.6 g Corg m−2year−1, and, since then, burial rates in the exotic seagrass meadows were higher than in native ones of Cymodocea nodosa and Posidonia oceanica. Carbon isotopic data indicated a 50% increase of the seagrass contribution to the total sediment Corg pool since the arrival of H. stipulacea. Our results demonstrate that the invasion of H. stipulacea may play an important role in maintaining the blue carbon sink capacity in the future warmer Mediterranean Sea, by developing new carbon sinks in bare sediments and colonizing areas previously occupied by the colder thermal affinity P. oceanica.

Soil Carbon and Nitrogen Storage in Natural and Prop-Scarred Thalassia Testudinum Seagrass Meadows - Arney, Rachel N.; Shepherd, Alison K.; Alexander, Heather D.; Rahman, Abdullah F. (Estuaries and Coasts, 2021)
Seagrass meadows are carbon (C) sinks and nitrogen (N)-limited ecosystems that experience degradation from climate change and anthropogenic stressors, including prop-scarring disturbances by boating vessels. To better understand the variability in C and N pools of undisturbed seagrass soils and the recovery of these pools following boat propeller scarring, we quantified organic carbon (Corg) and N pools within the top 1 m of soils in undisturbed Thalassia testudinum seagrass beds of the Lower Laguna Madre (LLM), Texas, USA—a sub-tropical, uniquely hypersaline, and heavily used recreational boating lagoon—and used a chronosequence approach to compare these undisturbed soil pools to those in different aged prop scars (1–3, 4–6, 7–9, and 10+ years). We found that undisturbed soils stored 108.41 ± 2.93 and 6.65 ± 0.26 Mg (megagram) ha−1 of Corg and N, respectively, in the top 1 m, with ~ 30% of these pools stored within the top 20 cm. Scarring impacted these shallow, organic-rich pools, exposing higher bulk density (BD) mineral soils with lower %Corg and %N. Consequently, young scars (1–3 years) had significantly lower %Corg and %N values in the top 20 cm of soil compared with undisturbed soils, but the greater BD offset these changes, leading to no differences in total Corg and N pools in the top 1 m between scarred and undisturbed soils. Scars 10+ years had similar %Corg, %N, and BD soil characteristics to undisturbed soils, producing similar Corg and N pools in both upper and lower soil horizons. These findings indicate that recovery of Corg and N pools of prop-scarred seagrass soils within T. testudinum beds of the LLM will likely recover a decade or more post-disturbance. Our findings contribute to the growing global database on seagrass C and N storage and demonstrate the rate at which seagrass meadows recover post-disturbance.

Spatial cost–benefit analysis of blue restoration and factors driving net benefits globally - Stewart-Sinclair, Phoebe J.; Klein, Carissa J.; Bateman, Ian J.; Lovelock, Catherine E. (Conservation Biology, 2021)
Marine coastal ecosystems, commonly referred to as blue ecosystems, provide valuable services to society but are under increasing threat worldwide due to a variety of drivers, including eutrophication, development, land-use change, land reclamation, and climate change. Ecological restoration is sometimes necessary to facilitate recovery in coastal ecosystems. Blue restoration (i.e., in marine coastal systems) is a developing field, and projects to date have been small scale and expensive, leading to the perception that restoration may not be economically viable. We conducted a global cost–benefit analysis to determine the net benefits of restoring coral reef, mangrove, saltmarsh, and seagrass ecosystems, where the benefit is defined as the monetary value of ecosystem services. We estimated costs from published restoration case studies and used an adjusted-value-transfer method to assign benefit values to these case studies. Benefit values were estimated as the monetary value provided by ecosystem services of the restored habitats. Benefits outweighed costs (i.e., there were positive net benefits) for restoration of all blue ecosystems. Mean benefit:cost ratios for ecosystem restoration were eight to 10 times higher than prior studies of coral reef and seagrass restoration, most likely due to the more recent lower cost estimates we used. Among ecosystems, saltmarsh had the greatest net benefits followed by mangrove; coral reef and seagrass ecosystems had lower net benefits. In general, restoration in nations with middle incomes had higher (eight times higher in coral reefs and 40 times higher in mangroves) net benefits than those with high incomes. Within an ecosystem type, net benefit varied with restoration technique (coral reef and saltmarsh), ecosystem service produced (mangrove and saltmarsh), and project duration (seagrass). These results challenge the perceptions of the low economic viability of blue restoration and should encourage further targeted investment in this field.

Structural Characteristics of the Tallest Mangrove Forests of the American Continent: A Comparison of Ground-Based, Drone and Radar Measurements - Castellanos-Galindo, Gustavo A.; Casella, Elisa; Tavera, Hector; Zapata Padilla, Luis Alonso; Simard, Marc (Frontiers in Forests and Global Change, 2021)
The Panama Bight eco-region along the Pacific coast of central and South America is considered to have one of the best-preserved mangrove ecosystems in the American continent. The regional climate, with rainfall easily reaching 5–8 m every year and weak wind conditions, contribute to the exceptionally tall mangroves along the southern Colombian and northern Ecuadorian Pacific coasts (Nariño Department and Esmeraldas Province areas). Here we evaluate the use of different methods (ground-based measurements, drone imagery and radar data [Shuttle Radar Topography mission-SRTM and TanDEM-X]) to characterize the structure of the tallest of these forests. In November 2019, three mangrove sites with canopy heights between 50 and 60 m, previously identified with SRTM data, were sampled close to the town of Guapi, Colombia. In addition to in situ field measurements of trees, we conducted airborne drone surveys in order to generate georeferenced orthomosaics and digital surface models (DSMs). We found that the extensive mangrove forests in this area of the Colombian Pacific are almost entirely composed of Rhizophora spp. trees. The tallest mangrove tree measured in the three plots was 57 m. With ca. 900 drone photographs, three orthomosaics (2 cm pixel–1 resolution) and digital surface models (3.5 cm pixel–1) with average area of 4,0 ha were generated. The field-measured canopy heights were used to validate the drone-derived and radar-derived data, confirming these mangrove forests as the tallest in the Americas. The drone-derived orthomosaics showed significant patches of the Golden Leather Fern, Acrostichum aureum, an opportunistic species that can be associated to mangrove degradation, indicating that the mangrove forests investigated here may be threatened from increased selective logging requiring improvements and effective implementation of the current mangrove management plans in Colombia. The techniques used here are highly complementary and may represent the three tiers for carbon reporting, whereby the drone-derived canopy height maps, calibrated with local in situ measurements, provides cheap but reliable Tier 3 estimates of carbon stocks at the project level.
Keywords: Colombia; Rhizophoraspp; Shuttle Radar Topography mission; eastern Pacific; mangrove above-ground biomass; mangrove degradation; structure from motion (SFM); unoccupied aerial vehicles (UAVs)

The NASA AfriSAR campaign: Airborne SAR and lidar measurements of tropical forest structure and biomass in support of current and future space missions - Fatoyinbo, Temilola; Armston, John; Simard, Marc; Saatchi, Sassan; Denbina, Michael; Lavalle, Marco; Hofton, Michelle; Tang, Hao; Marselis, Suzanne; Pinto, Naiara; Hancock, Steven; Hawkins, Brian; et al. (Remote Sensing of Environment, 2021)
In 2015 and 2016, the AfriSAR campaign was carried out as a collaborative effort among international space and National Park agencies (ESA, NASA, ONERA, DLR, ANPN and AGEOS) in support of the upcoming ESA BIOMASS, NASA-ISRO Synthetic Aperture Radar (NISAR) and NASA Global Ecosystem Dynamics Initiative (GEDI) missions. The NASA contribution to the campaign was conducted in 2016 with the NASA LVIS (Land Vegetation and Ice Sensor) Lidar, the NASA L-band UAVSAR (Uninhabited Aerial Vehicle Synthetic Aperture Radar). A central motivation for the AfriSAR deployment was the common AGBD estimation requirement for the three future spaceborne missions, the lack of sufficient airborne and ground calibration data covering the full range of ABGD in tropical forest systems, and the intercomparison and fusion of the technologies. During the campaign, over 7000 km2 of waveform Lidar data from LVIS and 30,000 km2 of UAVSAR data were collected over 10 key sites and transects. In addition, field measurements of forest structure and biomass were collected in sixteen 1-hectare sized plots. The campaign produced gridded Lidar canopy structure products, gridded aboveground biomass and associated uncertainties, Lidar based vegetation canopy cover profile products, Polarimetric Interferometric SAR and Tomographic SAR products and field measurements. Our results showcase the types of data products and scientific results expected from the spaceborne Lidar and SAR missions; we also expect that the AfriSAR campaign data will facilitate further analysis and use of waveform lidar and multiple baseline polarimetric SAR datasets for carbon cycle, biodiversity, water resources and more applications by the greater scientific community.

The Ocean and Cryosphere in a Changing Climate in Latin America : Knowledge Gaps and the Urgency to Translate Science Into Action - Muelbert, Mônica M C; Copertino, Margareth; Cotrim, Leticia (2021)

The sediment carbon stocks of intertidal seagrass meadows in Scotland - Potouroglou, Maria; Whitlock, Danielle; Milatovic, Luna; MacKinnon, Gillian; Kennedy, Hilary; Diele, Karen; Huxham, Mark (Estuarine, Coastal and Shelf Science, 2021)
Seagrasses are highly productive ecosystems and hotspots for biodiversity, providing a plethora of benefits to the environment and to people. Their value in sequestering and storing carbon is increasingly being recognised, as the world searches for ways to mitigate the effects and slow the pace of climate change. However, many uncertainties remain, with basic information such as average carbon stocks, variability and species-specific differences missing for many regions. This study evaluates, for the first time, the carbon storage capacity of Zostera noltii and Zostera marina from intertidal seagrass meadows in Scotland. Sediment carbon stocks in the top 50 cm from vegetated and reference unvegetated plots were quantified at 10 estuaries distributed along the Scottish east and west coasts. The organic carbon stocks in the top 50 cm of the seagrass sediment ranged from a minimum of 14.94 Mg C ha−1 at the Moray Firth to a maximum of 105.72 Mg C ha−1 at the Firth of Forth, with a mean (±SD) of 54.79 ± 35.02 Mg C ha−1 across the 10 estuaries sampled. Moreover, seagrass areas showed enhanced carbon storage compared to reference unvegetated ones, however this was highly variable across depth, and among sites and estuaries. This paper addresses key gaps in knowledge concerning the role of intertidal Scottish seagrass meadows as carbon sinks and discusses the implication of this emerging information for their effective management and conservation.

Total Ecosystem Carbon Stocks of Mangroves in Lamu, Kenya; and Their Potential Contributions to the Climate Change Agenda in the Country - Kairo, James; Mbatha, Anthony; Murithi, Martin M.; Mungai, Fredrick (Frontiers in Forests and Global Change, 2021)
Mangroves are carbon-rich ecosystems found in tropical and subtropical areas around the world. However, they are threatened by a combination of natural and human-induced factors. When mangroves are lost or degraded, their co-benefits to human society are greatly diminished along with the ecosystem’s ability to sequester carbon. The current study assessed mangrove cover and cover change, as well as measuring carbon stocks and their emissions levels from the mangroves of Lamu County, Kenya. We sampled above-and below-ground carbon pools, including soil organic carbon (SOC), in 191 plots distributed throughout the study area. Lastly, we evaluated the economics of avoiding mangrove deforestation based on the carbon-offset market. The total carbon stock of mangroves in Lamu was estimated at 20 million Mg C, with an average density of 560.22 ± 79.79 Mg C ha–1. Southern swamps recorded significantly higher carbon densities (p < 0.05) than other mangrove management blocks in Lamu. At least 1,739 ha of mangroves in Lamu were lost between 1990 and 2019 due to anthropogenic activities, representing a decline of 60 ha yr–1. Total emissions from loss and degradation of mangroves in Lamu is estimated at 140.1 Mg C ha–1; which translates to 30,840.1 Mg CO2e yr–1. Assuming an offset price of US$10/Mg CO2e, the estimated costs of avoided emissions in Lamu is US$308,401 yr–1 plus other co-benefits such as fishery functions and shoreline protection. Mainstreaming mangroves and associated blue carbon ecosystems into national development and climate change agenda could accelerate Kenya’s achievements of both Sustainable Development Goals (SDGs) and the Paris Agreement.

Tracing organic matter sources in the estuarine sediments of Vanga, Kenya, and provenance implications - Kimeli, Amon; Cherono, Shawlet; Mutisya, Bonface; Tamooh, Fredrick; Okello, Judith; Westphal, Hildegard; Koedam, Nico; Kairo, James (Estuarine, Coastal and Shelf Science, 2021)
Mangrove ecosystems can potentially and indirectly modulate the effects of sea level rise due to their ability to trap and retain sediments. In order to gain a better understanding of the potential sediment sources and dynamics in the mangroves of Vanga, Kenya, inter-seasonal riverine, estuarine and coastal/marine sediments together with agricultural soil and mangrove tissues were studied. Elemental ratios (C/N) and carbon (δ13C) stable isotope composition, were analysed to disentangle sources of sediment organic matter (SOM) in the Vanga, Estuary. The organic carbon (C) content, C/N ratios and δ13C values ranged between 0.1 and 2.4%, 9.9 to 35.5 and −24.8 to −19.9‰ respectively. These contents were also as expected relatively higher in mangrove tissues than in all the sediment samples. δ13C values of mangrove sediments were higher than those of the mangrove tissues, which was attributed to rapid decomposition, dilution by freshwater and mineral organic matter (OM) discharged by the Umba River as well as outwashing by ebb tides. On average, C/N ratios were also observed to be greater than 10 in all samples collected during both the dry and wet season. This has been shown to reflect a pronounced contribution of allochthonous organic matter. Using a combination of δ13C values and C/N ratio, the dominance of riverine POM was also evident from a Bayesian Stable Isotope Mixing Model in R-program (SIMMR) that indicated OM source mixing but with a dominant (∼60%) contribution of riverine OM. The observed and modeled variability of SOM in the Vanga estuary points to the hypothesized influence of the Umba River on Vanga Estuary sediments but with evidence of potential material exchange and influence of tidal fluxes within the estuary.

Vegetation Type and Decomposition Priming Mediate Brackish Marsh Carbon Accumulation Under Interacting Facets of Global Change - Rietl, Anthony J.; Megonigal, J. Patrick; Herbert, Ellen R.; Kirwan, Matthew L. (Geophysical Research Letters, 2021)
Coastal wetland carbon pools are globally important, but their response to interacting facets of global change remain unclear. Numerical models neglect species-specific vegetation responses to sea level rise (SLR) and elevated CO2 (eCO2) that are observed in field experiments, while field experiments cannot address the long-term feedbacks between flooding and soil growth that models show are important. Here, we present a novel numerical model of marsh carbon accumulation parameterized with empirical observations from a long-running eCO2 experiment in an organic rich, brackish marsh. Model results indicate that eCO2 and SLR interact synergistically to increase soil carbon burial, driven by shifts in plant community composition and soil volume expansion. However, newly parameterized interactions between plant biomass and decomposition (i.e. soil priming) reduce the impact of eCO2 on marsh survival, and by inference, the impact of eCO2 on soil carbon accumulation.

Vulnerability of an arid zone coastal wetland landscape to sea level rise and intense storms - Lovelock, Catherine E.; Reef, Ruth; Masqué, Pere (Limnology and Oceanography, 2021)
Arid zone coastal wetlands provide disproportionally important ecosystem services due to their relatively high levels of productivity relative to adjacent terrestrial systems. However, these wetlands are vulnerable to sea level rise as sediments needed for vertical accretion are limited. In order to assess the processes important for vertical accretion in arid zone coastal wetlands, we assessed vertical accretion across an arid zone wetland landscape in Western Australia. We found that overall coastal wetlands were declining in elevation at −0.18 mm yr−1 (± standard error 0.12 mm yr−1). Vertical accretion in mangroves was evident in years of high mean sea level, but this was insufficient to counteract shallow subsidence. The high intertidal cyanobacterial mat and salt flat zones were eroding, particularly in years of high rainfall. We observed retreat of the seaward mangrove fringe associated with tree mortality caused by cyclones, but we also observed recruitment of mangroves onto the high intertidal cyanobacterial mat zone, attributed to higher sea levels. Our study found complexity in the factors causing landscape change across the intertidal zone, where variation in sea level, intense storms, and other climatic and biotic factors interact.

Warming Threatens to Propel the Expansion of the Exotic Seagrass Halophila stipulacea - Wesselmann, Marlene; Chefaoui, Rosa M.; Marbà, Núria; Serrao, Ester A.; Duarte, Carlos M. (Frontiers in Marine Science, 2021)
The spread of exotic species to new areas can be magnified when favored by future climatic conditions. Forecasting future ranges using species distribution models (SDMs) could be improved by considering physiological thresholds, because models solely based on occurrence data cannot account for plasticity due to acclimation of individuals to local conditions over their life-time or to adaptation due to selection within local populations. This is particularly relevant for the exotic seagrass Halophila stipulacea, which colonized the Mediterranean Sea a century ago and shifted its thermal niche, coping with a colder regime. Here, we used two hybrid models combining correlative SDMs with the thermal limits for growth of native and exotic H. stipulacea populations to predict the distribution of the species in its native (Indian Ocean and Red Sea) and exotic ranges (Mediterranean Sea and Caribbean Sea) under two scenarios forecasting limited (RCP 2.6) and severe (RCP 8.5) future climate changes by 2050 and 2100. Then, we assessed the differences between hybrid models based on native Red Sea thermal limits (niche conservatism: 17–36°C) and on exotic Mediterranean thermal limits (local adaptation: 14–36°C). At the Mediterranean exotic range, the local adaptation hybrid model accurately agreed with the present distribution of the species while the niche conservatism-based hybrid model failed to predict 87% of the current occurrences of the species. By contrast, both hybrid models predicted similar species distributions for the native range and exotic Caribbean range at present and projected that H. stipulacea will maintain its current worldwide under all future greenhouse gas emission scenarios. The hybrid model based on Mediterranean thermal limits projected the expansion of H. stipulacea through the western Mediterranean basin (except the gulf of Leon) under the most severe scenario (RCP 8.5) by 2100, increasing its distribution by 50% in the Mediterranean. The future expansion of H. stipulacea is related to its capacity to cope with warm waters and it may become a relevant species in the future, particularly under the projected decline of native Mediterranean seagrasses, resulting in important shifts in seagrass communities and overall ecosystem functions.

Water temperature control on CO2 flux and evaporation over a subtropical seagrass meadow revealed by atmospheric eddy covariance - Van Dam, Bryce R.; Lopes, Christian C.; Polsenaere, Pierre; Price, René M.; Rutgersson, Anna; Fourqurean, James W. (Limnology and Oceanography, 2021)
Subtropical seagrass meadows play a major role in the coastal carbon cycle, but the nature of air–water CO2 exchanges over these ecosystems is still poorly understood. The complex physical forcing of air–water exchange in coastal waters challenges our ability to quantify bulk exchanges of CO2 and water (evaporation), emphasizing the need for direct measurements. We describe the first direct measurements of evaporation and CO2 flux over a calcifying seagrass meadow near Bob Allen Keys, Florida. Over the 78-d study, CO2 emissions were 36% greater during the day than at night, and the site was a net CO2 source to the atmosphere of 0.27 ± 0.17 μmol m−2 s−1 (x̅ ± standard deviation). A quarter (23%) of the diurnal variability in CO2 flux was caused by the effect of changing water temperature on gas solubility. Furthermore, evaporation rates were ~ 10 times greater than precipitation, causing a 14% increase in salinity, a potential precursor of seagrass die-offs. Evaporation rates were not correlated with solar radiation, but instead with air–water temperature gradient and wind shear. We also confirm the role of convective forcing on night-time enhancement and day-time suppression of gas transfer. At this site, temperature trends are regulated by solar heating, combined with shallow water depth and relatively consistent air temperature. Our findings indicate that evaporation and air–water CO2 exchange over shallow, tropical, and subtropical seagrass ecosystems may be fundamentally different than in submerged vegetated environments elsewhere, in part due to the complex physical forcing of coastal air–sea gas transfer.

When "Blue Carbon" turns white: Isotopic evidence of calcification-driven CO2 emissions in a carbonate seagrass meadow - Zeller, Mary; Van Dam, Bryce; Lopes, Christian; Smyth, Ashley; Böttcher, Michael; Osburn, Christopher; Zimmerman, Tristan; Pröfrock, Daniel; Fourqurean, James; Thomas, Helmuth (EGU General Assembly, 2021)
Long-term “Blue Carbon” burial in seagrass meadows is complicated by other carbon and alkalinity exchanges that shape net carbon sequestration. We measured a suite of such processes, including denitrification, sulfur, and inorganic carbon cycling, and assessed their impact on air-water CO2 exchange in a typical seagrass meadow underlain by carbonate sediments. Eddy covariance measurements reveal a consistent source of CO2 to the at- mosphere at an average rate of 610 ± 990 ?mol m−2 hour−1 during our study and 700 ± 660 ?mol m−2 hour−1 (6.1 mol m−2 year−1) over an annual cycle. Net alkalinity consumption by ecosystem calcification explains >95% of the observed CO2 emissions, far exceeding organic carbon burial and anaerobic alkalinity generation. We argue that the net carbon sequestration potential of seagrass meadows may be overestimated if calcification-induced CO2 emissions are not accounted for, especially in regions where calcification rates exceed net primary produc- tion and burial.

Widespread mangrove damage resulting from the 2017 Atlantic mega hurricane season - Adame, María Fernanda Maria Fernanda; Brown, Christopher James; Bejarano, Marylin; Herrera-Silveira, Jorge Alfredo; Ezcurra, Paula; Kauffman, John Boone J.B. Boone; Birdsey, Richard A; Sur, Pronatura; Bell-james, Justine; Fitzsimons, James A.; Gillies, Chris L; Shumway, Nicole; et al. (Frontiers in Marine Science, 2021)
A revised guide to supporting coastal wetland programs and projects using climate finance and other financial mechanisms
Keywords: 19 march 2013; 210Pb dating; 210Pb sediment dating; 3-PG; Aboveground biomass; Accretion; Adventitious; Aerenchyma; Allochthonous carbon; Allometric models; Amazon; Aquaculture; Aquaculture ponds; Atmospheric CO2; Avicennia schaueriana; Baseline; Belize; Biodiversity; Biomass; Biomass allocation; Blue Carbon; Blue carbon; CO2 emissions; CO2 sequestration; Carbon; Carbon accumulation; Carbon burial; Carbon credits; Carbon dioxide rise; Carbon dynamics; Carbon flux; Carbon footprint; Carbon sequestration; Carbon stock; Carbon stocks; Carnegie Airborne Observatory; Cattle pastures; Celestun; Central America; China; Chlorophyll a fluorescence; Climate; Climate change; Climate change mitigat; Climate change mitigation; Climate mitigation; Climate-change mitigation; Co-benefits; Coastal; Coastal ecosystems; Coastal habitat; Coastal management policies; Coastal restoration; Coastal wetlands; Colombia; Complementarity; Connectivity; Conservation; Decomposition; Deforestation; Degradation; Dendrometer; Determinants of plant community diversity and stru; Diameter increment; Disturbance; Diversion; Dynamics; Earthquake; Ecohydrology; Economic value; Ecosystem carbon pools; Ecosystem carbon stocks; Ecosystem services; Eelgrass; El Niño; Emission factor; Emissions; Encroachment; Environmental drivers; Environmental impact; Estuary; Export; Facilitator species; Fertilization; Fire; Fisheries rebuilding; For; Forest conversion; Forest degradation; Forest inventory; Geographic information systems; Global; Global fisheries; Governance; Greenhouse gas accounting; Growth and yield modelling; Guano; Halodule uninervis; Halophila gaudichaudii; Halophila ovalis

A Guide to International Climate Mitigation Policy and Finance Frameworks Relevant to the Protection and Restoration of Blue Carbon Ecosystems - Vanderklift, Mathew A.; Herr, Dorothée; Lovelock, Catherine E.; Murdiyarso, Daniel; Raw, Jacqueline L.; Steven, Andrew D.L. (Frontiers in Marine Science, 2022)
The protection, management and restoration of vegetated ecosystems on land and in the ocean (‘natural climate solutions’) can be a useful strategy for reducing net greenhouse gas emissions to help limit global warming. Their potential contribution to reducing net emissions has led to the development of policies and financial incentives for their protection and restoration. These have in turn created a set of expectations among some stakeholders, and interest in expanding these to encompass other ecosystems. However, there are specific rules about how abatement is calculated in international policy and climate finance, and the frameworks and terminology associated with them are often complex. This can be a barrier to stakeholders who want to leverage the potential of natural climate solutions, sometimes leading to incongruence between realised and anticipated benefits. In this article, we attempt to outline some of the key international policy and carbon market frameworks for coastal ‘blue carbon’ ecosystems, and the extent to which different ecosystems are accommodated. Currently, among the coastal ecosystems, only mangrove forests, seagrass meadows, and tidal marshes are typically considered in international policy and carbon market frameworks. The defining feature of these ecosystems is that the foundation species are plants that grow in sediment (soil). They are the only coastal ecosystems currently included in IPCC guidelines for national greenhouse gas inventories, and in compliance and voluntary carbon markets. There is interest in potentially including other marine ecosystems, such as kelp forests and unvegetated tidal flats, into carbon accounting frameworks, but there are unresolved questions about whether sequestration and storage of carbon by these ecosystems meets the rigorous standards required. Voluntary carbon markets have greater flexibility than mechanisms linked to national greenhouse gas inventories, and so might be early implementers of expanding methods to include other ecosystems. Incorporating coastal ecosystems into national greenhouse gas inventory is a useful action countries can take that will likely help generate incentives for protection and restoration of these important ecosystems.

A review of carbon monitoring in wet carbon systems using remote sensing - Campbell, Anthony D.; Fatoyinbo, Temilola; Charles, Sean P.; Bourgeau-Chavez, Laura L.; Goes, Joaquim; Gomes, Helga; Halabisky, Meghan; Holmquist, James; Lohrenz, Steven; Mitchell, Catherine; Moskal, L. Monika; Poulter, Benjamin; et al. (Environmental Research Letters, 2022)
Carbon monitoring is critical for the reporting and verification of carbon stocks and change. Remote sensing is a tool increasingly used to estimate the spatial heterogeneity, extent and change of carbon stocks within and across various systems. We designate the use of the term wet carbon system to the interconnected wetlands, ocean, river and streams, lakes and ponds, and permafrost, which are carbon-dense and vital conduits for carbon throughout the terrestrial and aquatic sections of the carbon cycle. We reviewed wet carbon monitoring studies that utilize earth observation to improve our knowledge of data gaps, methods, and future research recommendations. To achieve this, we conducted a systematic review collecting 1622 references and screening them with a combination of text matching and a panel of three experts. The search found 496 references, with an additional 78 references added by experts. Our study found considerable variability of the utilization of remote sensing and global wet carbon monitoring progress across the nine systems analyzed. The review highlighted that remote sensing is routinely used to globally map carbon in mangroves and oceans, whereas seagrass, terrestrial wetlands, tidal marshes, rivers, and permafrost would benefit from more accurate and comprehensive global maps of extent. We identified three critical gaps and twelve recommendations to continue progressing wet carbon systems and increase cross system scientific inquiry.

A systematic review of mangrove restoration studies in Southeast Asia: Challenges and opportunities for the United Nation’s Decade on Ecosystem Restoration - Gerona-Daga, Maria Elisa B.; Salmo, Severino G. (Frontiers in Marine Science, 2022)
Mangroves provide valuable ecological and socio-economic services. The importance of mangroves is particularly evident in Southeast (SE) Asia where the most extensive and diverse forests are found. To recover degraded mangroves, several SE Asian countries have implemented restoration programs. However, to date, there has been no systematic and quantitative synthesis on mangrove restoration studies in the region. Here, we provide a bibliometric-based analysis of mangrove restoration to provide understanding on trends and future directions needed to meet biodiversity and restoration targets in the region. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, we analyzed 335 articles (249 articles with ecological attributes; 86 articles with social attributes) published until February 2022 from Scopus and Web of Science databases. Mangrove restoration studies with ecological and social attributes started around the early 1990s mostly from Indonesia, Thailand, Malaysia, Vietnam, and the Philippines. Majority of SE Asian countries have stronger collaboration to western countries rather than within the region. Reasons for restoration vary per country, but mostly were intended to rehabilitate damaged mangroves. Direct planting was the most common restoration method used while hydrological rehabilitation was less practiced. Research on ecological attributes were dominated by biodiversity-related studies focused on flora and fauna, and less on other ecosystem services (e.g., coastal protection, fisheries production, etc.). Studies with social attributes only accounted for <30% of the publications, mostly on topics related to ecological economics. Although mangrove restoration studies are apparent, some thematic restoration foci are needed. We propose priority research topics to help achieve the biodiversity and restoration targets by 2030.

Accelerated sea-level rise is suppressing CO2 stimulation of tidal marsh productivity: A 33-year study - Zhu, Chunwu; Langley, J. Adam; Ziska, Lewis H.; Cahoon, Donald R.; Megonigal, J. Patrick (Science Advances, 2022)
Accelerating relative sea-level rise (RSLR) is threatening coastal wetlands. However, rising CO2 concentrations may also stimulate carbon sequestration and vertical accretion, counterbalancing RSLR. A coastal wetland dominated by a C3 plant species was exposed to ambient and elevated levels of CO2 in situ from 1987 to 2019 during which time ambient CO2 concentration increased 18% and sea level rose 23 cm. Plant production did not increase in response to gradually rising ambient CO2 concentration during this period. Elevated CO2 increased shoot production relative to ambient CO2 for the first two decades, but from 2005 to 2019, elevated CO2 stimulation of production was diminished. The decline coincided with increases in relative sea level above a threshold that hindered root productivity. While elevated CO2 stimulation of elevation gain has the potential to moderate the negative impacts of RSLR on tidal wetland productivity, benefits for coastal wetland resilience will diminish in the long term as rates of RSLR accelerate.

Ambitious global targets for mangrove and seagrass recovery - Buelow, Christina A.; Connolly, Rod M.; Turschwell, Mischa P.; Adame, Maria F.; Ahmadia, Gabby N.; Andradi-Brown, Dominic A.; Bunting, Pete; Canty, Steven W.J.; Dunic, Jillian C.; Friess, Daniel A.; Lee, Shing Yip; Lovelock, Catherine E.; et al. (Current Biology, 2022)
There is an urgent need to halt and reverse loss of mangroves and seagrass to protect and increase the ecosystem services they provide to coastal communities, such as enhancing coastal resilience and contributing to climate stability.1,2 Ambitious targets for their recovery can inspire public and private investment in conservation,3 but the expected outcomes of different protection and restoration strategies are unclear. We estimated potential recovery of mangroves and seagrass through gains in ecosystem extent to the year 2070 under a range of protection and restoration strategies implemented until the year 2050. Under a protection-only scenario, the current trajectories of net mangrove loss slowed, and a minor net gain in global seagrass extent (∼1%) was estimated. Protection alone is therefore unlikely to drive sufficient recovery. However, if action is taken to both protect and restore, net gains of up to 5% and 35% of mangroves and seagrasses, respectively, could be achieved by 2050. Further, protection and restoration can be complementary, as protection prevents losses that would otherwise occur post-2050, highlighting the importance of implementing protection measures. Our findings provide the scientific evidence required for setting strategic and ambitious targets to inspire significant global investment and effort in mangrove and seagrass conservation.

An assessment of future tidal marsh resilience in the San Francisco Estuary through modeling and quantifiable metrics of sustainability - Morris, James T.; Drexler, Judith Z.; Vaughn, Lydia J.S.; Robinson, April H. (Frontiers in Environmental Science, 2022)
Quantitative, broadly applicable metrics of resilience are needed to effectively manage tidal marshes into the future. Here we quantified three metrics of temporal marsh resilience: time to marsh drowning, time to marsh tipping point, and the probability of a regime shift, defined as the conditional probability of a transition to an alternative super-optimal, suboptimal, or drowned state. We used organic matter content (loss on ignition, LOI) and peat age combined with the Coastal Wetland Equilibrium Model (CWEM) to track wetland development and resilience under different sea-level rise scenarios in the Sacramento-San Joaquin Delta (Delta) of California. A 100-year hindcast of the model showed excellent agreement (R2 = 0.96) between observed (2.86 mm/year) and predicted vertical accretion rates (2.98 mm/year) and correctly predicted a recovery in LOI (R2 = 0.76) after the California Gold Rush. Vertical accretion in the tidal freshwater marshes of the Delta is dominated by organic production. The large elevation range of the vegetation combined with high relative marsh elevation provides Delta marshes with resilience and elevation capital sufficiently great to tolerate centenary sea-level rise (CLSR) as high as 200 cm. The initial relative elevation of a marsh was a strong determinant of marsh survival time and tipping point. For a Delta marsh of average elevation, the tipping point at which vertical accretion no longer keeps up with the rate of sea-level rise is 50 years or more. Simulated, triennial additions of 6 mm of sediment via episodic atmospheric rivers increased the proportion of marshes surviving from 51% to 72% and decreased the proportion drowning from 49% to 28%. Our temporal metrics provide critical time frames for adaptively managing marshes, restoring marshes with the best chance of survival, and seizing opportunities for establishing migration corridors, which are all essential for safeguarding future habitats for sensitive species.

An Australian blue carbon method to estimate climate change mitigation benefits of coastal wetland restoration - Lovelock, Catherine E.; Adame, Maria F.; Bradley, Jennifer; Dittmann, Sabine; Hagger, Valerie; Hickey, Sharyn M.; Hutley, Lindsay B.; Jones, Alice; Kelleway, Jeffrey J.; Lavery, Paul S.; Macreadie, Peter I.; Maher, Damien T.; et al. (Restoration Ecology, 2022)
Restoration of coastal wetlands has the potential to deliver both climate change mitigation, called blue carbon, and adaptation benefits to coastal communities, as well as supporting biodiversity and providing additional ecosystem services. Valuing carbon sequestration may incentivize restoration projects; however, it requires development of rigorous methods for quantifying blue carbon sequestered during coastal wetland restoration. We describe the development of a blue carbon accounting model (BlueCAM) used within the Tidal Restoration of Blue Carbon Ecosystems Methodology Determination 2022 of the Emissions Reduction Fund (ERF), which is Australia's voluntary carbon market scheme. The new BlueCAM uses Australian data to estimate abatement from carbon and greenhouse gas sources and sinks arising from coastal wetland restoration (via tidal restoration) and aligns with the Intergovernmental Panel for Climate Change guidelines for national greenhouse gas inventories. BlueCAM includes carbon sequestered in soils and biomass and avoided emissions from alternative land uses. A conservative modeled approach was used to provide estimates of abatement (as opposed to on-ground measurements); and in doing so, this will reduce the costs associated with monitoring and verification for ERF projects and may increase participation in blue carbon projects by Australian landholders. BlueCAM encompasses multiple climate regions and plant communities and therefore may be useful to others outside Australia seeking to value blue carbon benefits from coastal wetland restoration.

Assessing the potential vulnerability of sedimentary carbon stores to bottom trawling disturbance within the UK EEZ - Black, Kirsty E.; Smeaton, Craig; Turrell, William R.; Austin, William E.N. (Frontiers in Marine Science, 2022)
It is estimated that within the UK exclusive economic zone (UK EEZ), 524 Mt of organic carbon (OC) is stored within seabed sediment. However, the stability and potential vulnerability of OC in these sediments under anthropogenic stressors, such as bottom trawling activity, remains poorly quantified. To improve our understanding of the areas where sedimentary OC is likely to be at greatest risk from trawling events, we have developed a carbon vulnerability ranking (CVR) to identify areas of the seabed where preventative protection may be most beneficial to help maintain current OC stocks while further research continues to shed light on the fate of OC after trawling (e.g., remineralization, transport, and consumption). Predictive maps of currently available fishing intensity, OC and sediment distribution, and sediment OC lability have been generated within ArcGIS using fuzzy set theory. Our results show that the west coast of Scotland represents one of the key areas where sedimentary OC is potentially at greatest risk from bottom trawling activity. This is due mainly to the high reactivity of these OC rich sediments combined with the pressures of repetitive trawling activity within inshore waters. Our research shows that these OC hotspots are potentially at risk of disturbance from bottom trawling activity and should be prioritized for the consideration of future safeguarding (management) measures to ensure emissions are minimized and to provide greater protection of this natural carbon capital resource.
Keywords: disturbance; fishing gear; mapping; organic carbon (OC); seabed; sediment

Assessment of Mangrove Colonization of Aquaculture Ponds Through Satellite Image Analysis: Implications for Mangrove Management - delos Santos, Kriselda Anna; Avtar, Ram; Salmo, Severino; Fujii, Masahiko (2022)
… Landsat 5 and 8 Surface Reflectance Tier-1 (SRT-1) images, available from the GEE platform, were acquired and composited for the decadal mangrove forest change detection (Table …

Belize Blue Carbon: Establishing a National Carbon Stock Estimate for Mangrove Ecosystems - Morrissette, Hannah; Baez, Stacy K.; Beers, Lisa; Bood, Nadia; Martinez, Ninon; Novelo, Kevin; Andrews, Gilbert; Balan, Luis; Beers, C. Scott; Betancourt, Sumeet A.; Blanco, Reynel; Bowden, Eeryn; et al. (SSRN Electronic Journal, 2022)

Biomass allocation of tidal freshwater marsh species in response to natural and manipulated hydroperiod in coastal deltaic floodplains - Rovai, Andre S.; Twilley, Robert R.; Christensen, Alexandra; McCall, Annabeth; Jensen, Daniel J.; Snedden, Gregg A.; Morris, James T.; Cavell, John A. (Estuarine, Coastal and Shelf Science, 2022)
Deltaic floodplains are highly vulnerable to relative sea level rise (RSLR) depending on the sediment supply from river channels that provides elevation capital as adaptation mechanism. In river channels where levees have restricted sediment supply to coastal deltaic floodplains, river sediment diversions have been proposed as a restoration strategy to increase elevation allowing for marshes to establish and cope with RSLR. The response of coastal wetlands to surface elevation has been well-defined for estuarine marshes, but models for coastal deltaic floodplain marshes have not been resolved. Here we coupled field observations from biomass plots and a mesocosm experiment (‘marsh organ’) with remote sensing techniques to assess biomass allocation of tidal freshwater marsh species in response to gradients in hydroperiod in Wax Lake Delta (WLD), coastal Louisiana, U.S.A. We found that, contrary to salt-tolerant species, Colocasia esculenta aboveground biomass (AGB) is strongly positively correlated with percent inundated time (R2 = 0.79, P < 0.001), increasing from (mean ± 1SE) 186 ± 69 g/m2 in the supratidal zone to 1422 ± 148 g/m2 beyond its natural occurrence range in the lower intertidal zone. Belowground biomass consistently exceeded AGB at 2363 ± 294 g/m2 on average across elevation treatments. We also found that C. esculenta expanded its surface coverage area by 31% in five years consistent with the growth and emergence of WLD's subaqueous platforms, reflecting this species ability to cope with higher inundation time. In contrast to earlier studies conducted in brackish and saline settings, where longer hydroperiods had negative effects on biomass accumulation, our data suggest that tidal freshwater marshes can cope with longer hydroperiods caused by river sediment diversions.

CADANGAN BLUE CARBON PADA EKOSISTEM LAMUN DI PULAU BINTAN PROPINSI KEPULAUAN RIAU - Maemunah, Lilis; Rachmad, Basuki; Zulkifli, Dadan; Dewi, Ita Junita Puspa; Mulyoto, Mulyoto; Rizki F, M. Nur; Rahman, Abdul (PROSIDING SEMINAR NASIONAL PERIKANAN INDONESIA, 2022)
Peningkatan CO₂ menjadi penyebab utama perubahan iklim dan pemanasan global. Karbon biru/blue carbon menjadi topik utama pada ekosistem di wilayah pesisir, karena ekosistem ini mampu mengurangi buangan gas CO₂ dengan menyerap dan menstabilkan karbon dalam wujud senyawa organik, salah satunya adalah lamun. Lamun di Pulau Bintan mencakup area yang cukup luas. Penelitian dimulai sejak Maret hingga Mei 2020 di Pulau Bintan, dengan 4 stasiun pengamatan (Pengudang, Tanjung Siambang, Busung dan Malang Rapat) dan bertujuan untuk mengetahui struktur komunitas dan cadangan blue carbon serta parameter kualitas air pada ekosistem lamun. Teridentifikasi beberapa spesies lamun adalah Thalassia hemprichii, Enhalus acroides, Cymodocea rotundata, Syringodium isoetifolium serta Halophila ovali. Perhitungan cadangan karbon lamun adalah dengan menghitung karbon cadangan yang ada pada sedimen dan habitatnya, Dari penelitian diperoleh besaran karbon yang terkandung dalam lamun terbesar di Pengudang 245.03 gC/m² atau 348.26 MgC/ha. Biomassa tertinggi pada Pengudang sebesar 1283.48 gDW/m², sehingga dapat disimpulkan bahwa lamun yang mempunyai peran dominan sebagai penyerap blue carbon di Pulau Bintan Provinsi Kepulauan Riau adalah di stasiun Pengudang.

Can Coastal Habitats Rise to the Challenge? Resilience of Estuarine Habitats, Carbon Accumulation, and Economic Value to Sea-Level Rise in a Puget Sound Estuary - Moritsch, Monica M.; Byrd, Kristin B.; Davis, Melanie; Good, Anthony; Drexler, Judith Z.; Morris, James T.; Woo, Isa; Windham-Myers, Lisamarie; Grossman, Eric; Nakai, Glynnis; Poppe, Katrina L.; Rybczyk, John M. (Estuaries and Coasts, 2022)
Sea-level rise (SLR) and obstructions to sediment delivery pose challenges to the persistence of estuarine habitats and the ecosystem services they provide. Restoration actions and sediment management strategies may help mitigate such challenges by encouraging the vertical accretion of sediment in and horizontal migration of tidal forests and marshes. We used a process-based soil accretion model (Coastal Wetland Equilibrium Model) combined with a habitat classification model (MOSAICS) to estimate the effects of SLR, suspended sediment, and inland habitat migration on estuarine habitats, soil carbon accumulation, and economic value of climate change mitigation of carbon accumulation (social cost of carbon dioxide) in a macrotidal estuary in the northwest USA over 100 years (2011 to 2110). Under present-day sediment levels, we projected that after 100 years, most high salt marsh would remain with < 100 cm SLR, but substantial area converted to transitional (low) salt marsh and mudflat with ≥ 100 cm SLR. Increasing sediment availability increased the projected resilience of transitional salt marsh to SLR but did not prevent declines in high marsh area. Projected total carbon accumulation plateaued or declined with ≥ 100 cm SLR, yet the economic value of carbon accumulation continued to rise over time, suggesting that the value of this ecosystem service was resilient to SLR. Doubling or tripling sediment availability increased projected carbon accumulation up to 7.69 and 14.2 kg m−2 and increased total economic value up to $373,000 and $710,000, respectively. Allowing marsh migration supported conversion of upland to freshwater marsh, with slight increases in carbon accumulation. These results inform climate adaptation planning for wetland managers seeking to understand the resilience of estuarine habitats and ecosystem services to SLR under multiple management strategies.

Capitalizing on the global financial interest in blue carbon - Friess, D A; Howard, J; Huxham, M; Macreadie, P I; Ross, F. (PLOS Climate, 2022)

Carbon sequestration is not inhibited by livestock grazing in Danish salt marshes - Graversen, Anna Elizabeth Løvgren; Banta, Gary T.; Masque, Pere; Krause-Jensen, Dorte (Limnology and Oceanography, 2022)
Climate change has created a need for solutions that can counteract greenhouse gas emissions. One is the expansion and maintenance of natural carbon (C)-sequestration habitats, such as forests and coastal and marine vegetated ecosystems, socalled “blue carbon ecosystems” including salt marshes, which represent large and long-term C-storage potential. While salt marsh blue carbon is gaining international attention, Baltic and Nordic salt marshes have been neglected in the blue carbon context. Here, we quantified C-stocks and C-sequestration rates in grazed and nongrazed sites of three Danish salt marshes, and evaluated whether grazing livestock, the standard management to increase biodiversity of the marshes, affect C-stocks and sequestration rates. The aboveground biomass and vegetation height in nongrazed salt marshes were significantly larger than for grazed salt marshes, but this did not lead to significantly enhanced overall sediment- or C-accumulation rates. Detailed model analyses of sediment profiles even indicated significantly higher C-densities in surface layers at grazed sites. Averaged C-densities, C-stocks (top 43 cm sediment) and sequestration rates estimated from 210Pb profiles ranged 0.011–0.022 g C cm−3, 4228–8178 g C m−2, and 17–45 g C m−2 yr−1, respectively, with the latter being low in the global context. While this pioneering study for the Baltic and Nordic regions showed a neutral to positive effect of grazing on C-sequestration, there is a need to explore the overall C-footprint of this practice, including effects on net greenhouse gas emissions and coastal defense capacity, and define blue carbon management strategies for salt marshes to maximize their climate change mitigation and adaptation capacity while supporting biodiversity.

Climate change mitigation and improvement of water quality from the restoration of a subtropical coastal wetland - Iram, Naima; Maher, Damien T.; Lovelock, Catherine E.; Baker, Tallis; Cadier, Charles; Adame, Maria F. (Ecological Applications, 2022)
Coastal wetland restoration is an important activity to achieve greenhouse gas (GHG) reduction targets, improve water quality, and reach the Sustainable Development Goals. However, many uncertainties remain in connection with achieving, measuring, and reporting success from coastal wetland restoration. We measured levels of carbon (C) abatement and nitrogen (N) removal potential of restored coastal wetlands in subtropical Queensland, Australia. The site was originally a supratidal forest composed of Melaleuca spp. that was cleared and drained in the 1990s for sugarcane production. In 2010, tidal inundation was reinstated, and a mosaic of coastal vegetation (saltmarshes, mangroves, and supratidal forests) emerged. We measured soil GHG fluxes (CH4, N2O, CO2) and sequestration of organic C in the trees and soil to estimate the net C abatement associated with the reference, converted, and restored sites. To assess the influence of restoration on water quality improvement, we measured denitrification and soil N accumulation. We calculated C abatement of 18.5 Mg CO2−eq ha−1 year−1 when sugarcane land transitioned to supratidal forests, 11.0 Mg CO2−eq ha−1 year−1 when the land transitioned to mangroves, and 6.2 Mg CO2−eq ha−1 year−1 when the land transitioned to saltmarshes. The C abatement was due to tree growth, soil accumulation, and reduced N2O emissions due to the cessation of fertilization. Carbon abatement was still positive, even accounting for CH4 emissions, which increased in the wetlands due to flooding and N2O production due to enhanced levels of denitrification. Coastal wetland restoration in this subtropical setting effectively reduces CO2 emissions while providing additional cobenefits, notably water quality improvement.

Constraints on the adjustment of tidal marshes to accelerating sea level rise - Saintilan, Neil; Kovalenko, Katya E.; Guntenspergen, Glenn; Rogers, Kerrylee; Lynch, James C.; Cahoon, Donald R.; Lovelock, Catherine E.; Friess, Daniel A.; Ashe, Erica; Krauss, Ken W.; Cormier, Nicole; Spencer, Tom; et al. (Science, 2022)
Much uncertainty exists about the vulnerability of valuable tidal marsh ecosystems to relative sea level rise. Previous assessments of resilience to sea level rise, to which marshes can adjust by sediment accretion and elevation gain, revealed contrasting results, depending on contemporary or Holocene geological data. By analyzing globally distributed contemporary data, we found that marsh sediment accretion increases in parity with sea level rise, seemingly confirming previously claimed marsh resilience. However, subsidence of the substrate shows a nonlinear increase with accretion. As a result, marsh elevation gain is constrained in relation to sea level rise, and deficits emerge that are consistent with Holocene observations of tidal marsh vulnerability.

Contrasting Effects of Local Environmental and Biogeographic Factors on the Composition and Structure of Bacterial Communities in Arid Monospecific Mangrove Soils - Thomson, T.; Fusi, M.; Bennett-Smith, M. F.; Prinz, N.; Aylagas, E.; Carvalho, S.; Lovelock, C. E.; Jones, B. H.; Ellis, J. I. (Microbiology Spectrum, 2022)
Mangrove ecosystems are increasingly being recognized for their potential to sequester atmospheric carbon, thereby mitigating the effects of anthropogenically driven greenhouse gas emissions. The bacterial community in the soils plays an important role in the breakdown and recycling of carbon and other nutrients. Mangrove forests are important biotic sinks of atmospheric CO 2 and play an integral role in nutrient-cycling and decontamination of coastal waters, thereby mitigating climatic and anthropogenic stressors. These services are primarily regulated by the activity of the soil microbiome. To understand how environmental changes may affect this vital part of the ecosystem, it is key to understand the patterns that drive microbial community assembly in mangrove forest soils. High-throughput amplicon sequencing (16S rRNA) was applied on samples from arid Avicennia marina forests across different spatial scales from local to regional. Alongside conventional analyses of community ecology, microbial co-occurrence networks were assessed to investigate differences in composition and structure of the bacterial community. The bacterial community composition varied more strongly along an intertidal gradient within each mangrove forest, than between forests in different geographic regions (Australia/Saudi Arabia). In contrast, co-occurrence networks differed primarily between geographic regions, illustrating that the structure of the bacterial community is not necessarily linked to its composition. The local diversity in mangrove forest soils may have important implications for the quantification of biogeochemical processes and is important to consider when planning restoration activities. IMPORTANCE Mangrove ecosystems are increasingly being recognized for their potential to sequester atmospheric carbon, thereby mitigating the effects of anthropogenically driven greenhouse gas emissions. The bacterial community in the soils plays an important role in the breakdown and recycling of carbon and other nutrients. To assess and predict changes in carbon storage, it is important to understand how the bacterial community is shaped by its environment. Here, we compared the bacterial communities of mangrove forests on different spatial scales, from local within-forest to biogeographic comparisons. The bacterial community composition differed more between distinct intertidal zones of the same forest than between forests in distant geographic regions. The calculated network structure of theoretically interacting bacteria, however, differed most between the geographic regions. Our findings highlight the importance of local environmental factors in shaping the microbial soil community in mangroves and highlight a disconnect between community composition and structure in microbial soil assemblages.

Cross-cutting research themes for future mangrove forest research - Dahdouh-Guebas, Farid; Friess, Daniel A.; Lovelock, Catherine E.; Connolly, Rod M.; Feller, Ilka C.; Rogers, Kerrylee; Cannicci, Stefano (Nature Plants, 2022)

Drivers of global mangrove loss and gain in social-ecological systems - Hagger, Valerie; Worthington, Thomas A.; Lovelock, Catherine E.; Adame, Maria Fernanda; Amano, Tatsuya; Brown, Benjamin M.; Friess, Daniel A.; Landis, Emily; Mumby, Peter J.; Morrison, Tiffany H.; O’Brien, Katherine R.; Wilson, Kerrie A.; et al. (Nature Communications, 2022)
Mangrove forests store high amounts of carbon, protect communities from storms, and support fisheries. Mangroves exist in complex social-ecological systems, hence identifying socioeconomic conditions associated with decreasing losses and increasing gains remains challenging albeit important. The impact of national governance and conservation policies on mangrove conservation at the landscape-scale has not been assessed to date, nor have the interactions with local economic pressures and biophysical drivers. Here, we assess the relationship between socioeconomic and biophysical variables and mangrove change across coastal geomorphic units worldwide from 1996 to 2016. Globally, we find that drivers of loss can also be drivers of gain, and that drivers have changed over 20 years. The association with economic growth appears to have reversed, shifting from negatively impacting mangroves in the first decade to enabling mangrove expansion in the second decade. Importantly, we find that community forestry is promoting mangrove expansion, whereas conversion to agriculture and aquaculture, often occurring in protected areas, results in high loss. Sustainable development, community forestry, and co-management of protected areas are promising strategies to reverse mangrove losses, increasing the capacity of mangroves to support human-livelihoods and combat climate change.

Ecogeomorphology of Salt Marshes - Fagherazzi, Sergio; FitzGerald, Duncan M.; Fulweiler, Robinson W.; Hughes, Zoe; Wiberg, Patricia L.; McGlathery, Karen J.; Morris, James T.; Tolhurst, Trevor J.; Deegan, Linda A.; Johnson, David S.; Lesser, Justin S.; Nelson, James A. (Treatise on Geomorphology, 2022)
The coupling of geomorphological and ecological processes is critical for the maintenance or disappearance of salt marshes. Emergent macrophytes dampen wave- and tide-generated shear stresses promoting sediment deposition and marsh formation. The complex interactions among marsh primary productivity, sea level, and sedimentation determine the equilibrium elevation of the marsh platform and its resilience against external drivers. The strength of the root system can affect the ability of marsh edge scarps to resist erosion. Some marshes are commonly inhabited by a number of species of crab, whose burrows have been implicated in marsh edge erosion, whereas mussels and other bivalves can be very important in stabilizing marsh sediment by both slowing wave and current velocities and binding sediment to the root mat. Nutrient enrichment has the potential to invoke negative feedbacks that will ultimately affect marsh geomorphic configuration and biogeochemical cycling, by altering plant production and community characteristics and increasing microbial decomposition of organic matter. In this chapter we present a broad overview of the feedbacks between biota and sedimentological processes in salt marshes, including recent numerical models that have been utilized to study the ecogeomorphic evolution of intertidal areas.

Ecological development of mangrove plantations in the Bangladesh Delta - Uddin, Mohammad Main; Hossain, Mohammad Mosharraf; Aziz, Ammar Abdul; Lovelock, Catherine E. (Forest Ecology and Management, 2022)
Afforestation is a process used in recovering the global mangrove cover. Succession or development in mangrove communities during mangrove afforestation has rarely been described yet is important for understanding the potential of afforestation in creating diverse and functional mangroves. Since 1966, the Government of Bangladesh has created nearly 280 km2 of plantation mangroves (7.5% of the extent of the Sundarbans mangrove forest and 0.21% of the global mangroves extent) on the Delta of the Ganges, Brahmaputra and Meghna Rivers, located east of the Sundarbans mangroves. Here, we investigated the development of these plantation mangroves, assessing their community structure and species richness over a 40-year chronosequence in comparison to natural mangroves in the same region. Tree communities in the plantations reached a maximum mean aboveground biomass (AGB) of ∼157 ± 13 Mg dry weight ha−1, achieving equivalence in tree aboveground biomass and tree density (255 ± 2 individuals ha−1) to natural mangroves by 20 and 39 years respectively. Our dataset from plantations aged between 10 and 42 years indicated that structural complexity (Ic) was higher in older plantations than in younger plantations. We found that the tree community structure of older mangrove plantations was more diverse in the eastern region of the delta compared to the central and western regions, and the landward plantations were more diverse than the plantations fringing the oceans. One of the originally planted mangrove species, Sonneratia apetala, was dominant in these plantations. However, we recorded 8 mangrove tree species from 5 genera in the plantations, despite only two species (S. apetala and Avicennia officinalis) being planted. Our data indicated that while the tree structure of the established mangrove plantations was similar to natural mangroves within 42 years, equivalent species richness may not be reached for more than 40 years. Therefore, adoption of management to enhance natural successional or development processes in afforestation programs, for example by planting a diverse mix of species, could improve the effectiveness of afforestation in conserving biodiversity.

Editorial: Drivers of mangrove forest change and its effects on biodiversity and ecosystem services - Howard, Jennifer; Andradi-Brown, Dominic A.; Hagger, Valerie; Sasmito, Sigit D.; Bosire, Jared (Frontiers in Forests and Global Change, 2022)

eDNA envisaged conservation of IUCN threatened taxa of the tropical mangrove ecosystems - Kannan, S.; Balamurugan, S.; Ragavan, P.; Deivasigamani, B.; Wee, A. K.S.; Salmo, S. G.; Basyuni, M.; Kajita, T. (IOP Conference Series: Earth and Environmental Science, 2022)
eDNA sampling is a more affordable, quick, and consistent method to understand the aquatic ecosystem, especially the ocean, with freely associated DNA in water suitable for estimating diversity, composition, and behaviour. Furthermore, it helps to propose management plans to use sustainable ocean resources. The world's mangroves are currently under threat, and they also provide habitat for International Union Conservation of Nature (IUCN)-listed threatened species (e.g., Dugong, Bengal Tiger, etc.). These species are inextricably linked to the mangrove ecosystem, forming a sustenance chain that can be disrupted if lost. On the other hand, the more reliable methods to monitor threatened species are not clearly established and mostly depend on the non-standardized method, which requires practical and taxonomic expertise and limits the data-driven conservation acts. The implementation of eDNA in ocean data collection and monitoring of endangered species is still in a progressive stage and the studies on the eDNA of threatened species from mangrove ecosystems are few. Environmental DNA surveys have also mapped the distribution of endangered European eel (Anguilla anguilla) during spring and documented threatened sharks and rays across eastern Indonesia. As a hallmark, UNESCO recently launched a project to understand the richness of biodiversity. The main objective is to monitor fishes, including the IUCN red-listed species, through eDNA collected across the selected marine World Heritage sites. The recent observations ensure that eDNA might be used to monitor the IUCN-designated threatened taxa found in the tropical mangrove ecosystem. The outcomes of this eDNA technique are crucial for providing information regarding conservation priorities.

Fingerprinting Arctic and North Atlantic Macroalgae with eDNA – Application and perspectives - Ørberg, Sarah B.; Krause-Jensen, Dorte; Geraldi, Nathan R.; Ortega, Alejandra; Díaz-Rúa, Rubén; Duarte, Carlos M. (Environmental DNA, 2022)
Macroalgae are key primary producers in North Atlantic and Arctic coastal ecosystems, and tracing their fate and distribution is vital to improve our understanding of their ecological role and provision of ecosystem services. Recent advances from environmental DNA (eDNA) have added a new capacity to fingerprint and trace macroalgae. However, further development of resources for amplifying and identifying macroalgal eDNA are much needed. Here, we examined the performance in terms of resolution and specificity of two 18S primers (18S-V7 and 18S-V9) recently applied in identifying macroalgae from eDNA. We also built a local barcode database for primer 18S-V7 with 31 widespread Arctic and North Atlantic macroalgal species to complement the existing DNA databases. Furthermore, we applied metabarcoding of eDNA to identify macroalgae in Arctic marine sediments (Disko Bay, W. Greenland) and evaluated the contributions from our local barcode database. We identified macroalgal DNA from 19 families across 11 orders in surface (0–1 cm, with both primers) and sub-surface (5–10 cm, with 18S-V7 primer) sediments. The barcode database developed here with the 18S-V7 primer improved the identification of unique families, from 16 to 19 families, thereby strengthening the taxonomic assignment possible relative to pre-existing barcode reference sequences. Overall, this study demonstrates the feasibility of eDNA to resolve contributions of macroalgae in Arctic marine sediments, and enhances the fingerprinting resolution. We thereby document a novel pathway to answer key questions on the ecological role and fate of macroalgae in the Arctic.

Future Mangrove Carbon Storage Under Climate Change and Deforestation - Chatting, Mark; Al-Maslamani, Ibrahim; Walton, Mark; Skov, Martin W.; Kennedy, Hilary; Husrevoglu, Y. Sinan; Le Vay, Lewis (Frontiers in Marine Science, 2022)
Mangroves are important sinks of organic carbon (C) and there is significant interest in their use for greenhouse gas emissions mitigation. Adverse impacts on organic carbon storage potential from future climate change and deforestation would devalue such ambitions, thus global projections of future change remains a priority research area. We modeled the effects of climate change on future C stocks and soil sequestration rates (CSR) under two climate scenarios (“business as usual”: SSP245 and high-emissions: SSP585). Model results were contrasted with CO2 equivalents (CO2e) emissions from past, present and future rates of deforestation on a country specific scale. For C stocks, we found climate change will increase global stocks by ∼7% under both climate scenarios and that this gain will exceed losses from deforestation by the end of the twenty-first century, largely due to shifts in rainfall. Major mangrove-holding countries Indonesia, Malaysia, Cuba, and Nigeria will increase national C stocks by > 10%. Under the high-end scenario, while a net global increase is still expected, elevated temperatures and wider temperature ranges are likely increase the risk of countries’ C stocks diminishing. For CSR, there will likely be a global reduction under both climate change scenarios: 12 of the top 20 mangrove-rich countries will see a drop in CSR. Modeling of published country level mangrove deforestation rates showed emissions have decreased from 141.4 to 6.4% of annual CSR since the 1980’s. Projecting current mangrove deforestation rates into the future resulted in a total of 678.50 ± 151.32 Tg CO2e emitted from 2012 to 2095. Reducing mangrove deforestation rates further would elevate the carbon benefit from climate change by 55–61%, to make the proposition of offsetting emissions through mangrove protection and restoration more attractive. These results demonstrate the positive benefits of mangrove conservation on national carbon budgets, and we identify the nations where incorporating mangrove conservation into their Nationally Defined Contributions offers a particularly rewarding route toward meeting their Glasgow Agreement commitments.

Geomorphic and Climatic Drivers Are Key Determinants of Structural Variability of Mangrove Forests along the Kenyan Coast - Njiru, Derrick Muthomi; Githaiga, Michael Njoroge; Nyaga, Justine Muhoro; Lang’at, Kipkorir Sigi; Kairo, James Gitundu (Forests, 2022)
Mangrove forests occur across a diversity of coastal landforms that influence their structural development and productivity. Preliminary studies in Kenya indicate that mangroves growing in the region north and south of Tana River delta have different structural attributes. We hypothesise a close relationship between mangrove distribution, climate and landform types. Floristic composition of mangroves along the coast of Kenya was characterised and differences illustrated using non-metric multidimensional scaling (nMDS). Other structural properties of mangroves such as tree height, basal area, stand density and standing biomass were also assessed and their differences tested using analysis of variance (ANOVA). A hierarchical cluster analysis was used to compare mangrove species based on structural properties. Additionally, a regression fit model was used to investigate the relationship between mangrove standing biomass and possible drivers of variability. The study revealed significant differences in mangrove tree diameter, tree height, basal area, stand density and standing biomass across the sampled sites. High values of structural complexity were observed in estuarine and deltaic settings with high influence of freshwater input whereas low levels of structural complexity were observed for peri-urban with direct human influence. Our findings suggest that structural variability of mangroves in Kenya is highly influenced by geomorphological and climatic variability along the coast as well as the past and present management regimes of the forest.

Global biodiversity patterns of marine forests of brown macroalgae - Fragkopoulou, Eliza; Serrão, Ester A.; De Clerck, Olivier; Costello, Mark J.; Araújo, Miguel B.; Duarte, Carlos M.; Krause-Jensen, Dorte; Assis, Jorge (Global Ecology and Biogeography, 2022)
Aim: Marine forests of brown macroalgae create essential habitats for coastal species and support invaluable ecological services. Here, we provide the first global analysis of species richness and endemicity of both the kelp and fucoid biomes. Location: Global. Time period: Contemporary. Major taxa studied: Marine forests of brown macroalgae, formed by kelp (here defined as orders Laminariales, Tilopteridales and Desmarestiales) and fucoid (order Fucales), inhabiting subtidal and intertidal environments. Methods: We coupled a large dataset of macroalgal observations (420 species, 1.01 million records) with a high-resolution dataset of relevant environmental predictors (i.e., light, temperature, salinity, nitrate, wave energy and ice coverage) to develop stacked species distribution models (stacked SDMs) and yield estimates of global species richness and endemicity. Results: Temperature and light were the main predictors shaping the distribution of subtidal species, whereas wave energy, temperature and salinity were the main predictors of intertidal species. The highest regional species richness for kelp was found in the north-east Pacific (maximum 32 species) and for fucoids in south-east Australia (maximum 53 species), supporting the hypothesis that these regions were the evolutionary sources of global colonization by brown macroalgae. Locations with low species richness coincided between kelp and fucoid, occurring mainly at higher latitudes (e.g., Siberia) and the Baltic Sea, where extensive ice coverage and low-salinity regimes prevail. Regions of high endemism for both groups were identified in the Galapagos Islands, Antarctica, South Africa and East Russia. Main conclusions: We estimated the main environmental drivers and limits shaping the distribution of marine forests of brown macroalgae and mapped biogeographical centres of species richness and endemicity, which largely coincided with the expectation from previous evolutionary hypotheses. The mapped biodiversity patterns can serve as new baselines for planning and prioritizing locations for conservation, management and climate change mitigation strategies, flagging threatened marine forest regions under different climate change scenarios.

Global patterns and drivers of tidal marsh response to accelerating sea-level rise - Saintilan, Neil; Kovalenko, Katya; Guntenspergen, Glenn; Rogers, Kerrylee; Lynch, James; Cahoon, Donald; Lovelock, Catherine; Friess, Daniel; Ashe, Erica; Krauss, Ken; Cormier, Nicole; Spencer, Tom; et al. (Reseach Square, 2022)
The vulnerability of the world’s tidal marshes to sea-level rise threatens their substantial contribution to fisheries, coastal protection, biodiversity conservation and carbon sequestration. Feedbacks between relative sea-level rise (RSLR) and the rate of mineral and organic sediment accumulation in tidal wetlands, and hence elevation gain, have been proposed to ameliorate this risk. Here we report on changes in tidal marsh elevation and shoreline position in relation to our network of 387 fixed benchmarks in tidal marshes on four continents measured for an average of 10 years. During this period RSLR at these marshes reached on average 6.6 mm yr-1, compared to 0.34 mm yr-1 over the past millenia. While the rate of sediment accretion corresponded to RSLR, the loss of elevation to shallow subsidence increased in proportion to the accretion rate. This caused a deficit between elevation gain and RSLR which increased consistently with the rate of RSLR regardless of position within the tidal frame, suggesting that long-term in situ tidal marsh survival is unlikely. While higher tidal range (>3m) conferred a greater stability in measures of shoreline change and vegetation cover, other regions showed a tendency towards instability and retreat.

High Biomass of Floating Macroalgae Supports Carbon Sequestration Potential within and Beyond a Greenland Fjord - Ager, Thomas Gjerluff; Krause-Jensen, Dorte; Sejr, Mikael; Olesen, Birgit; Carlson, Daniel F.; Winding, Mie Hylstofte Sichlau (SSRN Electronic Journal, 2022)
Despite growing attention to the potential contribution of macroalgae to Blue Carbon, there is a gaping lack of evidence of their export to carbon sinks in the deep ocean and marine sediments. In this study, we quantified the annual carbon export of floating macroalgae in a large sub-arctic fjord system, Nuup Kangerlua, Greenland, from April to August 2021 and trajectories of exported biomass within and beyond the fjord. We identified extensive macroalgae communities within the fjord system, which sustained 55.44 kg wet weight km-2 of floating macroalgal biomass on average in the fjord system. Using GPS drifters we identified transport pathways and the likelihood of macroalgal export out of the fjord to sinks in the deep ocean. The annual export of floating macroalgae beyond the fjord amounted to 445.73 t C yr-1. Our observation suggests that most of the floating biomass is retained in the fjord where its fate in relation to long-term sequestration is unknown. The floating macroalgal biomass was composed of intertidal macroalgae species (58%) (Fucus vesiculosus, Fucus distichus, and Ascophyllum nodosum), and kelps (42%) (Alaria esculenta, Saccharina latissima & Saccharina longicruris). Macroalgae densities and species composition varied seasonally with the highest levels after storms. Dominance of intertidal species in the spring suggests that ice scouring related to ice melt is an important driver of export. Sea urchin barrens occupied 15% of the potential macroalgae habitats of the fjord and, hence, limited standing biomass and associated blue carbon potential. Highlights  Sub-Arctic Greenland fjords sustain high amount of floating macroalgae  Significant macroalgae export out of the fjord could potentially reach deep ocean carbon sinks  Potential for in-fjord carbon sequestration by retained macroalgae  Large temporal variation in floating macroalgae density

How Sustainable is Mangrove Harvesting in Lamu? An Analysis of Forest Structure - Mbatha, Anthony; Githaiga, Michael N.; Kiplagat, Kotut; Kairo, James; Mungai, Fredrick (Journal of Sustainable Forestry, 2022)
Sustainable management of mangrove resources requires monitoring of status and conditions of the forest over time. This study assessed structure and regeneration of mangroves across five mangrove management blocks in Lamu, Kenya. Using stratified random sampling strategy, mangroves were sampled in 152 square plots of 400 m2 along belt transects established perpendicular to the shoreline. Linear regeneration sampling (LRS) was employed to assess composition and patterns of natural regeneration. Six mangrove species were encountered during this study. Based on importance value index, the dominant mangrove species in Lamu are Rhizophora mucronata and Ceriops tagal. At least 42% of the forest is stocked with low-quality poles, an indicator of prolonged human pressure. However, natural regeneration rate of 7,342 ± 450 juveniles ha−1 observed in the forest is considered adequate to support forest recovery after disturbance. The findings of the study have direct applications in the development of harvest plans for mangroves in Lamu.

Hurricane Damages to Mangrove Forests and Post-Storm Restoration Techniques and Costs. - Herrera Silveira, Jorge A.; Teutli Hernandez, Claudia; Secaira Fajardo, Fernando; Braun, Rod; Bowman, Janet; Geselbracht, Laura; Musgrove, Marcia; Rogers, Martha; Schmidt, Joseph; Robles Toral, Pedro Javier; Canul Cabrera, Jesús Andrés; Guerra Cano, Lucia (The Nature Conservancy, 2022)
the efforts of our market analysis in Mexico, Florida and The Bahamas and identify specific locations where a mangrove insurance product could be piloted. As described in this report, tropical storms and hurricanes can cause significant damages to mangroves and restoration costs can be high. Financing these restoration activities, through innovative solutions like an insur- ance product, will be critical to ensuring that the protective benefits of mangroves are sustained in the future.

Integrated Modeling of Dynamic Marsh Feedbacks and Evolution Under Sea-Level Rise in a Mesotidal Estuary (Plum Island, MA, USA) - Alizad, Karim; Morris, James T.; Bilskie, Matthew V.; Passeri, Davina L.; Hagen, Scott C. (Water Resources Research, 2022)
Around the world, wetland vulnerability to sea-level rise (SLR) depends on different factors including tidal regimes, topography, creeks and estuary geometry, sediment availability, vegetation type, etc. The Plum Island estuary (PIE) is a mesotidal wetland system on the east coast of the United States. This research applied a newly updated Hydro-MEM (integrated hydrodynamic-marsh) model to assess the impacts of intermediate-low (50 cm), intermediate (1 m), and intermediate-high (1.5 m) SLR on marsh evolution by the year 2100. Model advancements include capturing vegetation change, inorganic and below and aboveground organic matter portion of marsh platform accretion, and mudflat creation. Although the results indicate a low vulnerability marsh at the PIE, the vegetation changes from high to low marsh under all SLR scenarios (2%–22%), with the higher bounds belonging to higher rise scenarios. Lower SLR produces more productive marsh (13% gain in high productivity regions), whereas the highest SLR scenario causes increased tidal inundation, which leads to loss in productivity (12% change from high to low productivity regions), generation of mudflats (17% of the domain land), and marsh migration to higher lands. Sensitive nonlinear tidal flow changes, which may be increased or decreased with SLR as a result of mudflat creation, marsh migration, and bottom friction change, emphasize the importance of integrated modeling approaches that include dynamic marsh feedbacks in hydrodynamic modeling and varying hydrodynamic effects on the marsh system.

Interspecific Competition is Prevalent and Stabilizes Plant Production in a Brackish Marsh Facing Sea Level Rise - Gabriel, Jared R.; Reid, Jessica; Wang, Le; Mozdzer, Thomas J.; Whigham, Dennis F.; Megonigal, J. Patrick; Langley, J. Adam (Estuaries and Coasts, 2022)
Tidal marsh plant species commonly zonate along environmental gradients such as elevation, but it is not always clear to what extent plant distribution is driven by abiotic factors vs. biotic interactions. Yet, the distinction has importance for how plant communities will respond to future change such as higher sea level, particularly given the distinct flooding tolerances and contributions to elevation gain of different species. We used observations from a 33-year experiment to determine co-occurrence patterns for the sedge, Schoenoplectus americanus, and two C4 grasses, Spartina patens and Distichlis spicata, to infer functional group interactions. Then, we conducted a functional group removal experiment to directly assess the interaction between sedge and grasses throughout the range in which they cooccur. The observational record suggested negative interactions between sedge and grasses across sedge- and grass-dominated plots, though the relationship weakened in years with greater flooding stress. The removal experiment revealed mutual release effects, indicating competition was the predominant interaction, and here, too, competition tended to weaken, though nonsignificantly, in more flooded, lower elevation zones. Whereas zonation patterns in undisturbed portions of marsh suggest that the sedge will dominate this marsh as flooding stress increases with sea level rise, we propose that grasses may exhibit a competition release effect and contribute to biomass and elevation gain even in sedge-dominated communities as sea level continues to rise. Even as abiotic stresses drive changes in the relative contributions of sedges and grasses, competition among them moderates fluctuations in total plant biomass production through time.

Mangrove forests under climate change in a 2°C world - Friess, Daniel A.; Adame, Maria Fernanda; Adams, Janine B.; Lovelock, Catherine E. (Wiley Interdisciplinary Reviews: Climate Change, 2022)
The world's nations are committed to keeping global temperature rises to less than 2°C to avoid the worst impacts of climate change. Such a target is crucial for mangrove forests, because they are located primarily in tropical and subtropical regions that are expected to see large changes in climatic conditions; their intertidal location and sensitivity to changes in environmental conditions means that mangroves are expected to be on the front line of climate change impacts. We conceptualize what a 2°C world might look like for mangroves, and in particular the potential negative and positive responses of the mangrove ecosystem to anticipated changes in future atmospheric CO2 concentrations, temperature, sea level, cyclone activity, storminess and changes in the frequency, and magnitude of climatic oscillations. We also assess the spatial distribution of such stressors, their relative contributions to mangrove ecosystem dynamics, and discuss the challenges in attributing mangrove ecosystem dynamics to climate change versus other global change stressors. Such knowledge can help future-proof conservation and restoration activities, improve the Intergovernmental Panel on Climate Change's confidence level ascribed to climate change impacts on mangrove forests, and highlight the key temperature thresholds beyond which the future of the world's mangroves is less certain. This article is categorized under: Climate, Ecology, and Conservation > Modeling Species and Community Interactions Climate, Ecology, and Conservation > Observed Ecological Changes.

Mangroves Cover Change Trajectories 1984-2020: The Gradual Decrease of Mangroves in Colombia - Murillo-Sandoval, Paulo J.; Fatoyinbo, Lola; Simard, Marc (Frontiers in Marine Science, 2022)
Awareness of the significant benefits of mangroves to human lives and their role in regulating environmental processes has increased during the recent decades. Yet there remains significant uncertainty about the mangrove change trajectories and the drivers of change at national scales. In Colombia, the absence of historical satellite imagery and persistent cloud cover have impeded the accurate mapping of mangrove extent and change over time. We create a temporally consistent Landsat-derived dataset using the LandTrendr algorithm to track the historical land cover and mangrove conversion from 1984-2020 across Colombia. Over this period, mangrove extent decreased by ~48.000ha (14% of total mangrove area). We find a gradual reduction of mangrove extent along the Pacific coast since 2004, whereas, in the Caribbean, mangrove cover declined around during 1984-1988 and also after 2012. Our time-series analysis matches with drivers of mangrove change at three local sites. For instance, hydroclimatic events, dredging activities, and high sediment loads transported by the rivers have collectively improved mangrove recovery in some sites. In contrast, human activities pressure linked to agricultural expansion and road construction have degraded mangroves. The transition from dense mangrove to other vegetation types is the most significant conversion affecting mangrove cover in Colombia, impacting an area of 38,469 ± 2,829 ha. We anticipate increased mangrove loss, especially along the Pacific coast, resulting from intensified human activity. Prioritization of conservation areas is needed to support local institutions, maintain currently protected areas, and develop strategies (e.g. payment for ecosystem services) to preserve one of the most pristine mangrove regions in the Western Hemisphere.

Mangroves provide blue carbon ecological value at a low freshwater cost - Krauss, Ken W.; Lovelock, Catherine E.; Chen, Luzhen; Berger, Uta; Ball, Marilyn C.; Reef, Ruth; Peters, Ronny; Bowen, Hannah; Vovides, Alejandra G.; Ward, Eric J.; Wimmler, Marie Christin; Carr, Joel; et al. (Scientific Reports, 2022)
“Blue carbon” wetland vegetation has a limited freshwater requirement. One type, mangroves, utilizes less freshwater during transpiration than adjacent terrestrial ecoregions, equating to only 43% (average) to 57% (potential) of evapotranspiration (ET). Here, we demonstrate that comparative consumptive water use by mangrove vegetation is as much as 2905 kL H2O ha−1 year−1 less than adjacent ecoregions with Ec-to-ET ratios of 47–70%. Lower porewater salinity would, however, increase mangrove Ec-to-ET ratios by affecting leaf-, tree-, and stand-level eco-physiological controls on transpiration. Restricted water use is also additive to other ecosystem services provided by mangroves, such as high carbon sequestration, coastal protection and support of biodiversity within estuarine and marine environments. Low freshwater demand enables mangroves to sustain ecological values of connected estuarine ecosystems with future reductions in freshwater while not competing with the freshwater needs of humans. Conservative water use may also be a characteristic of other emergent blue carbon wetlands.

Maximising resilience to sea-level rise in urban coastal ecosystems through systematic conservation planning - Nguyen, Nhung T.H.; Friess, Daniel A.; Todd, Peter A.; Mazor, Tessa; Lovelock, Catherine E.; Lowe, Ryan; Gilmour, James; Ming Chou, Loke; Bhatia, Natasha; Jaafar, Zeehan; Tun, Karenne; Yaakub, Siti Maryam; et al. (Landscape and Urban Planning, 2022)
Coastal cities and their natural environments are vulnerable to the impacts of climate change, especially sea-level rise (SLR). Hard coastal defences play a key role in protecting at-risk urban coastal populations from flooding and erosion, but coastal ecosystems also play important roles in the overall sustainability and resilience of cities and urban centres by contributing to coastal protection. Conserving coastal ecosystems and maximising their resilience will ensure that urban coastal communities can continue to benefit from ecosystem services and improve their adaptive capacity to cope with adverse impacts in the future. Using the hyper-urbanised coast of Singapore as a case study, we modelled the resilience of coastal wetlands to SLR and integrated resilience in conservation planning. We found that the responses of coastal habitats to rising sea level vary across the modelling periods. While there is a slight net gain in the extent of mangrove forests and tidal flats by the end of the century due to potential habitat conversion, the existing habitats will experience a loss in coverage. Highly modified coastlines associated with urbanisation impede the ability of existing wetlands to migrate landward, which is a key mechanism for coastal habitats to cope with rising sea levels. Systematic conservation planning can identify sites that are potentially resilient to SLR and incorporate factors that influence an ecosystem's capability to respond to change. Crucially, the relatively slow rates of SLR and persistence of coastal wetlands during the earlier half of this century present an opportunity to introduce management interventions aimed at enhancing ecosystem resilience.

Megabenthic communities distributed in the outer margins of the Yucatan shelf and their relationship to environmental variables - Rubio-Polania, J.; Torruco-Gómez, D.; González-Solís, A.; Rodríguez-Canul, R.; Améndola-Pimenta, M.; Mariño-Tapia, I.; Herrera-Silveira, J.; Árcega-Cabrera, F.; Ceja-Moreno, V.; Romo-Alvarado, J.; Lizarraga-Castro, I.; Gutiérrez-Solís, C. (Marine Biology Research, 2022)
Megabenthic communities on continental margins benefit from structural complexity of the seafloor and sedimentary dynamics. These communities were tested in the outer margins of the Yucatan continental shelf (YCS) during August 2016 to evaluate the relationships between community attributes with environmental variables. The total capture was 1,366 103 ind km−2 and 2,078 kg ash free dry weight (AFDW) km−2, distributed among 319 species. Crustaceans and molluscs were co-dominant in abundance (576,629 ind km−2 ∼42.2% and 481,372 ind km−2 ∼35.2%), while crustaceans and sponges were the greatest contributors to community biomass (699.84 kg AFDW km−2 ∼33.6% and 47.8 kg AFDW km−2 ∼23.0%). Local diversity was higher than reported for other areas of the GoM, showing a pseudo-latitudinal gradient of richness related to the karstic bottom and autogenic species. Beta diversity showed no species loss in these communities. The BIOENV test pointed to longitude, temperature, sorting, vanadium, 2.6-dimethyl naphthalene, latitude, chlorophyll, average grain size, n-C16 and n-C23 as the most important variables. Hydrocarbons were recorded at lower concentrations than the threshold effects level (TEL) reference values; however, the significant correlation between richness and dibenzothiophene must be evaluated. Beta diversity exhibited a high turnover and functional diversity showed an absence of regional distribution. Differences in benthic megafauna among sites were because of gradients in latitude and concentrations of aliphatic compounds which can be attributed to the distance from the stations to the coastline or groundwater flow. Environmental monitoring programmes are recommended because of petrogenic compounds that influence the community structure.

Microbial mediation of salinity stress response varies by plant genotype and provenance over time - Lumibao, Candice Y.; Torres Martínez, Lorena; Megonigal, J. Patrick; Van Bael, Sunshine A.; Blum, Michael J. (Molecular Ecology, 2022)
Although it is becoming widely appreciated that microbes can enhance plant tolerance to environmental stress, the nature of microbial mediation of exposure responses is not well understood. We addressed this deficit by examining whether microbial mediation of plant responses to elevated salinity is contingent on the environment and factors intrinsic to the host. We evaluated the influence of contrasting environmental conditions relative to host genotype, provenance and evolution by conducting a common-garden experiment utilizing ancestral and descendant cohorts of Schoenoplectus americanus genotypes recovered from two 100+ year coastal marsh seed banks. We compared S. americanus productivity and trait variation as well as associated endophytic microbial communities according to plant genotype, provenance, and age cohort under high and low salinity stress with and without native soil inoculation. The magnitude and direction of microbial mediation of S. americanus responses to elevated salinity varied according to individual genotype, provenance, as well as temporal shifts in genotypic variation and G × E (gene by environment) interactions. Relationships differed between plant traits and the structure of endosphere communities. Our findings indicate that plant-microbe associations and microbial mediation of plant stress are not only context-dependent but also dynamic. Our results additionally suggest that evolution can shape the fate of marsh ecosystems by altering how microbes confer plant tolerance to pressures linked to global change.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Lovelock, Catherine E.; Adame, M. Fernanda; Butler, Don W.; Kelleway, Jeffrey J.; Dittmann, Sabine; Fest, Benedikt; King, Karen J.; Macreadie, Peter I.; Mitchell, Katherine; Newnham, Mark; Ola, Anne; Owers, Christopher J.; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site-based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

Modelling blue carbon farming opportunities at different spatial scales - Duarte de Paula Costa, Micheli; Lovelock, Catherine E.; Waltham, Nathan J.; Moritsch, Monica M.; Butler, Don; Power, Trent; Thomas, Evan; Macreadie, Peter I. (Journal of Environmental Management, 2022)
There is a growing interest in including blue carbon ecosystems (i.e., mangroves, tidal marshes and seagrasses) in climate mitigation programs in national and sub-national policies, with restoration and conservation of these ecosystems identified as potential activities to increase carbon accumulation through time. However, there is still a gap on the spatial scales needed to produce carbon offsets comparable with terrestrial or agricultural ecosystems. Here, we used the Coastal Blue Carbon InVEST 3.7.0 model to estimate future net carbon sequestration in blue carbon ecosystems along Australia's Great Barrier Reef (hereafter GBR) catchments, considering different management scenarios (i.e., reintroduction of tidal exchange through the removal of barriers, sea level rise, restoring low lying land) at three different spatial scales: whole GBR coastline, regional (14,000–16,300 ha), and local (335–370 ha) scales. The focus of the restoration (i.e., tidal marshes and/or mangroves) was dependent on data availability for each scenario. Furthermore, we also estimated the monetary value of carbon sequestration under each management scenario and spatial scale assessed in the study. We found that large scale restoration of tidal marshes could potentially sequester an additional ∼800,000 tonnes of CO2e by 2045 (potentially generating AU$12 million based on the average Australia carbon price), with greater opportunities when sea level rise is accounted for in the modelling. Also, we found that regional and local projects would generate up to 23 tonnes CO2e ha−1 by the end of the crediting period. Our results can guide future decisions in the blue carbon market and financing schemes, however, the return on investment is dependent on the carbon price and funding scheme available for project implementation.

Nitrogen Addition Increases Freeze Resistance in Black Mangrove (Avicennia germinans) Shrubs in a Temperate-Tropical Ecotone - Feller, Ilka C.; Berger, Uta; Chapman, Samantha K.; Dangremond, Emily M.; Dix, Nicole G.; Langley, J. Adam; Lovelock, Catherine E.; Osborne, Todd Z.; Shor, Audrey C.; Simpson, Loraé T. (Ecosystems, 2022)
Low temperature stress is the primary factor determining the latitudinal limits of tropical plants. As the climate warms, tropical species are migrating poleward, displacing native species and modifying ecosystem structure and function. Changes are particularly evident along latitudinal gradients with the highest velocity of change occurring in wetlands. In coastal wetlands, saltmarshes dominate at latitudes above 30°, whereas mangroves occur mostly in the tropics because most species are intolerant of freezing temperatures, but others, like Avicennia germinans (black mangrove), do tolerate freezing temperatures. In response to a warmer climate and fewer killing freezes, mangroves are currently expanding into saltmarshes. However, the speed of the transition from saltmarsh to mangrove can also be modified by extreme events and nutrient subsidies. In a fertilization experiment along the Atlantic coast of North America, we found that nitrogen addition altered plant traits in Avicennia, which increased their resistance to freezing temperatures. This trait shift resulted in negligible freeze effects during a January 2018 extreme freeze event compared to unfertilized plants, which lost more than 80% of the leaves and more than 40% of the wood in their canopies. The freeze-killed litter from unfertilized plants provided a nutrient pulse that influenced recovery, growth and mangrove cover for three years following the freeze. Nutrient enrichment and recovery from the freeze effects led to increased growth and structural complexity of the mangrove canopy, which further enhanced freeze tolerance, shrub growth form and the ability of Avicennia to displace the saltmarsh in the temperate–tropical ecotone.

Nordic Blue Carbon Ecosystems : Status and Outlook - Krause-jensen, Dorte; Gundersen, Hege; Björk, Mats; Gullström, Martin; Dahl, Martin; Asplund, Maria E; Boström, Christoffer; Holmer, Marianne; Banta, Gary T; Elizabeth, Anna; Graversen, Løvgren; Pedersen, Morten Foldager; et al. (2022)

Operationalizing marketable blue carbon - Macreadie, Peter I; Robertson, Alistar I; Spinks, Bernadette; Adams, Matthew P; Atchison, Jennifer M; Bell-james, Justine; Bryan, Brett A; Chu, Long; Filbee-dexter, Karen; Drake, Lauren; Duarte, Carlos M; Friess, Daniel A; et al. (One Earth, 2022)

Opportunities for coastal wetland restoration for blue carbon with co-benefits for biodiversity, coastal fisheries, and water quality - Hagger, Valerie; Waltham, Nathan J.; Lovelock, Catherine E. (Ecosystem Services, 2022)
Coastal wetlands are known to sequester significant amounts of carbon dioxide, while also providing valuable ecosystem services. We assessed the economic feasibility of restoring coastal wetlands for climate change mitigation by reinstating tidal flows on floodplain, agricultural land of the Wet Tropics catchments in Queensland, Australia. We assessed whether potential carbon credits would be sufficient to incentivise conversion of the land, or whether additional ecosystem service payments would be required. We explored the co-benefits for biodiversity, fisheries, and nitrogen removal using a prioritisation approach to identify profitable restoration solutions that maximise these benefits. We identified 5,046 ha of potential restorable area that could abate 221,006 tonnes of carbon dioxide-equivalent (CO2-e) annually from carbon sequestration in vegetation and soils and avoided greenhouse gas emissions. Cost-benefit analysis over 25 years demonstrate that 3,399 ha (67%) would be profitable under conventional farm management practice using the current Australian carbon price ($13.85 per tonne CO2-e), which increased to 4,534 ha (90%) at a higher carbon price ($25 per tonne CO2-e). The profitability of coastal wetland restoration was enhanced by a higher carbon price, which can be achieved by bundling ecosystem services, or through stacking ecosystem service payments. Prioritising restoration sites by cost-effectiveness and co-benefits can achieve multiple ecosystem services for a substantial profit.

Rapid evolution of a coastal marsh ecosystem engineer in response to global change - Mozdzer, Thomas J.; McCormick, Melissa K.; Slette, Ingrid J.; Blum, Michael J.; Megonigal, J. Patrick (Science of the Total Environment, 2022)
There is increasing evidence that global change can alter ecosystems by eliciting rapid evolution of foundational plants capable of shaping vital attributes and processes. Here we describe results of a field-scale exposure experiment and multilocus assays illustrating that elevated CO2 (eCO2) and nitrogen (N) enrichment can result in rapid shifts in genetic and genotypic variation in Phragmites australis, an ecologically dominant plant that acts as an ecosystem engineer in coastal marshes worldwide. Compared to control treatments, genotypic diversity declined over three years of exposure, especially to N enrichment. The magnitude of loss also increased over time under conditions of N enrichment. Comparisons of genotype frequencies revealed that proportional abundances shifted with exposure to eCO2 and N in a manner consistent with expected responses to selection. Comparisons also revealed evidence of tradeoffs that constrained exposure responses, where any particular genotype responded favorably to one factor rather than to different factors or to combinations of factors. These findings challenge the prevailing view that plant-mediated ecosystem outcomes of global change are governed primarily by differences in species responses to shifting environmental pressures and highlight the value of accounting for organismal evolution in predictive models to improve forecasts of ecosystem responses to global change.

Responses of Coastal Ecosystems to Climate Change: Insights from Long-Term Ecological Research - Reed, Daniel C; Schmitt, Russell J; Burd, Adrian B; Burkepile, Deron E; Kominoski, John S; McGlathery, Karen J; Miller, Robert J; Morris, James T; Zinnert, Julie C (BioScience, 2022)
Coastal ecosystems play a disproportionately large role in society, and climate change is altering their ecological structure and function, as well as their highly valued goods and services. In the present article, we review the results from decade-scale research on coastal ecosystems shaped by foundation species (e.g., coral reefs, kelp forests, coastal marshes, seagrass meadows, mangrove forests, barrier islands) to show how climate change is altering their ecological attributes and services. We demonstrate the value of site-based, long-term studies for quantifying the resilience of coastal systems to climate forcing, identifying thresholds that cause shifts in ecological state, and investigating the capacity of coastal ecosystems to adapt to climate change and the biological mechanisms that underlie it. We draw extensively from research conducted at coastal ecosystems studied by the US Long Term Ecological Research Network, where long-term, spatially extensive observational data are coupled with shorter-term mechanistic studies to understand the ecological consequences of climate change.

Seagrass biomass and sediment carbon in conserved and disturbed seascape - Reyes, Angeli Gabrielle B.; Vergara, Ma Camille S.; Blanco, Ariel C.; Salmo, Severino G. (Ecological Research, 2022)
Despite the Philippines having one of the widest extents and most diverse seagrasses, there are limited reports on the contribution of seagrass vegetation health to organic carbon (OC). Comparative assessments of OC between conserved and disturbed seagrass meadows in a seascape are also lacking. Conservation programs (e.g., marine protected area [MPA]) contribute to the maintenance of ecosystem health and OC storage in seagrass. However, disturbances may negate the effects of MPAs. Disturbances are often due to coastal development pressures linked to the need for industry, food production, and human settlement. Here, we assessed and compared the aboveground biomass (AGB), belowground biomass (BGB), and OC between conserved and disturbed seagrass meadows, then, tested its correlation with vegetation and water quality variables. The study was conducted in Oyon Bay (northwest Philippines), one of the key seascape MPAs in the Philippines. The bay experienced disturbances from a coal power plant, aquaculture, and human settlements for approximately 30 years. Results showed 7× higher AGB, 11× higher BGB, and 1.7× higher OC in conserved sites. The low biomass and OC values in the disturbed sites were correlated to poor vegetation and water quality conditions (particularly high turbidity [ρ = 0.38], high phosphates [ρ = −0.19], and low dissolved oxygen [ρ = −0.31]). Our study showed the effectiveness of MPAs in maintaining ecosystem health and OC in seagrass, but the magnitude of disturbances lessened the benefits from MPAs. Our results have implications on the over- or under-estimation of carbon sequestration not just in Philippine seagrasses but also in most Southeast Asian countries facing similar coastal development pressures.

Seagrass Thermal Limits and Vulnerability to Future Warming - Marbà, Núria; Jordà, Gabriel; Bennett, Scott; Duarte, Carlos M. (Frontiers in Marine Science, 2022)
Seagrasses have experienced major losses globally mostly attributed to human impacts. Recently they are also associated with marine heat waves. The paucity of information on seagrass mortality thermal thresholds prevents the assessment of the risk of seagrass loss under marine heat waves. We conducted a synthesis of reported empirically- or experimentally-determined seagrass upper thermal limits (Tlimit) and tested the hypothesis that they increase with increasing local annual temperature. We found that Tlimit increases 0.42± 0.07°C per°C increase in in situ annual temperature (R2 = 0.52). By combining modelled seagrass Tlimit across global coastal areas with current and projected thermal regimes derived from an ocean reanalysis and global climate models (GCMs), we assessed the proximity of extant seagrass meadows to their Tlimit and the time required for Tlimit to be met under high (RCP8.5) and moderate (RCP4.5) emission scenarios of greenhouse gases. Seagrass meadows worldwide showed a modal difference of 5°C between present Tmax and seagrass Tlimit. This difference was lower than 3°C at the southern Red Sea, the Arabian Gulf, the Gulf of Mexico, revealing these are the areas most in risk of warming-derived seagrass die-off, and up to 24°C at high latitude regions. Seagrasses could meet their Tlimit regularly in summer within 50-60 years or 100 years under, respectively, RCP8.5 or RCP4.5 scenarios for the areas most at risk, to more than 200 years for the Arctic under both scenarios. This study shows that implementation of the goals under the Paris Agreement would safeguard much of global seagrass from heat-derived mass mortality and identifies regions where actions to remove local anthropogenic stresses would be particularly relevant to meet the Target 10 of the Aichi Targets of the Convention of the Biological Diversity.

Seaweed forests are carbon sinks that can mitigate CO2 emissions - Filbee-Dexter, Karen; Pessarrodona, Albert; Duarte, Carlos M.; Krause-Jensen, Dorte; Hancke, Kasper; Smale, Dan A.; Wernberg, Thomas (EvoEcoRxiv, 2022)
The paper — Seaweed ecosystems may not mitigate CO2 emissions (Gallagher et al., 2022) — claims that seaweed ecosystems are carbon sources rather than carbon sinks because ‘respiration subsidies’ (from inputs of allochthonous organic carbon) create negative net ecosystem production. That is, that seaweed ecosystems produce more CO2 than they draw down, and thus may not mitigate CO2 emissions. They make this claim using a compiled dataset which shows that, on average, seaweed ecosystems are net heterotrophic. However, their assessment is flawed and conceptually misleading as key terms are misinterpreted, the data presented are biased, and the conclusions are not supported statistically. Here we discuss four flaws in the argument presented by Gallagher et al., which we believe risk confusing further research on seaweed blue carbon and unjustifiably seeding doubt around motivations and initiatives to protect and restore seaweed forests.

Sedimentation as a Support Ecosystem Service in Different Ecological Types of Mangroves - Cinco-Castro, Siuling; Herrera-Silveira, Jorge; Comín, Francisco (Frontiers in Forests and Global Change, 2022)
Mangrove vegetation is strongly dependent on the climate, the physicochemical variables of the sediment, and the hydrological dynamics. These drivers regulate the distribution of different mangrove ecotypes and their ecosystem services, so the net sediment accumulation rates in different mangrove ecotypes in Celestun Lagoon, a karstic zone in the NW Yucatan Peninsula, SE Mexico, were estimated. The measurements considering mangrove ecotypes and their spatial variability concerning the lagoon's salinity gradient (inner, middle, and outer lagoon zones) in three climate seasons (dry, rain, and “nortes”) were realized. We registered the structural variables of the forest, interstitial water physicochemical characteristics, and sediment variables that could influence the net sediment deposition. Fringe mangroves are exposed to low hydrodynamism and show the highest sedimentation rate (3.37 ± 0.49 kg m−2 year−1) compared to basin (1.68 ± 0.22 kg m−2 year−1), dwarf (1.27 ± 0.27 kg m−2 year−1), and “peten” (0.52 ± 0.12 kg m−2 year−1) mangroves. The highest sedimentation rate was recorded in the rainy season (0.24 ± 0.08 kg m−2 month−1), while spatially, the highest value was registered in the outer zone (0.44 ± 0.09 kg m−2 month−1). If the extension of each mangrove ecotype is considered, dwarf mangroves have the highest annual sediment accumulation (1,465 t year−1 in 14,706 ha). The structural, physicochemical, and sediment variables of the sites by mangrove ecotype show that dwarf mangroves represent a distinct group from those formed by fringe, basin, and peten mangroves. However, the sedimentation is high in fringe mangroves at the front of the lagoon and diminishes inland where peten mangroves exist. The differences are given by tree density, but salinity, as a proxy variable of the freshwater influence, significantly influences the sedimentation rate. These results indicate that mangroves in karstic environments can have critical roles in confronting climate change, considering water and sediment flows are the basis of sediment accumulation. According to their hydrogeomorphological drivers, conserving, managing, and restoring the mosaic of mangrove ecotypes improves ecosystem services, including mitigation and adaptation to climate change.
Keywords: conservation; ecosystem services (ES); karstic area; mangrove types; mitigation and adaptation; sedimentation rate

Severe drought events trigger long-term salt marsh dieback in the Southeastern and Gulf of Mexico USA - Rolando, JL; Hodges, M; Garcia, KD.; Krueger, G.; Williams, N.; Carr, J.; Robinson, J.; George, A.; Morris, J; Kostka, JE (bioRxiv, 2022)
The frequency of salt marsh dieback events has been increasing in the last 25 years with unknown consequences to the resilience of the ecosystem to accelerated sea level rise (SLR). Sudden dieback events triggered by extreme climatic events were previously thought to recover naturally within a few months to years. We provide evidence that about 15% of total marsh area has not revegetated 10- and 20-years after dieback events in two case studies in the Southeast and Gulf of Mexico USA, respectively. In both case studies, dieback onset coincided with severe drought events. In West Ashley, SC, dieback areas were associated with lower elevation zones in the interior of the marsh. Restoration by grass planting was shown to be effective in the South Carolina urban marsh, indicating that the stressors that caused dieback may be overcome despite that most of dieback areas have not recovered naturally. A mechanistic modelling approach was used to predict the resilience of the South Carolina salt marsh to accelerated SLR under different scenarios of primary productivity, ecological management, and rates of SLR. Predictions indicate that a highly productive restored marsh (2000 g m-2 y-1) would persist at a moderate SLR rate of 60 cm 100 y-1, whereas a non-restored mudflat would rapidly lose all of its elevation capital. Further, at an elevated SLR rate of 122 cm 100 y-1, most likely an extreme climate change scenario, even highly productive ecosystems augmented by sediment placement would not keep pace with SLR. Thus, both climate change adaptation and mitigation actions are urgently needed to preserve highly valuable present-day marsh ecosystems close to urban environments. ### Competing Interest Statement The authors have declared no competing interest.

Species Traits and Geomorphic Setting as Drivers of Global Soil Carbon Stocks in Seagrass Meadows - Kennedy, H.; Pagès, J. F.; Lagomasino, D.; Arias-Ortiz, A.; Colarusso, P.; Fourqurean, J. W.; Githaiga, M. N.; Howard, J. L.; Krause-Jensen, D.; Kuwae, T.; Lavery, P. S.; Macreadie, P. I.; et al. (Global Biogeochemical Cycles, 2022)
Our knowledge of the factors that can influence the stock of organic carbon (OC) that is stored in the soil of seagrass meadows is evolving, and several causal effects have been used to explain the variation of stocks observed at local to national scales. To gain a global-scale appreciation of the drivers that cause variation in soil OC stocks, we compiled data on published species-specific traits and OC stocks from monospecific and mixed meadows at multiple geomorphological settings. Species identity was recognized as an influential driver of soil OC stocks, despite their large intraspecific variation. The most important seagrass species traits associated with OC stocks were the number of leaves per seagrass shoot, belowground biomass, leaf lifespan, aboveground biomass, leaf lignin, leaf breaking force and leaf OC plus the coastal geomorphology of the area, particularly for lagoon environments. A revised estimate of the global average soil OC stock to 20 cm depth of 15.4 Mg C ha−1 is lower than previously reported. The largest stocks were still recorded in Mediterranean seagrass meadows. Our results specifically identify Posidonia oceanica from the Mediterranean and, more generally, large and persistent species as key in providing climate regulation services, and as priority species for conservation for this specific ecosystem service.

Stakeholders’ Perceptions of Nature-Based Solutions for Hurricane Risk Reduction Policies in the Mexican Caribbean - Moreno, Claudia Shantal; Roman-Cuesta, Rosa Maria; Canty, Steven W.J.; Herrera, Jorge; Teutli, Claudia; Muñiz-Castillo, Aarón Israel; McField, Melanie; Soto, Melina; do Amaral, Cibele; Paton, Steven; González-Trujillo, Juan David; Poulter, Benjamin; et al. (Land, 2022)
Nature-based solutions (NbSs) have long recognized the value of coastal and marine ecosystem management and associated ecosystem services as useful tools for climate change mitigation (e.g., blue carbon) and adaptation (e.g., coastal protection against flooding and storm surges). However, NbSs remain poorly acknowledged and mostly absent from coastal planning for disaster risk reduction policies in the Caribbean, as well as from ex-post disaster reconstruction funds. With the increasing frequency and intensity of hurricanes in the region, NbSs are now more needed than ever. Taking Mexico as a representative case study for the wider Caribbean, we here seek to identify and analyze the barriers and opportunities perceived by relevant stakeholders for mainstreaming coastal-marine NbSs into coastal management and disaster risk reduction policies (e.g., mangroves as green infrastructure) to protect coastal societies and national economies against hurricanes. We conduct semi-structured, in-depth interviews with twenty stakeholders covering academic, governmental, tourism, NGO, coastal planning, and financial domains. Among the twenty-three identified barriers, governance, institutional, financial, and human-capacity aspects are the most dominant perceptions behind the current lack of NbS implementation. Future action for the policy integration of NbSs requires widespread political will and better quantification of both the provision of ecosystem services and their economic benefits under conventional markets.

Stocks and Productivity of Dead Wood in Mangrove Forests: A Systematic Literature Review - Mugi, Lilian Mwihaki; Kiss, Dora; Kairo, James Gitundu; Huxham, Mark Richard (Frontiers in Forests and Global Change, 2022)
The functional and ecological importance of dead wood in terrestrial forests is widely recognized and researched. In contrast, much less is known about dead wood in mangrove forests, despite its known or demonstrated contribution to key ecological processes including nutrient cycling and seedling recruitment. In addition, mangrove dead wood provides an important service for millions of people; harvesting wood for fuel is widespread in mangroves and is often vital for the lives and wellbeing of people living close to these forests. Limited information on stocks and production, and the drivers of these, means that understanding and managing the supply of this service is difficult. Here we conduct a systematic review of the literature on dead wood stocks and production in mangrove ecosystems. Four hundred and seventy-five subject articles were found, with large gaps in geography, species, and forest type. After excluding records that were not relevant to our study and those from mass mortality events, 68 studies remained. We also added new data from 9 sites in Kenya, to provide overall estimates of mean (± SD) stocks of dead wood of 16.85 ± 25.35 Mg ha−1 standing and 29.92 ± 36.72 Mg ha−1 downed. Our analysis shows that potentially, higher stocks of dead wood might be found in forests without evidence of human impact. Average mean production with 95% CI was 6.30, 3.10–11.40 Mg ha−1 yr−1. Estimates of daily wood use were applied to give likely demands on wood from mangrove dependent communities. This review reveals the paucity of research on mangrove dead wood, hence these estimates of average stocks and productivity remain very limited and thus, further work on the dynamics of dead wood in mangroves and the ecological effects of its removal is needed.

Strong Dynamics in Tidal Marsh DOC Export in Response to Natural Cycles and Episodic Events From Continuous Monitoring - Menendez, Alana; Tzortziou, Maria; Neale, Patrick; Megonigal, Patrick; Powers, Leanne; Schmitt-Kopplin, Philippe; Gonsior, Michael (Journal of Geophysical Research: Biogeosciences, 2022)
The role of tidal wetlands as hotspots for carbon and nutrient exchange with adjacent waters has been well documented, but large uncertainties remain regarding the physical and biogeochemical controls on these fluxes, which have significant implications for coastal carbon cycling and budgets. This study elucidates the variability in lateral wetland dissolved organic (DOC) fluxes tidally, seasonally, and during extreme weather events for a brackish wetland within a sub-estuary of the northwestern Chesapeake Bay, USA. Continuous fluxes from the wetland-draining tidal creek were calculated based on DOC concentrations ([DOC]) estimated using optical and physicochemical properties measured in situ with concurrent water flow data. Mean export was found to be 8.59 (±1.20) kg C (n = 1,128) tidal cycle−1 and annual flux from the wetland to sub-estuary was 200.66 (±28.09) g C m−2 yr−1. Peaks in DOC flux were associated with Hurricane Joaquin in 2015, where just two tidal cycles accounted for ∼5% of annual export. Analysis of tidal creek water quality measurements reveal seasonal and tidal dependencies. Highest [DOC] and largest low versus high tide differences were observed in summer, corresponding to more fresh plant biomass and its mobilization, consistent with results from Fourier transform ion cyclotron resonance mass spectrometry. Despite summer highs in tidal creek [DOC], monthly DOC fluxes were greatest in early fall due to higher water flows. The annual flux presented here is higher than fluxes previously reported for this system, highlighting the importance of continuous measurements for monitoring carbon export under a wide range of environmental conditions.

Surface elevation changes in an estuarine mangrove forest in Vanga, Kenya: Implications for management and mitigation of sea-level rise - Kimeli, Amon Kibiwot; Cherono, Shawlet; Baya, Patience; Mathinji, Margaret; Okello, Judith Auma; Koedam, Nico; Westphal, Hildegard; Kairo, James Gitundu (Frontiers in Marine Science, 2022)
Mangrove ecosystems are often called “makers of land” due to their ability to promote deposition, trap, and augment sediments. Accurate location- and region-specific elevation information is required to assess and mitigate threats to mangroves caused by their vulnerability to sea-level rise. The provision of land building services by mangroves is primarily sediment-dependent. It is therefore influenced by local factors, including sediment availability and supply. In the present study from Kenya, we measured and examined the variations in surface elevation in mangroves at variable distances from the creek channel using a combination of surface-elevation tables and horizon markers for three years. Elevation changes varied with distance from the creek channel (p < 0.05), with both surface loss and gains recorded. Elevation changes varied between -80 mm (most significant subsidence) and 42 mm (highest accretion) in stations closer to the creek, while farther from the creek (~200 m away), elevation changes ranged between -68 mm (most significant subsidence) and 29 mm (highest accretion). However, net surface elevation changes over the three years showed that shallow subsidence occurred in both stations closer to the creek (-45 ± 7.2 mm) and those farthest from the creek (-20 ± 7.1 mm). At the same time, an average of 18 mm of sediments were accreted above the horizon markers translating to ~9 mm yr-1 of accretion, a rate larger than both the current global rates of sea-level rise (~3.1 mm yr-1) and local measured rates of sea-level rise (3.8 mm yr-1) in Mombasa, a tide-gauge station nearest (~100 km) to the study site. Cumulatively, sediment elevation changes in Vanga indicate that they are outpacing the current rates of sea-level rise. However, they could be vulnerable to predicted and accelerated rates. It, therefore, calls for more holistic management and monitoring of the dynamics within the mangrove forests and adjacent terrestrial hinterlands.

Tackling the mangrove restoration challenge - Lovelock, Catherine E.; Barbier, Edward; Duarte, Carlos M. (PLoS Biology, 2022)
Mangroves have been converted and degraded for decades. Rates of loss have declined over the past decades, but achieving resilient coastlines requires both conservation and restoration. Here, we outline the challenges for the global restoration of mangroves and what actions could enhance restoration. Ambitious global targets for mangrove restoration, if successful, could deliver global benefits of carbon sequestration, fisheries production, biodiversity, and coastal protection. However, large-scale mangrove planting efforts have often failed, and smaller projects may not deliver landscape-scale benefits, even though they are more suited to community management. Solutions to achieving global targets include reducing risks of large projects and increasing the uptake and effectiveness of smaller projects. Sustainable mangrove restoration requires investment in capacity building in communities and institutions, and mechanisms to match restoration opportunities with prospective supporters and investors. Global reporting standards will support adaptive management and help fully understand and monitor the benefits of mangrove restoration.

Temperature optimum for marsh resilience and carbon accumulation revealed in a whole-ecosystem warming experiment - Smith, Alexander J.; Noyce, Genevieve L.; Megonigal, James Patrick; Guntenspergen, Glenn R.; Kirwan, Matthew L. (Global Change Biology, 2022)
Coastal marshes are globally important, carbon dense ecosystems simultaneously maintained and threatened by sea-level rise. Warming temperatures may increase wetland plant productivity and organic matter accumulation, but temperature-modulated feedbacks between productivity and decomposition make it difficult to assess how wetlands and their thick, organic-rich soils will respond to climate warming. Here, we actively increased aboveground plant-surface and belowground soil temperatures in two marsh plant communities, and found that a moderate amount of warming (1.7°C above ambient temperatures) consistently maximized root growth, marsh elevation gain, and belowground carbon accumulation. Marsh elevation loss observed at higher temperatures was associated with increased carbon mineralization and increased microtopographic heterogeneity, a potential early warning signal of marsh drowning. Maximized elevation and belowground carbon accumulation for moderate warming scenarios uniquely suggest linkages between metabolic theory of individuals and landscape-scale ecosystem resilience and function, but our work indicates nonpermanent benefits as global temperatures continue to rise.

The Contribution of Subtidal Seagrass Meadows to the Total Carbon Stocks of Gazi Bay, Kenya - Omollo, Derrick Joannes; Wang’ondu, Virginia Wangeci; Githaiga, Michael Njoroge; Gorman, Daniel; Kairo, James Gitundu (Diversity, 2022)
Seagrass beds occur globally in both intertidal and subtidal zones within shallow marine environments, such as bays and estuaries. These important ecosystems support fisheries production, attenuate strong wave energies, support human livelihoods and sequester large amounts of CO2 that may help mitigate the effects of climate change. At present, there is increased global interest in understanding how these ecosystems could help alleviate the challenges likely to face humanity and the environment into the future. Unlike other blue carbon ecosystems, i.e., mangroves and saltmarshes, seagrasses are less understood, especially regarding their contribution to the carbon dynamics. This is particularly true in regions with less attention and limited resources. Paucity of information is even more relevant for the subtidal meadows that are less accessible. In Kenya, much of the available information on seagrasses comes from Gazi Bay, where the focus has been on the extensive intertidal meadows. As is the case with other regions, there remains a paucity of information on subtidal meadows. This limits our understanding of the overall contribution of seagrasses in carbon capture and storage. This study provides the first assessment of the species composition and variation in carbon storage capacity of subtidal seagrass meadows within Gazi Bay. Nine seagrass species, comprising of Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, Halodule uninervis, Halophila ovalis, Halophila stipulacea, Syringodium isoetifolium, Thalassia hemprichii, and Thalassodendron ciliatum, were found. Organic carbon stocks varied between species and pools, with the mean below ground vegetation carbon (bgc) stocks (5.1 ± 0.7 Mg C ha−1) being more than three times greater than above ground carbon (agc) stocks (0.5 ± 0.1 Mg C ha−1). Mean sediment organic carbon stock (sed Corg) of the subtidal seagrass beds was 113 ± 8 Mg C ha−1. Combining this new knowledge with existing data from the intertidal and mangrove fringed areas, we estimate the total seagrass ecosystem organic carbon stocks in the bay to be 196,721 Mg C, with the intertidal seagrasses storing about 119,790 Mg C (61%), followed by the subtidal seagrasses 55,742 Mg C (28%) and seagrasses in the mangrove fringed creeks storing 21,189 Mg C (11%). These findings are important in highlighting the need to protect subtidal seagrass meadows and for building a national and global data base on seagrass contribution to global carbon dynamics.

The novel mangrove environment and composition of the Amazon Delta - Bernardino, Angelo F.; Mazzuco, Ana Carolina A.; Souza, Fernanda M.; Santos, Thuareag M.T.; Sanders, Christian J.; Massone, Carlos G.; Costa, Rodolfo F.; Silva, Antônio Elves B.; Ferreira, Tiago O.; Nóbrega, Gabriel N.; Silva, Thiago S.F.; Kauffman, J. Boone (Current Biology, 2022)
Both freshwater floodplain (várzeas and igapós) forests and brackish-saline mangroves are abundant and well-described ecosystems in Brazil.1 However, an interesting and unique wetland forest exists in the Amazon Delta where extensive mangroves occur in essentially freshwater tidal environments. Unlike the floodplain forests found upriver, the hydrology of these ecosystems is driven largely by large macro-tides of 4–8 m coupled with the significant freshwater discharge from the Amazon River. We explored these mangroves on the Amazon Delta (00°52ʹ N to 01°41ʹ N) and found surface water salinity to be consistently <5; soil pore water salinity in these mangrove forests ranged from 0 nearest the Amazon mouth to only 5–11 at the coastal margins to the north (01°41ʹ N, 49°55′ W). We also recorded a unique mix of mangrove-obligate (Avicennia sp., Rhizophora mangle) and facultative-wetland species (Mauritia flexuosa, Pterocarpus sp.) dominating these forests. This unique mix of plant species and soil porewater chemistry exists even along the coastal strands and active coastlines of the Atlantic Ocean. Part of these unique mangroves have escaped current global satellite mapping efforts, and we estimate that they may add over 180 km2 (20% increase in mangrove area) within the Amazon Delta. Despite having a unique structure and function, these freshwater-brackish ecosystems likely provide similar ecosystem services to most mangroves worldwide, such as sequestering large quantities of organic carbon, protection of shoreline ecosystems from erosion, and habitats to many terrestrial and aquatic species (monkeys, birds, crabs, and fish).

Using citizen science to estimate surficial soil Blue Carbon stocks in Great British saltmarshes - Smeaton, Craig; Burden, Annette; Ruranska, Paulina; Ladd, Cai J.T.; Garbutt, Angus; Jones, Laurence; McMahon, Lucy; Miller, Lucy C.; Skov, Martin W.; Austin, William E.N. (Frontiers in Marine Science, 2022)
A new saltmarsh soil dataset comprising of geochemical and physical property data from 752 soil samples collected through a sampling program supported by citizen scientists has been brought together with existing data to make the first national estimates of the surficial (top 10 cm) soil OC stock for Great British (GB) saltmarshes. To allow the inclusion of secondary data in the soil stock estimate a new bespoke organic matter to organic carbon conversion for GB saltmarsh soil was developed allowing organic matter data measured using loss-on-ignition to be convert to organic carbon content. The total GB surficial soil OC stock is 2.320 ± 0.470 Mt; English saltmarshes hold 1.601 ± 0.426 Mt OC, Scottish saltmarshes hold 0.368 ± 0.091 Mt OC, and Welsh saltmarshes hold 0.351 ± 0.082 Mt OC. The stocks were calculated within a Markov Chain Monte Carlo framework allowing robust uncertainty estimates to be derived for the first time. Spatial mapping tools are available to accompany these stock estimates at individual saltmarsh habitats throughout GB. This data will aid in the protection and management of saltmarshes and represents the first steps towards the inclusion of saltmarsh OC in the national inventory accounting of blue carbon ecosystems.

Value chain and sustainability of mangrove wood harvesting in Lamu, Kenya - Riungu, Purity M.; Nyaga, Justine M.; Githaiga, Michael N.; Kairo, James G. (Trees, Forests and People, 2022)
Mangrove forests provide harvestable wood and non-wood resources to human society globally. The current study evaluated value chain of mangrove wood products from Lamu, Kenya, and how these impacts on resources’ sustainability. Results show that, exploitation of mangrove wood products in Kenya involves several actors, including national regulator, licensees, cutters, transporters, stockists and the consumers. Based on the differences between allowable and harvest data, Lamu mangroves can be said to be under-exploited. For the 1992–2018 period, an average of 223.5 scores ha−1yr−1 of mangrove poles were target for harvesting from Lamu. During the same period, the harvest data indicate an average of 6.2 scores ha−1yr−1 of mangrove poles were removed. However, based on stand level data generated as part of this study, mangroves in Lamu are over-exploited and stocked with non-merchantable poles. There are differentiated net income among various actors in mangrove trade in Kenya. Mangrove cutters are among the ‘losers’ in mangrove trade value chain earning a monthly net income of USD118.6 ± 17.9. Winners in mangrove trade is the Kenya Forest Service, Licensees, transporters, and mangrove dealers (or stockists) in urban centers. The findings of this study are critical in development of the harvesting plan for Lamu mangroves. The results will provide insights toward streamlining mangrove trade for community development, revenue generation and environmental sustainability.

Vegetation and hydrology stratification as proxies to estimate methane emission from tidal marshes - Derby, R. Kyle; Needelman, Brian A.; Roden, Ana A.; Megonigal, J. Patrick (Biogeochemistry, 2022)
Direct measurement of methane emissions is cost-prohibitive for greenhouse gas offset projects, necessitating the development of alternative accounting methods such as proxies. Salinity is a useful proxy for tidal marsh CH4 emissions when comparing across a wide range of salinity regimes but does not adequately explain variation in brackish and freshwater regimes, where variation in emissions is large. We sought to improve upon the salinity proxy in a marsh complex on Deal Island Peninsula, Maryland, USA by comparing emissions from four strata differing in hydrology and plant community composition. Mean CH4 chamber-collected emissions measured as mg CH4 m−2 h−1 ranked as S. alterniflora (1.2 ± 0.3) ≫ High-elevation J. roemerianus (0.4 ± 0.06) > Low-elevation J. roemerianus (0.3 ± 0.07) = S. patens (0.1 ± 0.01). Sulfate depletion generally reflected the same pattern with significantly greater depletion in the S. alterniflora stratum (61 ± 4%) than in the S. patens stratum (1 ± 9%) with the J. roemerianus strata falling in between. We attribute the high CH4 emissions in the S. alterniflora stratum to sulfate depletion likely driven by limited connectivity to tidal waters. Low CH4 emissions in the S. patens stratum are attributed to lower water levels, higher levels of ferric iron, and shallow rooting depth. Moderate CH4 emissions from the J. roemerianus strata were likely due to plant traits that favor CH4 oxidation over CH4 production. Hydrology and plant community composition have significant potential as proxies to estimate CH4 emissions at the site scale.

Blue carbon: A new paradigm of mangrove conservation and management in Indonesia - Sidik, Frida; Lawrence, Anissa; Wagey, Tonny; Zamzani, Franky; Lovelock, Catherine E. (Marine Policy, 2023)
Indonesia is the largest archipelagic country in the world and has vast natural resources. In the maritime sector, efforts to realize the sustainability of natural resources in coastal ecosystems have focused on mangroves and seagrass meadows, also known as blue carbon ecosystems, that have an important role in regulating the Earth's climate. The need for ecosystem-based climate change mitigation combined with economic recovery and improved environment conditions has shifted the motivation and escalated mangrove restoration efforts in Indonesia. As the richest mangrove nation with the greatest mangrove carbon stocks in the world, recently Indonesia has taken significant steps in the land use sector to reduce emissions by acknowledging the ‘true’ value of mangrove carbon and setting priorities for mangrove conservation and restoration within Indonesia's climate actions. This paper reviews opportunities and challenges in mainstreaming mangrove blue carbon into policy in Indonesia. We evaluate the gaps in regulations and policies and propose pathways for the national blue carbon action. As mangroves are embedded in both forestry and marine sectors and the responsibilities for management lies within several government ministries, an integrated framework is suggested to support the national blue carbon strategy. The Indonesia Blue Carbon Strategy Framework (IBCSF) encompasses three main elements that should be considered in order to address challenges and seize opportunities in blue carbon: coordination, policy and funding.

Capturing of organic carbon and nitrogen in eelgrass sediments of southern Scandinavia - Leiva-Dueñas, Carmen; Graversen, Anna Elizabeth Løvgren; Banta, Gary T.; Holmer, Marianne; Masque, Pere; Stæhr, Peter Anton Upadhyay; Krause-Jensen, Dorte (Limnology and Oceanography, 2023)
The ability of seagrass meadows to filter nutrients and capture and store CO2 and nutrients in the form of organic carbon (OC) and nitrogen (N) in their sediments may help to mitigate local eutrophication as well as climate change via meadow restoration and protection. This study assesses OC and N sediment stocks (top 50 cm) and sequestration rates within Danish eelgrass meadows. At four locations, eelgrass-vegetated and nearby unvegetated plots were studied in protected and exposed areas. The average OC and N sediment 50 cm stocks were 2.6 ± 0.3 kg OC m−2 and 0.23 ± 0.01 kg N m−2, including vegetated and unvegetated plots. In general, OC and N stocks did not differ significantly between eelgrass meadows and unvegetated sediments. Lack of accumulation of excess 210Pb suggested sediment erosion or low rates of sediment accumulation at most sites. OC accumulation rates ranged from 6 to 134 g m−2 yr−1 and N from 0.7 to 14 g m−2 yr−1. Generalized additive models showed that ≥ 80% of the variation in sediment OC and N stocks was explained by sediment grain size, organic matter source, and hydrodynamic exposure. Long cores, dated with 210Pb, showed declining OC and N densities toward present time, suggesting long-term declines in eelgrass OC and N pools. Estimates of potential nation-wide OC and N accumulation in eelgrass sediments show that they could annually capture up to 0.7% ± 0.5% of CO2 emissions and 6.9% ± 5.2% of the total terrestrial N load.

Challenges and opportunities for achieving Sustainable Development Goals through restoration of Indonesia’s mangroves - Sasmito, Sigit D.; Basyuni, Mohammad; Kridalaksana, Age; Saragi-Sasmito, Meli F.; Lovelock, Catherine E.; Murdiyarso, Daniel (Nature Ecology and Evolution, 2023)
Indonesia, the most mangrove-rich nation in the world, has proposed the most globally ambitious mangrove rehabilitation target (600,000 ha) of any nation, to be achieved by 2024 to support multiple Sustainable Development Goals (SDG 1–3, 6, 13 and 14). Yet, mangrove restoration and rehabilitation across the world have often suffered low success rates and been applied at small scales. Here, we identify 193,367 ha (estimated costs at US$0.29–1.74 billion) that have the potential to align with the national mangrove rehabilitation programme. Despite being only 30% of the national target, our robust assessment considered biogeomorphology, 20 years of land-use and land-cover change and state forest land status, all key factors moderating mangrove restoration success which have often been neglected in Indonesia. Increasing subnational government representation in mangrove governance as well as improving monitoring and evaluation will increase the likelihood of achieving the mangrove rehabilitation targets and reduce risks of failure. Rehabilitating and conserving mangroves in Indonesia could benefit 74 million coastal people and can potentially contribute to the national land-sector emissions reduction of up to 16%.

Changes in Mangrove Blue Carbon under Elevated Atmospheric CO 2 - Gu, Xiaoxuan; Qiao, Peiyang; Krauss, Ken W.; Lovelock, Catherine E.; Adams, Janine B.; Chapman, Samantha K.; Jennerjahn, Tim C.; Lin, Qiulian; Chen, Luzhen (Ecosystem Health and Sustainability, 2023)
While there is consensus that blue carbon ecosystems, such as mangroves, have an important role in mitigating some aspects of global climate change, little is known about mangrove carbon cycling under elevated atmospheric CO 2 concentrations ( e CO 2 ). Here, we review studies in order to identify pathways for how e CO 2 might influence mangrove ecosystem carbon cycling. In general, e CO 2 alters plant productivity, species community composition, carbon fluxes, and carbon deposition in ways that enhance mangrove carbon storage with e CO 2 . As a result, a negative feedback to climate change exists whereby e CO 2 adds to mangrove’s ability to sequester additional carbon, which in turn reduces the rate by which CO 2 builds. Furthermore, e CO 2 affects warming and sea-level rise (SLR) through alternate pathways, which coinfluence the mangrove response in both antagonistic (i.e., warming = greater carbon loss to decomposition) and synergistic (i.e., SLR = greater soil carbon burial) ways. e CO 2 is projected to become a more prominent driver in the future before reaching a steady state. However, given the complexity of the interactions of biological and environmental factors with e CO 2 , long-term field observations and in situ simulation experiments can help to better understand the mechanisms for proper model initialization to predict future changes in mangrove carbon sequestration.

Drivers of Mangrove Vulnerability and Resilience to Tropical Cyclones in the North Atlantic Basin - Hummel do Amaral, Cibele; Poulter, Benjamin; Lagomasino, David; Fatoyinbo, Temilola; Taillie, Paul; Lizcano, Gil; Canty, Steven W.J.; Silveira, Jorge Alfredo Herrera; Teutli-Hernández, Claudia; Cifuentes, Miguel; Charles, Sean Patrick; Moreno, Claudia Shantal; et al. (SSRN Electronic Journal, 2023)

Identifying priorities for reform to integrate coastal wetland ecosystem services into law and policy - Bell-James, Justine; Foster, Rose; Lovelock, Catherine E. (Environmental Science and Policy, 2023)
The ecosystem services concept has been slow to integrate into written law and policy in Australia. We sought to examine whether the concept has permeated deeper into practice, focusing on the coastal wetland protection, management and restoration context. We conducted a Delphi study involving 16 key informants. Over two rounds of interviews we found confirmation that the ecosystem services concept is not a central part of practice, and a strong consensus support for integrating and mainstreaming ecosystem services into law and policy through law reform. Our informants also provided additional new insights on how reform should proceed: (1) integration may occur through consolidated or interconnected law and policy instruments, (2) decision-maker discretion should be retained but subject to constraints, especially regarding (3) trade-offs between different ecosystem services and ecosystem services and other land uses. Our informants also called for (4) more effective and targeted policy to facilitate restoration projects, (5) incentivised protection and restoration across land tenure types, especially on privately-owned land and (6) caution in dealing with trade-offs and financial valuations of ecosystem services. The insights provided through this Delphi study will be instructive for law and policy reform in Australia and other jurisdictions grappling with fragmented management, protection and restoration of coastal wetlands.

Importance of mangrove plantations for climate change mitigation in Bangladesh - Uddin, Mohammad Main; Abdul Aziz, Ammar; Lovelock, Catherine E. (Global Change Biology, 2023)
Mangroves have been identified as blue carbon ecosystems that are natural carbon sinks. In Bangladesh, the establishment of mangrove plantations for coastal protection has occurred since the 1960s, but the plantations may also be a sustainable pathway to enhance carbon sequestration, which can help Bangladesh meet its greenhouse gas (GHG) emission reduction targets, contributing to climate change mitigation. As a part of its Nationally Determined Contribution (NDC) under the Paris Agreement 2016, Bangladesh is committed to limiting the GHG emissions through the expansion of mangrove plantations, but the level of carbon removal that could be achieved through the establishment of plantations has not yet been estimated. The mean ecosystem carbon stock of 5 to 42 years aged (average age: 25.5 years) mangrove plantations was 190.1 (± 30.3) Mg C ha‐1, with ecosystem carbon stocks varying regionally. The biomass carbon stock was 60.3 (± 5.6) Mg C ha‐1 and the soil carbon stock was 129.8 (± 24.8) Mg C ha‐1 in the top one meter of which 43.9 Mg C ha‐1 was added to the soil after plantation establishment. Plantations at age 5 to 42 years achieved 53% of the mean ecosystem carbon stock calculated for the reference site (Sundarbans natural mangroves). Since 1966, the 28,000 ha of established plantations to the east of the Sundarbans have accumulated approximately 76,607 Mg C yr‐1 sequestration in biomass and 37,542 Mg C yr‐1 sequestration in soils, totaling 114,149 Mg C yr‐1. Continuation of the current plantation success rate would sequester an additional 664,850 Mg C by 2030, which is 4.4% of Bangladesh's 2030 GHG reduction target from all sectors described in its NDC, however, plantations for climate change mitigation would be most effective 20 years after establishment. Higher levels of investment in mangrove plantations and higher plantation establishment success could contribute up to 2,098,093 Mg C to blue carbon sequestration and climate change mitigation in Bangladesh by 2030.

Macroalgal habitats support a sustained flux of floating biomass but limited carbon export beyond a Greenland fjord - Ager, Thomas Gjerluff; Krause-Jensen, Dorte; Olesen, Birgit; Carlson, Daniel F.; Winding, Mie Hylstofte Sichlau; Sejr, Mikael K. (Science of the Total Environment, 2023)
Despite growing attention on the contribution of macroalgae to carbon cycling and sequestration (blue carbon), more observational data is needed to constrain current estimates. In this study, we estimate the floating macroalgal carbon flux within and beyond a large sub-Arctic fjord system, Nuup Kangerlua, Greenland, which could potentially reach carbon sinks. Our study estimates 1) the fjord-scale area with macroalgal coverage and barrens caused by sea urchin grazing, 2) the floating macroalgal biomass in the fjord, and 3) the annual export flux of floating macroalgae out of the fjord system. ROV surveys documented that macroalgal habitats cover 32 % of the seafloor within the photic zone (0-30 m) with an average coverage of 39.6, 22, and 7.2 % in the depth intervals 0–10, 10–20, and 20-30 m, respectively. 15 % of the area suitable for macroalgae was denuded by sea urchin grazing. Floating macroalgae were common with an average biomass of 55 kg wet weight km−2. Densities and species composition varied seasonally with the highest levels after storms. The floating biomass was composed of intertidal macroalgal species (58 %) (Fucus vesiculosus, Fucus distichus, and Ascophyllum nodosum) and kelps (42 %) (Saccharina longicruris, S. latissima, and Alaria esculenta). We deployed surface GPS drifters to simulate floating macroalgal trajectories and velocity. Data indicated that 80 % of the floating biomass is retained in the fjord where its fate in relation to long-term sequestration is unknown. Export beyond the fjord was limited and indicated an annual floating macroalgal export beyond the fjord of only 6.92 t C yr−1, which is equal to ~0.02 % of the annual net primary production. Our findings suggest that floating macroalgae support a limited blue carbon potential beyond this fjord and that future research should focus on the fate of retained floating macroalgae and subsurface export to resolve the connectivity between macroalgal habitats and long-term carbon sinks.

Mangrove reforestation provides greater blue carbon benefit than afforestation for mitigating global climate change - Song, Shanshan; Ding, Yali; Li, Wei; Meng, Yuchen; Zhou, Jian; Gou, Ruikun; Zhang, Conghe; Ye, Shengbin; Saintilan, Neil; Krauss, Ken W.; Crooks, Stephen; Lv, Shuguo; et al. (Nature Communications, 2023)
Significant efforts have been invested to restore mangrove forests worldwide through reforestation and afforestation. However, blue carbon benefit has not been compared between these two silvicultural pathways at the global scale. Here, we integrated results from direct field measurements of over 370 restoration sites around the world to show that mangrove reforestation (reestablishing mangroves where they previously colonized) had a greater carbon storage potential per hectare than afforestation (establishing mangroves where not previously mangrove). Greater carbon accumulation was mainly attributed to favorable intertidal positioning, higher nitrogen availability, and lower salinity at most reforestation sites. Reforestation of all physically feasible areas in the deforested mangrove regions of the world could promote the uptake of 671.5–688.8 Tg CO2-eq globally over a 40-year period, 60% more than afforesting the same global area on tidal flats (more marginal sites). Along with avoiding conflicts of habitat conversion, mangrove reforestation should be given priority when designing nature-based solutions for mitigating global climate change.

Mapping intertidal macrophytes in fjords in Southwest Greenland using Sentinel-2 imagery - Carlson, Daniel F.; Vivó-Pons, Antoni; Treier, Urs A.; Mätzler, Eva; Meire, Lorenz; Sejr, Mikael; Krause-Jensen, Dorte (Science of the Total Environment, 2023)
Changes in the distribution of coastal macrophytes in Greenland, and elsewhere in the Arctic are difficult to quantify as the region remains challenging to access and monitor. Satellite imagery, in particular Sentinel-2 (S2), may enable large-scale monitoring of coastal areas in Greenland but its use is impacted by the optically complex environments and the scarcity of supporting data in the region. Additionally, the canopies of the dominant macrophyte species in Greenland do not extend to the sea surface, limiting the use of indices that exploit the reflection of near-infrared radiation by vegetation due to its absorption by seawater. Three hypotheses are tested: I) 10-m S2 imagery and commonly used detection methods can identify intertidal macrophytes that are exposed at low tide in an optically complex fjord system in Greenland impacted by marine and land terminating glaciers; II) detached and floating macrophytes accumulate in patches that are sufficiently large to be detected by 10-m S2 images; III) iceberg scour and/or turbid meltwater runoff shape the spatial distribution of intertidal macroalgae in fjord systems with marine-terminating glaciers. The NDVI produced the best results in optically complex fjord systems in Greenland. 12 km2 of exposed intertidal macrophytes were identified in the study area at low tide. Floating mats of macrophytes ranged in area from 400 m2 to 326,800 m2 and were most common at the mouth of the fjord. Icebergs and turbidity appear to play a role in structuring the distribution of intertidal macrophytes and the retreat of marine terminating glaciers could allow macrophytes cover to expand. The challenges and solutions presented here apply to most fjords in Greenland and, therefore, the methodology may be extended to produce a Greenland-wide estimate of intertidal macrophytes.

Opportunities for blue carbon restoration projects in degraded agricultural land of the coastal zone in Queensland, Australia - Rowland, Phebe I.; Hagger, Valerie; Lovelock, Catherine E. (Regional Environmental Change, 2023)
Restoring degraded agricultural lands to their original coastal wetland cover is an approach for enhancing blue carbon storage. This approach enhances carbon sequestration in biomass and soils whilst reducing greenhouse gas emissions and delivering other conservation benefits such as enhancing biodiversity, improving water quality, and protecting coastlines from sea level rise. In Queensland, Australia, tens of thousands of hectares of coastal land have been converted to agriculture since the 1900s, often through drainage. We evaluated the characteristics of degraded agricultural land to identify opportunities for blue carbon restoration projects. Degraded agricultural land was identified through visual inspection of satellite imagery. Our analysis revealed degradation was associated with historical Melaleuca-dominated wetland vegetation and current land uses other than intensive agriculture. Field sampling of a subset of paired degraded and non-degraded sites found that water content, organic carbon, and electrical conductivity were significantly higher at degraded sites. We also observed standing water, drainage structures, and dead trees at degraded sites. From our analyses, we inferred land degradation is likely caused by waterlogging, salinisation, and land management choices. Degraded land historically vegetated by Melaleuca-dominated wetlands could be targeted for blue carbon restoration projects that protect remaining soil carbon and enhance carbon storage, restore ecosystem services, and provide new income streams for landowners. Further characterisation of the distribution of degraded lands may contribute to prioritisation of sites suitable for restoration.

Prospects and challenges of environmental DNA (eDNA) metabarcoding in mangrove restoration in Southeast Asia - Wee, Alison K. S.; Salmo III, Severino G.; Sivakumar, Kannan; Then, Amy Y-H; Basyuni, Mohammad; Fall, Jean; Habib, Kazi Ahsan; Isowa, Yukinobu; Leopardas, Venus; Peer, Nasreen; Artigas-Ramirez, Maria D.; Ranawana, Kithsiri; et al. (Frontiers in Marine Science, 2023)
Species detection using environmental DNA (eDNA) is a biomonitoring tool that can be widely applied to mangrove restoration and management. Compared to traditional surveys that are taxa-specific and time-consuming, eDNA metabarcoding offers a rapid, non-invasive and cost-efficient method for monitoring mangrove biodiversity and characterising the spatio-temporal distribution of multiple taxa simultaneously. General guidelines for eDNA metabarcoding are well-established for aquatic systems, but habitat-specific guidelines are still lacking. Mangrove habitats, as priority ecosystems for restoration in Southeast Asia, present unique prospects and challenges in these regards. Environmental DNA metabarcoding can be used to (1) track functional recovery in ecological restoration, (2) prioritise conservation areas, (3) provide early warning for threats, (4) monitor threatened taxa, (5) monitor response to climate change, and (6) support community-based restoration. However, these potential applications have yet been realized in Southeast Asia due to (1) technical challenges, (2) lack of standardised methods, (3) spatio-temporal difficulties in defining community, (4) data limitations, and (5) lack of funding, infrastructure and technical capacity. Successful implementation of eDNA metabarcoding in mangrove restoration activities would encourage the development of data-driven coastal management and equitable conservation programs. Eventually, this would promote Southeast Asia’s shared regional interests in food security, coastal defence and biodiversity conservation.

Quantifying blue carbon stocks and the role of protected areas to conserve coastal wetlands - Duarte de Paula Costa, Micheli; Adame, Maria Fernanda; Bryant, Catherine V.; Hill, Jack; Kelleway, Jeffrey J.; Lovelock, Catherine E.; Ola, Anne; Rasheed, Michael A.; Salinas, Cristian; Serrano, Oscar; Waltham, Nathan; York, Paul H.; et al. (Science of the Total Environment, 2023)
Vegetated coastal ecosystems, in particular mangroves, tidal marshes and seagrasses are highly efficient at sequestering and storing carbon, making them valuable assets for climate change mitigation and adaptation. The state of Queensland, in northeastern Australia, contains almost half of the total area of these blue carbon ecosystems in the country, yet there are few detailed regional or state-wide assessments of their total sedimentary organic carbon (SOC) stocks. We compiled existing SOC data and used boosted regression tree models to evaluate the influence of environmental variables in explaining the variability in SOC stocks, and to produce spatially explicit blue carbon estimates. The final models explained 75 % (for mangroves and tidal marshes) and 65 % (for seagrasses) of the variability in SOC stocks. Total SOC stocks in the state of Queensland were estimated at 569 ± 98 Tg C (173 ± 32 Tg C, 232 ± 50 Tg C, and 164 ± 16 Tg C from mangroves, tidal marshes and seagrasses, respectively). Regional predictions for each of Queensland's eleven Natural Resource Management regions revealed that 60 % of the state's SOC stocks occurred within three regions (Cape York, Torres Strait and Southern Gulf Natural Resource Management regions) due to a combination of high values of SOC stocks and large areas of coastal wetlands. Protected areas in Queensland play an important role in conserving SOC assets in Queensland's coastal wetlands. For example, ~19 Tg C within terrestrial protected areas, ~27 Tg C within marine protected areas and ~ 40 Tg C within areas of matters of State Environmental Significance. Using multi-decadal (1987–2020) mapped distributions of mangroves in Queensland; we found that mangrove area increased by approximately 30,000 ha from 1987 to 2020, which led to temporal fluctuations in mangrove plant and SOC stocks. We estimated that plant stocks decreased from ~45 Tg C in 1987 to ~34.2 Tg C in 2020, while SOC stocks remained relatively constant from ~107.9 Tg C in 1987 to 108.0 Tg C in 2020. Considering the level of current protection, emissions from mangrove deforestation are potentially very low; therefore, representing minor opportunities for mangrove blue carbon projects in the region. Our study provides much needed information on current trends in carbon stocks and their conservation in Queensland's coastal wetlands, while also contributing to guide future management actions, including blue carbon restoration projects.

Ranking the risk of CO2 emissions from seagrass soil carbon stocks under global change threats - Dahl, Martin; McMahon, Kathryn; Lavery, Paul S.; Hamilton, Serena H.; Lovelock, Catherine E.; Serrano, Oscar (Global Environmental Change, 2023)
Seagrass meadows are natural carbon storage hotspots at risk from global change threats, and their loss can result in the remineralization of soil carbon stocks and CO2 emissions fueling climate change. Here we used expert elicitation and empirical evidence to assess the risk of CO2 emissions from seagrass soils caused by multiple human-induced, biological and climate change threats. Judgments from 41 experts were synthesized into a seagrass CO2 emission risk score based on vulnerability factors (i.e., spatial scale, frequency, magnitude, resistance and recovery) to seagrass soil organic carbon stocks. Experts perceived that climate change threats (e.g., gradual ocean warming and increased storminess) have the highest risk for CO2 emissions at global spatial scales, while direct threats (i.e., dredging and building of a marina or jetty) have the largest CO2 emission risks at local spatial scales. A review of existing peer-reviewed literature showed a scarcity of studies assessing CO2 emissions following seagrass disturbance, but the limited empirical evidence partly confirmed the opinion of experts. The literature review indicated that direct and long-term disturbances have the greatest negative impact on soil carbon stocks per unit area, highlighting that immediate management actions after disturbances to recover the seagrass canopy can significantly reduce soil CO2 emissions. We conclude that further empirical evidence assessing global change threats on the seagrass carbon sink capacity is required to aid broader uptake of seagrass into blue carbon policy frameworks. The preliminary findings from this study can be used to estimate the potential risk of CO2 emissions from seagrass habitats under threat and guide nature-based solutions for climate change mitigation.

Rapid plant trait evolution can alter coastal wetland resilience to sea level rise - Vahsen, M. L.; Blum, M. J.; Megonigal, J. P.; Emrich, S. J.; Holmquist, J. R.; Stiller, B.; Todd-Brown, K. E.O.; McLachlan, J. S. (Science, 2023)
Rapid evolution remains a largely unrecognized factor in models that forecast the fate of ecosystems under scenarios of global change. In this work, we quantified the roles of heritable variation in plant traits and of trait evolution in explaining variability in forecasts of the state of coastal wetland ecosystems. A common garden study of genotypes of the dominant sedge Schoenoplectus americanus, “resurrected” from time-stratified seed banks, revealed that heritable variation and evolution explained key ecosystem attributes such as the allocation and distribution of belowground biomass. Incorporating heritable trait variation and evolution into an ecosystem model altered predictions of carbon accumulation and soil surface accretion (a determinant of marsh resilience to sea level rise), demonstrating the importance of accounting for evolutionary processes when forecasting ecosystem dynamics.

Status and Trajectories of Soft-Bottom Benthic Communities of the South Florida Seascape Revealed by 25 Years of Seagrass and Water Quality Monitoring - Krause, Johannes R.; Lopes, Christian C.; Wilson, Sara S.; Boyer, Joseph N.; Briceño, Henry O.; Fourqurean, James W. (Estuaries and Coasts, 2023)
Although seagrass ecosystems are valued for the services they provide, anthropogenic impacts have led to global declines in seagrass area. South Florida harbors one of the most extensive and iconic seagrass landscapes in the world, but historic seagrass losses appeared to threaten their integrity. The establishment of the Florida Keys National Marine Sanctuary (FKNMS) in 1995 created a benthic community and water quality monitoring network to aid management efforts. With this study, we report on the status and trajectories of benthic communities in South Florida using 25 years of monitoring data. Overall, most of our permanent monitoring sites maintained stable benthic communities over the period of observation. However, for areas that did experience decline, we identified mechanisms for loss of the climax seagrass Thalassia testudinum in the FKNMS with no or only partial recovery over decadal timescales. We observed a shift towards fast-growing Halodule wrightii meadows at anthropogenically nutrient-enriched nearshore sites along the Florida Keys. In addition, we describe almost complete loss of seagrass meadows at some exposed, back-reef sites offshore from the Florida Keys resulting from physical disturbance by major hurricanes. This study demonstrates the utility of long-term monitoring programs for the identification of benthic community trajectories and their putative drivers on the seascape scale, offering valuable lessons for the design of future seagrass monitoring programs.

Sustainable natural resource management must recognise community diversity - Hamza, Amina Juma; Esteves, Luciana S.; Cvitanović, Marin; Kairo, James G. (International Journal of Sustainable Development and World Ecology, 2023)
Deforestation and overexploitation of mangrove forests are affecting the livelihoods of millions of families that rely on their ecosystem services. Understanding local perceptions about the status and threats to mangroves is therefore crucial in addressing this issue. This research aims to enhance understanding of how sociodemographic factors influence resource use and perceptions of environmental changes through a questionnaire survey (n = 592 households) in five locations in Lamu County, home to 62% of Kenya’s mangroves. The results highlight the variability of mangrove use, ecosystem service recognition, and perceptions and drivers of change across locations, which are influenced by sociodemographic factors such as gender, education, and occupation. Although 89% of respondents reported using mangrove products, only 56% were able to identify mangrove ecosystem services, with those without formal education being less likely to recognize them. Interestingly, 50% of respondents perceived an increase in mangrove cover, contrary to research showing mangrove loss in the area over the last decade. Results show that communities are diverse and perceptions vary between groups, suggesting that implementing uniform management measures may be incomplete or ineffective. Awareness campaigns and capacity-building efforts must be tailored to reduce misperceptions about the state of local resources and to address the specific needs and challenges faced by different groups. Recommendations made here are widely applicable to promote more inclusive and sustainable community engagement in the management of natural resources in developing countries worldwide.

Variability of Mangroves Along the Brazilian Coast: Revisiting - Cintrón-Molero, Gilberto; Schaeffer-Novelli, Yara; Rovai, André S.; Coelho-, Clemente; Menghini, Ricardo P.; de Almeida, Renato; do Vale, Cláudia Câmara; Bernini, Elaine; Moraes de Oliveira Abuchahla, Guilherme; Cunha-Lignon, Marília (2023)
Brazil’s coastline contains landscape features that are favorable for mangrove development. By revisiting the 1990 paper entitled “Variability of Mangroves Along the Brazilian Coast,” we review aspects of the notion of variability, considering...